Blockchain Implementation Challenges in Developing Countries: An evidence-based systematic review and bibliometric analysis - Abu Naser Mohammad Saif; K. M. Anwarul Islam; Afruza Haque; Hamida Akhter; S.M. Masudur Rahman; Nusrat Jafrin; Rasheda Akter Rupa and Rehnuma Mostafa (Technology Innovation Management Review, 2022)
Contemporary research on technology and innovation management has gauged blockchain as a catalyst for the electronic-information era. As developing countries around the globe are facing challenges to adopt and implement blockchain, this evidence-based systematic review aims to identify the implementation challenges of blockchain technology for developing countries. A total of 1,298 published documents during the period 2016-2021 from the Scopus, Web of Science, IEEE Xplore, and ScienceDirect databases were explored to recognize 19 appropriate publications for research analysis using a PRISMA flow diagram. Based on the identified challenges from the thorough reviews of these 19 publications, using the association technique, the authors developed four comprehensive themes as broad challenges: technological, governance, organizational and environmental, and knowledge. Later, they performed bibliometric analyses using VOSviewer 1.6.17, and based on the bibliometric evidence constructed term co-occurrence network plots. The results show that developing countries face challenges vis-à-vis technological, governance, organizational and environmental, and knowledge issues when implementing blockchain technology. Hence, to make blockchain adoption and implementation processes successful in developing countries, these broad categories of challenges must be properly addressed. In addition, practitioners of disruptive technology, policymakers, consultants, IT experts, business people, top company managers, and above all, respective governments need to pay attention to these challenges for accelerating the blockchain adoption and implementation process in developing countries.
Keywords: bibliometric analysis; blockchain; challenges; developing country; implementation; PRISMA; systematic review; VOSviewer

Can Blockchain Improve Healthcare Management? - Marc Pilkington (Technology Innovation Management Review, 2022)
The paper sets out to examine the relevance of blockchain technology for healthcare management in general, and specifically for consumer medical electronics and connected portable devices. After considering the pivotal role of electronic health records in the first part of the paper, we then analyze the holistic transformative role of blockchain for healthcare data management, illustrated by a set of emerging use cases. Following that, we address the fast-growing segment of consumer medical electronics and the Internet of Medical Things. Finally, we highlight the digital community-building role of public private partnerships for emerging healthcare strategy design.
Keywords: Blockchain Technology; Electronic Health Records; healthcare; Internet of Things

The Diffusion of Blockchain as a General Purpose Technology Driving Digital Transformation - Jason Windawi (Technology Innovation Management Review, 2022)
Digital transformation as a process is integrally linked to the creation and diffusion of a set of general purpose technologies (GPTs) that provide both the motive force, as well as the means, for the transformation of existing industries and the creation of entirely new ones. This article takes as its subject the diffusion of one such technology - blockchain - and explores the relationship between the Schumpeterian innovation at the core of its diffusion and digital transformation as a macro process. Theoretically, I work from Rogers' definition of diffusion as a locally heterogeneous process in which variation in a new technology’s use and adaptation are driven by the decisions of entrepreneurs working in specific contexts, as well as Schumpeter's concept of innovation as a form of recombination. I explore variation in these processes of innovation and recombination across three broad clusters of implementations: Digital Economies, Extra-Institutional Trust, and Digital Finance. I find that each of these clusters is marked by a distinct form of innovation defined by differing patterns of recombination with other digital GPTs, and by the role that institutions and institutional actors play in this variation.
Keywords: blockchain; digital; general purpose technology; innovation; institutions; transformation

Editorial: Blockchain and Digital Transformation (1/2, 2022) - Mika Westerlund; Gregory Sandstrom (Technology Innovation Management Review, 2022)

The Impact of FinTech and Blockchain Technologies on Banking and Financial Services - Anitha Kumari; N. Chitra Devi (Technology Innovation Management Review, 2022)
With the emergence of new technologies, banks and financial services around the globe are taking advantage. The rapid development of information technology, internet connectivity, and smartphones has influenced the banking and financial services sector. The combination of financial technology (FinTech) and blockchain is deliberately transforming digital banking services. This study explores the intervention of FinTech and blockchain technologies in digital banking and financial services. The present study shows that FinTech and blockchain have a strong influence on the digitalization trends. The research focuses on processes of modernization in banking and financial services in addition to particular focus on the community.
Keywords: Blockchain Technology; decentralized finance; digital banking; FinTech

Interview: Blockchain and Digital Transformation in Financial Services. Part II: Governance and Legal Issues, Future Opportunities, Development Needs and Research Pathways - Maryanne Morrow; Matthew Midson; Gregory Sandstrom (Technology Innovation Management Review, 2022)
This interview on “Blockchain and Digital Transformation in Financial Services” between 9th Gear Technologies, Inc., CPQi and the TIM Review took place on April 22nd and 29th, 2022. The interviewees were Maryanne Morrow, CEO, Founder, and Chairman of 9th Gear, and Matthew Midson, CEO, North America, CPQi. The interview was conducted by Gregory Sandstrom, Managing Editor, TIM Review.
Keywords: blockchain; digital transformation; distributed ledger technology; FinTech; Real Time Settlement

Interview: Blockchain and Digital Transformation in Financial Services. Part I: Transformation and Adoption of DLTs, Technology and Innovation, Markets and Money Management - Maryanne Morrow; Matthew Midson; Gregory Sandstrom (Technology Innovation Management Review, 2022)
This interview on “Blockchain and Digital Transformation in Financial Services” between 9th Gear Technologies, Inc., CPQi and the TIM Review took place on April 22nd and 29th, 2022. The interviewees were Maryanne Morrow, CEO, Founder, and Chairman of 9th Gear, and Matthew Midson, CEO, North America, CPQi. The interview was conducted by Gregory Sandstrom, Managing Editor, TIM Review.
Keywords: blockchain; digital transformation; distributed ledger technology; FinTech; Real Time Settlement

The Acceptance of Digital Surveillance in an Age of Big Data - Mika Westerlund; Diane A. Isabelle; Seppo Leminen (Technology Innovation Management Review, 2021)
News media companies and human rights organizations have been increasingly warning about the rise of the surveillance state that builds on distrust and mass surveillance of its citizens. The COVID-19 pandemic is fostering digitalization and state-corporate collaboration, leading to the introduction of contact tracing apps and other digital surveillance technologies that bring about societal benefits, but also increase privacy invasion. This study examines citizens' concerns about their digital identity, the nation-state's intelligence activities, and the security of biodata, addressing their impacts on the trust in and acceptance of governmental use of personal data. Our analysis of survey data from 1,486 Canadians suggest that those concerns have negative impacts on citizens' acceptance of governmental use of personal data, but not necessarily on their trust in the nation-state being respectful of privacy. Government and corporations, it is concluded, should be more transparent about the collection and uses of data, and citizens should be more active in "watching the watchers" in the age of Big Data.
Keywords: Acceptance; Biometric; Citizen Privacy; digital identity; Digital surveillance; Intelligence activities; Mass surveillance; personal data; privacy

Antecedents, Decisions, and Outcomes of a Sharing Economy: A Systematic Literature Review - Shweta Shirolkar; Kanchan Patil (Technology Innovation Management Review, 2021)
This article provides a comprehensive framework-based review of literature on "Sharing Economy" (SE) using an ADO (antecedents, decisions, and outcomes) framework. Based on extensive coverage of studies published over a period of 12 years between 2008 and 2020, we reviewed extant research on this phenomenon from both, more developed and emerging countries. Using PRISMA methodology inclusion and exclusion criteria, we selected 93 articles for the review. The motivation to undertake this research was to understand emerging consumer behavior that intends to collaborate for consumption with the help of technological innovation. We identified major theoretical frameworks developed for investigating SEs and collaborative consumption behavior. The findings of the paper reveal possible antecedents, decisions, and outcomes of SEs. Many areas in the SE domain remain underexplored, despite recent significant advancements, and for this the paper provides directions for future research.
Keywords: access-based economy; antecedents and motivators; collaborative consumption; decisions; determinants; gig economy; outcomes; sharing economy

Barriers to Value Specification when Carrying out Digitalization Projects - Sten Grahn; Anna Granlund; Erik Lindhult (Technology Innovation Management Review, 2021)
If digitalization projects aim to effectively create value for a company, one precondition is having a shared view among company staff and project members of what the "desirable" value is. However, it has been shown that few companies fully understand the value that digitalization projects can create for them, while many companies still launch digitalization projects without having gained much understanding. This contributes to the current "alarmingly" low success rate for digitalization projects. Developing effective methods to specify the desired values of digitalization projects has hence become important. One step in developing improved specification methods is to ask what the possible barriers are to improving current value specification practices. The purpose of the current study is to address this. We analyzed several digitalization projects regarding how specifications of desired project value were carried out, finding that very limited resources are spent on specifying desired values in digitalization projects, this limits project success. Likewise, there are several barriers to increasing resources for specifying desired values. Our findings contribute to understanding the development of value specification methods that aim to overcome these barriers and thus could help improve the success rate of digitalization projects.
Keywords: automation; digitalization; effectiveness; resource-efficiency; Value specification

Call for Papers: Blockchain and Digital Transformation (Technology Innovation Management Review, 2021)
Keywords: blockchain; decentralized autonomous organizations; digital transformation; distributed ledger technology

Call for Papers: Distributed Ledger Technologies for Smart Digital Economies (Technology Innovation Management Review, 2021)
Keywords: artificial intelligence; blockchain; cybersecurity; digital economy; distributed ledger technology; smartification

Can Artificial Intelligence be a Critical Success Factor of Construction Projects? Practitioner perspectives - Virender Kumar; Amrendra Pandey; Rahul Singh (Technology Innovation Management Review, 2021)
The construction sector has not been altogether successful in adopting automated systems. Related research on artificial intelligence has mainly been confined to the development of software models for a specific subset of construction work. This study aims to identify whether artificial intelligence is a potential critical success factor for construction project success. Data were collected through semi-structured interviews and analyzed using content analysis. The interviewees were selected on the basis of convenience and included highly experienced project managers from the global community with expertise in project management working on large construction projects. Our research shows that senior project managers perceive artificial intelligence as different from information technology and advanced project management software. Major drawbacks of artificial intelligence were found to be (i) lack of soft skills, (ii) lack of intelligence to interpret things in various ways like human beings, and (iii) lack of human relationship capabilities, including the ways people manage projects. The interviewees believe that artificial intelligence is still years away from becoming self-aware. This study improves the understanding of artificial intelligence as a success factor for construction projects and provides future directions for research in this field.
Keywords: artificial intelligence; Construction Projects; Critical Success Factors; Project Success

The Catch-22 in Strategizing for Radical Innovation - Helle Alsted Søndergaard; Mette Præst Knudsen; Nicolai Søndergaard Laugesen (Technology Innovation Management Review, 2021)
Corporate strategy development is a well-oiled and recurring process in most established companies. Innovation strategy, however, especially for radical innovation, is new and unknown territory. This creates challenges for companies with radical innovation ambitions. We followed the innovation strategy work of nine large organisations, finding that they all struggle with the process and how to link innovation with corporate strategy in a meaningful way, while at the same time not hampering the innovative ambitions of the organisation. We identify two main challenges of gravitation and alignment, and develop a framework aimed at asking the questions necessary for increasing awareness about inherent business challenges, and how to overcome them at the intersection between corporate and innovation strategy work.
Keywords: corporate strategy; innovation strategy; radical innovation; strategy challenges

Charting a Course of Action: An Insider-Outsider Approach - Paul Woodfield; Katharina Ruckstuhl; Rafaela C.C. Rabello (Technology Innovation Management Review, 2021)
We explore an alternative approach to action research that can be implemented throughout the lifespan of a science and technology research programme. We do this by examining the emergence and development of a participant-observer research approach where a researcher is also part of the same community of practice as those being observed in the technology and innovation management context. Our motivation stems from the need to understand innovation processes and management over a long period. Typically, consultants are employed for a given period to carry out action research. We present a case where social scientists, as opposed to action research consultants, carried out action research after a history of relationship building and becoming embedded within a longitudinal science and technology research programme. This allowed the social science researchers to build trust and rigor with those being observed before engaging an action research approach. We present our case as a narrative of experiences, events and turning points, reporting on what was observed and experienced by these social scientists. Our study extends current knowledge by mapping the research journey toward action research through three phases: navigation, iteration, and reflection phases. We argue that richer insights are generated when participant-observers engage early, and that their insights lead to action research that is more informed.
Keywords: action research; Ethnography; Innovation management; Insider-Outsider; narrative; Participant-Observer; Reflexivity; Sense-Making

A Closer Look at Living Labs and Higher Education using a Scoping Review - Renée van den Heuvel; Susy Braun; Manon de Bruin; Ramon Daniëls (Technology Innovation Management Review, 2021)
As society changes rapidly, there is a need to educate professionals who contribute to innovation and complex adaptations in organizations. As part of this education, companies, governmental bodies and other stakeholders have sought collaboration on complex issues in "living labs". Living labs are recognized as educational environments to prepare students in higher education for future roles. The aim of this article is to explore the nature and extent of the scientific literature about living labs in which actors in higher education actively participate. In total, 21 articles were included in this scoping review. Research into this topic appears to be relatively new. Definitions of living labs are mostly in line with the definition used by the European Network of Living Labs (ENoLL), with its large variation of lab locations. Few results about organization and governance were identified. Different lessons learned regarding processes, interaction and requirements for successful living labs were found. The design of learning is mostly described by learning activities. Learning outcomes are described in generic and specific competences and assessments in living labs are rarely described. The authors recommend more detailed studies into aspects of the successful participation of higher education to gain knowledge about enhancing learning outcomes, and the effects of educational activities within living lab environments.
Keywords: approaches; definitions; higher education; key elements; Living lab; scoping review

Cloud-Based Approach for Tracking and Monitoring of Hay Bales in Smart Agriculture - Ilpo Pölönen; Antti Suokannas; Antti Juntunen (Technology Innovation Management Review, 2021)
The introduction of new technology to agriculture has resulted in enormous amounts of data and their handling and utilization challenge. Data is typically gathered from several sources such as field sensors, machines, industrial processes, different laboratories and officials. This has led to several complicated systems that are not always compatible. Farmers are confused, unaware, and face challenges in seeing the benefits for their business in relation to the time required. This paper introduces an automatic digital tracking and monitoring system for round feed bales on farms. In this system, bale data from sensors, switches, and a GPS-device in the baling machine are collected by hardware and sent to the cloud with the bale ID read from a RFID tag attached to each bale. A digital inventory of bales forms instantly, and baling can be followed on the map application with a mobile device. Data in the cloud is utilized for the farmer's user interface. The farmer can manage and do various operations with bales. An important outcome is the yield report, showing basic statistics, quantities, and qualities of bales in a digitalized field parcel. If the farmer wants to sell bales, this can easily be done with the tool. It makes sales by connecting the farmer to an e-commerce portal. A key question and challenge to be resolved involves who owns the data. All the benefits of digitalization can be achieved only with good cooperation and mutual agreement from farmers who want to have control of their data under all circumstances.
Keywords: bale inventory; bale trade; big data; precision farming; RFID; round bales; silage; Smart farming

Coping with the Double-Edged Sword of Data Sharing in Ecosystems - Petra Kugler; Thomas Plank (Technology Innovation Management Review, 2021)
Researchers and practitioners agree upon the huge potential of Big Data Analytics (BDA) for firms' competitive advantage. Capitalizing on Big Data (BD) often requires sharing firms' data with their stakeholders in an ecosystem. Sharing data, however, is a double-edged sword, because firms might also risk losing their competitive advantage by doing so. This conceptual paper uses extant literature on data analytics to introduce a comprehensive data sharing strategy framework that helps firms decide which data can be shared in an ecosystem, which should be kept secret, or if additional rules and regulations are required for sharing the data. The framework combines two distinct categorizations of data, and it relates the data categories to firms' strategic competitive advantage by employing the Resource-Based View (RBV). Firstly, the framework is grounded in the stages of the data analytics process and secondly, it distinguishes between operative, strategic and monetizable data, a new categorization introduced by this paper. Depending on the categories of data a company intends to share, the framework recommends five distinct data sharing strategies that help mitigating the risk of losing their competitive advantage.
Keywords: Big Data Analytics Capabilities; competitive advantage; data sharing; ecosystem; Resource-Based View

A Cross-Pollination of Ideas about Distributed Ledger Technological Innovation through a Multidisciplinary and Multisectoral lens: Insights from the Blockchain Technology Symposium ’21 - Victoria L. Lemieux; Atefeh Mashatan; Rei Safavi-Naini; Jeremy Clark (Technology Innovation Management Review, 2021)
Blockchain Technology Symposium 2021 (BTS'21) is a forum where academic researchers, industry professionals, and decision makers came together to present recent advancements, discuss adoption barriers, tackle common challenges, and explore future roadmaps surrounding blockchain and its related technologies such as consensus algorithms, smart contracts, cryptocurrencies, and distributed ledger technologies generally. As a follow-up to BTS'18 and BTS'20, which were hosted by Ryerson University and The Fields Institute, and by popular demand, BTS 2021 gathered a diverse audience from academia, industry, and policy makers to engage in a dialogue around crucial topics in the adoption of blockchain technology, with the aim of cross-fertilizing ideas from these communities to address the challenges and seize the opportunities brought forward by this promising technology. BTS'21 featured multidisciplinary and multi-sectoral talks and presentations on four major themes: (1) decentralized finance (DeFi), (2) decentralized identity, (3) decentralized health and (4) decentralized supply chain management. This article provides reflections on some of the key insights found in the BTS’21 presentations.
Keywords: blockchain; decentralization; decentralized finance; decentralized health; decentralized identity; decentralized supply chains; distributed ledgers; innovation; technology adoption; technology management

Developing Social Impact Evaluation Methods for Research: viewpoints on commercialization and sustainability - Leena Kunttu; Helka Kalliomäki; Sorin Dan; Jari Kuusisto (Technology Innovation Management Review, 2021)
The social contributions of research activities have become more and more important in the rapidly changing innovation environment. Despite the fact that industrial commercialization of research results constitutes one of the most essential drivers for innovation and competitiveness, most generally used social impact evaluation criteria do not include clear metrics involving research commercialization possibilities. In a similar manner, principles regarding sustainable development have been largely omitted from the impact criteria. This paper considers the "broader impacts criteria" (BIC) model developed for social impact evaluation in the National Science Foundation in United States. We propose extensions to the BIC criteria related to commercialization and sustainable development viewpoints on impact evaluation. This paper also considers a newly introduced extension to BIC, called "inclusion-immediacy criteria" (IIC). Based on it, we propose an extended version of the model that aims to additionally evaluate the impact of research from a commercialization point of view.

Discovery and Validation of Business Models: How B2B Startups can use Business Experiments - Patrick Brecht; Daniel Hendriks; Anja Stroebele; Carsten H. Hahn; Ingmar Wolff (Technology Innovation Management Review, 2021)
Startups searching for a business model face uncertainty. This research aims to demonstrates how B2B startups can use business experiments to discover and validate their business model's desirability quickly and cost-effectively. The research study follows a design science approach by focusing on two main steps: build and evaluate. We first created a B2B-Startup Experimentation Framework based on well-known earlier frameworks. After that, we applied the framework to the case of the German startup heliopas.ai. The framework consists of four steps (1) implementation of a measurement system, (2) hypothesis development and prioritization, (3) discovery, and (4) validation. Within its application, we conducted business experiments, including online and offline advertisements, as well as interviews. This research contributes in several ways to the understanding of how B2B-startups can use business experiments to discover and validate their business models: First, the designed B2B-Startup Experimentation Framework can serve as a guideline for company founders. Second, the results were used to improve the existing business model of the German B2B startup heliopas.ai. Finally, applying the framework allowed us to formulate design principles for creating business experiments. The design principles used in the study can be further tested in future studies.
Keywords: B2B Startup; Business Experiment Design; Business Experiments; business model; Customer Development Process; Four-Step Iterative Cycle; Growth Hacking; lean startup

Distributed Ledger Technologies and Social Machines: How to “smartify” the economy with blockchain-based digital extension services? - Gregory Sandstrom (Technology Innovation Management Review, 2021)
This paper examines the broad impact of digitalization on economic development. More specifically, it addresses the computer science-derived notion of "social machines", along with the invention of distributed ledger technologies (DLTs) (or blockchain), as potential signposts on the pathway to "smart(er) digital economies". The paper investigates blockchain-based ecosystems as examples of social machines that assist in economic "smartification" and development. It looks at distributed ledger-based communities (DLCs) that provide examples of functioning social machines for a variety of business and personal network communications purposes. It then analyses the scaleup of DLT-based social machines by comparison with "extension services", largely in education and agriculture, which are currently undergoing processes of digitalization. Overall, this conceptual study examines the general horizons and potential impact of blockchain and social machines on the provision of online products and services, across a range of sectors and industries. The paper offers interpretative assistance to managers, entrepreneurs, technology experts, and academics with lingering questions about blockchain in and for business and economic development.
Keywords: artificial intelligence; blockchain; digital economy; digital platform; distributed ledger technology; economic development; extension services; extension thinking; innovation diffusion; Internet of Things; ledger community; smartification; social machines; web science

Ecosystems, Design, and Glocalization: A multi-level study of Technovation - Jasmine A. Shaw; Steven M. Muegge (Technology Innovation Management Review, 2021)
Business ecosystems are an increasingly prominent organizational form in both management research and practice. A growing body of research exists about ecosystem design, but designing local ecosystem instances within a global ecosystem is not yet well understood or defined. This article contributes a multilevel, embedded case study of the global and local ecosystems anchored around the Technovation Girls competition - the world's largest technology entrepreneurship challenge for girls. We first define the process platform driving this ecosystem and anchoring the local instances. Second, we identify key architectural properties of a global-local ecosystem. Lastly, we specify a process for defining design rules in an organizational setting. In addition to theoretical relevance for ecosystem scholarship, our results are also of practical relevance to leaders of existing or nascent global ecosystems, who may benefit from techniques described in this paper that involve designing a flexible global ecosystem architecture that accommodates local variation.
Keywords: business ecosystems; Canada; design rules; glocalization; Mexico; multisided platform; technology entrepreneurship; Technovation

Editorial: Aligning Multiple Stakeholder Value Propositions (April 2021) - Tony Bailetti; Christian Keen; Stoyan Tanev (Technology Innovation Management Review, 2021)

Editorial: Celebrating the World of Innovation (March 2021) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2021)

Editorial: Digital Innovations in the Bioeconomy (February 2021) - Iivari Kunttu (Technology Innovation Management Review, 2021)

Editorial: Distributed Ledger Technologies for Smart Digital Economies (June 2021) - Steven Muegge; Gregory Sandstrom (Technology Innovation Management Review, 2021)

Editorial: Insights (11/12, 2021) - Mika Westerlund; Gregory Sandstrom (Technology Innovation Management Review, 2021)

Editorial: Insights (Issue 7/8, 2021) - Mika Westerlund; Gregory Sandstrom (Technology Innovation Management Review, 2021)

Editorial: Insights (January 2021) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2021)
Keywords: Digital disruption; digital ecosystem; eCommerce; ecosystem; FAIR; Global eCom; innovation; Innovation management; innovation process; internationalization; interoperability; knowledge; opportunity; roadmap; scientometrics; small business; sustainability; text mining; university cooperation

Editorial: Insights (May 2021) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2021)

Editorial: Living Labs (9/10, 2021) - Seppo Leminen; Dimitri Schuurman (Technology Innovation Management Review, 2021)

The Effects of Competence-Based, Expressive and Collaborative Service Performance on the B2B Service Relationship - Wenting Zou; Saara A. Brax; Risto Rajala (Technology Innovation Management Review, 2021)
Service performance is considered an essential determinant of successful business relationships. It affects the customer’s repurchase intentions and, therefore, the continuity of the relationship between the service provider and the customer. Yet, due to the complexity of B2B relationships, service performance is a multi-faceted issue. It includes at least three crucial aspects: competence-based, expressive, and collaborative performance. The present paper investigates the effects of these dimensions on the buyer-supplier relationship and analyzes their mediated impact on customer repurchasing intentions. In so doing, we establish a structural equation model and test multiple hypotheses with a sample of 141 purchasing professionals from 23 countries. The findings indicate that expressive and collaborative service performance are more significant determinants of successful business relationships and influence business relationship continuity more than competence-based service performance. Also, relationship performance was found to fully mediate the links between expressive and collaborative service performance with customer repurchase intentions. The study underscores that service providers can ensure business continuity with their customers by investing in expressive and collaborative service performance.
Keywords: B2B services; Business services; Relationship performance; Repurchase intentions; Service performance; Service purchasing

Enabling and Promoting Sustainability through Digital API Ecosystems: An example of successful implementation in the smart city domain - Maurizio Brioschi; Michele Bonardi; Nadia Fabrizio; Alfonso Fuggetta; Emiliano Sergio Verga; Maurilio Zuccalà (Technology Innovation Management Review, 2021)
Recent studies have recognized that digital ecosystems can enhance the transformation of enterprises and the sustainability of cooperation networks by enabling a regulated and governed exchange of data between different stakeholders according to common rules. Thanks to digital ecosystems, data can be effectively distributed and leveraged to build innovative services in various contexts, such as smart cities or corporate solutions. In this paper we apply the Cefriel Digital Ecosystem Toolkit approach, which was first adopted to foster digital interoperability during the 2015 World Exposition in Milan, Italy. The goal of this lightweight approach is to combine technologies for building API-based solutions with governance processes and common participation guidelines. Moreover, we argue that this approach fosters data sustainability responding to the FAIR (Findability, Accessibility, Interoperability, Reusability) principles for data management and stewardship. Since 2015, this approach has been applied in several projects and featured by the European Commission's JRC and the USA's NIST. The Cefriel Digital Ecosystem Toolkit approach now supports the creation of many-to-many digital relationships between stakeholders operating in various domains, allowing the discovery and reuse of digital assets owned by companies and organizations of any type and size, as well as supporting the development of added value services for citizens and other end-users.
Keywords: digital ecosystem; FAIR; interoperability; sustainability

Expect the Unexpected: Investigating co-creation projects in a Living Lab - Katharina De Vita; Riccardo De Vita (Technology Innovation Management Review, 2021)
Living Labs (LLs) are complex multi-stakeholder environments that enable real-life testing and experimentation of products, services, and systems. Despite increasing attention by practitioners as well as policymakers, and growing scholarly interest in the field, the literature exploring congruency between organisational objectives and outcomes when utilising LLs is still scarce. To fill this gap, a qualitative case study is employed to gain an in-depth understanding of objectives and project outcomes of organisations utilising LLs. The LL JOSEPHS® was chosen as this study's empirical context, in which 14 different projects were analysed. In-depth interviews revealed eight categories of measurable project outcomes: market acceptance, price acceptability, exposure, product testing, market intelligence, legitimisation, method testing, and networking. This study not only highlights what companies have achieved in comparison to their original project objectives, but also identifies additional unplanned outcomes that they accomplished. The findings offer important project-level insights into the potential and limitations of LLs. The results form a basis upon which to develop a better understanding of how innovation performance can be nurtured in LLs. Insights from the study may also help firms and facilitators by providing a deeper understanding of LLs at an individual project-level, and by articulating potential objectives and outcomes associated with organisations' involvement in LLs.
Keywords: co-creation; innovation; Innovation management; Living lab; Open innovation

An Exploration of Blockchain-based Traceability in Food Supply Chains: On the Benefits of Distributed Digital Records from Farm to Fork - Mika Westerlund; Soham Nene; Seppo Leminen; Mervi Rajahonka (Technology Innovation Management Review, 2021)
There are growing internal and external pressures for traceability in food supply chains due to food scandals. Traceability refers to tracking food from the consumer back to the farm and vice versa for quality control and management. However, many traceability solutions have failed to meet the needs of supply chain stakeholders. Blockchain is a novel distributed database technology that could solve some issues of traditional traceability systems, such as cost of adoption and vulnerabilities to hacking and data tampering. This study aims to gain insights on the benefits of applying blockchain technology for traceability in food supply chains through literature review and an investigation of five companies that are experimenting with blockchain-based food traceability. Our findings suggest that, upon implementation and contribution by all supply chain participants, blockchain-based traceability can provide cost-savings, reduced response time to food scandals and food-borne illness outbreaks, improved security and accuracy, better compliance with government regulations, and thus increase consumer trust.
Keywords: blockchain; distributed ledger technology; food innovation; Food safety; food supply chain; supply chain management; traceability

Framing Multi-Stakeholder Value Propositions: A wicked problem lens - Yat Ming Ooi; Kenneth Husted (Technology Innovation Management Review, 2021)
Balancing various stakeholder (often contradictory) expectations creates tensions when developing value propositions for a new firm. Customers, funders, owners, and society-at-large often expect different value outcomes from a firm. They therefore have different motivations for being involved in the firm. These differences in value expectations are more strongly expressed in technology-based ventures, which often rely heavily on access to heterogeneous external resources such as capital, specialised knowledge, distribution, and service. In this paper, we use a wicked problem lens to explore specific challenges for companies to mediate seemingly contradictory propositions. We use two dimensions of wicked problems involving complexity and complicatedness, and conduct a secondary analysis of seven technology venture case studies from Australia and New Zealand. We then categorise the configuration types of these firms' stakeholder value propositions in the context of their scale-up process. We contribute to the value proposition and business model development research streams by suggesting that the challenge of mediating value propositions that conflict can manifest itself in four types of configurations: easy, complicated, complex and wicked. Complicated and complex propositions are thorny, but with structures and processes in place, they can be adequately addressed. On the other hand, wicked propositions consist of many unknowns and require firms to collaborate with stakeholders to derive outcomes that align company scaling objective with stakeholder value propositions.
Keywords: complexity; complicatedness; scaling-up; stakeholders; value proposition; wicked problem

Global Market Entry for Finnish SME eCommerce Companies - Marko Mäki; Tuija Toivola (Technology Innovation Management Review, 2021)
The aim of this paper is to contribute to knowledge about the expansion of eCommerce (eCom) operations by small and medium-sized enterprises (SMEs) to global markets. We investigate the literature on eCom and reflect on our experiences working with several Finnish eCom companies and consulting firms to boost their global sales. In addition, one important goal of our study was to acquire knowledge and boost participants' learning of fast growing digital business models. Our findings show that digital disruption and digitalization in general are driving forces behind eCom growth. The study's conclusions underline the importance of targeted marketing activities, knowledge sharing, and capability building for global eCom operations.
Keywords: Digital disruption; eCommerce; Global eCom; internationalization; university cooperation

How Can Firms Effectively Use Technology in Customer Journey Management - William Boscardini Helouani (Technology Innovation Management Review, 2021)
Customer Journey (CJ) mapping offers a view of the Customer Experience (CX) from a customer's standpoint, which acts as the first step towards a myriad of actions that can be performed to improve CX. While CJ mapping has proven to be helpful in a wide range of use cases, companies still struggle to apply technology to make it effective. This research performs a literature review to identify how IT and digital assets can be used in the CJ context, providing practical examples for organizations willing to implement a consumer-centered IT strategy. As a result, it was found that IT can be used in three primary contexts for CJ: mapping, enabling, and monitoring.
Keywords: customer experience; customer journey; digital transformation; Managerial Requirements; Technology Drivers

Human Factors in Living Lab Research - Nele A.J. De Witte; Leen Broeckx; Sascha Vermeylen; Vicky Van Der Auwera; Tom Van Daele (Technology Innovation Management Review, 2021)
Human factors research is still in its infancy in healthcare and other fields. Yet it has the potential to allow organisations and living labs to assess and improve innovation quality, while closely involving potential end users. "Human factors" involve a scientific focus on the interaction between individuals and systems with the goal of improving safety, performance, and user acceptability. Studies simulating challenging real-life circumstances in selected samples and using a multi-method approach can provide important insights for organisations and governments and allow for better and safer services for the end user. By combining existing theory and case examples, the current paper aims to situate human factors research and to help researchers determine when and how this methodology could be applied.
Keywords: human factors; Living lab; methodology; safety; usability

Ideologies in Energy Transition: Community Discourses on Renewables - Petra Berg; Rumy Narayan; Arto Rajala (Technology Innovation Management Review, 2021)
This paper examines discourses in five Finnish municipalities' energy transition processes to identify and explain different ideological discourses among its members. The study fills a gap in research extending the idea of sense making to capture the ideologies that hide in discourses during socio-technical transitions. We identify three types of ideological discourses labelled as Clan, Solarpunk and Native. The implications of the ideologies embedded in municipal, multi-partner networks that participate in energy transition affect who will be heard in a local context. This impacts future choices directly related to sustainability outcomes. We propose that discourses in these multi-partner networks, conceptualized from the perspective of municipal energy systems, help us to uncover underlying ideologies that imperil change. And yet at the same time, these revelations offer opportunities for sustainability-oriented innovation.
Keywords: Ideological Discourses; Municipal Energy Transition; Renewable Energy; Sense making; Sustainability Transitions

Integrated Test Sites for Innovation Ecosystems - Michaela Kesselring; Stéphane Ruiz-Coupeau; Moritz Kirsch; Frank Wagner; Richard Gloaguen (Technology Innovation Management Review, 2021)
Natural test sites are resource-intensive and often limited to single industries or technologies. Drawing upon two strands of research into technology development and innovation strategies, the research question in this paper investigates how converging test sites may provide opportunities for multiple industries and regions. The paper analyzes multi-industrial test sites regarding, (i) the requirements of the social and physical environment, logistic requirements, as well as technical requirements, (ii) the added value for technology developers, as well as, (iii) the absorptive capacity of the region. Qualitative and quantitative research designs were adopted to analyze multi-industrial test sites. The results indicate that the suitability of multi-industrial test sites depends on the market and research fit of the test target, the quality of the benchmark data, as well as logistical, organizational, legal, social, and ecological factors. The study shows that multi-industrial test sites increase and strengthen the absorptive capacity of regions. Additionally, the study discusses managerial and political implications of multi-industrial test sites. Until now corporate and public test site practices have received only scant recognition in technology management literature, a gap closed by this paper.
Keywords: absorptive capacity; Demonstration; Exploitative Innovation; Exploratory Innovation; Mineral Exploration; Proof-of-Concept; Test Sites

The Interplay of Digital Transformation and Collaborative Innovation on Supply Chain Ambidexterity - Sara Abdalla; Koichi Nakagawa (Technology Innovation Management Review, 2021)
This study aims at investigating the impact of digital transformation on the efficiency and adaptability of a supply chain (SC). It also identifies the role of collaborative innovation as a catalyst in these relationships. Survey data from Japanese manufacturing companies was examined using hierarchical multiple regression analysis to test the study’s hypotheses. According to the results, collaborative innovation with SC members, that is, suppliers and customers, strengthens the impact of digital transformation on adaptability, but not on efficiency. In contrast, collaborative innovation with market participants, such as competitors and partners, reinforces the positive relationship between digital transformation and efficiency, with no evidence supporting its effect on the innovation-adaptability relationship. These findings encourage firms to widen the scope of their collaborative innovation activities to include different types of partners. For firms with limited abilities to conduct such complex collaboration projects, the findings can assist managers in making well-informed decisions to include partners that accommodate prioritized organizational goals.
Keywords: collaboration; digital transformation; innovation; resource-based view.; supply chain ambidexterity; supply chain management

Interview: Discussing Value Proposition Research in the Context of New Companies Committed to Scaling Early and Rapidly - Adrian Payne; Pennie Frow; Stoyan Tanev (Technology Innovation Management Review, 2021)
Keywords: business ecosystems; implicitly vs. explicitly formulated value propositions; new scaling companies; value proposition; value proposition alignment

Learning from Early Adopters of Blockchain Technology: A Systematic Review of Supply Chain Case Studies - Sevda Dede; Mesut Can Köseoğlu; H. Funda Yercan (Technology Innovation Management Review, 2021)
Blockchain technology is widely seen as a promising technology for global supply chains, though early adoption of the technology is both costly and risky. Along with many other discouraging factors, large investments required to enter or develop a blockchain raise barriers to entry. Concerns about potential benefits, on the other hand, have led to companies questioning whether it is worth it. Consequently, many players in the global arena are still preferring to wait by observing current practices before making investments, while trying to figure out what the technology might bring them. Hence, the main purpose of this paper is to research various implementations of blockchain technology in supply chains, in order to learn from its early adopters. For this purpose, we chose case studies as the research method, which we used in a systematic way. We focused on multiple relevant case studies from previous research concerning the use of blockchain technology in supply chain practices. Through a systematic analysis of case studies, the study paper aims at bringing forward different views, approaches and results about blockchain adoption, as a way to show the pros and cons of adopting the technology under certain circumstances. The previous research was obtained from the Web of Science Core Collection. This paper contributes to the literature by showcasing the use of blockchain in supply chains via multiple cases to learn from early blockchain adopters in supply chain practices.
Keywords: blockchain; digitalization; distributed ledger technology; supply chain; systematic review

Living Labs for Public Sector Innovation: insights from a European case study - Anne Vorre Hansen; Lars Fuglsang; Christine Liefooghe; Luis Rubalcaba; David Gago; Ines Mergel & Nathalie Haug; Maria Taivalsaari Røhnebæk & Francesco Mureddu (Technology Innovation Management Review, 2021)
Living labs have gained increased attention in research and practice as both a practical and theoretical innovation phenomenon that emphasizes co-creation, real-life settings, and user/customer involvement. More recently, living labs have also emerged as a specific approach to open innovation processes in the context of publics across the EU. Nevertheless, it is still not clear how the understanding of living labs can be translated and organized into new sectorial settings, what type of public sector innovation challenges it addresses, and what role citizens and users have. The aim of this article is therefore to explore and analyze how living labs are applied as processes for public sector innovation. Based on a mixed method approach of 21 European living lab cases, the analysis reveals a pattern of three different processes for living lab organizational and actor roles: living labs organized as cross-sectorial collaboration, living labs emerging within the public sector as main initiator and beneficiary, and living labs developed by civil society actors. The findings are presented as three scenarios for implementing living labs, which also acts as a background for the article's final discussion about the potentials and pitfalls of living labs in public sector contexts.
Keywords: Citizen engagement; co-creation; living labs; Open innovation; Public sector innovation

Managing the Disruption of Mobility Services: How to align the value propositions of key ecosystem players - Joel Wolff; Esko Hakanen (Technology Innovation Management Review, 2021)
Many industries nowadays are facing drastic changes that enable and require new forms of interdependencies that facilitate complex ecosystems of interconnected actors. This paper investigates such a transformation facing the mobility sector, as user-centric bundles of mobility services are being introduced and compiled, by referring to the Mobility-as-a-Service (MaaS) concept. In the process, new value propositions arise that call for aligning the established players with new entrants. The implementation of MaaS is still in its infancy, and many open questions remain about how local authorities should support its emergence. One key challenge relates to decomposing the focal offering of the MaaS ecosystem into complementary value propositions for key players in the industry. This paper presents the results of a constructive design research project, building on interviews with a leading MaaS provider, as well as stakeholders representing national and local authorities in four European cities. The findings emphasize the need to balance a shared desire to disrupt conventional ways of offering mobility services against reluctance to overturn the industry's public and private incumbents. The co-design framework that results serves to summarize five steps that enable MaaS by guiding strategic interaction between local authorities and various players in the mobility ecosystem. In addition, the article builds on ecosystem research insights and emphasizes the need to align value propositions among multiple stakeholders. The study suggests that the mobility sector provides a prominent empirical context for future ecosystem research.
Keywords: Design Framework; ecosystem; Mobility-as-a-Service (MaaS); Urban Mobility; value proposition

Perspectives from Higher Education: Applied Sciences University Teachers on the Digitalization of the Bioeconomy - Essi Ryymin (Technology Innovation Management Review, 2021)
The bioeconomy is being disrupted due to global trends of digitalization and automation. Knowledge-intensive businesses and sustainable solutions in carbon-smart food production have resulted in various consequences for the professionals working in and for bioeconomy. This paper examines bioeconomy teachers' perceptions of digitalization. It draws on research data from semi-structured focus-group interviews that were conducted with bioeconomy teachers in applied sciences higher education. The theoretical frame for the analysis was Mishra and Koehler's (2006) teacher knowledge framework for technology integration called Technological Pedagogical Content Knowledge (TPACK). The results suggest that although applied sciences university teachers have strong Technological Pedagogical Knowledge (TPK), they need more systematic approach and support to develop Technological Content Knowledge (TCK) in a disruptive field. Teaching in a rapidly transforming discipline, like bioeconomy, requires continuous co-development of all TPACK knowledge components by teachers.
Keywords: Applied Sciences Universities; Bioeconomy; Digital disruption; Higher Education Teachers; Technological Pedagogical Content Knowledge (TPACK)

A Practitioner’s View on Distributed Storage Systems: Overview, Challenges and Potential Solutions - Michel Legault (Technology Innovation Management Review, 2021)
This paper provides an overview on how content can be managed with a blockchain or other distributed ledger technology (DLT), and what challenges need to be addressed in managing this content as part of transactions. Transactions on a blockchain may require supporting documents, for example, photos, reference documents, or actual contracts. As DLTs becoming an increasingly popular method to complete transactions and share information, several issues are arising that need to be addressed, such as: Where should this electronic content in documents be stored? Will the storage system have the features and functionality to properly manage this content through the "information lifecycle", including the retention and disposition of business records based on legal and regulatory requirements? The paper presents an overview of the emerging technology involved with distributed storage systems. It presents five solutions currently available, including their designs, how they secure and store files, and whether or not these files can be deleted in order to meet record disposition requirements and regulations. The discussion points out the need for alignment between multiple stakeholders and consortium members in a distributed ledger-based community with shared ecosystem scaling objectives. The challenges of scaling include the need to protect personal and sensitive information, especially when this information should normally be disposed after a record's retention period has ended.

Reinvigorating the Discourse on Human-Centered Artificial Intelligence in Educational Technologies - André Renz; Gergana Vladova (Technology Innovation Management Review, 2021)
The increasing relevance of artificial intelligence (AI) applications in various domains has led to high expectations of benefits, ranging from precision, efficiency, and optimization to the completion of routine or time-consuming tasks. Particularly in the field of education, AI applications promise immense innovation potential. A central focus in this field is on analyzing and evaluating learner characteristics to derive learning profiles and create individualized learning environments. The development and implementation of such AI-driven approaches are related to learners' data, and thus involves several privacies, ethics, and morality challenges. In this paper, we introduce the concept of human-centered AI, and consider how an AI system can be developed in line with human values without posing risks to humanity. Because the education market is in the early stages of incorporating AI into educational tools, we believe that this is the right time to raise awareness about the use of principles that foster human-centered values and help in building responsible, ethical, and value-oriented AI.
Keywords: artificial intelligence; design for value approach.; educational technology; human-centered AI; intelligent tutoring systems

A Review of Living Lab Research and Methods for User Involvement - Judy Hong Huang; Elisa Thomas (Technology Innovation Management Review, 2021)
Living lab initiatives attempt to solve challenges by stimulating innovative collaboration and outcomes, which unfold in multifarious activities. This study investigates the progress of Living lab research over time. It explores its current trends, along with methods and tools used by Living labs for user involvement. By employing a two-step approach, the study first presents a bibliometric analysis of 535 publications, including detection of convergence towards areas like the aging problem of societies, smart cities, Urban Living labs, and overall sustainability. Urban Living lab clusters have been growing rapidly and forming their own research domain. Subsequently, a review of 42 empirical papers explores the methods and tools adopted by Living labs for user involvement during the innovation process. We categorize the methods into the following eight groups: 1) Structured interaction, 2) Flexible interaction, 3) Extended network, 4) Special actors, 5) Learning and engaging, 6) Design approaches; 7) Techniques, 8) Operational guidelines. The study contributes both to theoretical and practice-oriented Living lab research and offers potential support especially to practitioners.
Keywords: bibliometric analysis; co-creation; literature review; Living lab; user involvement

A Roadmap for Systematically Identifying Opportunities in Ecosystems Using Scientific Publications Data - Behrooz Khademi; Hannele Lampela; Kosmas X. Smyrnios (Technology Innovation Management Review, 2021)
Opportunity identification is a continuous process in ecosystems. However, ambiguities and challenges associated with knowledge exploration and exploitation can retard opportunity recognition processes. This in turn may culminate in excessive expenditure of resources or loss of latent opportunities. The present study adopts an analytical approach and proposes a methodological roadmap that utilizes scientometric and text mining techniques. The roadmap uses data from Web of Science as input, and generates insights that support decision-making about resource saving, strategic planning, investment, and policymaking. Our roadmap extends methods used in studying ecosystems by combining existing and novel techniques in data analytics. Using Python and VOSViewer, we show an exemplary application of the new roadmap, framed in the context of the Nordic countries’ renewable energy ecosystem.
Keywords: ecosystem; knowledge; opportunity; roadmap; scientometrics; text mining

The Role of Digital Platforms in Resident-Centric Housing Concepts - Inka Lappalainen; Maija Federley (Technology Innovation Management Review, 2021)
Platform-enabled services targeted to make everyday life easier have become increasingly available in recent decades, which in some cases challenge traditional ways of owning and working. However, comprehensive data-driven value creation opportunities, which are seamlessly connected to various needs in the everyday life of citizens or residents, are still largely untapped and unstudied. This article investigates value creation opportunities for holistic housing concepts with related ecosystems designed to combine the physical environment of residents along with a digital platform. The novelty of this study builds on a holistic understanding of value co-creation in housing, enabled by digital platforms at the ecosystem level. The empirical study focuses on a qualitative multi-case study of four holistic and resident-centric service concepts, which all include digital platforms. The main findings are concluded as follows: First, digital platforms enable various value creation opportunities in resident-centric housing concepts and related ecosystems. Second, exploring strategic choices regarding competitiveness, innovation, and growth revealed that digital platforms played various roles such as informative, supportive, integrative, or even embedded in novel housing as a service platform concepts, which call for totally new orchestration and business models across traditional industrial and ecosystem boundaries. Third, in light of the basic mechanisms for ensuring competitiveness and growth in data and a platform economy, we identify two main alternative strategic approaches. The findings serve both practitioners and researchers exploring opportunities of a platform economy, with a particular benefit for those in largely unstudied housing markets.
Keywords: digital platforms; housing; platform design; platform ecosystems; S-D logic; value creation and capture

Rural Living Labs: Inclusive Digital Transformation in the Countryside - Abdolrasoul Habibipour; Johanna Lindberg; Mari Runardotter; Yomn Elmistikawy; Anna Ståhlbröst; Diana Chronéer (Technology Innovation Management Review, 2021)
Digital transformation (DT) has received increasing attention in recent years. Up until now, most of the current studies focus on digital transformation in advanced and dense societies, especially urban areas and technologies. Hence, the phenomenon of DT is under-researched in the context of rural and sparsely populated contexts. This study aims at exploring how a rural living lab (RLL) can be shaped and how this approach can be designed to support digital transformation processes in rural contexts. In so doing, following a design science research methodology (DSRM) approach, we have made an artefact (that is, RLL framework) that is an "instantiation" that supports user centric digitalization of rural areas. The designed framework is developed based on the key components of "traditional" and "urban" living labs, as well as empirical data which was collected within the context of the DigiBy project. The DigiBy project aims at conducting DT pilots in rural areas to elevate peoples' understanding of digitalization and the application of digitalization opportunities for service development in rural areas in the north of Sweden. As a result of these studies, five key components that guide the design of digital transformation pilots in rural areas emerged, namely: 1) rural context, 2) digitalization, 3) governance, control, and business mode, 4) methods facilitating DT processes, and 5) quintuple helix actors. We also offer an empirically derived definition of the rural living lab concept, followed by avenues for future research.
Keywords: Components; digital transformation; Living lab; Rural living lab; Rural residents; user engagement

Simulating a Biorefinery Ecosystem to Manage and Motivate Sustainable Regional Nutrient Circulation - Olli Koskela; Clemens Dempers; Maritta Kymäläinen; Jarkko Nummela (Technology Innovation Management Review, 2021)
Creating an ecologically sustainable circulation of nutrients requires local solutions with commitment from all participating parties. Due to vast differences between various regions, it is very complicated, if not impossible, to create fair, simple, and applicable legislation that can consider all of these differences in a meaningful way. Thus, there is a need for clear and easy ways of developing sustainable and viable solutions locally, as well as communicating them with local community and all the way up to the supervising governmental representatives. To meet this need, we developed a simulation tool that allows the user to explore the effectiveness and impact of a local biorefinery in waste management. As an iterative model based on state machine agents, it can easily be modified for a multitude of scenarios with changes taking place over time, while considering the viewing points of all involved. In this article, we report the first version of this tool and demonstrate its usefulness in estimating suitable biogas reactor size in a biorefinery.
Keywords: Bioreactor; circular economy; nutrient recycling; simulation; waste management

SMEs and the Innovation Management Process: A multi-level process conceptual framework - Angelo Dossou-Yovo; Christian Keen (Technology Innovation Management Review, 2021)
The aim of this paper is to propose a conceptual framework to manage the innovation process in small businesses. It is based on research from 11 case studies in the Montreal software industry using contingency and resource dependency theories. This conceptual framework provides a view of the innovation process that differs from the linear approach often used in many studies to investigate innovation in small and medium sized businesses (SMEs). The linear approach considers the process as a set of activities that includes developing from one stage to another, while depending on the previous one. We conceptualize the innovation process in small businesses as an interactive process that involves a set of six subprocesses and several keys points of resources mobilization, which requires interacting with both internal and external business actors. Successful mobilization of innovation resources at all key points determines the success or failure of SMEs' innovation processes.
Keywords: innovation; Innovation management; innovation process; small business

Strategies for a Small to Medium-sized Enterprise to Engage in an Existing Ecosystem - Ermela Bashuri; Tony Bailetti (Technology Innovation Management Review, 2021)
Recent advances in ecosystem theory prescribe that companies need to develop offers that are modular and form unique or supermodular complementarities with other offers. However, both academic and managerial knowledge of the strategies that especially small and medium sized enterprises (SMEs) can use to engage in existing ecosystems for value creation remains scattered and predominantly vague. This article thus aims to explore applicable ecosystem engagement strategies from the perspective of SMEs, as discussed in previous scholarly literature. In so doing, the article puts forward and elaborates three distinct strategies that SMEs can apply to become part of value-creating ecosystems. In this way, the findings contribute to the literature on ecosystems.
Keywords: Complementarities; ecosystem; engagement; Entry; SME; strategy; value creation

Technology Project Summaries as a Predictor of Crowdfunding Success - Mika Westerlund; Ishdeep Singh; Mervi Rajahonka; Seppo Leminen (Technology Innovation Management Review, 2021)
Crowdfunding has emerged in recent years as an important alternative means for technology entrepreneurs to raise funds for their products and business ideas. While the success rate of crowdfunding projects is somewhat low, scholarly understanding of what distinguishes projects that reach their fundraising goals from those that fail remains incomplete. Further, studies on crowdfunding success often examine a number of variables that make predicting success a challenge for entrepreneurs wiling to use crowdfunding. This study uses topic modelling on a data set of over 21,000 technology projects from Kickstarter to investigate if short-text project summaries can reveal predictors of fundraising success on crowdfunding platforms. The results indicate that compared to those that fail in fundraising, project summaries of successfully funded technology projects put forward more trendy topics, use wording that reflects novelty, and focus on solving a social problem. Our results contribute to theory and practice by suggesting the importance of summarizing project content for crowdfunding success.
Keywords: backers; crowdfunding; failure; funding; fundraising; Kickstarter; prediction; project; success; topic modelling

Urban Living Labs and Transformative Changes: A qualitative study of the triadic relationship between financing, stakeholder roles, and the outcomes of Urban Living Labs in terms of impact creation in the city of Groningen, the Netherlands - Stefano Blezer; Nurhan Abujidi (Technology Innovation Management Review, 2021)
Urban Living Labs (ULLs) have become a popular instrument for finding solutions to urban challenges faced by cities. While ULLs have achieved a certain level of normalisation in cities, a general lack of understanding remains regarding the character and purpose of the ULL phenomenon still leaves many challenges open to be overcome. One challenge involves the potential impact of ULLs in contributing to meaningful transformative changes. By combining a literature review with a comparative case study of three ULLs in the city of Groningen, the Netherlands, this study confirms and adds to current theoretical positions taken about how to overcome the challenge in terms of holding a shared ideology and reviewing the concepts of agency and power. It also shows that opportunity comes along with trust-building among stakeholders in ULLs, as a way to enhance their potential in practise. Consequently, this study calls for further research regarding underexplored theories and models of ULLs, power dynamics in ULLs, and into their self-sustaining character, both in terms of social adoption and ownership, as well as financial sustainability.
Keywords: Impact Creation; Transformative Changes; Trust Building; urban living labs

Using Web Text Analytics to Categorize the Business Focus of Innovative Digital Health Companies - Abdulla Aweisi; Daman Arora; Renée Emby; Madiha Rehman; George Tanev; Stoyan Tanev (Technology Innovation Management Review, 2021)
Categorizing the market focus of larger samples of companies can be a tedious and time-consuming process for both researchers and business analysts interested in developing insights about emerging business sectors. The objective of this article is to suggest a text analytics approach to categorizing the application areas of companies operating in the digital health sector based on the information provided on their websites. More specifically, we apply topic modeling on a collection of text documents, including information collected from the websites of a sample of 100 innovative digital health companies. The topic model helps in grouping the companies offering similar types of market offers. It enables identifying the companies that are most highly associated with each of the topics. In addition, it allows identifying some of the emerging themes that are discussed online by the companies, as well as their specific market offers. The results will be of interest to inspiring technology entrepreneurs, organizations supporting new ventures, and business accelerators interested to enhance their services to new venture clients. The development, operationalization, and automation of the company categorization process based on publicly available information is a methodological contribution that opens the opportunity for future applications in research and business practice.
Keywords: Digital health sector; machine learning; Market offer; topic modeling algorithm; value proposition; web analytics

Value Proposition Misalignment and the Failure to Become a Born-Global Company - Roshana Prabaharan; Martin Bliemel; Stoyan Tanev (Technology Innovation Management Review, 2021)
This inductive study explores factors by which some new and innovative firms try yet fail to achieve born-global status. Born-global studies have a survivorship bias, with errors of omission that paint a favourable picture of how innovative and well-funded new ventures internationalise. In this paper, we counter such biases by focussing on innovative ventures that expressed intentions to become born global but failed to do so. Our findings reveal that these new ventures fail in two ways. Either they underestimate the need to tailor a portfolio of value propositions and over-extend their efforts across too many markets, a pattern called "baby born-global". Or they over-commit to one market at a time, thus limiting their capacity to develop value propositions in similar markets, a pattern called "micro multinational".
Keywords: Born-global; failure; internationalisation; premature scaling; value propositions

A Year Acquiring and Publishing Drone Aerial Images in Research on Agriculture, Forestry, and Private Urban Gardens - Olli Niemitalo; Eero Koskinen; Jari Hyväluoma; Esa Lientola; Henrik Lindberg; Olli Koskela; Iivari Kunttu (Technology Innovation Management Review, 2021)
Drone imaging has been shown to have increasing value in monitoring and analysing different kinds of processes related to agriculture and forestry. In long-term monitoring and observation tasks, huge amounts of image data are produced and stored. Environmental drone image datasets may have value beyond the studies that produced the data. A collection of image datasets from multiple data producers can, for example, provide more diverse training input for a machine learning model for vegetation classification, compared with a single dataset limited in time and location. To ensure reproducible research, research data such as image datasets should be published in usable and undegraded form, with sufficient metadata. Timely storage in a stable research data repository is recommended, to avoid loss of data. This work presents research datasets of 2020 drone images acquired from agricultural and forestry research sites of Häme University of Applied Sciences, and from Hämeenlinna urban areas. Those images that do not contain personal data are made freely available under a Creative Commons Attribution license. For images containing personal data, such as images of private homes, privacy preserving forms of data sharing may be possible in the future.

Agile New Solution Development in Manufacturing Companies - Tuomas Huikkola; Marko Kohtamäki (Technology Innovation Management Review, 2020)
This conceptual paper proposes a new agile solution development model for technology and manufacturing companies. The flexible model consists of five key phases: 1) new idea screening, 2) idea nurturing, 3) conversion of ideas into "good enough" solutions, 4) solution productization, and 5) solution revamping. These phases are iterative by nature and follow partial stage model logic, hence combining elements of both the waterfall and agile methods. For technology and manufacturing companies, the new model presents a new way to consider ideas related to new product, service, process, and business model development. It is framed in contrast with older models that are typically product oriented, which potentially restrict companies in the ability to strategically renew themselves fast enough in turbulent product-service markets.
Keywords: agile development; innovation practices; new service development (NSD); Open innovation; servitization and digital servitization; solution business; solution development

Agile Product Development Practices for Coping with Learning Paradox in R&D Offshore Units - Janne Kuivalainen; Iivari Kunttu; Marko Kohtamäki (Technology Innovation Management Review, 2020)
R&D offshoring involves the relocation of in-house R&D activities to subsidiary units located in other countries, often associated with low-cost engineering work, to meet global operational requirements. The main motivation behind R&D offshoring by global technology companies is usually to utilize local resources, knowledge, and competencies provided by geographically dispersed subsidiaries in the most effective manner, which in most cases involves high expectations for project performance. However, offshore units often have their own local interests, such as developing their activities to compete with the company's other global R&D units, by not only building their project performance, but also demonstrating learning and innovativeness. This causes a learning paradox in which the R&D unit is expected to possess capabilities for innovation and learning, while at the same time demonstrating a high product development performance. This paper presents a qualitative case study that analyzes how R&D managers in the offshore units of a global technology company can cope with conflicting tensions between learning and performance. The results present a variety of coping practices that are based on developing local innovation strategies, constant learning, and supporting local innovation culture. The results also underline the meaning of agile working models in facilitating local innovation activities.
Keywords: Agile R&D; Learning paradox; R&D offshoring

AI-Driven Digital Platform Innovation - Sergey A. Yablonsky (Technology Innovation Management Review, 2020)
Artificial Intelligence (AI) innovation becomes useful today when it enriches decision-making that is enhanced by applications of big data (BD), advanced analytics (AA), and some element of human interaction using digital platforms. This research aims to investigate the potential combination of AI, BD and AA for digital business platforms. In doing so, it develops a multi-dimensional AI-driven platform innovation framework with AI/BD/AA innovation value chain and related levels of AI maturity improvement. The framework can be used with a focus on the data-driven human-machine relationship and the application of AI at different levels of an AI-driven digital platform technology stack.
Keywords: Advanced Analytics; AI maturity; AI value chain; AI-driven platform innovation; Artificial Intelligence (AI); big data; enterprise platform

Approaching a Data-Dominant Logic - Petra Kugler (Technology Innovation Management Review, 2020)
This paper introduces the construct of "data-dominant logic". The findings of a multi-step exploratory study indicate that SME have an established mindset (dominant logic) that often hinders these firms from turning data in innovative products, services, and business models. The availability of large amounts of data and the use of this data through data science-driven practices has reached a stage when it now enables new and promising possibilities for firms to innovate. However, the actual use of data and data science insights has proven to be difficult for many companies. The firms under consideration in this paper recognize that the availability of data fundamentally changes their businesses. But also, they lack the appropriate culture, mindset, and business repertoire that would enable them to act by turning data into innovation. The paper concludes that firms first need to establish a new mindset in which data plays a central role. Here I term this mindset "data-dominant logic" (DDL). Future research is required to further concretize the construct beyond this introduction.
Keywords: Data science; data-dominant logic; dominant logic; empirical study; organizational and managerial requirements; SMEs

Blockchain-enabled Clinical Study Consent Management - Hans H. Jung; Franz M.J. Pfister (Technology Innovation Management Review, 2020)
Written informed consent (WIC) is required in the context of voluntary participation in a clinical trial. The trial participant gives WIC in accordance with various regulatory requirements. We present a framework concept for a blockchain-based distributed ledger solution, which aims at implementing simple and secure management of WIC documentation, along the entire data value chain from acquiring consent to academic publication, and (commercially) exploiting the results of a clinical study. This may include (but is not limited to) clinical deployment, security monitoring, and conformity with data privacy and ethical standards. Thus, we present a potential “Health AI” application that goes beyond WIC documentation, to enabling the creation of a holistic data provenance trail graph. Such a framework concept aims to create sustainable value for study participants, clinicians, data scientists, and ultimately consumers. The framework’s usefulness is relevant for ensuring the ethical development of artificial intelligence applications in the healthcare domain.
Keywords: AI Ethics.; blockchain; Clinical Study; Health Artificial Intelligence (AI); Platform Business Model; Written Informed Consent

Call for Papers: Aligning multiple stakeholder value propositions: the challenge of new companies committed to scale early and rapidly - Tony Bailetti; Christian Keen; Stoyan Tanev (Technology Innovation Management Review, 2020)

Call for Papers: Digital Innovations in the Bioeconomy - Iivari Kunttu (Technology Innovation Management Review, 2020)

Citizen Perceptions of Government’s Resistance to Shared Parking - Mika Westerlund (Technology Innovation Management Review, 2020)
Sharing economy services is one of the fastest growing segments in today’s economy, especially in urban centres. However, some cities have taken a negative stance and sought to prohibit sharing economy services, which has raised tensions between citizens and the local government. This paper adopts a case study approach to investigate what the main topics are in citizen perceptions of their government's resistance to shared parking in Ottawa, the capital city of Canada, where shared parking is considered illegal. In so doing, the study applies topic modelling on readers' comments following news about local residents being threatened with legal action by the city for providing shared parking services to government employees suffering from insufficient office parking resources. Based on six identified topics, the study establishes a conceptual framework that contributes to the literature on sharing economies by illustrating how citizens perceive their government's resistance toward sharing economies. The paper considers whether sharing economy services could be an innovation that would benefit societies, and how understanding citizen perceptions through online comments can help a government to solve policy issues and create win-win resolutions.
Keywords: government; innovation resistance; parking; Sharing economy services; topic modelling

Company Offers to Meet the Needs of Business-to-Business Customers: Customer Strategy and Orientation - Mikko Mäntyneva (Technology Innovation Management Review, 2020)
<Companies develop and refine their market offer by creating new products for current and potential customers. Customer-focused research and development (R&D) is expected to shorten the time to market, improve cash flow, and reduce risks. It considers both customer strategy as well as customer orientation. In practice, this means that customer strategy directs current and potential customers to a company's offering, while customer orientation allocates R&D activities to meet customers' needs. This paper contributes to customer-driven R&D research by investigating whether a company's offer meets customer needs that can be supported by customer strategy and orientation. Specific focus is given to companies operating in business-to-business (B2B) markets. The paper is based on an analysis of quantitative survey data from 292 respondents representing key account management and sales management professionals in Finnish firms across several industries. The findings indicate that offer meeting customers' needs are supported by customer strategy and orientation. The paper provides guidelines on how companies can align their research and development activities to address both existing customers as well as current and potential needs and requirements.
Keywords: B2B; customer orientation; customer strategy; Market offer; research and development; value proposition

A Conceptual Development of a Business Model Typology in Tourism: the impact of digitalization and location - Gabriel Linton; Christina Öberg (Technology Innovation Management Review, 2020)
This paper aims to conceptually develop a business model typology in tourism. It focuses on digitalization and destination location as important contextual factors when developing the typology. The paper builds on prior research on business models and tourism research by adopting configuration theory to create a typology of business models in tourism businesses. Four business model archetypes are identified: (1) bricks and mortar business models, (2) digitalized destinations, (3) create a destination, and (4) intermediary business models. The typology contributes to the literature by identifying different types of business models in the tourism sector. The typology also helps to ground the business model concept theoretically, something that has been considered as missing in previous business model research.
Keywords: business models; configurations; destination; digitalization; location; technology; tourism; typology

Correlation between Entrepreneurial Orientation and Implementation of AI in Human Resources Management - Rico Baldegger; Maurizio Caon; Kreshnik Sadiku (Technology Innovation Management Review, 2020)
This paper develops the concept of adopting artificial intelligence (AI) in human resources management (HRM) through a research questionnaire and reports the results of a study designed to investigate the perception of adopting and introducing AI in HRM processes. In addition, it investigates the correlation between entrepreneurship orientation (EO) and AI in HRM processes. A survey was conducted with a sample of 310 firm members in the HR Section Romande, as well as a literature review on the adoption of new technologies. The results indicate a perceived positive value of introducing AI in HRM and a correlation between the level of a company's EO and the introduction of AI in HRM. This means that the more a company is entrepreneurially oriented, the more it tends to implement or include already implemented AI projects and tools in HRM processes. The perceived value of AI in HRM was evaluated by comparing answers to research questions involving the introduction of AI in HRM tools, and expectations of widely implementing AI in the next five years. The main barrier of adopting AI in HRM appeared to be a lack of skills and training. In addition, potential features of implementing AI in HRM were identified as potential steps toward introducing AI as a new technology. Questions regarding the evaluation of EO were based on a research Colvin Slevin (1989). It is important for SMEs to invest in information technology to set the basis for further development. Owing to intensified competitive pressures and the necessity of entering global markets, SMEs are incrementally employing Information Technology (IT) to create substantial benefits. Most prior research has focused more on IT adoption in large organizations, yet when regarding the limited resources of SMEs, the IT adoption process is considerably different. (Ghobakhloo, Sabouri, Hong and Zulkifli, 2011).
Keywords: artificial intelligence; entrepreneurial orientation; Human Resource Management

Criminal Enforcement of Trade Secret Theft: Strategic Considerations for Canadian SMEs - Matt Malone (Technology Innovation Management Review, 2020)
Many innovative small and medium enterprises (SMEs) face unique challenges in protecting their intellectual property (IP). Potential theft of trade secrets is a key feature of these challenges, which arises often in the context of disputes related to employee mobility. Despite the risks these challenges pose, SMEs often confront significant resource barriers in protecting themselves from trade secret theft. The passage of a recent criminal law by the Canadian federal government, section 391 of the Criminal Code, creates a powerful new tool for innovative SMEs to report, investigate, and prosecute theft of trade secrets. It also comes with specific considerations and risks that innovative SMEs should examine and contemplate. This article explores strategies for SMEs in Canada to use section 391 to protect their trade secrets, navigate the legal environment during theft of a trade secret, and remediate such theft.
Keywords: confidential information; criminal law; economic espionage; enforcement; small and medium-sized enterprises; trade secrets

Demystifiying the Meaning of Transnational Entrepreneurship: Indian transnational entrepreneurs in comparative perspective - Supriya Singh; Punit Saurabh; Nityesh Bhatt (Technology Innovation Management Review, 2020)
Migration of people from one geographical location to another, within or outside a country, has a major role to play in the socio-economic development across the globe. "Migrants" and "immigrants" that showcase entrepreneurial traits and are valued in both home and host countries. Transnational entrepreneurs are often studied in various cross-national entrepreneurial research streams, like international entrepreneurship, immigrant entrepreneurship, thus causing ambiguity in the existing definitions. This paper contributes a specific definition of "transnational entrepreneurship", based on secondary research, which takes into account different mobility types. It emphasizes the importance of this construct for developing transnational entrepreneurial typologies. The authors propose a "framework of transnational entrepreneurship" in the paper.
Keywords: diaspora; entrepreneurship; immigrant; migration; transnational

Designing a Visual Tool for Teaching and Learning Front-End Innovation - Priscilla Kan John; Emmaline Lear; Patrick L’Espoir Decosta; Shirley Gregor; Stephen Dann; Ruonan Sun (Technology Innovation Management Review, 2020)
This paper presents work on the design and development of a guided visual tool, the project client map (PCM), which is intended to assist students in their class projects solving real-world problems with industry clients. We use a design science research approach to contribute to existing knowledge through the design of an artefact (the PCM) that has a clear educational and learning goal, and that provides utility. Circumscribing a problem is an essential step to seed the ideation process in front-end innovation. While this step can employ existing tools that focus separately on the organisational, environmental, and human contexts of the problem under scrutiny, there is no formalised roadmap for how to integrate these tools. The PCM addresses this gap. We present a first version of the PCM in this paper, which will be refined in further work.
Keywords: design thinking; Evidence-based Learning; Evidence-based Teaching; front-end innovation; Problematisation; Visual tools

Digitalization and SMEs’ Export Management: Impacts on Resources and Capabilities - Benjamin Dethine; Manon Enjolras; Davy Monticolo (Technology Innovation Management Review, 2020)
Digitalization is becoming an increasingly central issue for companies. However, most companies, and in particular SMEs, are struggling to engage in a coherent global digital transformation process. Indeed, digitalization affects much of a company's organizational strategy, including the development of market opportunities. Digitalization has been identified as an element that fosters the internationalization of SMEs. However, the integration of digital technology requires investments and changes in a company's internal practices through the mobilization of new resources, as well as by implementing specific capabilities to manage them. The objective of this research work is therefore to examine the impact of SMEs' digital transformation on their internationalization capability. Relying on an extensive exploratory literature review, digital facilitators were identified and classified into three categories: e-commerce, e-marketing, and e-business. Then, a cross-analysis between the identification of digital facilitators from the literature and a framework of SMEs' export practices (the Potential Export Index, Enjolras et al., 2016) was conducted in order to highlight differentiated impacts that can be theoretically identified. The most impacted export practices are related to the strategic vision of the firm, the customization of its offerings, its network dynamic, and its internal organization. E-commerce facilitators concern the supply chain organization, e-marketing facilitators are related to communications and customer relations, and e-business facilitators impact the company as a whole.
Keywords: digitalization; export practices; facilitators; impacts; SME

Digitalization, Entrepreneurial Orientation and Internationalization of Micro-, Small- and Medium-Sized Enterprises - Annaële Hervé; Christophe Schmitt; Rico Baldegger (Technology Innovation Management Review, 2020)
Nowadays, we are living in a digitally connected global economy that is completely transforming trade in foreign markets and exposing firms, particularly micro, small and medium-sized enterprises (MSMEs), to major changes and new opportunities. As the use of digital technologies is creating more fluidity and nonlinearity across time and space in entrepreneurial processes, our research adopted a conceptual process to investigate how the digital transformation of MSMEs will support decision-makers in international businesses. Based on a quantitative research design, we demonstrate that the more a company digitalizes its functions, the more it favours entrepreneurial behavior to lead successful strategic decisions in foreign markets. Our results are discussed in detail and we propose several ways to benefit from opportunities arising from the use of digital technologies.
Keywords: digital entrepreneurship; digitalization; Entrepreneurial Orientaton; international entrepreneurship; MSMEs

Digitalization, Internationalization and Scaling of Online SMEs - Mika Westerlund (Technology Innovation Management Review, 2020)
While small- and medium-sized enterprises (SMEs) are increasingly required to look for growth beyond their national markets, the increasing digitalization of the global economy provides them with ample opportunities for internationalization. However, many SMEs are unable to internationalize digitally because they were not initially designed to scale that way, and managing business model scaling in the online environment is challenging. In response to this, the current study applies a quantitative descriptive analysis of survey data on business adoption of digital technologies by 535 Canadian online-based SMEs. The aim is to understand, 1) how internationally-oriented online SMEs differ in terms of their digitalization from those focused on domestic markets, and 2) how these differences are related to the companies’ business model for scaling internationally. The results show that internationally-oriented online SMEs differ from their domestically-oriented peers, in terms of a higher degree in the 1) use of information systems, 2) extent of value networks, 3) emphasis on key internal resources, and, 4) dealing with cybersecurity issues. The study contributes to the literature by suggesting that online SMEs willing to scale internationally through digitalization need to develop a set of capabilities in regard to partnering, customer relationship, and business process management, as well as investing in information and communication (ICT) resources and cyber resilience.
Keywords: business model; digitalization; internationalization; scaling; SME

Ecosystem Value Creation and Capture: A Systematic Review of Literature and Potential Research Opportunities - Behrooz Khademi (Technology Innovation Management Review, 2020)
Collaboration, co-creation, and competition are essential strategies for success in today’s modern businesses. In comparison with former ways of doing business in isolation, ecosystems nowadays have created ample opportunities for generating significantly more values. However, there are also potential threats in the pathway towards success in ecosystems. Ecosystem value creation and capture (EVCC) has recently gained significant attention in the academic literature of business and management. Yet, due to the complex structures of ecosystems and ambiguity in understanding value creation and capture in ecosystems, the contributions heretofore are fragmented, where scholars analysed different aspects of EVCC. The present study offers a systematic review of the literature to shed light on the EVCC studies. The content analysis of a fine-grained sample of articles relevant to EVCC revealed that despite the initiation of discussions in 2007, the topic did not gain noticeable attention until 2016. A 150% increase in the number of papers has since been observed. The paper contributes to the intersection of strategy and studies on EVCC by synthesizing existing knowledge, illuminating current EVCC research, and highlighting potential research avenues.
Keywords: ecosystem; strategy; Systematic literature review; value capture; value creation

Editorial: Digitalization and Internationalization (April 2020) - Christophe Schmitt; Rico Baldegger (Technology Innovation Management Review, 2020)
Keywords: business network hubs; businessmodel; coaching; digital entrepreneurship; digitalization; digitalmarketing; entrepreneurial orientation; export practices; facilitators; impacts; international entrepreneurship; internationalization; liability of foreignness; MSMEs; network view; scaling; SME internationalization; SMEs; support institutions; training

Editorial: Innovating in Times of Crisis (September 2020) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2020)

Editorial: Insights (December 2020) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2020)
Keywords: 5G technology; Bitcoin; blockchain; business model; business model innovation; crypto assets; cryptocurrencies; Diem; Diem Association; digital currency; distributed ledger technology; Facebook; fiat currencies; financial inclusion; Financial industry; front-end; ideation; innovation; Libra; local currencies; Management Model; not-for-profit; research center; strategic foresight; strategy; technology firms; project portfolio management; tokenization; product innovativeness; visioning

Editorial: Insights (February 2020) - Gregory Sandstrom (Technology Innovation Management Review, 2020)

Editorial: Insights (January 2020) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2020)
Keywords: AI; artificial intelligence; B2B sales; big data; business-to-business sales; data-based value; digital solutions; ecosystem; ecosystems; Ethics; Gujarat State; Indian IT industry; innovation; IT clusters; Knowledge Innovation clusters; Networks Analysis; regional development; Roboethics; Smart robot; strategy; Systematic literature review; technology; value capture; value creation; value sales

Editorial: Insights (July 2020) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2020)

Editorial: Insights (June 2020) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2020)
Keywords: Bitcoin; blockchain; crowdfunding; crypto assets; cryptocurrencies; developing countries.; distributed ledger technology; Employeedriven innovation; entrepreneurial finance; entrepreneurship; Ethereum; Financial industry; FinTech; ICOs; IEO; innovation; intellectual property rights; internationalization; IT industry; job autonomy; mining industry; moral hazard; need for autonomy; new company; Porter's Five Forces framework; regulation; scaling company value; scaling-up; self-leadership; signaling; SME; STO; sustainability; technological environment; technology; technology readiness; token offering; token sales; tokenization; value proposition; value proposition alignment; venture capital

Editorial: Insights (November 2020) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2020)
Keywords: AI innovation and maturity; and diaspora entrepreneurs.; artificial intelligence; confidential information; criminal law; digitally enhanced teamwork; economic espionage; entrepreneurship; health technology; immigrants; Innovation management; living labs; migration; Multidisciplinarity; situated practice; small and medium-sized enterprises; stakeholder participation; sustainability; trade secrets; transnationals

Editorial: Insights (October 2020) - Gregory Sandstrom (Technology Innovation Management Review, 2020)
Keywords: Advanced Analytics; AI maturity. Data science; AI value chain; AI-driven platform innovation; Artificial Intelligence (AI); big data; business decision-making; business model components; business models; content analysis; data-dominant logic; dominant logic; empirical study; enterprise platform; industries; online communication; online data collection; organizational and managerial requirements; principal component analysis; R&D; research and development; secondary data. Sustainability; SMEs. Disruptive innovation; sustainable innovation

Editorial: ISPIM Bangkok (August 2020) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2020)
Keywords: Basic research; biotech startups.; co-working; Conceptual research; disruption; incubators; innovation; Integrative marketing; investors; knowledge-sharing; Open marketing; organizational capabilities; Pharmaceutical companies; roles; service ecosystems; service entities; service-dominant logic; stakeholders; strategic marketing; strategy-innovation link; structured literature review; triadic relationships; University and Public research institute; value co-creation

Editorial: Rapid Product Development and R&D (March 2020) - Iivari Kunttu; Charles Camarda; Antti Perttula (Technology Innovation Management Review, 2020)

Editorial: Sharing Economy and Government Innovation (May 2020) - Shenja van der Graaf; Carina Veeckman (Technology Innovation Management Review, 2020)

The Effect of Machine Learning on Knowledge-Intensive R&D in the Technology Industry - Daniel Viberg; Mohammad H. Eslami (Technology Innovation Management Review, 2020)
The impact of such current state-of-the-art technology as machine learning (ML) on organizational knowledge integration is indisputable. This paper synergizes investigations of knowledge integration and ML in technologically advanced and innovative companies, in order to elucidate the value of these approaches to organizational performance. The analyses are based on the premise that, to fully benefit from the latest technological advances, entity interpretation is essential to fully define what has been learned. Findings yielded by a single case study involving one technological firm indicate that tacit and explicit knowledge integration can occur simultaneously using ML, when a data analysis method is applied to transcribe spoken words. Although the main contribution of this study stems from the greater understanding of the applicability of machine learning in organizational contexts, general recommendations for use of this analytical method to facilitate integration of tacit and explicit knowledge are also provided.
Keywords: artificial intelligence; explicit knowledge; knowledge integration; ML; tacit knowledge; technological firm

Embracing Product Innovativeness in Technology Firms: The Impact of Management Model Principles - Pınar Büyükbalcı; Esin Ertemsir; Zayneb Boukari (Technology Innovation Management Review, 2020)
Extending the debate on how to enable and manage innovation requires a discussion of the potential beneficial impact of management models and corresponding principles. In this paper, we draw on literature involving product innovativeness and management models to propose that product innovativeness is facilitated and influenced by practices and principles traceable in different management models. We test our hypotheses with data from a sample of high technology firms. Findings suggest that management models and principles have varying impacts on product innovativeness. Specifically, we found the principles of obliquity, emergence, and intrinsic motivation as significant enablers of product innovativeness, along with extrinsic motivation. Also, each management model differently impacted and fostered product innovativeness.
Keywords: innovation; Management Model; Product innovativeness; Technology firms

An Empirical Study into the Individual-Level Antecedents to Employee-Driven Innovation - Chukwuemeka K. Echebiri (Technology Innovation Management Review, 2020)
The purpose of this paper is to link individual-level factors (such as need for autonomy, self-leadership, and perceived job autonomy) to employee-driven innovation with self-leadership as an indirect link. The study is based on survey data of 315 employees in the banking sector, collected in two waves where the variables were separated in time. The hypothesized model was analysed using a structural equation model on Stata. First, it was found that the need for autonomy had an indirect association with employee-driven innovation through self-leadership. Second, the findings show that self-leadership had a positive relationship with employee-driven innovation. Finally, there was no support found for the moderating role of perceived job autonomy between self-leadership and employee-driven innovation. The findings in this paper are important because they identify individual-level antecedents of employee-driven innovation.
Keywords: employee-driven innovation; job autonomy; need for autonomy; self-leadership

Enabling Rapid Product Development through Improved Verification and Validation Processes - Antti Perttula; Joni Kukkamäki (Technology Innovation Management Review, 2020)
Fierce competition in consumer electronics market has raised a lot of challenges for product development. Products now must enter to the market as fast as possible. The verification and validation (V&V) process is normally the most resource-demanding activity in product development (PD), and thus also has huge potential for improvement. The V&V process is traditionally executed near the end of the development process, and is one of the most critical activities because it identifies design errors. Error correction for a nearly complete product is often difficult and therefore can cause unexpected delays in product delivery. Performing V&V activities in early phases of the PD process and utilising V&V methods other than testing has proven to be a good approach to reduce risks associated with taking a long time to reach the market. However, V&V can only be carried out when verifiable requirements exist. This paper focuses on the importance of moving V&V activities to each phase of PD by defining the requirements for components and modules. In addition, we explore how some of product-level requirements can be verified before a product has been integrated, and explain the difference between definitions of verification and validation requirements. Finally, we present the idea of changing the focus of verification activities from being set-based in the early phase of development, to being point-based when the product is close to completion.
Keywords: agile; requirements; set-based design; validation; Verification

The Ethical Dimensions of Public Opinion on Smart Robots - Mika Westerlund (Technology Innovation Management Review, 2020)
This article investigates public opinion about smart robots, with special focus on the ethical dimension. In so doing, the study reviews relevant literature and analyzes data from the comments sections of four publically available online news articles on smart robots. Findings from the content analysis of investigated comments suggest that public opinion about smart robots remains fairly negative, and that public discussion is focused on potentially negative social and economic impacts of smart robots on society, as well as various liability issues. In particular, many comments were what can only be called “apocalyptical”, suggesting that the rise of smart robots is a threat to the very existence of human beings, and that the replacement of human labour by smart robots will lead to deepening the socio-economic gap, and concentrating power and wealth in the hands of even fewer people. Further, public discussion seems to pay little attention to the debate on whether robots should have “rights”, or on the increasing environmental effects of the growth in robotics. This study contributes to the extant literature on “roboethics”, by suggesting a dendrogram approach to illustrate themes based on a qualitative content analysis. It suggests that smart robot manufacturers should ensure better transparency and inclusion in their robotics design processes to foster public adoption of robots.
Keywords: Content analysis.; Ethics; Public opinion; Roboethics; Smart robot

An Ethical Framework for Smart Robots - Mika Westerlund (Technology Innovation Management Review, 2020)
This article focuses on “roboethics” in the age of growing adoption of smart robots, which can now be seen as a new robotic “species”. As autonomous AI systems, they can collaborate with humans and are capable of learning from their operating environment, experiences, and human behaviour feedback in human-machine interaction. This enables smart robots to improve their performance and capabilities. This conceptual article reviews key perspectives to roboethics, as well as establishes a framework to illustrate its main ideas and features. Building on previous literature, roboethics has four major types of implications for smart robots: 1) smart robots as amoral and passive tools, 2) smart robots as recipients of ethical behavior in society, 3) smart robots as moral and active agents, and 4) smart robots as ethical impact-makers in society. The study contributes to current literature by suggesting that there are two underlying ethical and moral dimensions behind these perspectives, namely the “ethical agency of smart robots” and “object of moral judgment”, as well as what this could look like as smart robots become more widespread in society. The article concludes by suggesting how scientists and smart robot designers can benefit from a framework, discussing the limitations of the present study, and proposing avenues for future research.
Keywords: AI; artificial intelligence; Ethics; Roboethics; Smart robot

Examining the Relationship Between Cybersecurity and Scaling Value for New Companies - Tony Bailetti; Daniel Craigen (Technology Innovation Management Review, 2020)
We explore the cybersecurity-scaling relationship in the context of scaling new company value rapidly. The relationship between the management of what a new company does to protect against the malicious or unauthorized use of electronic data, and the management of what a new company does to scale company value rapidly is important, but not well understood. We use a topic modelling technique to identify the eight topics that best describe a corpus comprised of 137 assertions about what new companies do to scale company value rapidly, manually examine the stability of the topics extracted from the dataset, and describe the relationship between 17 assertions about how to manage cybersecurity in new companies, and the six topics found to be stable. The six stable topics are labelled Fundraise, Enable, Position, Communicate, Innovate, and Complement. We find that of the 17 cybersecurity assertions, seven are related to Position, two to Innovate, one to Fundraise and, one to Complement. Six cybersecurity assertions were not found to be strongly related to any of the eight topics. This paper contributes to our understanding of cybersecurity in the context of a new company that scales its value rapidly, an application of topic modelling to perform small-scale data analysis, and a manual approach to examine the stability of the topics extracted by the topic modelling technique. We expect this paper to be relevant to new companies’ top management teams, members of the networks upon which new companies depend for to scale company value, accelerators and incubators, as well as academics teaching or carrying out research in entrepreneurship.
Keywords: cybersecurity; scaling company value; scaling initiatives; topic model stability

Examining the Relationship Between Value Propositions and Scaling Value for New Companies - Tony Bailetti; Stoyan Tanev (Technology Innovation Management Review, 2020)
To scale company value rapidly, a new company needs to develop value propositions for diverse parties, customers, investors, partners, suppliers, employees, and other resource owners, as well as align these value propositions with its scaling objectives. The purpose of this paper is to examine the relationships between value propositions for a diverse set of parties, and efforts from a new company to scale company value rapidly. We review the value proposition literature and then examine the relationships between 19 assertions about value propositions, as well as six stable topics that best describe the SERS corpus, which is comprised of 137 assertions about scaling companies early, rapidly, and securely. Conducting a topic model of eight topics led to six stable topics: Fundraise, Enable, Position, Communicate, Innovate, and Complement. We find that of the 19 assertions about value propositions, four are connected to Complement, four to Innovate, one to Position, one to Fundraise, and one to Communicate. A total of eight assertions about value propositions are not connected to any of the six stable topics. This paper contributes to our understanding of how a new company scales company value rapidly, adding an application of topic modelling to perform small-scale data analysis. The findings are expected to be relevant to entrepreneurs and new companies worldwide.
Keywords: scaling company value; scaling objectives; topic modeling; topic stability; value proposition

Facebook’s Digital Currency Venture “Diem”: the new Frontier ... or a Galaxy far, far away? - Jahja Rrustemi; Nils S. Tuchschmid (Technology Innovation Management Review, 2020)
This article focuses on Facebook's new digital currency, initially called "Libra" and renamed in December 2020 "Diem", that has been designed and proposed by the Diem Association (formerly the Libra Association). It briefly reflects on the historical meaning of money and currency, as well as "local currencies" viewed as precursors to the new "digital currencies" or "cryptocurrencies". The paper presents a general overview of the Diem project, particularly from the perspective of financial theory and practise. It looks specifically into Diem's business model and analyzes the project's planned and potential revenue streams, according to official documents published by the Diem Association. The research identifies potential obstacles and hurdles this digital currency would (since it has not happened yet) face on launch day and assesses whether the project is feasible in its current form. In the authors' view, although some early concerns were addressed in the Diem White Paper 2.0, the Diem project is only questionably ready for commercial launch in its current state. Speaking directly to the financial aspects of the Diem Association's project, the current regulatory hurdles and institutional pressures seem difficult to bypass without making some additional noticeable and meaningful changes to Diem.
Keywords: Bitcoin; blockchain; crypto assets; cryptocurrencies; Diem; Diem Association; digital currency; distributed ledger technology; Facebook; fiat currencies; financial inclusion; Financial industry; Libra; local currencies; tokenization

Fundraising Campaigns in a Digital Economy: Lessons from a Swiss Synthetic Diamond Venture's Initial Coin Offering (ICO) - Jahja Rrustemi; Nils S. Tuchschmid (Technology Innovation Management Review, 2020)
As economies digitalize and many local businesses gradually internationalize, crowdfunding platforms have offered a new way for ventures to raise capital. Relying on distributed ledger technology (DLT, blockchain), the method of "tokenization" now seems to be the next way for digital economics to be actualised in practise. Digitalizing some of the production and selling processes through crypto-tokenization technology has brought with it new perspectives and opportunities. Any thorough consideration of the logic of "distributed systems" applied to economics is bound to see that it potentially brings considerable disruptions and significant changes in how companies get access to funding. Cryptocurrencies, and subsequently "tokens" initially issued from "initial coin offerings" (ICOs) have answered an obvious need for efficient, borderless, and secure flows of capital. This article first summarizes what early academic research tells us about ICOs based on DLTs and their factors of success. We then use the case of LakeDiamond, a Swiss venture in the business of growing and polishing synthetic diamonds, to present and contextualize the process of holding an ICO, which ultimately did not succeed. In the final section, we present two fund raising models that have recently gained traction and popularity, namely "security token offerings" (STOs) and "initial exchange offerings" (IEOs), and highlight their main advantages compared to ICOs.
Keywords: Bitcoin; blockchain; crowdfunding; crypto assets; cryptocurrencies; distributed ledger technology; entrepreneurial finance; Ethereum; Financial industry; FinTech; ICOs; IEO; moral hazard.; signaling; STO; token offering; token sales; tokenization; venture capital

How Institutions Promote Digital Marketing in Small and Medium International Companies: a Comparison Between Costa Rica and France - Karen V. H. Carpio; Susan Arce; Manon Enjolras; Mauricio Camargo (Technology Innovation Management Review, 2020)
The objective of this paper is to analyze institutional promotions to small and medium international enterprises on the subject of digital marketing. The authors conduct qualitative research with a descriptive scope, including 12 institutions in Costa Rica and France. The study is dedicated to working with SMEs involved in an internationalization process and offering them some type of training. for the collection of information, an in-depth interview with each participant was applied. It concludes that SMEs promote digital marketing through institutions, and that the way in which they carry it out varies between the two countries, Costa Rica being a more general and structured service, and France a more customized one.
Keywords: coaching; digital marketing; internationalization; SMEs; support institutions; training

How to Digitally Enhance Bioeconomy Collaboration: Multidisciplinary Research Team Ideation for Technology Innovation - Essi Ryymin; Laura Lamberg; Annukka Pakarinen (Technology Innovation Management Review, 2020)
In this paper we examine the potential of digital platforms for managing multidisciplinary collaboration and particularly the ideation processes of multidisciplinary research and development in the case of technology-supported vertical farming. The article draws on research data from semi-structured interviews and a collaborative workshop that was conducted with researchers representing biological, digital, and technological domains. The results of this research indicate that digital platforms may offer impactful, process-accelerating support during the kick-off phase of multidisciplinary technological innovations. A digital platform can support ideation and the prioritisation of ideas and can be especially fruitful when paired with face to face discussion and non-digital interaction.
Keywords: digitally enhanced teamwork; ideation; Multidisciplinarity; sustainability; technological innovation

Human-Centered Design for Collaborative Innovation in Knowledge-based Economies - Tiago Filipe Pereira da Silva; João Paulo Coelho Marques (Technology Innovation Management Review, 2020)
This research explores a university-industry collaboration based on the case study of an innovation project based on Stanford University's ME310 Design Innovation program. The Porto Design Factory and IKEA Industry joined forces to tackle a problem using what has come to be called a human-centered design approach. The case study provides an understanding of outcomes that reveal the potential of using a human-centered design approach to solve technical problems while enhancing customer experience. It also identifies the benefits that each institution gained by collaborating. The outcomes show that companies benefit from building interfaces with external partners, and that universities are relevant players in the innovation ecosystem, satisfying their third mission of being entrepreneurial institutions.
Keywords: co-creation; design thinking; Human-Centered Design; innovation; ME310; new product development; Project-based Learning; University-Industry Collaboration

“I Stood By and Watched”: An Autoethnography of Stakeholder Participation in a Living Lab - Samuel Schrevel; Meralda Slager; Erwin de Vlugt (Technology Innovation Management Review, 2020)
An emerging and innovative way of organizing projects in health technology and innovation is the so-called "living lab" Because of their characteristics, living labs may provide a solution to a very old problem: how to facilitate the meaningful participation of stakeholders in science and technology? In this article, I (we use a first-person perspective in the paper) aim to contribute to the literature by providing an account of my experiences as a participation researcher with stakeholder participation in a living lab in the Netherlands. I participated in a yearlong project on ensuring freedom for residents in a closed psychogeriatric ward. Using three key moments from that experience, I illustrate why participation was the intention, but was harder to achieve in practice. Participation processes and living labs are situated in specific social and physical contexts. I discuss the "situatedness" of living labs and propose to reconceptualize them as "situated practices" the value of a living lab lies in the processes of work it conducts on specific innovations situated in its local context. A key conclusion is that providing narrative descriptions of living lab projects, with attention to situatedness and stakeholder participation, can provide invaluable examples, insights, and inspirations for other researchers in the field.
Keywords: dementia; health technology; living labs; nursing home; psychogeriatric care; situated practice; stakeholder participation

The Importance of Global Business Hubs on Internationalizing SMEs: an empirical analysis of psychic and geographic distance - Pascal Wild (Technology Innovation Management Review, 2020)
This article investigates the influence of psychic and geographic distance, as well as country and market-related variables, on the preference of high-technology small and medium-sized enterprises (SMEs) to connect with, and settle in major business hubs. Literature in the field of SME internationalization and international entrepreneurship increasingly emphasizes a network approach in which the characteristics and linkages of the internationalizing firm’s network are studied. We aim to contribute to this network-based internationalization research by integrating a further element present in complex social and technical networks: network hubs. Hubs are highly connected nodes within a network. In global business, hubs can be defined as business sites that have a high interconnection with the world economy through tremendous flows of goods and capital. The empirical findings of our research suggest that internationalizing high technology SMEs tend to connect with, or settle in to foreign market business hubs, when focal markets are more distant from their home market. These findings are significant for both geographic and psychic distances between home and focal markets.
Keywords: business network hubs; international entrepreneurship; liability of foreignness; network view; SME internationalization

Integrated AI and Innovation Management: The Beginning of a Beautiful Friendship - Nina Bozic Yams; Valerie Richardson; Galina Esther Shubina; Sandor Albrecht; Daniel Gillblad (Technology Innovation Management Review, 2020)
There is a growing consensus around the transformative and innovative power of Artificial Intelligence (AI) technology. AI will transform which products are launched and how new business models will be developed to support them. Despite this, little research exists today that systematically explores how AI will change and support various aspects of innovation management. To address this question, this article proposes a holistic, multi-dimensional AI maturity model that describes the essential conditions and capabilities necessary to integrate AI into current systems, and guides organisations on their journey to AI maturity. It explores how various elements of the innovation management system can be enabled by AI at different maturity stages. Two key experimentation stages are identified, 1) an initial stage that focuses on optimisation and incremental innovation, and 2) a higher maturity stage where AI becomes an enabler of radical innovation. We conclude that AI technologies can be applied to democratise and distribute innovation across organisations.
Keywords: AI innovation; AI maturity; artificial intelligence; IMS ISO 56002; Innovation management; maturity model

Integrated Innovation and Sustainability Analysis for New Technologies: An approach for collaborative R&D projects - Johannes Gasde; Philipp Preiss; Claus Lang-Koetz (Technology Innovation Management Review, 2020)
In order to effectively shape the impact of an innovation on sustainability, the early phases of the innovation process are crucial. This is especially true for complex collaborative R&D projects with multiple partners. We have found that there is an increasing need for simple methods that enable partners in such R&D projects to guide them towards sustainability-oriented innovations (SOI). In response, we have developed a methodology called Integrated Innovation and Sustainability Analysis (IISA). It is based on the early involvement of stakeholders, along with a sustainability assessment of the planned innovation to provide feedback loops into technology development. The overall goal of the method is to improve the potential impact on sustainability in the three dimensions: economic, environmental, and social. The IISA method and its application in two collaborative R&D projects with several research and industry partners that serve as practical examples, is presented and discussed in this paper.
Keywords: Innovation and sustainability analysis; R&D collaborations; sustainability-oriented innovation; stakeholder dialogue; stakeholder integration.

Internationalization and Digitalization: Applying digital technologies to the internationalization process of small and medium-sized enterprises - Annaële Hervé; Christophe Schmitt; Rico Baldegger (Technology Innovation Management Review, 2020)
Digitalization is playing an increasingly important role in the growth of firms and is leading to structural and strategic transformations. The use of digital technologies presents new opportunities for SMEs to expand and succeed in foreign markets. The purpose of this paper is to investigate how the impact of digital technologies on the internationalization process of SMEs has been acknowledged in the literature. It offers an in-depth analysis of five of the most highly relevant recent scientific research papers. The findings are synthetized through key points that highlight how SMEs acting in foreign markets could benefit from digital technologies. This paper complements previous research on the international trade transition initiated by digital technologies and provides a new perspective on contemporary research regarding the internationalization of firms. It concludes by identifying implications for research by scholars seeking to further study the digital aspects of traditional theoretical models of internationalization.
Keywords: digital entrepreneurship; digital technologies; digitalization; international business; internationalization; SMEs.

Kondratieff’s Economic Waves and Future Scenarios Planning: an approach for organizations - Marcos Ferasso; Eloisio Andrey Bergamaschi (Technology Innovation Management Review, 2020)
This manuscript aims to present connections between scenario building techniques and Kondratieff's long economic waves, as a way of identifying patterns in medium and long-term planning for companies' future scenarios. This essay considers two different conceptual contributions to improve forecasting on organizations taking as a departure point Kondratieff's economic waves and Schwartz's future scenario planning. Analyzing these two theoretical contributions, we concluded that the information obtained through the path of Kondratieff's waves can delineate future scenarios as a way to anticipate challenges, opportunities, and threats for organizations' contingency planning. As a contribution for practitioners, considering these two approaches together enables greater performance for strategic planning of future scenarios that can be applied by organizations across a range of industries.
Keywords: Economic waves; foresight; Future studies; Kondratieff.; Strategic Planning

More for Less? Sharing Economy as a Driver of Public Welfare Innovation - Eva Pallesen; Marie Aakjær (Technology Innovation Management Review, 2020)
This article investigates sharing economy as a path to welfare innovation. It is based on a case where a digital platform is activated in order to support sharing among citizens with lung disease, and thereby increase health and well-being. The case exemplifies how sharing economy currently is taken up by public actors in the attempt to prolong the goals of the public sector beyond itself. This implies drawing everyday sharing practices into a new middle between formal organization and private relations. In a critical response to literature on sharing economy that tends to reduce "sharing" to "transaction", the article draws attention to how sharing entangles with hopes, fears, and affectual engagements of everyday life, and to how it interacts with technology in unforeseen ways and beyond anticipated outcomes. Based on the analysis, the article concludes that there may be good reasons for public welfare authorities to engage in facilitating sharing among citizens. This is not because it is likely to provide "more for less" in relation to predetermined goals, but rather because it can open up other kinds of welfare outcomes that cannot be produced by public organizations themselves.
Keywords: innovation; public sector; sharing economy; technology; welfare state

Multi-Actor Network Perspective: CaliBaja an emergent binational innovation ecosystem - Sylvia Mónica Pérez-Núñez; Arturo Serrano-Santoyo (Technology Innovation Management Review, 2020)
To contribute to the field of management of technology and innovation, this paper focuses on a multi-actor network perspective to map stakeholders and identifies key actors in CaliBaja’s binational innovation ecosystem. This region has a unique territorial extension and population dynamics. It is a land of opportunity for global businesses, houses world-class colleges, universities and applied research institutes, and has been recently acknowledged as a global innovative mega-region. We apply social network analysis to this region as an innovative and valuable methodology to identify significant local contributors, defined as according to key elements and success factors that promote and establish communication and interaction among the network stakeholders.
Keywords: innovation ecosystems; Networks Analysis; regional development

Open Marketing: Conceptualizing external parties’ strategic marketing activities - Christina Öberg (Technology Innovation Management Review, 2020)
Open marketing as conceptualized in this paper refers to how external parties take part in strategic, integrative marketing activities. To distinguish this more recent trend in marketing from traditional meanings of marketing, the paper provides a typology on roles and role keepers in marketing. Four types of roles and role keepers are outlined: marketing as 1) solely being performed by actors in the supplier company communicating offerings, 2) an activity shared among functions of the supplier company, 3) external parties communicating offerings, and 4) external parties contributing to strategic marketing. Using the concept of 'roles' in marketing helps to structure activities and actors - or roles and role keepers - and provides a basis for understanding that marketing results from what is done, not merely from who performs it. The paper underlines how new ways of conducting business also have implications for a company's marketing beyond its borders.
Keywords: Conceptualization; Integrative marketing; Open marketing; roles; Strategic marketing.

Organizing the Development of Digital Product-Service Platforms - Johan Simonsson; Mats Magnusson; Anders Johanson (Technology Innovation Management Review, 2020)
Servitization is today a common theme among manufacturing companies, with the goal of better addressing the needs of their customers. Digitalization is one key enabler of servitization. One aspect of this concept can be provided through digital product-service platforms, which may facilitate the enrichment of a market offer, as well as keeping costs under control. Platforms are in general a well-established concept for manufacturing companies, as enablers of rich product offerings based on a few components. Less is known, however, about how the ambition to create digital product-service platforms interplays with the business model innovation needed as a result of the servitization efforts, along with processes and organization. This paper identifies a number of challenges that manufacturing companies may face when undertaking platform development for services, based on an empirical study made in the Swedish company Husqvarna Group.
Keywords: business model innovation; corporate entrepreneurship; digital platforms; servitization

Is Porter's Five Forces Framework Still Relevant? A study of the capital/labour intensity continuum via mining and IT industries - Diane Isabelle; Kevin Horak; Sarah McKinnon; Chiara Palumbo (Technology Innovation Management Review, 2020)
Porter's Five Forces (P5F) framework, published in 1979, helps us to understand the attractiveness of an industry. The five competitive forces are: the threat of new entrants, the bargaining power of buyers, the bargaining power of suppliers, the threat of substitute products of services, and the rivalry among existing competitors. This framework has recently come under scrutiny and been called into question. To contribute to the debate, this paper investigates the relevance of Porter's framework by contrasting vastly different industries. The use cases consist of a resource-based, capital-intensive industry, the mining industry, and a knowledge-based, labor-intensive industry, the information technology industry. Drawing from research on Porter's Five Forces framework, and through an internationalization lens, the paper proposes a modified framework augmented with four additional forces. These additional forces are: the competitor's level of innovativeness, exposure to globalization, threat of digitalization, and industry exposure to de/regulation activities. These forces were added to capture the increased interconnectivity and complexity of businesses operating in the 21st century. The paper contributes to this body of knowledge by augmenting a popular framework and applying it to vital industrial sectors. The findings aim to incite researchers, managers, entrepreneurs and policymakers to go beyond the traditional five forces as a way to help monitor their business environment and enhance decision-making processes, particularly in a post-COVID-19 world.
Keywords: internationalization; IT industry; mining industry; Porter's Five Forces framework; regulation

Project Portfolio Management in the Front-End of Innovation of Research Centers: a Literature Review - Rui Nuno Castro; João José Pinto Ferreira (Technology Innovation Management Review, 2020)
The beginning of an innovation process, also known as “front-end of innovation” (FEI), counts as an essential contributor to the successful development of new products and for their market appeal. Nevertheless, while helpful procedures and techniques for developing new products are well-known and widely applied, FEI is still an understudied area, and models for managing it are not yet commonly used in technology-oriented companies. FEI, also known as "fuzzy front end", can even be "fuzzier" in not-for-profit research centers. That is because the focus of these centers is advancing of scientific knowledge, rather than commercializing the results of those activities. This study summarizes the insights from a literature review on the topic of “project portfolio management” (PPM) in relation to innovation and, more specifically, with FEI and its components of ideation, innovation management, innovation strategy, foresight, and incremental or radical innovation. The authors selected and reviewed content from 170 papers published in SCOPUS prior to February 2019. The discussion uses a theoretical framework called "Front-End of Innovation Integrative Ontology (FEI2O)" to assist in framing the discussion.
Keywords: front-end; ideation; innovation; not-for-profit; Project Portfolio Management; research center

Rapid Learning and Knowledge-Gap Closure During the Conceptual Design Phase – Rapid R&D - Charles J. Camarda; Stephen J. Scotti; Iivari Kunttu; Antti Perttula (Technology Innovation Management Review, 2020)
New product development strategies, such as set-based concurrent engineering design (SBCED) or set-based design (SBD), have demonstrated improved ways to address knowledge gaps in alternate design concepts prior to the decision to select a single concept for development. Most of the corpus in this field addresses engineering product development that relies on systems and subsystems with years of prior experience in testing, development, and operation. These often have known or existing solutions, and use state-of-the-art (SOA), or near SOA technology. In addition, most papers do not dive into the details of how knowledge was attained to rapidly close critical knowledge gaps. This paper attempts to explain how a research-based method to construct knowledge can accelerate the knowledge capture critical for developing solutions to extremely challenging problems. This rapid R&D methodology enables a rapid acquisition of critical knowledge to understand potential failure modes of concepts in a set-based way. Thus, it enables intelligent decisions for the selection of the final concept as well as the continuous maturation of parallel concepts. The continuous, parallel maturation of multiple concepts enables effective off-ramps in the design process as requirements and new knowledge arise in the course of the development program, without incurring excessive rework, cost growth, and schedule creep. The goal of this paper is to describe a method that accelerates the generation of critical knowledge early in the conceptual design phase, as a way to close knowledge gaps quickly, and thus enable intelligent design decisions and concept selections early in the product development cycle. The methodological descriptions are illustrated with case examples from NASA technology development.
Keywords: knowledge gaps; R&D; Rapid product development; set-based design

Rapid Product Development in University-Industry Collaboration: Case Study of a Smart Design Project - Jari Jussila; Jukka Raitanen; Atte Partanen; Vesa Tuomela; Ville Siipola; Irma Kunnari (Technology Innovation Management Review, 2020)
University-industry collaboration aims at mutually beneficial knowledge and technology exchange between higher education and business. Prototyping new products is one sweet spot where industry can gain new valuable knowledge and understanding of technology, while higher education institutions develop the skills and competences of students by encouraging them to work on authentic real-life problems. From the “design thinking” perspective, rapid product development can be defined as the creation of new products, in the shortest timescales possible, that meet the criteria of desirability, feasibility, and viability. This article addresses rapid product development by presenting a case study of developing prototypes in university-industry collaboration. As a result, the study highlights key design principles, such as the importance of involving teachers, business representatives, and students in collaborative project design, of focusing on the customers or service users who will benefit from the design, and of guiding students participating in co-creation activities. Presenting conclusions for both academics and the industry, the article contributes to design thinking and rapid product development in university-industry collaboration.
Keywords: co-creation; Co-creation pedagogy; design thinking; Rapid product development; University-Industry Collaboration

The Role of Academics, Users, and Customers in Industrial Product Development - Leena Kunttu; Yrjö Neuvo (Technology Innovation Management Review, 2020)
Industrial research and development (R&D) is often adopted as a leading strategy for innovation in high-technology firms. It has been recognized that collaboration with external actors has become increasingly crucial for R&D practices in a world where product and service innovation are increasingly challenging for companies involved in knowledge-intensive technology areas. Thus, high-technology firms are increasingly engaging in collaborative relationships with external stakeholders to transfer valuable new knowledge for industrial purposes, or to create new knowledge through a joint learning process. These external stakeholders may include research institutes such as universities, customer firms, or end users of the firm's products or services. Academic involvement in industrial innovation projects has traditionally focussed on the early stages of a product's development process, when new ideas and innovations are being developed. On the other hand, the interaction between a firm and its customers takes place during the final stages of the R&D process, when innovations are brought to market. In this paper, we explore how users and customers can be involved in university-industry collaboration projects from the beginning of the product development process. Based on a case study comprising five long-term university-industry collaborations in Finland, this paper presents collaborative practices through which academic actors, users, and industrial customers may actively take part in the industrial innovation processes.
Keywords: commercialization; customer involvement; stakeholder involvement; University-Industry Collaboration; user involvement

The Role of Analytics in Data-Driven Business Models of Multi-Sided Platforms: An exploration in the food industry - Diane Isabelle; Mika Westerlund; Mohnish Mane; Seppo Leminen (Technology Innovation Management Review, 2020)
The collection and use of data play an increasingly important role in the growth and success of today’s digital multi-sided platforms (MSPs). However, many aspiring MSPs lack effective strategies for using data to establish a profitable data-driven business model (DDBM). This study explores how MSPs in the food industry can utilize data to develop such a DDBM. Based on an analysis of seven illustrative cases of high-growth MSPs, namely food delivery and meal kit providers, the study identifies eight factors that reveal the role of analytics in those firms’ DDBM, and further classifies them into three DDBM boosters. The findings contribute to our extant knowledge on MSPs and DDBM by addressing how digital platforms in the food industry can leverage big data to optimize their current business processes, predict future value of their product and service offerings, and develop their partnerships.

Seeking 'Strategy' in Business Intelligence Literature: Theorizing BI as part of strategy research - Yassine Talaoui; Marko Kohtamäki; Risto Rajala (Technology Innovation Management Review, 2020)
This paper connects the business intelligence (BI) literature with research in strategic management by plotting the existing research strands on BI: environmental scanning, competitive intelligence, executive information systems, and business intelligence, against the strategic dimensions of a) orientation (External vs. Internal), b) focus (Content vs. Process), and c) practice realms. The article accordingly offers a new re-conceptualization of BI as a strategic artifact across four strategic clusters: BI as a system, BI as a planned process, BI as a product, and BI as a decisional paradigm. This conceptual article contributes to the literature by integrating disparate views on BI and placing them within the content, process, and practice streams of strategy research.
Keywords: Business intelligence (BI); Conceptualization; definition.; literature review; strategy as practice; strategy content; strategy process; strategy realms

Selling Data-Based Value in Business-to-Business Markets - Tuija Rantala; Tiina Apilo; Katariina Palomäki; Katri Valkokari (Technology Innovation Management Review, 2020)
The purpose of this paper is to study what aspects a sales function needs to consider when selling new data-based value in business-to-business (B2B) markets. The paper combines literature on the business-to-business sales process with data-based value. The study includes altogether 29 qualitative interviews from eight companies, representing seller companies at different stages in big data utilization. In addition, the study includes customer perspectives with six interviews from four customer companies. As a result, selling new data-based value is studied from several perspectives. First, we evaluate the impacts of the generated new data-based value from the seller and the market perspective. Secondly, we study what sales representatives need to understand, both from the customer’s perspective, and in relation to data and digital solutions during the sales process. Thirdly, on the customer side, we explore the roles of “digitalist” and old-school buyers, and their effect on the sales process. Our research findings highlight the crucial understanding of customer business and knowledge about real-time data management, digital twins, and artificial intelligence (AI) when selling data-based solutions that create real-time data, recommendations, and value for a customer’s business.
Keywords: B2B sales; big data; business-to-business sales; data-based value; digital solutions; value sales

Social Acceptance of Wind Energy in Urban Landscapes - Mika Westerlund (Technology Innovation Management Review, 2020)
Although wind energy has high potential as a sustainable energy source to fight climate change, and the post COVID-19 world may require accelerated transition to renewable energy systems, many wind energy projects nevertheless face community resistance. Research on social acceptance of wind energy has increased rapidly, but understanding still lacks regarding the different types of acceptance, whether or not the acceptance correlates with demographics, and what drives acceptance of wind farms in the urban landscape. Our analysis of 2,376 residents in Helsinki, the capital of Finland, focused on the gaps in understanding and identified three groups of people: Protagonists, Centrists, and Antagonists. While Protagonists are highly positive about wind energy projects in the city, Antagonists oppose them, and Centrists adopt a middle-of-the-road approach. Further, three factors matter for social acceptance in urban landscapes: 1) distance, as residents prefer offshore wind farms to be farther away from the city's inhabitants, 2) gender, as women are more accepting of wind energy compared with men, and outright opponents of wind energy are more likely men, and 3) participation, as residents wish to participate in decision-making processes regarding wind farms, but lack interest in having ownership of and responsibility for wind energy projects. The study discusses the implications of these findings for developers and policymakers of wind energy projects in the urban context.
Keywords: city; clean energy; Social acceptance; sustainability; wind energy

Sustainability-related Communication Patterns on the Websites of European Top R&D Spenders - Giacomo Liotta; Stoyan Tanev; Andrea Gorra; Alicja Izabela Pospieszala (Technology Innovation Management Review, 2020)
Many firms struggle to incorporate "sustainability" into their operations in a way that can capture economic value and deliver social and environmental benefits. This article aims to answer two questions in this regard: (i) How do companies articulate the sustainability aspects of their businesses online, and (ii) In what ways does the degree of articulation of specific sustainability aspects relate to company performance metrics, such as sales and R&D expenditure. The research method measures the occurrences of a set of sustainability-related keywords on the websites of a sample of 387 firms that were ranked as top R&D spenders in Europe for 2013. We processed the keyword occurrences in a simplified version of latent semantic analysis based on the application of principal component analysis to identify the specific combinations of words used by companies to communicate sustainability issues on their websites. The results show that "sustainable innovation" and "sustainable operations" based on partnerships and cooperation represent a dominant part of companies' online communication strategies. One of the findings suggests a strong relationship between the communication of sustainable innovation aspects and sales, which offers a promising message to companies looking for evidence about the potential impact of their commitment to sustainable operations and innovation.
Keywords: business decision-making; online communication; online data collection; principal component analysis; R&D; research and development; sustainability; sustainable innovation

A Systematic Analysis of how Practitioners Articulate Business Models across Disruptive Industries - Alina Marie Herting; Alexander Lennart Schmidt (Technology Innovation Management Review, 2020)
Ongoing debates surround the role of business models in understanding the dynamics related to disruptive innovation. Too little is still known about how practitioners highlight different characteristics of business models across industries confronted with disruptive dynamics. This shortcoming in current debates hampers a better understanding of the context-dependent phenomenon of "disruption", ultimately limiting the development of adequate business strategies for incumbents and entrepreneurs alike. Consequently, we generated a systematic database of communicated business models from 1,095 relevant press releases and company reports published between 1995 and 2019. The business models from the retrieved articles were assigned to their corresponding industry using the Global Industry Categorization Standard (GICS) to allow for diverse categorization. Subsequently, we performed a deductive coding procedure, building on accepted business model component classifications. Our study contributes insights about relevant business model components, drawing on practitioner experiences in the face of disruptive dynamics.
Keywords: business model components; business models; content analysis; disruptive innovation; industries; secondary data

Technology Adaptation and Survival of SMEs: A Longitudinal Study of Developing Countries - Supriyo Das; Amit Kundu; Arabinda Bhattacharya (Technology Innovation Management Review, 2020)
In the current era of internationalizing business activities and globalizating markets, technology has become an essential tool for enhancing market competitiveness. With globalization, a country's economic and business scenarios can change drastically. Many companies have seized on opportunities to pursue, and sometimes achieve economies of scale. Especially in some countries, however, the technological revolution creates significant challenges for small business entrepreneurs. Technological development plays a pivotal role in making small and medium enterprises (SMEs) competitive, as well as leading to sustainable growth. Under such circumstances, it is relevant to consider a country's technological environment for ways that can lead SMEs towards sustainable development. In the present study, we explore the impact of volatility in technological environments on the sustainability of SMEs in developing countries with emerging economies. We use the Global Competitive Index Report for the period 2012-2016, in which six parameters were applied to define the technological environment of developing nations. Two factors, namely, institutional capabilities and external capabilities emerged as significant factors according to factor analysis. We also studied the impact of emerging factors in new technological environments on the sustainability of SMEs in the specific time period using a regression analysis. The results indicate that both institutional capabilities and external capabilities become significant when time is taken as a selection variable. The highly significance of the time variable indicates the dynamism of today's technological environments. As well, institutional capabilities were found to have a strong impact on a business' sustainability, in comparison with external capabilities and the high level of technological volatility.
Keywords: developing countries; SME; sustainability; technological environment; technology readiness

A Triadic Actor View of Value Co-creation in Business Incubation - Ronald Beckett; John Dalrymple (Technology Innovation Management Review, 2020)
In this paper we view an incubator as a service entity that may take different forms. We contribute to the literature by exploring the utility of the service-dominant logic (SDL) paradigm (Vargo & Lusch, 2016) to better understand incubation operations. Value co-creation is a central axiom of SDL, as is engagement with a supporting service ecosystem. Whilst some studies have considered dyadic incubator-client value creation arrangements, we extend this to include interaction with other service ecosystem stakeholders that we characterise as investors. This way a triadic interaction model is presented. We consider four different cases of a service entity supporting start-up development from this actor-oriented perspective. Adopting a client company perspective, we draw a parallel between various kinds of incubation services and department stores, where clients may access what they need when they need it from a variety of offerings, and obtain the assistance they require.
Keywords: co-working; incubators; investors; knowledge-sharing; service ecosystems; service entities; service-dominant logic; stakeholders; triadic relationships.; value co-creation

Trust, Transparency and Security in the Sharing Economy: What is the Government's Role? - Ruben D’Hauwers; Jacobus van der Bank; Mehdi Montakhabi (Technology Innovation Management Review, 2020)
To obtain access to goods or services between people or stakeholders, some collaboration between actors is a necessary component. Sharing and a sharing economy is closely related to trust. Within the context of 'the' sharing economy, especially digital trust is assumed to play a crucial role. Access to information is a crucial digital cue which can lead to trust yet, sharing economies are subject to asymmetry of information, wherein certain actors have limited access to market information on the consumption behaviour of users, the pricing of a product and, the reliability of peers. The lack of confidential market information between actors is thus limiting the potential for collaboration, as it reduces trust between them. Governments are amongst the (usually more trustworthy) candidates to undertake critical roles in enhancing the sharing of sensitive data. This paper aims to identify the role of government in facilitating and enabling data sharing between various actors in sharing economies. In this paper, we analyse the adequacy of a government's potential role in enabling transparency, trust and security, while operating within a sharing economy scenario, based on two case studies. Additionally, the role of technology is briefly defined for digital platforms and for blockchain-based opportunities for sharing economies. The use cases for the paper concern a digital platform for industrial symbioses, and peer-to-peer electricity trading based on blockchain technology.
Keywords: blockchain; government; network; P2P; peer-to-peer; sharing economy; trust

A Two-Staged Approach to Technology Entrepreneurship: Differential Effects of Intellectual Property Rights - Saurav Pathak; Etayankara Muralidharan (Technology Innovation Management Review, 2020)
In this article we examine how the strength of the intellectual property rights (IPR) regime drives technology entrepreneurship innovation (TEI) that comprise novel unfamiliar technological products and new business models, which in turn lead to new product-market combinations. We consider TEI to be a two-stage process that involves access and use of new technologies and technological resources by entrepreneurs. While stronger IPR may constrain easy availability of new technologies and technological resources for entrepreneurs, use of these leads to TEI. We suggest that stronger IPR regimes could lead to TEI and its positive effect is felt through easy accessibility of the latest technologies and technology resources by entrepreneurs. Our model contributes to the understanding of the effect of strong IPR regimes on the different stages of the innovation process.
Keywords: entrepreneurship; innovation; intellectual property rights; technology

Understanding Civic Crowdfunding as a Mechanism for Leveraging Civic Engagement and Urban Innovation - Bastiaan Baccarne; Tom Evens; Lieven De Marez (Technology Innovation Management Review, 2020)
This article studies the emergence of government-initiated civic crowdfunding platforms. Such platforms can be considered as governmental responses for bottom-up peer-to-peer support mechanisms related to urban innovation, which also allows top-down governance and governmental support systems for civic entrepreneurship. To better understand the implications of these innovative ICT-enabled interaction interfaces for collective urban innovation, this study investigates participation inequalities from the perspective of campaign instigators, using in-depth interviews (N=28), and from the perspective of the citizen-funder, using a survey (N=265). The analysis shows that urban crowdfunding practices mainly contribute to higher-level development of collective identities with increased neighborhood capacities. Although participation in such ICT-enabled interaction interfaces could reinforce digital inequalities and existing power balances, this research shows a more nuanced perspective, in which online and offline practices intertwine. Furthermore, while civic crowdfunding campaigns are driven by a traditional 'participation elite', the deliberation process on development projects involves new publics that are not typically engaged in civic activities. Hence, civic crowdfunding formulates a new mode of civic engagement in which institutional involvement acts as a trust broker between civic funders and civic entrepreneurs, as well as adding legitimacy to innovation processes in the public sphere.
Keywords: Civic crowdfunding; Civic engagement; Civic entrepreneurship; Civic identity; Digital citizenship; Participation inequalities; Peer-to-peer economy; Social cohesion; Urban innovation

Understanding the Strategy-Innovation Link in an Era of Disruptions - Karl Breunig; Tale Skjølsvik (Technology Innovation Management Review, 2020)
Whereas innovation and strategy traditionally are treated as two separate fields of expertise and research, this conceptual paper aims to identify how strategy theory can be linked to recent developments within the innovation field. Innovation research seeks to explain the process of creating new products and services. Strategy research, in turn, intends to explain how businesses create lasting competitive advantages. In recent years, research in strategy has shifted towards explaining how organizational capabilities and environmental turbulence are related, increasingly recognizing that it is difficult to retain sustainable competitive advantages, unless market dynamics and business renewal are addressed. To establish a systematic integration and analysis, we present the results of an extensive literature review of 1,268 research articles published between 2007-2017 to address the question: To what degree, and how, have strategy and innovation been linked in leading management journals? Our analysis reveals that research addressing both strategy and innovation is limited, but highly cited. Moreover, we identify 5 main themes, which in turn reflected 12 subsidiary themes addressed in extant research. These themes combine to give important insights about the research that been done and what is likely to be needed going forward.
Keywords: Conceptual research; disruption; organizational capabilities; strategy-innovation link.; structured literature review

Using Foresight to Shape Future Expectations in Circular Economy SMEs - Anne-Mari Järvenpää; Iivari Kunttu; Mikko Mäntyneva (Technology Innovation Management Review, 2020)
Future foresight in business plays a central role in firms’ strategic planning, innovation, and product development activities. This is particularly true for the firms that are operating in rapidly changing business environments, in which a firm may obtain significant competitive advantages by coming up with new innovations and customer solutions. This article studies future foresight mechanisms and practices in innovative SMEs operating in circular economy–related industries. The future demands set by legislation and regulation, consumer buying behaviour, and environmental consciousness, all have a strong impact on an SME’s future horizon, in which there may be prosperous business opportunities as well as several challenges. This paper presents a qualitative case study conducted on seven Finnish circular economy-oriented SMEs. The case study reveals that the SMEs in this industrial sector are quite active in foresight activities, and that they have developed a variety of practices for effectively utilizing foresight information in their product development and strategic planning activities.
Keywords: circular economy; foresight; innovation; PESTEL; SMEs

Values and Practices behind Collaborative Childcare in Knowledge-based Organizations - Gianluca Schiavo; Chiara Leonardi; Massimo Zancanaro (Technology Innovation Management Review, 2020)
New forms of socializing care that leverage community networks and are based on alternative social arrangements are being experimented with in different grassroots contexts. They are being framed as innovative practices to facilitate the integration of professional and caring responsibilities. In this changing landscape, the private sector might benefit from new forms of welfare policies and family-friendly practices that are based on the co-participation of employees, and encouraged by public policies targeting workplace solutions for childcare. This paper intends to contribute to the ongoing debate on socio-technical innovation in management by exploring how collaborative childcare services might be deployed in workplace settings. At the same time, it investigates the role of digital technology in facilitating employees' engagement and participation.
Keywords: Collaborative workplace practices; Employee participation; Grounded design.; Sharing networks; Work-life balance

Visioning Business Model Innovation for Emerging 5G Mobile Communications Networks - Sara Moqaddamerad (Technology Innovation Management Review, 2020)
The purpose of this research is to introduce and apply a novel approach for developing business model innovation. It shows step-by-step how to envision and create business model innovation activities. The data was collected through a case study of a European provider of technical services in the electricity and telecommunications network industry, which is coping with the uncertainty and complexity of emerging fifth generation mobile communications networks (5G) and subsequently the transformation of telecom markets. This paper contributes to the intersection of strategic foresight and business model innovation by synthesizing existing knowledge and in-depth case evidence to demonstrate how business model innovation is developed in the context of emerging disruptive technologies using future-oriented methods.

What are the Challenges of Building a Smart City? - Haven Allahar (Technology Innovation Management Review, 2020)
The recent emergence of the concept of 'smart cities' presents challenges to city administrators for planning, managing, and governing modern cities in the digital age. Research on smart cities tends to focus on the attributes of cities at a more developed stage, instead this article departs from that trend by discussing an aspiring smart city in a small-island developing country. The purpose of the study is to examine the steps required for building a smart city against a background of the concept of smart cities, taken in the context of an empirical study of an aspiring small smart city. The main finding is that there is no single route to becoming a smart city, but rather there are critical steps that can be adopted as part of a building process for achieving that objective. This work adds value in presenting a way to synthesize the smart city concept with empirical work involving one small smart city's aspirations and achievements. The article fills a partial gap in the smart city literature and has implications for aspiring city administrators, smart city builders, persons concerned with the application of ICT to address city challenges, as well as for students of urban planning, development, and management.
Keywords: building smart cities; ICT and smart cities; Smart cities concept; smart city case studies; smart city initiatives

What impedes the success of late mover IT clusters despite economically favorable environments? A case study of an Indian IT cluster - Harini Mittal; Punit Saurabh; Devang Rohit; Kathak Mehta (Technology Innovation Management Review, 2020)
The Information Technology (IT) industry in India, is one of the major contributors to the country’s growth story. It is organized in a few strong and dominant clusters across the country. Recent research focuses on the emergence, growth and success of the seven big IT clusters that account for 96.55% of total software exports from the country. Unlike the six successful late mover clusters, there are several other late mover IT clusters that have not experienced similar growth. Why do some of the late mover IT clusters in India succeed while others fail to take off despite favorable economic conditions? This paper applies a case study method to answer this research question by examining a single cluster, using both primary and secondary data. The paper concludes with a new framework to explain how an IT cluster lacks the motivation to succeed when it has to gain traction alongside the competing dynamics of traditional businesses. We find this to be the case more so when traditional businesses are thriving and growing.
Keywords: Gujarat State; Indian IT industry; IT clusters; Knowledge Innovation clusters; technology

What Makes Value Propositions Distinct and Valuable to New Companies Committed to Scale Rapidly? - Tony Bailetti; Stoyan Tanev; Christian Keen (Technology Innovation Management Review, 2020)
One of the most valuable resources a company owns is the "portfolio of value propositions" to its diverse external stakeholders, such as customers, investors, and resource owners. In this article, we fill a gap in the value proposition literature by identifying features that make the value propositions of new companies different from other resources, along with factors that make them valuable. A value proposition is conceived as being what enables and improves business transactions between a new company and external stakeholders. We reason that two features in particular make value propositions of new companies distinct: (1) business transactions between a new company and one or more external stakeholders, and (2) investments to create and improve a new company's value propositions that enable business transactions. We provide a definition of "value proposition" and postulate that a value proposition will benefit a new company when it: (1) strengthens the new company's capabilities to scale; (2) increases demand for the new company's products and services; and (3) increases the number, diversity, and rapidity of external investments in the new company's value proposition portfolio.
Keywords: new company; scaling company value; scaling-up; value proposition; value proposition alignment

Which Factors Influence a Company’s Evaluation of the Contribution of Basic Research to Innovation? - Hiromi S. Nagane; Koichi Sumikura (Technology Innovation Management Review, 2020)
This paper empirically analyses how individuals in companies evaluate the contributions of basic research by universities and public research institutes to industry from multiple perspectives: manager as a spokesperson of the company (science-based industry or others), position within the company (managers or inventors), affiliations of inventors (large pharmaceutical companies or biotech start-ups), and educational background. This paper focuses on the case of Japan. Questionnaire surveys were sent to managers and inventors in established companies and start-ups across several industries. This study found that, 1) the more science-oriented the company, the higher their managers evaluate academic research, 2) inventors evaluate academic research more highly than managers, 3) inventors from biotech start-ups evaluate academic research more highly than inventors from large companies in the pharmaceutical industry, and 4) the more advanced their educational background, the more highly inventors evaluate academic research. This study suggests that 'closeness to science' is an important factor for companies to evaluate contributions of basic research to innovation. The findings also suggest that problems within the current educational system are an indirect cause of the innovation crisis in Japan.
Keywords: Basic research; Biotech start-ups; innovation; Pharmaceutical companies; University and Public research institute

The 3S Process: A Framework for Teaching AI Strategy in Business Education - Navneet Bhalla (Technology Innovation Management Review, 2019)
A gap has emerged in teaching artificial intelligence (AI) in business education, where a style of curriculum based on strategy is missing. This article presents a new framework, the 3S Process, as a method for teaching leaders how to strategically adopt AI within their organizations. At a high-level, the 3S Process consists of three stages (Story, Strategy, and Solution), which are described in detail in the article. Stage 1: Story in the process is inspired by the Harvard Case Method to provide context for a problem. Stage 2: Strategy uses Design Thinking to produce candidate solutions. The substage of Empathy in Design Thinking plays a crucial role to reduce bias in designing AI. Virtualization technology is a tool for students to experience hands-on learning in prototype development. Stage 3: Solution is where students advocate for their conceptual AI solution in the context of the case study. AI is a type of complex system; therefore, students should consider feedback loops and the potential for unintended biases to enter a deployed solution. The presentation of the 3S Process in this article is conceptual. Further empirical studies, including evaluations of the 3S Process in classroom settings, will be considered in the future.
Keywords: 3S Process; artificial intelligence; Business Education; design thinking; Harvard Case Method

Alliances in Financial Ecosystems: A Source of Organizational Legitimacy for Fintech Startups and Incumbents - Christopher Svensson; Jakob Udesen; Jane Webb (Technology Innovation Management Review, 2019)
Financial ecosystems are transforming around new financial technology, or “fintech”. As such ecosystems transform, the basis for being seen as legitimate also changes for all actors. Thus, alliances between actors within financial ecosystems are increasingly formed to help gain, maintain, and repair organizational legitimacy. From interviews with fintech startups in Sweden and with venture capitalist firms investing in fintech startups in Sweden, we explore the intertwined quests for organizational legitimacy in a transforming financial ecosystem. As Swedish fintech startups seek to establish a sense of their legitimacy, simultaneously incumbents seek to maintain and repair their organizational legitimacy. Adopting a legitimacy-based view of strategic alliances, we set out the aspects of organizational legitimacy that incumbents and fintech startups look for in a potential partner and how these aspects meet the legitimacy needs of each partner. We argue that alliances further enhance the organizational legitimacy of both fintech startups and incumbents.
Keywords: financial ecosystems; fintech startups; organizational legitimacy; relational perspective; strategic alliances

Applying a Living Lab Approach Within an eHealth Accelerator - Lotta Haukipuro; Satu Väinämö; Leena Arhippainen; Timo Ojala (Technology Innovation Management Review, 2019)
Through this study, we seek to understand the impact of the use of the living lab approach on product and business development in an eHealth accelerator. In the case accelerator, 20 startups developed innovative products atop the European FIWARE Future Internet technology platform. The novel design element of the case accelerator was the use of the living lab approach that was included for the purpose of engaging end users in the development and testing of new product prototypes. Our main result is that the living lab approach provided added value to participating companies and resulted in changes in their product development and marketing strategies. Overall, the case accelerator and the use of the living lab approach had a significant impact on the development, growth, and market success of the companies. Based on the results of the case accelerator, we propose the generic accelerator model presented by Pauwels and co-authors in 2016 to be extended with a new design element, the living lab approach.
Keywords: accelerator; case study; ehealth; Living lab; Open innovation; SME; startup

Are High-Tech Companies More Competitive Than Others? An Empirical Study of Innovative and Exporting French SMEs - Manon Enjolras; Mauricio Camargo; Christophe Schmitt (Technology Innovation Management Review, 2019)
The main objective of this research work is to question the relationship between the technological intensity of SMEs (defined by the share of R&D expenditure in turnover, according to the OECD) and their growth potential (defined by their innovation and export capabilities). Through a multiple case study conducted with a panel of nine French SMEs, and through an analysis combining a qualitative approach (illustrative cases study) and a quantitative one (multidimensional statistical methods), several hypotheses were tested. Finally, this study points out that technological intensity, as defined by the OECD, is not directly correlated with the growth potential of SMEs. On the other hand, a company’s technological intensity would have an impact on the way it manages its innovation and internationalization process, and thus the way it manages its internal practices.
Keywords: export; innovation; multiple-case study; SMEs; technological intensity

Artificial Intelligence for Innovation in Austria - Erich Prem (Technology Innovation Management Review, 2019)
It has been claimed that Artificial Intelligence (AI) carries enormous potential for service and product innovation. Policy makers world-wide nowadays aim to foster environments conducive for AI-based innovation. This paper addresses the current lack of empirical data for evidence-based innovation policies and the management of AI-based innovation. It focuses on “AI and innovation management” in addressing the question whether innovation that is based on new AI technology requires a management approach different from other forms of IT innovation. We present results from a study of Austrian companies on the degree of use and implementation of AI, and on challenges related to AI-based innovation management. This study used a keyword-list approach to define “Artificial Intelligence” and to find AI-based innovation projects in research databases. These projects facilitated the identification of experts from organisations developing AI-based innovation. In total, eleven experts were interviewed about their AI-based innovation activities. The results show that AI is a very fast emerging technology that is being applied in many sectors. A broad range of innovative solutions are being developed and some have already reached the market. Specific AI business models are, however, less clear and still developing. Companies are facing multiple challenges from regulation to human resources and data collection. Managing AI-based innovation will be particularly difficult for smaller enterprises, where problems are often more pronounced than in larger industries. Explicit challenges for managing AI-based innovations include the necessary attention to managing expectations and ensuring historic metadata expertise essential for many AI-based solutions. Policies to support AI-based innovation therefore should focus on human aspects. This includes increasing the availability of AI experts, but also concerns the development of new job profiles, such as experts in AI training. AI innovators also require clear AI regulation and research investments in key challenges, such as explainable AI.
Keywords: AI; AI innovation management; artificial intelligence; Austria; innovation; SME

Beyond the Hype: A Bibliometric Analysis Deconstructing Research on Digitalization - Andrea Holand; Silje Svadberg; Karl Joachim Breunig (Technology Innovation Management Review, 2019)
The accelerating emergent field of research addressing digitalization and related topics is complex, unstructured and hyped. Consequently, both research and practice lack a rigorous foundation of prior published research to underpin and direct future exploration into the opportunities and challenges provided by these exciting new digital technologies. This study employed a bibliometric analysis to explore extant published research within the digitalization field. We identified key articles that have enabled us to distinguish between interrelated digitalization concepts. Subsequently, we propose a taxonomy with characteristics for different levels of digitalization. The taxonomy contributes dimensions that create different commercial and organizational opportunities and challenges at various levels. The taxonomy offers a vantage point for subsequent empirical and conceptual research to extend insights on related digitalization themes, and especially those related to innovation and strategy decisions on scalability, automation, channel selection and connectivity.

Bridging Participatory Policy Trends and Research Traditions through Social Innovation - Malin Lindberg; Daniel Hallencreutz; Anna Tengqvist (Technology Innovation Management Review, 2019)
This study explores whether social innovation may serve as a bridge between participatory policy trends and research traditions when striving for improved societal relevance and impact of research and innovation (R&I). Despite their shared aim of relevance and impact through civic involvement, European R&I policies and participatory action research approaches seldom refer to each other or harness each other’s resources. The study advances the knowledge regarding how the participatory elements in the policies and research approaches relate through a participatory case study of a joint R&I process to develop a model for social innovation support in Sweden. The case study helps distinguish potential synergies between various degrees of involvement advocated in the policies and research approaches, as well as between the reliance on trending policy concepts vs. scientific notions of validity. Social innovation is perceived as a potential bridge between these elements, as it draws upon participatory academic traditions, while simultaneously tapping into current policy trends of co-creation, in the development of new approaches and solutions to societal challenges.
Keywords: action research; co-creation; innovation; participatory research; social innovation

Business Model Architecture by Design - Ronald C. Beckett; John Dalrymple (Technology Innovation Management Review, 2019)
In this article, we view business models as complex deal-making activity systems organized to create, deliver, and capture value. Unlike some other viewpoints, we emphasize both system components and their interconnection. Business activities are carried out by a network of actors drawing on a network of resources, and individual firms seek to configure these intersecting networks to enhance their competitive positioning. The business model literature refers to the significance of antecedent activities in providing context – opportunities the firm decides to pursue, the strategy adopted, and requisite capabilities. Drawing on this literature, we propose an approach to framing business model context. Drawing on the information systems literature, we identify a toolkit facilitating activity system architecture design. We suggest how this both draws out the underlying complexity of a business model and shows how a multiplicity of views makes sense.
Keywords: activity theory; architecture; business model; business networks; design; dynamic capabilities; ISO/IEC 42010; multiple viewpoints; relationship matrix; strategy; Zachman framework

Choosing an Outlet for Action Research: Publication Patterns in Innovation Journals - Magnus Hoppe (Technology Innovation Management Review, 2019)
With the aim to help innovation researchers choose outlets for articles based on participatory and action research methods, this article describes and discusses publication patterns of action research. A bibliographic study of 33 innovation journals ranked 4, 3, 2, and 1 in the 2018 Academic Journal Guide is complemented by a case study of this journal, the Technology Innovation Management Review, as an example of an established open access journal in the field with a wider scope and target group. From these two studies, we learn that the overall trend is towards more publications of action research articles in a diversity of outlets. Indirectly, the study supports the general view that articles striving towards adding practical relevance to research are becoming more frequent. There is no support for the notion that more renowned and higher-ranked journals would be more hesitant to accept articles with action research methods. The study also notes that there are interesting outlets beside those highly ranked and indexed in more conventional ways. The conclusion reached is that we lack a clear answer to the question of what are the best outlets for those of us who are interested in both innovation and action research. Instead, the study invites us to reflect upon what kind of impact we want to have and then act accordingly.
Keywords: action research; bibliography; case study; innovation; journals; participative; participatory action research

Conceptualizing a New Domain Using Topic Modeling and Concept Mapping: A Case Study of Managed Security Services for Small Businesses - Michael Weiss; Steven Muegge (Technology Innovation Management Review, 2019)
The objective of this paper is to show how topic modeling and concept mapping can be used to conduct a literature review in a new domain. The paper makes two contributions. First, it uses topic modeling to map out the literature in the new domain. Topic modeling provides an alternative to manual clustering of articles and allows the identification of non-obvious connections between ideas expressed in a collection of articles. Second, it identifies the underlying concepts in the new domain and their relationships by creating a concept map from the extracted topics . As a case study, the paper reviews the recent literature in the intersection of managed security services and small businesses. In particular, it identifies elements of the managed security services concept as it applies to small businesses. The audience of the paper includes anyone who is exploring a new domain by reviewing the literature, and in particular, students, researchers, and members of industrial R&D projects.

Connected Health Innovation: Data Access Challenges in the Interface of AI Companies and Hospitals - Laura Kemppainen; Minna Pikkarainen; Pia Hurmelinna-Laukkanen; Jarmo Reponen (Technology Innovation Management Review, 2019)
The purpose of this paper is to explore the challenges and potential solutions regarding data access for innovation in the realm of connected health. Theoretically, our study combines insights from data management and innovation network orchestration studies, taking thereby a new approach into issues that have emerged in these research streams. Empirically, we study these issues in the context of a development endeavor involving an AI-driven surgery journey solution in collaboration with hospitals and companies. Our study indicates that the challenges and solutions in data access can be categorised according to the level where they emerge: individual, organisational, and institutional. Depending on the level, the challenges require solutions to be searched from different categories. While solutions are generally still scarce, organizational level solutions seem The purpose of this paper is to explore the challenges and potential solutions regarding data access for innovation in the realm of connected health. Theoretically, our study combines insights from data management and innovation network orchestration studies, taking thereby a new approach into issues that have emerged in these research streams. Empirically, we study these issues in the context of a development endeavor involving an AI-driven surgery journey solution in collaboration with hospitals and companies. Our study indicates that the challenges and solutions in data access can be categorised according to the level where they emerge: individual, organisational, and institutional. Depending on the level, the challenges require solutions to be searched from different categories. While solutions are generally still scarce, organizational level solutions seem to hold wide-ranging potential in addressing many challenges. By discussing these dynamics, this paper provides new knowledge for academics and practitioners on the challenges and solutions for data access and management in networked contexts. The greatest challenges among healthcare providers and health technology companies lay on uncertainties and interpretations concerning regulation, data strategy, and guidelines. Creating guidelines for data use and access in a hospital can be a first step to creating connected health innovations in collaboration with AI companies. For their part, these companies need to put effort into gaining in-depth knowledge and understanding of the processes and standards in healthcare context. Our paper is one of the first to combine data management and innovation network orchestration literatures, and to provide empirical evidence on data access related issues in this setting.to hold wide-ranging potential in addressing many challenges. By discussing these dynamics, this paper provides new knowledge for academics and practitioners on the challenges and solutions for data access and management in networked contexts. The greatest challenges among healthcare providers and health technology companies lay on uncertainties and interpretations concerning regulation, data strategy, and guidelines. Creating guidelines for data use and access in a hospital can be a first step to creating connected health innovations in collaboration with AI companies. For their part, these companies need to put effort into gaining in-depth knowledge and understanding of the processes and standards in healthcare context. Our paper is one of the first to combine data management and innovation network orchestration literatures, and to provide empirical evidence on data access related issues in this setting.
Keywords: artificial intelligence; connected health; Data access; data management; governance; information mobility; innovation; orchestration; patient- centered

Design Rules for ‘Triple Helix’ Organizations - Ben Dankbaar (Technology Innovation Management Review, 2019)
The image of the triple helix with three forces spiraling around each other has proven to be a powerful and inspiring image of the collaboration between government, business, and academia. The partners in such collaborative arrangements no doubt share an interest in making the collaboration successful. However, they also have specific interests and goals of their own. Too many triple helix arrangements have failed, because they did not consider this basic fact. Achieving their own goals is not necessarily the intention with which partners enter the collaborative effort, but they may well end up following this strategy. We start this paper with a brief description of what can be considered a typical case of ‘successful failure’ in a triple helix organization. We then review the literature regarding reasons for success or failure of triple helix organizations. We find that transparency and credible sanctions for self-interested behaviour are important requirements for successful triple helix arrangements. We then use notions from cybernetics and organizational design to develop basic rules for the design of triple helix arrangements. Basically, these rules and arrangements aim to ensure that self-interest and common purpose will concur.
Keywords: design rules; leadership; motivation; sanctions; triple helix

Digital Payments: Impact Factors and Mass Adoption in Sub-Saharan Africa - Leigh Soutter; Kenzie Ferguson; Michael Neubert (Technology Innovation Management Review, 2019)
This study explores impact factors that affect the adoption of digital payment systems in sub-Saharan Africa. In this article, we investigate the impact factors that subject-matter experts consider most important to the success of FinTech payment models. The data and their responses are evaluated through the lens of Christensen’s market-creation theory, which contends that the adoption of market-creating innovations by a mass swathe of heretofore non-consumers “pulls” framework conditions into place, including missing infrastructure and enabling regulation. Then, we compare the findings with the literature and three case studies of mobile money adoption in Kenya, South Africa, and Nigeria. This study addresses a gap in the literature regarding the payment and money transfer segment of FinTech innovations in Africa using a multiple case study methodology. We drew together information from multiple sources, including semi-structured interviews, archival data in the form of industry and regulatory reports, and observational field notes. Our findings suggest that enabling environments (Kenya) do jumpstart adoption and difficult frameworks (Nigeria) do evolve. This study will help FinTech innovators, academics, and policymakers to understand how technology and framework conditions impact payment business models in Africa.
Keywords: adoption; blockchain; FinTech; mobile money; non-consumption; payments; sub-Saharan Africa

Digital User Involvement in a Multi-Context Living Lab Environment - Lotta Haukipuro; Satu Väinämö (Technology Innovation Management Review, 2019)
This article provides new knowledge on the long-term use and value of a digital user involvement tool as a part of a living lab particularly in ICT, health and public service development contexts. Research has been carried out within the authentic living lab environment in 2011–2018. Empirical evidence is gathered from case living lab digital user involvement platform and activities conducted in multiple contexts. The primary source of information are the 70 in-depth interviews with the customer companies, public organizations and other stakeholders. The digital user community and user involvement tool-specific value for the development of products and services are a fast, easy and efficient user involvement regardless of time and location, tailored online methods based on the need of the customer, and the richness and quality of the end-user feedback.
Keywords: Digital user involvement; living lab.; user community

A Discipline-Spanning Overview of Action Research and Its Implications for Technology and Innovation Management - Matthias Guertler; Nathalie Sick; Anton Kriz (Technology Innovation Management Review, 2019)
The iterative and learning character of action research is particularly beneficial for exploring complex socio-technical problems in technology and innovation management (TIM). In this respect, action research allows both rigorous and relevant research due to parallel solving of real-world problems, capability building, and gaining scientific insights. However, the use of action research within TIM research is surprisingly limited. Action research also is not a homogeneous research methodology since each research discipline, such as education and organizational science, has its own action research streams, which are often only loosely linked. A systematic overview of those action research traditions and specific best practices is still missing, which complicates a systematic transfer and use of action research in TIM. This article addresses this essential gap by building a cross-disciplinary overview of action research streams based on a bibliometric analysis using Scopus. The analysis includes relevant disciplines with action research traditions, their development over time, and the most influential journals, authors, institutions, and countries. Along with this discipline-spanning analysis, the article investigates particular TIM benefits and challenges of action research. The two key contributions of this article are: 1) a discipline-spanning overview of action research and its evolution and 2) an analysis of its implications for TIM research. These contributions build the basis for strengthening the use of action research in TIM. In the medium-term, action research has the capacity to link academia and industry more closely and, in doing so, assists important endeavours of translating more of our research outcomes into practice.
Keywords: action research; bibliometrics; discipline-spanning analysis; literature review; technology and innovation management

The Ecosystem Knowledge Explorer: A Tool to Systematically Discover External Knowledge - Behrooz Khademi (Technology Innovation Management Review, 2019)
It is crucial for any organization to discover knowledge from ecosystem-specific sources of knowledge that are considered external to the organization. Since knowledge exploration is a resource-intensive task for organizations, untimely or excessive knowledge exploration have detrimental impacts on the innovativeness and competitiveness of organizations. The benefits of performance measurement and management tools for knowledge management in organizations have been known for many years now. Therefore, the application of similar tools in ecosystems may enable actors to have access to valuable external knowledge. However, there is a paucity of such tools in management scholarship. The purpose of this study is to bridge this gap by proposing a conceptual tool – the Ecosystem Knowledge (EK) Explorer, which generates insightful knowledge for ecosystem actors using codified technical knowledge (e.g., scientific publications and patents). Not only does the EK Explorer reduce the uncertainty and fuzziness of the knowledge exploration phase for ecosystem actors, it also enables them to save resources and have access to strategic knowledge regarding competition, collaboration, technology management, and policy making in ecosystems. Bibliometric analysis, social network analysis, and text mining were used to conceptualize the constructs and measurable variables of the EK Explorer.
Keywords: ecosystem; knowledge management; performance measurement; social network analysis; text mining

Editorial: Action Research (April 2019) - Chris McPhee; Magnus Hoppe; Erik Lindhult (Technology Innovation Management Review, 2019)
Keywords: action research; innovation; participative; participatory research

Editorial: Action Research (May 2019) - Chris McPhee; Magnus Hoppe; Erik Lindhult (Technology Innovation Management Review, 2019)
Keywords: action research; innovation; participative; participatory research

Editorial: Artificial Intelligence and Innovation Management (December 2019) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2019)

Editorial: Celebrating Innovation in Florence (October 2019) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2019)
Keywords: behavioural economics; behavioural science; bibliometric analysis; business models; Buyer-Supplier Relationships; choice architecture; collaboration; consumer-to-business; Content creator-based business models; content creators; creativity management; digital platforms; digital technologies; digital transformation; Digital user involvement; digitalization; digitization; disruption; e-commerce; human-centered data economy; IIoT; Industry 4.0; innovation; innovation policy; intellectual commerce; Living lab; mission-led science; multisided platforms; personal data; research impact; social commerce; Supplier Integration; taxonomy; user-generated content

Editorial: Insights (November 2019) - Stoyan Tanev; Gregory Sandstrom (Technology Innovation Management Review, 2019)
Keywords: artificial intelligence; competitive advantage; cybersecurity; deep learning; Deepfake; design rules; digitalization; entrepreneurial ecosystems; entrepreneurial university; entrepreneurship; entrepreneurship education; fake news; innovation; international entrepreneurship; leadership; Learning Capabilities; marketing; motivation; new venture teams; quadruple helix; sanctions; SMEs; teamwork; triple helix; university business incubation

Editorial: Smart Cities (September 2019) - Iivari Kunttu (Technology Innovation Management Review, 2019)

The Effect of Digitalization on the Commercialization Process of High-Technology Companies in the Life Sciences Industry - Saheed A. Gbadegeshin (Technology Innovation Management Review, 2019)
This article examines how digitalization influences the commercialization of high technologies in the life sciences industry. It is based on a cross-case study focused on pharmaceutical, medical device, and e-health companies in Finland. Both company representatives and regional stakeholders were interviewed. The findings suggest that “digitalization” needs to be distinguished from “digitization” because both terms seem to be misused or used interchangeably. The findings also show that digitalization led to a concurrent implementation of commercialization processes. Furthermore, the findings revealed that digitalization positively influenced commercialization activities, especially information sourcing and management, various assessments, and official activities, big data creation, and activity routinization. It was also revealed that the creation of new sets of big data and fear of digital attacks are negative influences on digitalization. These findings make a theoretical contribution to the discourses on digitalization and commercialization, but they also provide insights for scientists, engineers, and life science companies.
Keywords: commercialization process; digitalization; Finland; life sciences

E-Leadership in Small and Medium-Sized Enterprises in the Developing World - Maksim Belitski; Bain Liversage (Technology Innovation Management Review, 2019)
Small- and medium-sized enterprises (SMEs) play an important role in the economies of many developing countries. A critical challenge faced by SME leaders, as digitization continues, is how to adopt digital technologies to create value and enable faster product commercialization. There is a paucity of empirical research examining how e-leadership in SMEs drives technology and new product commercialization processes in the developing world. In this study, we have broadened the notion of what constitutes e-leadership, from the perspective of how advanced information technologies affect the leadership dynamic and the appropriation of advanced information technologies. Although there have been several studies on leading technologies in developed countries, we focus on developing an e-leadership framework for SMEs in developing economies. Using this framework and five selection criteria, we conducted 11 interviews with a sample of successful SMEs selected from a pool of 2,240 firms in the city of Johannesburg, South Africa. We conclude by highlighting the five key findings of this study, which explain how SMEs can develop effective e-leadership to foster commercialization and improve firm performance.
Keywords: commercialization; developing country; digital technology; e-leadership; small- and medium-sized enterprises; SMEs

Elon Musk and SpaceX: A Case Study of Entrepreneuring as Emancipation - Steven Muegge; Ewan Reid (Technology Innovation Management Review, 2019)
Elon Musk and SpaceX are central to the profound change underway in the space industry, opening up the sector to entrepreneurship and innovation by non-traditional new entrants. We employ the emancipation perspective on entrepreneuring as a theoretical lens to describe, explain, and interpret the entrepreneuring activities of Musk to launch and grow SpaceX. Applying an event study approach combining case methods and process theory methods on publicly-available sources, we develop six examples of seeking autonomy, seven examples of authoring, and four examples of making declarations—the three core elements of the emancipation perspective. Our work contributes to the theory and practice of innovation by adding to the corpus of descriptive case studies that examine entrepreneuring as an emancipatory process.
Keywords: Elon Musk,

Embedded Master’s Students Conduct Highly Relevant Research Using Industry as Their Laboratory - Kristin Falk; Gerrit Muller (Technology Innovation Management Review, 2019)
This article analyzes participatory action research conducted by Systems Engineering master’s students embedded fifty percent in industrial companies for three years. The resulting papers authored by these students identify challenges and effective practices suitable for knowledge transfer between industry and academia. The analysis covers 181 completed master’s projects, with a detailed analysis of 40 papers that have been published in international conferences and journals. The publication rate of about 23% shows that these students contribute actively to the body of Systems Engineering knowledge. This study analyzes master’s projects at three levels – industrial problem and drivers; Systems Engineering methods; and research method feasibility – and provides valuable lessons learned by applying the industry-as-laboratory approach. Embedding students in industry has resulted in publications that do not suffer from the main challenges of participatory research such as delays, repeatability, and only action and not research. These insights are valuable both for industry and for academia in future work to enhance innovations.
Keywords: action research; energy; experimental learning; industrial knowledge; industry as laboratory; innovations; knowledge transfer; lessons learned; master project; master’s students; participatory research; situated learning; systems engineering; systems of systems

The Emergence of Deepfake Technology: A Review - Mika Westerlund (Technology Innovation Management Review, 2019)
Novel digital technologies make it increasingly difficult to distinguish between real and fake media. One of the most recent developments contributing to the problem is the emergence of deepfakes which are hyper-realistic videos that apply artificial intelligence (AI) to depict someone say and do things that never happened. Coupled with the reach and speed of social media, convincing deepfakes can quickly reach millions of people and have negative impacts on our society. While scholarly research on the topic is sparse, this study analyzes 84 publicly available online news articles to examine what deepfakes are and who produces them, what the benefits and threats of deepfake technology are, what examples of deepfakes there are, and how to combat deepfakes. The results suggest that while deepfakes are a significant threat to our society, political system and business, they can be combatted via legislation and regulation, corporate policies and voluntary action, education and training, as well as the development of technology for deepfake detection, content authentication, and deepfake prevention. The study provides a comprehensive review of deepfakes and provides cybersecurity and AI entrepreneurs with business opportunities in fighting against media forgeries and fake news.
Keywords: artificial intelligence; cybersecurity; deep learning; Deepfake; fake news

Employee-Driven Innovation: An Intervention Using Action Research - Mats Holmquist; Anna Johansson (Technology Innovation Management Review, 2019)
This article describes an intervention to design and test a method for employee-driven innovation and a model for learning among managers and development leaders. The empirical basis for the intervention focused on personal assistants in the home service within a municipality in Sweden. The intervention was carried out using action research in on a series of workshops with a group of employees, managers, development leaders. Using a “stage” and “stands” theatre metaphor, employees engaged in collective, innovative learning “on the stage” combined with observations and reflections from managers and development leaders “in the stands”. This article contributes a method that can generate creative ideas among the employees and a model that can stimulate experience-based learning through observations. The intervention also shows that action research can be used to develop and test methods and models.
Keywords: development; dialogue; ideas; learning; organizational innovation

Escaping the ‘Faster Horses’ Trap: Bridging Strategic Foresight and Design-Based Innovation - Adam Gordon; Rene Rohrbeck; Jan Schwarz (Technology Innovation Management Review, 2019)
Design thinking is inherently and invariably oriented towards the future in that all design is for products, services or events that will exist in the future, and be used by people in the future. This creates an overlap between the domains of design thinking and strategic foresight. A small but significant literature has grown up in the strategic foresight field as to how design thinking may be used to improve its processes. This paper considers the other side of the relationship: how methods from the strategic foresight field may advance design thinking, improving insight into the needs and preferences of users of tomorrow, including how contextual change may suddenly and fundamentally reshape these. A side-by-side comparison of representative models from each field is presented, and it is shown how these may be assembled together to create a foresight-informed design thinking process.
Keywords: design thinking,

Exploring Participation Needs and Motivational Requirements When Engaging Older Adults in an Emerging Living Lab - Tiziana C. Callari; Louise Moody; Janet Saunders; Gill Ward; Nikki Holliday; Julie Woodley (Technology Innovation Management Review, 2019)
There is a growing body of literature regarding living labs, which are seen as an effective way to develop and evaluate research for novel products and services with the actual end users. With growth in the living labs model, there is an increasing need for guidelines to steer and support the set-up and maintenance of initiatives, and to facilitate relationships and engagement with stakeholders and users in this context. This study seeks to address this need, in part, by exploring the needs, expectations, and motivations that older adults have in relation to research participation in an emerging living lab. This work is part of a wider research project to develop an integrated framework to guide emerging living labs. Eight semi-structured interviews were undertaken with six residents and two family members from two residential settings for older adults that were collaborating to establish a living lab environment. A concept-driven coding frame supported the coding and analysis of the interview transcripts. The results provide insights in relation to participant motivation to take part in research, and they identify some issues of concern for participants, both residents and family members, related to living lab initiatives. As a first step in developing a successful living lab culture of collaborative research, this study has demonstrated that open discussion with residents and their families should continue to guide processes and research design as the emerging living lab initiative continues.
Keywords: family views; Living lab; motivation to participate; older adults; research participation; user expectations; user needs

Giving Science Innovation Systems a 'Nudge' - Kirsty de Jong; Urs Daellenbach; Sally Davenport; Jarrod Haar; Shirley Leitch (Technology Innovation Management Review, 2019)
In this article we consider the role that contextual factors play in science innovation systems – that is, the choice architecture, that influences the orientation and outcomes of publicly-funded research. More specifically, we examine how choice architects, particularly policymakers and funding administrators, can affect the decision-making behaviour of researchers. The context for today’s science innovation systems continues to shift as governments seek solutions to the world’s “grand societal challenges”, such as climate change and ageing populations, in addition to greater and more demonstrable impact from funded research. This means that the assumptions of “basic research [being] performed without thought of practical ends” (Bush, 1945) that have shaped such projects, actually run counter to the growing expectations of greater commercialisation and use of multidisciplinary mission-led approaches. We argue that a closer examination of the choice architecture for publicly-funded research is required to understand and address how these potentially conflicting objectives may be pursued most productively through interventions that could form the basis of a novel, behaviourally-based toolkit for science innovation policy.
Keywords: behavioural economics; behavioural science; choice architecture; innovation policy; mission-led science; research impact.

How to Create Value(s) in the Sharing Economy: Business Models, Scalability, and Sustainability - Aurélien Acquier; Valentina Carbone; David Massé (Technology Innovation Management Review, 2019)
By organizing peer-to-peer exchanges and promoting access over ownership, the sharing economy is transforming a great variety of sectors. Enjoying fast growth, the sharing economy is an umbrella term encompassing heterogeneous initiatives that create different types of economic, environmental, or social value. This heterogeneity triggers tensions and intense disputes about the perimeter of the field. Do Airbnb and Uber belong to the sharing economy? How do we consider practices such as gifting, renting, and swapping that existed before the sharing economy boom? To sort out this complexity, we have adopted a pragmatic and grounded approach examining 27 initiatives that claim to be part of, or are perceived as emblematic of the sharing economy. We develop a typology of sharing economy business models revealing four configurations: shared infrastructure providers, commoners, mission-driven platforms, and matchmakers. Each configuration exhibits specific value-creation logics, scalability issues, sustainability impacts, and potential controversies. Our results provide guidance for sharing entrepreneurs, for established businesses that want to embrace the principles of the sharing economy, and for public actors wishing to regulate or support the field.
Keywords: business model; scalability; sharing economy; sustainability; value creation; value distribution

How to Develop a Digital Ecosystem: a Practical Framework - Omar Valdez-de-Leon (Technology Innovation Management Review, 2019)
Throughout the modern industrial era, industries have generally been organised as linear value chains. This gave birth to the vertically integrated organisation, which was organised in such a way in order to control the entire value chain and achieve economies of scale, which in turn would create a significant competitive advantage. As digital technologies continue gaining adoption, they start enabling new ways of organising how value is created. This transition means moving from value chains to digital ecosystems. This is giving way to new industry giants, which rely on the strength of their digital ecosystems to attain market dominance. However, there is still limited knowledge of digital ecosystems: how they are created, how they work and, importantly, how organisations beyond digital giants can approach digital ecosystems. Based on literature review and expert surveys and interviews, this piece puts forward a practical framework for both established organisations and entrepreneurs to better understand, plan and navigate the new paradigm of digital ecosystems.
Keywords: Digitization,

How to Develop an Impactful Action Research Program: Insights and Lessons from a Case Study - Victoria Lakiza; Isabelle Deschamps (Technology Innovation Management Review, 2019)
Action research holds great potential for helping bridge the gap between research and practice. By working closely together, researchers and practitioners can develop tangible customized solutions based on research findings. It becomes possible to go beyond generic best practices that might need adaptation for successful implementation and use, or that may not apply at all in some contexts. In this article, the mechanisms through which action research can create the desired change and impact in both industry and academia are illustrated by describing the relevance and contribution of the main steps of a longitudinal action research program in a Canadian manufacturing company. The authors share four guiding principles and six success factors that were revealed intuitively in the course of this multi-year research program. Their hope is to contribute to a better understanding of how it is possible to develop an adaptive action research methodology to increase the potential for research relevance and organizational change.
Keywords: action research; guiding principles; Innovation management; research practice gap; success factors

Human Capital, Its Constituents, and Entrepreneurial Innovation: A Multi-Level Modelling of Global Entrepreneurship Monitor Data - Vijay Vyas; Renuka Vyas (Technology Innovation Management Review, 2019)
In this study, we use multi-level modelling to analyze data of over 200,000 businesses in 96 countries to explain the failure of previous research to extend human capital theory to innovation. We trace this failure to, previously overlooked, conflicting influences of education and experience, the two key constituents of human capital that are often used in research as innovation antecedents and present a conceptual and empirical case against the use of work experience as a constituent of human capital. Our hierarchical exploration of innovation antecedents shows that, at the individual level, being young and recently educated are significant predictors of innovation whereas, at the societal level, national wealth dampens the negative effect of age on innovation and accentuates the positive effect of education on it.
Keywords: age,

The Impact of Digitalization and Resources on Gaining Competitive Advantage in International Markets: Mediating Role of Marketing, Innovation and Learning Capabilities - Yan Yin Lee; Mohammad Falahat (Technology Innovation Management Review, 2019)
International Entrepreneurship as a field of studies depends on digitalization as an essential factor that drives internationalization. Riding on the wave of digitalization, firms can produce and market their products and services globally through digital platforms with reduced costs and time savings. Yet, digitalization as a determinant of competitive advantages for small and medium enterprises in international markets is rarely examined. This study fills the gap by testing the direct and indirect effects of digitalization on enterprise, specifically focusing on price, product and service advantages in digitalized international markets. Based on the data collected from 143 exporting SME manufacturers in Malaysia, results from our analysis revealed that digitalization has no direct effect on competitive advantage, but rather has strong indirect effects on product and service advantages. Managers and policymakers can thus leverage digitalization to improve their company's internationalization plans according to its intended competitive strategies.
Keywords: competitive advantage; digitalization; innovation; international entrepreneurship; Learning Capabilities; marketing; SMEs

Increasing the Impact of Industry–Academia Collaboration through Co-Production - Anna Sannö; Anna Ericson Öberg; Erik Flores-Garcia; Mats Jackson (Technology Innovation Management Review, 2019)
Increased competition and globalization motivate us to join forces to enhance the impact of the research conducted. Collaboration between organizations with different views can, however, be difficult to manage and needs awareness and skills to meet different expectations. This article will consider both a mutual industrial and academic perspective into the development of action research and, in six research project cases, empirically explore how the impact can be enhanced by considering certain key factors in the research process. How the phases of problem formulation, methodology, and results are managed is critical for the success of a collaboration and, thereby, its impact. Counter-productive forces that could dilute the progress over time need to be considered given that combining practical relevance and scientific rigour comes with challenges.
Keywords: action research; co-production; collaboration; impact; industry–academia collaboration; key factors; relevance; rigour

Innovation Ecosystems as Structures for Value Co-Creation - Sanna Ketonen-Oksi; Katri Valkokari (Technology Innovation Management Review, 2019)
Despite the many recent discussions on “innovation ecosystems” as well as on open innovation or other co-innovation models, a more in-depth understanding of the multi-actor processes of value co-creation remains rather scarce. Hence, in this case study, we provide significant novel insight about innovation ecosystems as structures enabling multi-actor value co-creation in real-life innovation ecosystems. Based on our empirical findings, we identified two key principles: 1) in order to encourage the active participation of ecosystem actors in the value co-creation process, efforts must be made to ensure a clear vision and a shared value base on which the ecosystem activities can be built and 2) facilitation is needed to support the ecosystem actors to make new connections and to share their knowledge and resources in concrete ways. Most importantly, the more diversity there is among the ecosystem actors, the greater the support for innovativeness within the value co-creation process.
Keywords: ecosystems; innovation; platforms; value co-creation

Innovation Management in Living Lab Projects: The Innovatrix Framework - Dimitri Schuurman; Aron-Levi Herregodts; Annabel Georges; Olivier Rits (Technology Innovation Management Review, 2019)
Despite living labs being described as “orchestrators” and innovation intermediaries, there is scant literature providing concrete guidelines and tools for living lab practitioners on the topic of project-related innovation management. To address this need, we propose Innovatrix, an innovation management framework built upon existing business model and innovation management tools and frameworks and iterated based on practical experience in living lab projects. In this article, we illustrate the added value of the proposed framework through three practical case studies that lead to three propositions regarding innovation management in living lab projects. First, Innovatrix helps to scope the user involvement activities, which leads to greater efficiency and faster decision making. Second, Innovatrix forces the project owner to focus on a limited number of customer segments, which increases the speed of learning as the scarce entrepreneurial resources are dedicated to a limited number of segments. Third, Innovatrix allows practitioners to capture the iterations and pivots that were made during an innovation project, which helps to link specific outcomes with certain living lab activities.
Keywords: assumption; business modelling; Innovation management; living labs; testing; user research; validation

Is Joining a Business Incubator or Accelerator Always a Good Thing? - Kristina Lukosiute; Søren Jensen; Stoyan Tanev (Technology Innovation Management Review, 2019)
Business incubators and accelerators are often hailed as essential tools for fostering growth in startups. However, not only do entrepreneurs often face the question of which incubator or accelerator to join, we suggest that they should also question whether or not to join one at all. Is joining a business incubator or accelerator always a good thing? In this article, we investigate some of the negative outcomes entrepreneurs can experience when engaging with an incubator or accelerator. We apply a cross-case analysis of empirical observations from qualitative interviews with Danish and Canadian entrepreneurs to arrive at a set of recommendations that entrepreneurs should keep in mind when considering such an engagement. These points are further qualified based on informal interviews with four serial entrepreneurs.
Keywords: accelerator; Canada; Denmark; disadvantages; incubator; Lithuania; new venture; start-up

Kick-Start for Connectivity: How to Implement Digital Platforms Successfully in Industry 4.0 - Marie-Christin Schmidt; Johannes W. Veile; Julian M. Müller; Kai-Ingo Voigt (Technology Innovation Management Review, 2019)
Based on digitalization and interconnectedness, Industry 4.0 causes a structural change in the value creation processes, and thus reinforces the transformation of business processes and business models. One way for companies to cope with this development and its associated challenges is to apply digital platforms in the value creation process. As the potential of digital platforms for industrial value creation can only be leveraged to its full extent with adequate implementation, this paper addresses the research question: How are digital platforms best implemented in Industry 4.0 contexts; Using a qualitative case study design, based on 32 semi-structured expert interviews, the study identifies different triggers and initiators, challenges, and respective countermeasures, as thematic core elements of implementation, and requirements for platforms. The research insights contribute to existing literature on Industry 4.0 and digital platforms. In addition, the paper discusses practical implications for industrial companies.
Keywords: Buyer-Supplier Relationships; collaboration; digital platforms; Digital Technologies.; IIoT; Industry 4.0; Supplier Integration

Leveraging AI-based Decision Support for Opportunity Analysis - Wolfgang Groher; Friedrich-Wilhelm Rademacher; André Csillaghy (Technology Innovation Management Review, 2019)
The dynamics and speed of change in corporate environments have increased. At the front-end of innovation, firms are challenged to evaluate growing amounts of information within shorter time frames in order to stay competitive. Either they spend significant time on structured data analysis, at the risk of delayed market launch, or they follow their intuition, at the risk of not meeting market trends. Both scenarios constitute a significant risk for a firm’s continued existence. Motivated by this, a conceptual model is presented in this paper that aims at remediating these risks. Grounded on design science methodology, it concentrates on previous assessments of innovation search fields. These innovation search fields assist in environmental scanning and lay the foundation for deciding which opportunities to pursue. The model applies a novel AI-based approach, which draws on natural language processing and information retrieval. To provide decision support, the approach includes market-, technology-, and firm-related criteria. This allows us to replace intuitive decision-making by fact-based considerations. In addition, an often-iterative approach for environmental scanning is replaced by a more straightforward process. Early testing of the conceptual model has shown results of increased quality and speed of decision-making. Further testing and feedback is still required to enhance and calibrate the AI-functionality. Applied in business environments, the approach can contribute to remediate fuzziness in early front-end activities, thus helping direct innovation managers to “do the right things”.
Keywords: front-end of innovation; environmental scanning; information processing; opportunity; innovation search field; information retrieval; artificial intelligence; decision-making; latent semantic indexing; design-science

Live and Let Die: On the Management of Creativity - Michael Hartmann; Désirée Laubengaier; Kai Foerstl (Technology Innovation Management Review, 2019)
Literature has pointed to the importance of feedback on creative ideas in innovation management processes. However, little is known about the practices that constitute the feedback process and their effect on employees’ future willingness to consistently and recurrently contribute with creative ideas to organized innovation management efforts. In this research, we draw on data from a single case study at a German multinational manufacturing firm. We show the flip side of managerial attempts to provide feedback and foster employees’ creative output. In particular, we identify distinct practices organizational actors employ along the sequence of idea generation, elaboration, championing, and implementation, and find that the practices can turn organized innovation management efforts into a political process. Furthermore, we present a virtuous and a vicious circle of managerial attempts to manage creativity in innovation processes. In doing so, we highlight the value of taking a practice lens to better understand the challenges in organized innovation management efforts and propose future research in other contexts. We suggest that managers should flexibly design organized innovation management processes to account for radical ideas and to pay close attention to a coherent communication when providing feedback and encouraging employees to contrive creative ideas. Our work contributes to the body of research on innovation management by shedding light on the dark side of organized innovation management efforts.
Keywords: case study; creativity; Feedback; Innovation management; Qualitative Research.

A Management Innovation Approach to Project Planning - Haven Allahar (Technology Innovation Management Review, 2019)
Innovation is viewed as indispensable to the economic and social development of countries, and the subject has been widely researched. The initial research focused on the development of new products and services by firms applying technological initiatives. The concept has expanded to cover many domains and features of innovation that led to innovation in non-technological areas, currently referred to as “management innovation”. Many tools were developed by management specialists and gurus such as strategic planning, vision and mission statements, benchmarking, customer-satisfaction measurement, and outsourcing to target performance improvements in firms. The output of this article is a project development planning model that integrates management innovation tools related to the field of project planning as a novel approach tested by a consulting firm over several applications. The article has implications for managers, consultants, and professionals involved in the design, planning, and implementation of a varied range of development projects.
Keywords: innovation; management innovation; management innovation tools; scenario planning; strategic foresight

Mastering the Digital Transformation Process: Business Practices and Lessons Learned - Lucija Ivančić; Vesna Bosilj Vukšić; Mario Spremić (Technology Innovation Management Review, 2019)
Due to its unique features and accessibility, the focus of implementing digital technology is no longer just to improve internal operations, but to expand internal dimensions, reach customers and external partners, affect services, integrate processes, disrupt markets, and fundamentally change industries. It is no surprise that the notion of digital transformation has garnered much research interest, especially from the practitioners’ point of view, but academic achievements are somehow lagging behind, possibly because frameworks for digital transformation are still evolving. In this article, we tried to address that gap by conducting holistic research of digital transformation in companies. We used a series of in-depth interviews to inform comprehensive case studies of three companies from different industries that are in different stages of digital transformation. We carefully investigated the companies’ experiences in the process of digital transformation, which are discussed here to provide valid theoretical framing. We conclude that, in addition to technology adoption, important factors for successful digital transformation are the ability of an organization to change and operational excellence in the integration of external digital services with internal IT support. In that light, we summarize our findings in a form of discovered (sub)dimensions that are the basis for the proposed digital transformation framing, while the narratives and case experiences provide with examples of best practice.
Keywords: case study; change management; digital business; digital model; digital transformation; digital transformation model; digitization; human capital; Innovation management; talent management

Multidimensional Data-Driven Artificial Intelligence Innovation - Sergey A. Yablonsky (Technology Innovation Management Review, 2019)
This is a critical time for the development and adoption of Artificial Intelligence (AI). The field has existed since the 1950s and is only now emerging as viable for commercial markets. Many enterprises are placing bets on AI that will determine their future. Today AI innovation becomes useful when it enriches decision-making that is enhanced by applying Big Data (BD) and Advanced Analytics (AA), with some element of human interaction using digital platforms. This research investigates an opportunity for cross-fertilization between AI, BD, and AA with related disciplines. The paper aims to investigate the potential relationship of AI, BD, and AA with digital business platforms. In doing so, it develops a multidimensional BD-driven AI innovation taxonomy framework with an AA/BD/AA innovation value chain, related levels of BD, and analytics maturity improvement. This framework can be used with a focus on data-driven human-machine relationships, and applying AI at different levels of data driven automation maturity.
Keywords: Advanced Analytics; AI maturity; AI value chain; Artificial Intelligence (AI); big data; enterprise platform; innovation

Navigating Boundaries in Additive Manufacturing through Action Research - Katharina Ruckstuhl; Rafaela C. C. Rabello; Sally Davenport (Technology Innovation Management Review, 2019)
Action research – both as praxis but also from a critical orientation – can elaborate modes of action, identifying the borders and margins that act as both the productive spaces for collaboration as well as the fuzzy areas that require reflection and clarification. In this exploratory case study, action research is used to follow an additive manufacturing project team in real time as it navigates fuzzy areas to integrate knowledge to produce commercializable science innovation in one of New Zealand’s National Science Challenges (NSC): Science for Technological Innovation – Kia Kotahi Mai: Te Ao Pūtaiao me Te Ao Hangarau (SfTI). Through action research as praxis and as critical orientation, we have identified key mechanisms in interdisciplinary and transdisciplinary research for commercialization, particularly in the context of New Zealand’s indigenous Māori people. Our preliminary analysis indicates that an explicit understanding of the fuzzy spaces can help teams find creative and collaborative means to navigate the productive but challenging “interstices of disciplines” (Mengis et al., 2018) to produce science innovation and discoveries and to galvanize relationships with industry and Māori participants. The findings also indicate that action research can promote structural, relational, and knowledge changes within teams, helping them solve complex problems in real time.
Keywords: action research; critical orientation; innovation; science; SfTI; transformative praxis

Open Data and Open Source Enabling Smart City Development: A Case Study in Häme Region - Jari Jussila; Joni Kukkamäki; Mikko Mäntyneva; Juuso Heinisuo (Technology Innovation Management Review, 2019)
Open data offers possibilities to accelerate both innovations and co-creation activities in cities and regions. Likewise, open source software development is an efficient way to create new services. Open data can be used to promote better information sharing and offers various opportunities for third-party developers. Co-creation improves the commitment of different stakeholders and ensures that the created solutions are based on real needs. For these reasons, it is only logical that these two themes are linked together in smart city activities. This paper presents a practical open data and co-creation development made in the region of Häme, Finland. This paper contributes to smart cities research by describing the development of two smart city services: the Tavastia Events API and "Hämeenlinna in pocket" smartphone application. It describes strategies that facilitate beneficial participation and collaboration in smart city open data initiatives. Based on Linked Events, an open source solution developed for the city of Helsinki, modification and implementation were made to create a centralized and open service, to collect and publish event-related data via an application programming interface (API) in the Häme region. A smartphone application was then developed, making use of the developed Events API and other data sources, to provide citizens with the most common digital services, and a platform for digital participation in Häme.
Keywords: Smart city,

Open Strategy in a Smart City - Suvi Einola; Marko Kohtamäki; Harri Hietikko (Technology Innovation Management Review, 2019)
To attract new companies and a talented workforce in a way that increases income streams, cities are searching for strategic capabilities by using a variety of strategic practices. The present study participates in the theoretical debate between micro- and macro-strategizing by focusing on the interplay between the city organization and its institutional environment. As such, the study elucidates the open strategy process used in the strategy work of a medium-sized city in Finland. To make the strategy work open and encourage citizens’ participation, the city decided to utilize crowdsourcing as a tool that was part of a broader strategy process to develop a city strategy in a participative manner. The present study analyzes the responses of almost 2000 citizens who addressed the role of an open strategy in developing a smart city. The study contributes by depicting how the open strategy was utilized in practice and what types of outcomes it produced.

Q&A. What Can Action Research Learn from Business Environment Analysis? - Bengt Wahlström (Technology Innovation Management Review, 2019)
Keywords: action research; business environment analysis; consultancy; consultants; organizations

Scientific Excellence in Participatory and Action Research: Part I. Rethinking Research Quality - Erik Lindhult (Technology Innovation Management Review, 2019)
A core impetus of participatory and action research is making science relevant and useful for solving pressing problems and improving social conditions, and enabling stakeholders to participate in research and development processes. There are claims in the community of participatory and action research of the potential for heightened scientific excellence, but at the same time, there are critiques in the mainstream community that more engaged, even activist, stances threaten scientific norms or that position these type of research approaches outside the field of science, for example, as issues of application. In the search of clarification of the scientific identity and the specific qualities of participatory and action research, scholars have been moving away from and sometimes have rejected traditional conceptions of quality. This leads to confusion about how to relate to the discourse on research quality and scientific excellence in mainstream science. Integration in this discourse is important in order to attain academic legitimation in prevailing institutions of science, for example, in applications for funding, in seeking to publish research, and in the acceptance of dissertations based on participatory and action research. The purpose of this article is to contribute to this integration by reconstructing the way traditional quality concepts – validity, reliability, and objectivity – can be fruitfully used in expanded frameworks for quality where scientific excellence of participatory and action approaches are visible and where mainstream science approaches also can be harboured. In this conceptual article, reconstruction of understanding of scientific inquiry is first made based on a praxis-oriented epistemology inspired by pragmatism. Through rethinking truth as trustworthiness, new proposals for the conceptualization and frames for research quality and scientific excellence are introduced. Second, a framework for understanding purpose in science and its basis in validity, reliability, and the core characteristics of participatory and action research is developed. Third, the turn to action, practice, and participation enables plural ways of knowing and ways that knowledge claims can be validated and made trustworthy. The article concludes that participatory and action research offers a broader landscape of purpose and validation than more traditional approaches to science. In a subsequent article, reliability and objectivity, and their use in participatory and action research, will be clarified.
Keywords: action research; participatory research; quality

Scientific Excellence in Participatory and Action Research: Part II. Rethinking Objectivity and Reliability - Erik Lindhult (Technology Innovation Management Review, 2019)
The purpose of this article is to deal with the following question: Can the concepts of reliability and objectivity be reconceptualized and reappropriated to enable understanding of scientific excellence in participatory and action research? The article shows that it is fruitful to consider the “subjective” and active role of researchers as vital in enabling scientific objectivity and reliability. As an expansion from a replication logic, reliability can be conceptualized as adaptive, goal-seeking, dynamically regulated processes enabled by effective organization of interactive and participatory learning processes where all participants can contribute to learning and correction in inquiry. Instead of erasing subjectivity, objectivity can be enabled by critical subjectivity, intersubjectivity, practical wisdom, impartial norms of inquiry, and open democratic dialogue. Reliability and objectivity in this understanding can be enabled by participatory and action research through skilful performance of research practices such as reflective conversations between parties, dialogue conferences, experimentation, and experiential learning as part of action-research cycles, etc., which are common in participatory and action research initiatives and projects. By rethinking validity, reliability, and objectivity, recognizing the substantially more active and participatory stances enables scientific excellence, it can expand the repertoire of strategies for promoting research quality, and it helps to mainstream this type of approach in the scientific community.
Keywords: action research; objectivity; participatory research; reliability

The SDG-Check: Guiding Open Innovation towards Sustainable Development Goals - Justus von Geibler; Julius Piwowar; Annika Greven (Technology Innovation Management Review, 2019)
The “fuzzy front end” of innovation is argued to be crucial for the success and sustainability impact of a final product. Indeed, it is a promising area of focus in efforts to achieve the United Nations’ 2015 Sustainable Development Goals (SDGs), which provide a globally accepted framework for sustainability. However, the usability of the 17 goals and the large number of sub-goals represent barriers to innovation practitioners. Moreover, this early innovation stage proves to be a challenge for corporate practitioners and innovators, largely due to the concept’s intangible, qualitative nature and the lack of data. To help overcome these barriers, this article proposes a four-stage approach for structuring the innovation process using an online tool called the “SDG-Check”, which help assess an innovator’s sustainability orientation in the early phases of product and service development. It is a semi-quantitative tool to gather and combine assessments by experts involved in innovation processes with implications for the United Nations’ SDGs. Furthermore, this article presents our first experiences in applying the SDG-Check based on three living lab innovation cases. The results indicate that the tools can support and inspire a dialogue with internal and external stakeholders with regards to sustainability considerations in the early design stages of product and service development.
Keywords: fuzzy front end of innovation; Living lab; Open innovation; SDG-Check; sustainability assessments; sustainability inspiration; sustainable development goals

Smart Mobility: Services, Platforms and Ecosystems - Jukka Pulkkinen; Jari Jussila; Atte Partanen; Igor Trotskii; Aki Laiho (Technology Innovation Management Review, 2019)
In this study, we provide novel insight into building and managing growth in a new emerging market: the operation and maintenance of a heterogeneous and expanding vehicle fleet in a smart city environment. There are several different types of players in this emerging market and a dominant player is still missing. Based on our empirical findings, we identified three key characteristics of a growing business and the ability to reach a leading position: 1) co-creation through resource integration and service exchange is preferable for responding to market demands; 2) a digital platform is critical to create the necessary knowledge for resource integration and service exchange; and 3) smart services glue the ecosystem and platform together and create the outcome that solves the defined business problem. Most importantly, all three elements—ecosystem, platform and smart services—create a uniform environment in which to grow the business in a new emerging market.

The Status and Future of Action Research: An Interview with Professor David Coghlan - David Coghlan; Erik Lindhult (Technology Innovation Management Review, 2019)
Keywords: action research; David Coghlan; insider action research; interiority; interview; reflection

The Strategies of Technology Startups Within and Between Business Ecosystems - Taina Tukiainen; Thommie Burström; Martin Lindell (Technology Innovation Management Review, 2019)
Technology startups build strategies in order to survive within the framework of business ecosystems. However, the knowledge required to make such strategies effective is scarce. This article poses the question: “How do small technology startups strategize within and between business ecosystems?” Based on an explorative qualitative study, this article defines and presents a dynamic strategic framework of three strategies employed by technology startups. Some startups choose to act within one defined business ecosystem, most startups use a multi-ecosystem strategy to act between and draw benefits from many business ecosystems, and the rest act as ecosystem creators that challenge the logics of existing ecosystems.
Keywords: boundaries; business ecosystems; entrepreneurship; startups; strategy

Strategy-as-Process in a Technology Venture: A Case Study of Pivots, Pauses, Partners, and Progress - Andrew G. Earle; Michael J. Merenda; J. Matthew Davis (Technology Innovation Management Review, 2019)
Technology commercialization is an often nonlinear process that tends to pass through various “stages” or “phases” as a venture attempts to shepherd a technology from the laboratory to marketplace. Between these phases are “junctures” or “transitions” that present particular challenges for entrepreneurs as they often comprise fundamental changes to the venture instead of simply scaled versions of previous challenges. In this study, we use a participant-observer methodology to deeply explore how a technology venture in the renewable energy sector negotiated these transitions. Our findings highlight the development of a “repertoire” of tools entrepreneurs can use to help successfully negotiate these transitions.
Keywords: innovation systems; managing critical junctures and transitions; process research; technology commercialization; technology entrepreneurship

Towards a Smart City Concept in Small Cities - Heikki Ruohomaa; Vesa Salminen; Iivari Kunttu (Technology Innovation Management Review, 2019)
The smart city concept brings together technology, government and different layers of society, utilizing technological enablers, such as the internet of things (IoT) and artificial intelligence (AI). These enablers, in turn, facilitate development of various aspects of the smart city including, e.g., transportation, governance, education, safety and communications. However, the transition towards smarter cities involves not only technological development but also the changing and evolving roles of citizens, service providers and city authorities. In this transition, the key issue is creating and growing roles of collaboration, participation and coordination. Whereas mainstream research focuses on smart city transformation in big cities, aspects of this transformation in the context of small cities has been a widely neglected topic. This paper presents three cases of smart city development in small cities in Finland, each concentrating on a different aspect of smart city development. The cases reveal how a relatively small-sized city may take remarkable steps in smart city development by selecting a specific theme on which to build smart city activities. These examples also emphasize the critical role of public sector actors, showing that the public sector has a key role in creating the foundations for fruitful ecosystem-based development work.

Towards a Taxonomy of E-Commerce: Characterizing Content Creator-based Business Models - Martin D. Mileros; Nicolette Lakemond; Robert Forchheimer (Technology Innovation Management Review, 2019)
Currently, new business models can be observed in content creator-based e-commerce. The research on e-commerce has grown rapidly and new concepts have emerged such as social commerce, platforms, and user-generated content. However, no overarching perspective has yet been formulated for distinguishing new content creator-based business models within e-commerce. The aim of this paper is therefore to characterize content creator-based business models by formulating a taxonomy of e-commerce based on a structured literature review of the concepts mentioned above. The results of our study point toward eight types of content creator-based business models. Our paper outlines theoretical and practical implications for the emerging phenomenon of content creator-based business, which we refer to as intellectual commerce. In addition, we describe 19 concepts related to Web 1.0, Web 2.0, and e-commerce.
Keywords: consumer-to-business; Content creator-based business models; content creators; e-commerce; human-centered data economy; intellectual commerce; multisided platforms; personal data; social commerce; user-generated content

Uncovering Research Streams in the Data Economy Using Text Mining Algorithms - Can Azkan; Markus Spiekermann; Henry Goecke (Technology Innovation Management Review, 2019)
Data-driven business models arise in different social and industrial sectors, while new sensors and devices are breaking down the barriers for disruptive ideas and digitally transforming established solutions. This paper aims at providing insights about emerging topics in the data economy that are related to companies’ innovation potential. The paper uses text mining supported by systematic literature review to automatize the extraction and analysis of beneficial insights for both scientists and practitioners that would not be possible by a manual literature review. By doing so, we were able to analyze 860 scientific publications resulting in an overview of the research field of data economy and innovation. Nine clusters and their key topics are identified, analyzed as well as visualized, as we uncover research streams in the paper.
Keywords: big data; Data Economy; Data Ecosystem; Data Market; digital economy; digital transformation; literature review; Network Graph; Text Mining.

Understanding Digital Innovation from a Layered Architectural Perspective - Jesper Lund; Esbjörn Ebbesson (Technology Innovation Management Review, 2019)
Managing successful digital innovation processes is a challenging task, especially when it involves heterogeneous actors with different sets of knowledge. By gaining a better understanding of how different architectural layers of digital technology interplay with digital innovation, we can be better prepared for managing the complex and messy processes that often arise when working with digital innovation. In this article, we therefore ask: How does the layered architecture of digital technology interplay with digital innovation processes? A case study approach was selected to studied events involving multiple actors in an innovation and development project called the Smart Lock project. The theoretical basis for our study is digital innovation from the perspective of knowledge exchange and relationships. A temporal bracketing strategy was used to support a process analysis of the case data. The article primarily contributes to the body of research concerning digital innovation and provides an example to practitioners of how digital innovation processes can be coordinated and managed based on the innovation at hand.
Keywords: collaborative innovation; concept development; digital innovation; digital technology; innovation process

A University Business School as an Entrepreneurial Ecosystem Hub - Haven Allahar; Ron Sookram (Technology Innovation Management Review, 2019)
This article assesses the progress of a business school toward achieving the status of an entrepreneurial ecosystem hub with emphasis on the components related to entrepreneurial universities, entrepreneurship education, university business incubators, and university-enterprise-government-civil society collaboration. The objective of a business school serving as an entrepreneurial ecosystem hub, is to stimulate economic development, generate employment, and create innovative technology-based ventures or service businesses. These components are discussed from theoretical and practical viewpoints in order to provide greater understanding of the concepts. An insider action research assessment of the university-affiliated business school was conducted to gauge the progress made in building an embryonic entrepreneurial ecosystem centered upon a business school as a hub. Emphasis is placed on the need to develop strong collaboration among key stakeholders for achieving success in building an effective entrepreneurial ecosystem based on a quadruple helix system, consistent with the lead-in quotation to the article.
Keywords: entrepreneurial ecosystems; entrepreneurial university; entrepreneurship education; quadruple helix; triple helix; university business incubation

Urban Living Labs: Towards an Integrated Understanding of their Key Components - Diana Chronéer; Anna Ståhlbröst; Abdolrasoul Habibipour (Technology Innovation Management Review, 2019)
In today’s ongoing urbanization and escalating climate change, there is an increasing demand on cities to be innovative and inclusive to handle these emerging issues. As an answer to these challenges, and in order to generate and adopt sustainable innovations and nature-based solutions in the urban areas, the concept of urban living labs has emerged. However, to date, there is confusion concerning the concept of the urban living lab and its key components. Some interpret the urban living lab as an approach, others as a single project, and some as a specific place – and some just do not know. In order to unravel this complexity and better understand this concept, we sought to identify the key components of an urban living lab by discussing the perspective of city representatives in the context of an urban living lab project. To achieve this goal, we reviewed previous literature on this topic and carried out two workshops with city representatives, followed by an open-ended questionnaire. In this article, we identify and discuss seven key components of an urban living lab: governance and management structure; financing models; urban context; nature-based solutions; partners and users (including citizens); approach; and ICT and infrastructure. We also offer an empirically derived definition of the urban living lab concept.
Keywords: definition; innovation; key components; Living lab; nature-based solutions; NBS; ULL; UNaLab; urban living lab

Using Action Research to Organize Technology Transfer in Complex Innovation Contexts - Armando Machevo Ussivane; Paul Ellwood (Technology Innovation Management Review, 2019)
Technology transfer projects increasingly consist of multiple, diverse organizations, with each pursuing their own agenda as well as that of the overarching programme. In this article, we adopt a participatory action research methodology in order to explain and improve the coordination of the autonomous innovation activities within an organizationally complex project. The context of the research involved the transfer of rice production technology from China to Mozambique. The action research identified four categories of boundary within the project that were hindering performance: Intellectual/Land property rights; Public/Private sector logics; Inside/Outside programme; and Collaboration/Competition between programme actors. The process of co-inquiry with stakeholders enabled by the action research allowed programme actors to reach an understanding of others, and it created a new thinking space for mutual problem solving. By these means, the action research process makes a resource of the differences between stakeholders rather than it being seen as a barrier to be compromised through negotiation.
Keywords: action research; agricultural innovation; boundaries; international collaboration; technology transfer

Women Managers and Entrepreneurs and Digitalization: On the Verge of a New Era or a Nervous Breakdown? - Mervi Rajahonka; Kaija Villman (Technology Innovation Management Review, 2019)
The purpose of this article is to examine how female managers and entrepreneurs are employing digital technologies in their working and private lives and what they think about digitalization. The material for the study was gathered through interviews with women in South Savo, Finland. The article builds on the theory of technology domestication, emphasizing the role of users in making a technology usable in their everyday contexts. The findings show that women experience challenges but also gain clear benefits when employing digital technologies. Among the challenges is that women are traditionally rather reserved when it comes to applying technology. Among the benefits is the practice-oriented stance of women towards digital technologies. Moreover, the rise of digital social media and its increasing importance in the working and business environments could make it easier for women to manage both work- and family-related communication. This may improve their wellbeing at work and help women towards equality at work. However, they need support in finding their digitalized career paths.
Keywords: domestication; family; ICT; technology; wellbeing; women; work

Working with Startups? These are the Three Things You Ought to Know about Startup Teams - Anna Brattström (Technology Innovation Management Review, 2019)
While much has been written about how startups work to develop their product, this paper focuses instead on how to manage the startup team. Based on a systematic review of current research, I present actionable insights about startup team characteristics; who they are, how they work, and how they stay together. I explain how these characteristics imply both opportunities and threats for the viability of the team and discuss how startup teams can be managed to increase the likelihood of their survival and growth. Given that the majority of startup failures are attributed to the team, not to the product, these insights are valuable both to aspiring entrepreneurs and to their external stakeholders.
Keywords: entrepreneurship; new venture teams; teamwork

World Heritage meets Smart City in an Urban-Educational Hackathon in Rauma - Anu Helena Suominen; Seija Halvari; Jari Jussila (Technology Innovation Management Review, 2019)
UNESCO World Heritage cities can become smart cities if they take into account their cultural heritage and integrate diverse actors, including universities in their innovation practices. This article addresses the hackathon as an innovation contest method in the urban and educational context. Specifically, it concentrates on hackathon design, particularly the focus of the event, as well as the outputs. Although the design plays an integral part in a hackathon, particularly in goal achievement, design has not yet been thoroughly studied in mainly descriptive hackathon research. To address the subject, this article presents a case study of a dual-focused, i.e., combined urban and educational hackathon in the City of Rauma, which has a World Heritage Old Town that aims to integrate its historical uniqueness with modern city services. As a result, the article portrays the process and outputs of a hackathon carried out with the collaboration of two higher education institutions (HEIs) and the Entrepreneur Association of Rauma. Presenting conclusions for both academics and the public sector, the article contributes to the literature on urban and educational hackathons in smart cities with a heritage context.

Additive Manufacturing and Business Models: Current Knowledge and Missing Perspectives - Christina Öberg; Tawfiq Shams; Nader Asnafi (Technology Innovation Management Review, 2018)
Additive manufacturing, that is 3D printing technology, may change the way companies operate their businesses. This article adopts a business model perspective to create an understanding of what we know about these changes. It summarizes current knowledge on additive manufacturing within management and business research, and it discusses future research directions in relation to business models for additive manufacturing. Using the scientific database Web of Science, 116 journal articles were identified. The literature review reveals that most research concerns manufacturing optimization. A more holistic view of the changes that additive manufacturing may bring about for firms is needed, as is more research on changed value propositions, and customer/sales-related issues. The article contributes to previous research by systematically summarizing additive manufacturing research in the business and management literature, and by highlighting areas for further investigation related to the business models of individual firms.
Keywords: 3D printing; additive manufacturing; business model; literature review

Approach for a Pattern-Based Development of Frugal Innovations - Anne-Christin Lehner; Christian Koldewey; Jürgen Gausemeier (Technology Innovation Management Review, 2018)
Emerging markets have become increasingly interesting for companies from industrialized countries, but the requirements in these markets differ dramatically from those in the companies’ traditional markets. New products and services are demanded – so-called frugal innovations. Since the challenges for the development of frugal innovations are often quite similar – for example, low income of the target customer, poor infrastructure, etc. – the hypothesis appears that the solutions will also be similar. In our earlier TIM Review article (Lehner & Gausemeier, 2016), we showed how solution patterns for frugal innovations can be derived. The article at hand summarizes those findings and supplements an innovation process for frugal innovation using the solution patterns. The validation based on the example of telemedical assistant systems shows the benefit of the pattern-based development of frugal innovations. The article addresses managers and engineers who plan to introduce frugal innovations, as well as university-based researchers interested in the development of frugal innovations.
Keywords: business model; emerging markets; frugal innovations; patterns; products and services

Collaboration Strategies in Innovation Ecosystems: An Empirical Study of the German Microelectronics and Photonics Industries - Fabian Schroth; Johann Jakob Häußermann (Technology Innovation Management Review, 2018)
Effective collaboration between companies and research organizations is key to successful innovation systems. Against the background of digitalization, a shift from traditional innovation systems towards innovation ecosystems can be observed. In this article, we investigate how companies operating in innovation ecosystems address the challenge of collaboration in dynamic innovation ecosystems. We focus on microelectronics and photonics in Germany as examples of knowledge- and research-intensive industries and analyze the strategies of companies to collaborate with research organizations. We explore whether and to what extent companies develop different and new strategies for collaborating with research institutions within innovation ecosystems, on the basis of which we identify two ideal types of strategies. Whereas ideal type A is aiming towards obtaining specific knowledge in order to further develop a particular technology or product (i.e., towards incremental innovation), ideal type B seeks to harness the new and full potential of innovation ecosystems (i.e., aiming at rather radical innovation). Finally, our findings contribute to a better understanding of innovation ecosystems and give managerial implications for collaborating in such systems.
Keywords: business ecosystem; collaboration; development and innovation; innovation ecosystem; innovation ecosystem strategies; knowledge ecosystem; microelectronics; photonics; research

Convergent Innovation in Food through Big Data and Artificial Intelligence for Societal-Scale Inclusive Growth - Laurette Dubé; Pan Du; Cameron McRae; Neha Sharma; Srinivasan Jayaraman; Jian-Yun Nie (Technology Innovation Management Review, 2018)
Inclusive innovation has not yet reached societal scale due to a well-entrenched divide between wealth creation and social equity. Taking food as the initial test bed, we have proposed the convergent innovation model to address such challenges still facing 21st century society by bridging sectors and disciplines around an integrated goal on both sides of the social-economic divide for innovations that target wealth creation with an upfront consideration of its externalities. The convergent innovation model is empowered by two key enablers that integrate an advanced digital infrastructure with leading scientific knowledge on the drivers of human behaviour in varying contexts. This article discusses the structure, methods, and development of an artificial intelligence platform to support convergent innovation. Insights are gathered on consumer sentiment and behavioural drivers through the analysis of user-generated content on social media platforms. Empirical results show that user discussions related to marketing, consequences, and occasions are positive. Further regression modelling finds that economic consequences are a strong predictor of consumer global sentiment, but are also sensitive to both the actual price and economic awareness. This finding has important implications for inclusive growth and further emphasizes the need for affordable and accessible foods, as well as for consumer education. Challenges and opportunities inspired by the research results are discussed to inform the design, marketing, and delivery of convergent innovation products and services, while also contributing to dimensions of inclusion and economic performance for equitable health and wealth.
Keywords: artificial intelligence; convergent innovation; food; social media; user-generated content

Data Science as an Innovation Challenge: From Big Data to Value Proposition - Victoria Kayser; Bastian Nehrke; Damir Zubovic (Technology Innovation Management Review, 2018)
Analyzing “big data” holds huge potential for generating business value. The ongoing advancement of tools and technology over recent years has created a new ecosystem full of opportunities for data-driven innovation. However, as the amount of available data rises to new heights, so too does complexity. Organizations are challenged to create the right contexts, by shaping interfaces and processes, and by asking the right questions to guide the data analysis. Lifting the innovation potential requires teaming and focus to efficiently assign available resources to the most promising initiatives. With reference to the innovation process, this article will concentrate on establishing a process for analytics projects from first ideas to realization (in most cases: a running application). The question we tackle is: what can the practical discourse on big data and analytics learn from innovation management? The insights presented in this article are built on our practical experiences in working with various clients. We will classify analytics projects as well as discuss common innovation barriers along this process.
Keywords: analytics; big data; digital innovation; idea generation; innovation process

Does Entrepreneurial Marketing Underrate Competition? - Mika Westerlund; Seppo Leminen (Technology Innovation Management Review, 2018)
This study aims to investigate the relationship between marketing needs and actions in entrepreneurial marketing. So doing, it explores how the entrepreneur’s interpretation of the needs that arise from the changes and opportunities in the business environment affects their actions in entrepreneurial marketing. We establish and test a set of hypotheses over a sample of 3,097 entrepreneur-led small firms from Finland. The results show that entrepreneurial perception of environmental pressure in terms of partners, customers, and competitors is linked to the marketing practices of small firms in terms of developing business relations, publicity, and offerings. That is, actions in entrepreneurial marketing depend on the entrepreneur’s ability to interpret needs based on the signals in the business environment. However, the study confirms that entrepreneurs pay less attention to competition, which affects their marketing actions, and it suggests that both research and practice of entrepreneurial marketing should pay more regard to competition.
Keywords: competition; entrepreneurial; environment; marketing; orientation

The Dynamics of Knowledge Sharing in the Biotechnology Industry: An Indian Perspective - Tripurasundari Joshi (Technology Innovation Management Review, 2018)
The role of biotechnology in providing an alternate, more productive approach to new drug development is well accepted globally. Multinational pharmaceutical companies have begun outsourcing product development and its clinical validation to biotechnology firms in India. The sector in India has also witnessed the entry of startups in various phases of the drug development value chain. Technological innovation is a key growth driver in the “bio pharma” vertical in recognition of which numerous alliances are seen in the sector in India. These alliances have put in place a structure for technological learning to happen, which is necessary for innovation. However, the nature of knowledge in biotechnology, in large measure, is both tacit and complex. Such knowledge is difficult to transfer. At the same time, transferability of knowledge is critical to developing technological capability, which in turn can facilitate the technological innovations that are crucial for the growth of the sector in India. The current research is motivated by the question of how the firms in this sector deal with this paradox. An exploratory approach is adopted to understand the practices of knowledge sharing as well as its perceived impediments at the firm level in the Indian context.
Keywords: absorptive capacity; biotechnology; India; knowledge sharing; tacit knowledge

Exploring the Transdisciplinary Learning Experiences of Innovation Professionals - Mariana Zafeirakopoulos; Mieke van der Bijl-Brouwer (Technology Innovation Management Review, 2018)
Transdisciplinary innovation inherently involves learning how to integrate disciplines towards exploring a problem or towards developing a solution or technology. Thus, transdisciplinary innovation and transdisciplinary learning are practically interchangeable. Although transdisciplinary learning has been studied and experimented with in educational research, the understanding of it in a professional context is limited. We therefore aim our research at addressing this question of how people shift their practice towards other disciplines to address complex issues. We chose to focus on a particularly challenging context – the shift from positivist to non-positivist learning across the career of transdisciplinary innovators when addressing complex problems. What makes this context challenging is that the siloed and heavily specialized nature of working within a disciplinary construct discourages collaboration on real-world complex problems. This context is also challenging because the analytic focus from positivist disciplines results in a reductionist approach, which limits an innovator’s ability to explore problems holistically and abductively. An understanding of the learning experiences of practitioners in these contexts will inform the identification of relevant variables and attributes that encourage innovative learning for ultimately innovative practice. This identification might help us develop better support and education for innovation professionals who want to adopt transdisciplinary practices for the purposes of addressing complex problems. In this article, we discuss the results of a series of in-depth interviews to understand the learning experiences of design innovation practitioners who experienced a shift away from positivist approaches towards transdisciplinary innovation practice. We explore the research approach undertaken to study the motivations and drivers, the emotions experienced during the shift, and the implementation and dissemination of the new learning into professional practice.
Keywords: emotion; experience; learning; professional; transdisciplinary

Exploring the Use of Stakeholder Analysis Methodology in the Establishment of a Living Lab - Marius Imset; Per Haavardtun; Marius Stian Tannum (Technology Innovation Management Review, 2018)
This article explores how to conduct a cost-effective stakeholder analysis to investigate opportunities and interest in establishing a living lab for an autonomous ferry connection. Using an action research approach, we share our experiences with the process and results, and we reflect openly on the strengths and weaknesses of both the stakeholder methodology generally as well as our own implementation specifically. According to the cyclic nature of action research and experiential learning, the research was conducted in two iterations, with the second iteration drawing upon input from the first. We compare and discuss these two approaches in terms of costs and benefits from a practitioner’s perspective. The article provides a contribution to stakeholder analysis methodology for complex, multi-stakeholder innovation initiatives, such as living labs.
Keywords: action research; autonomous vessels; living labs; management; maritime; Open innovation; quadruple helix; stakeholder analysis

A Framework for Field Testing in Living Lab Innovation Projects - Lynn Coorevits; Annabel Georges; Dimitri Schuurman (Technology Innovation Management Review, 2018)
Within innovation research and, more specifically, living lab projects, a crucial component is to test an innovation in a real-life context with potential end users. Such a field test can validate assumptions by combining insights on behaviour and attitudes towards the innovation. This allows for iterative tailoring of the innovation to the needs and wants of the potential end users. Moreover, relevant insights can be gathered to stop or rescope the innovation project before big investments are made. Although studies indicate that testing innovations (or prototypes) in real-life contexts improves the innovation process, there is no specific framework on how to conduct a field test for an innovation. This is important because, in living lab field tests, users are actively involved in co-creating the solutions, which impacts the operational side of setting up living lab projects. Therefore, within this article, we propose a framework for field testing based on the degree to which it reflects reality and the stage within the living lab process. We distinguish four types of field tests: concept, mock-up, pilot, and go2market field test. Based on this framework, we propose some practical guidelines for setting up living lab field tests.
Keywords: context research; field test; living labs; testing; user innovation

From Closed to Open Innovation in Emerging Economies: Evidence from the Chemical Industry in Brazil - Elisa Thomas (Technology Innovation Management Review, 2018)
In this article, we examine how firms in an emerging economy perform research and development (R&D) activities in regards to the concept of open innovation. Most literature on open innovation shows multinational knowledge-intensive firms with well-established R&D processes mainly in developed countries. Searching for management contributions for firms in emerging economies, we qualitatively analyzed two chemical firms in Southern Brazil that have different profiles and are representative samples of typical firms in the region. Our results show that firms did not fully exploit the potential benefits brought by open innovation, even when complete opening was not the main goal. The firms were similar concerning interactions with partners and stages where relationships occur. The generation of ideas was an open activity performed both by firms and by clients, and interactions with universities were getting stronger. On the other hand, intellectual property has not been used as means of profiting from innovation activities. Our main finding refers to the internal mediation of relationships with partners. R&D teams rarely contact external organizations directly; instead, they leave such interactions to other departments within their firms. Relationships with clients are mediated through technical and commercial departments, and interactions with suppliers are intermediated by the supply staff.
Keywords: collaboration; emerging economy; intermediary; Open innovation; R&D

From Importing Innovations to Co-Producing Them: Transdisciplinary Approaches to the Development of Online Land Management Tools - Alex Baumber; Graciela Metternicht; Peter Ampt; Rebecca Cross; Emily Berry (Technology Innovation Management Review, 2018)
While traditional approaches to innovation diffusion often assume that innovations come from outside a local system, transdisciplinary co-production offers an alternative paradigm in which local stakeholders are engaged as co-producers of innovations. The use of digital online tools for agriculture, conservation, and citizen science is an area of expanding opportunities, but landholders are often dependent on tools developed outside their local communities. This article looks at the potential for transdisciplinary co-production to be used as a framework for more participatory development of digital online land management tools, with a case study from the Central Tablelands of New South Wales, Australia. This research has implications beyond rural land management to other industries and contexts where reflexive and integrative strategies are needed to overcome barriers to stakeholder participation and engagement with new technologies.
Keywords: adaptive; co-production; collaboration; decision-support; innovation; land management; tools; transdisciplinary

From Organizations to Organizational Fields: The Evolution of Civic Innovation Ecosystems - Matthew Claudel (Technology Innovation Management Review, 2018)
Contemporary approaches to urban technology emphasize local “innovation ecosystems”. Two organizational models – living labs and innovation integrators – are commonly used as hubs to broker these ecosystems. Curiously, both coexist in some cities, allowing a comparison of their impact and an analysis of their development over time and in context. The case studies presented in this article suggest that our analytical frameworks for technology policy may fall short, in that they contemplate only the organizations themselves – the living labs or innovation integrators. The dynamics observed in each city are well articulated, however, in the sociotechnical systems literature. The hub can be understood as a “niche”, which fosters radical innovations and new processes. As these prototypes are increasingly deployed and accepted, there is a regime shift, ultimately creating an experimentalist culture that fills the role previously held by the hub. This conclusion is neither a challenge to ecosystem theory nor a critique of innovation policy and its implementation. Rather, I suggest that we must extend these theoretical frameworks, drawing on sociotechnical systems literature to better account for institutions and for systems change as we design policy for urban technology. This article therefore makes a contribution by using a sociotechnical systems lens to explain the evolution of local urban innovation ecosystems.
Keywords: city; civic technology; innovation policy; innovation systems; Living lab

Frugal or Fair? The Unfulfilled Promises of Frugal Innovation - Mario Pansera (Technology Innovation Management Review, 2018)
Frugal innovation has become a popular buzzword among management and business scholars. However, despite its popularity, I argue that the frugal innovation literature, in its present form, is problematic for at least two reasons. First, the frugal innovation literature assumes that scarcity is a normal condition of the “Global South”. In this article, I show that this assumption neglects the fact that scarcity can be socially constructed to deny certain social sectors the access to resources essential for their flourishing. Second, despite all the good intentions underpinning the idea of “alleviating poverty”, frugal innovation studies rarely challenge, or even discuss, the causes of destitution and social exclusion. Innovation, as well as technology, is overwhelmingly framed in an agnostic and neutral way that sidelines the socio-economic complexity of the exclusion mechanisms that cause poverty and underdevelopment. By ignoring this, the frugal innovation literature risks limiting the understanding of the problems it seeks to solve and, most importantly, it risks limiting its impact. Most frugal innovation literature, in other words, seems to elude the fact that, rather than being a mere lack of resources or technology, poverty is a matter of social justice. In order to be empowering, technology has to be value-based, normative framed, socially controlled, and democratically debated. In this article, I propose that we should use these principles to develop a new wave of frugal innovation literature and practice.
Keywords: frugal innovation; inclusive innovation; scarcity; social justice

Gender-Specific Constraints on Academic Entrepreneurship and Engagement in Knowledge and Technology Transfer - Anna Sinell; Roda Müller-Wieland; Antonia Muschner (Technology Innovation Management Review, 2018)
This article analyzes gender-specific constraints impacting scientists’ engagement in knowledge and technology transfer and entrepreneurial activities at public research institutions in the fields of science, technology, engineering, and mathematics (STEM). To this end, we followed an exploratory case study approach and conducted qualitative, semi-structured interviews with 40 academic entrepreneurs. The analysis revealed constraints impacting scientists’ active engagement in transfer and entrepreneurship on two levels. On the meta-level, we identified constraints related to: i) nationwide transfer culture and ii) funding guidelines and structures. On the operational level, we identified constraints related to: i) organizational strategies and practices; ii) organizational culture; and iii) individual attributes and attitudes. By analyzing gender differences among these constraints, the study contributes to an understanding of varying needs for gender-specific founding support programs. The study also derives several implications for managing transfer at research organizations.
Keywords: academic entrepreneurship; academic spin-offs; gender; qualitative study; research-based companies

How Doctoral Students and Graduates Can Facilitate Boundary Spanning between Academia and Industry - Leena Kunttu; Essi Huttu; Yrjö Neuvo (Technology Innovation Management Review, 2018)
The mobility of scientific competences from universities to industrial firms enables firms to absorb and utilize the knowledge developed in academia. However, too few young doctors are currently employed in industry, despite the fact that they could transfer and integrate valuable academic knowledge for industrial purposes and facilitate its utilization towards commercial ends. In this article, we investigate the role of doctoral students and graduates as academic boundary spanners by presenting three joint programs between universities and industrial players that facilitate and promote the industrial involvement of doctoral students and graduates. The cases highlight the meaning of university–industry collaboration in doctoral education and present practical examples of how industrial firms may facilitate the transfer of academic knowledge to industry through jointly organized doctoral education and postdoctoral mobility programs.
Keywords: academic engagement; doctoral education; industrial engagement; knowledge transfer; university–industry collaboration

How to Build Competencies for a Data-Driven Business: Keys for Success and Seeds for Failure - Jyrki Koskinen (Technology Innovation Management Review, 2018)
Data analysis to create deep understanding and insights holds vast potential for innovation, but there is a severe shortage of data scientists. How then can a company create the competencies needed to obtain a competitive edge in the era of data-driven business? This article describes “Data Driven Business”, a program developed to coach company teams in Finland in the use of an innovation platform combining data analysis and service design using real-life case projects. The results suggest that this approach is an efficient way to build data-analysis competencies in a company: after taking the 14-week coaching course, 58% of the participating companies had launched a new product or service in the market within six months from the end of the course. After the program, a network called DOBit was established to share experiences among the members and to leverage data analysis and service thinking in society. This article describes the development and implementation of the course, its results and outcomes, and the keys for success and seeds for failure when attempting to build competencies for a data-driven business.
Keywords: best practices; case projects; data analysis; data-intensive services; design thinking; experiences; innovation platform; service design; service thinking; team building

How to Deal With and Repair Broken Trust in an R&D Partnership - Anna Brattström (Technology Innovation Management Review, 2018)
This article offers an actionable framework for dealing with trust violations in R&D partnerships: it explains how to turn around a conflicted R&D partnership, repair trust, and learn from the experience. As innovation becomes more open, firms increasingly find themselves involved in R&D collaborations with suppliers, customers or even competitors. Trust plays a fundamental role in such partnerships to work. Yet, trust cannot be taken for granted. In fact, trust in R&D partnerships is often violated – and without executive intervention, trust violations can soon turn even the most promising partnership into a value-destroying predicament. Although much has been written about trust formation in R&D partnerships, this article focuses instead on what to do when trust has been broken. The analysis is based on a review of academic research and is illustrated with real-life examples of trust repair processes.
Keywords: conflict; Open innovation; R&D partnerships; trust; trust repair

How to Develop Innovation KPIs in an Execution-Oriented Company - Victoria Lakiza; Isabelle Deschamps (Technology Innovation Management Review, 2018)
Numerous established companies look for ways to rejuvenate their innovation capabilities, as it is essential for their long-term survival. One way is through the development of key performance indicators (KPIs) to measure innovation success. However, the wrong performance measurement approach can hinder innovation efforts. This case study explores the steps and challenges associated with the development of innovation KPIs in an established execution-oriented manufacturing company. Three prerequisites are proposed for such a project in a similar context: 1) a minimal maturity level of innovation processes, 2) strategic alignment, and 3) commitment to innovation. It is also proposed that, in such an execution-oriented company, it might be more effective to start with KPIs that would encourage behaviours more favourable to innovation. Then, with stronger innovation capabilities, it will be easier to develop appropriate KPIs to measure the success of innovation endeavours.

Impact of Business Intelligence Solutions on Export Performance of Software Firms in Emerging Economies - Michael Neubert; Augustinus Van der Krogt (Technology Innovation Management Review, 2018)
The article is written with the aim of understanding how well software firms in emerging economies perform when exporting their goods. Focusing on Paraguay as a representative context, a multiple-case-study research design was adopted using different sources of evidence, including 15 in-depth interviews with founders, shareholders, and CEOs. The data were analyzed using grounded theory in order to develop patterns and categories, and to understand differences and regularities. The revised Uppsala internationalization process model was used as a theoretical framework. This article highlights the experts’ views of the impact of business intelligence on the export performance of software firms in Paraguay. Although only a few of the interviewees currently use business intelligence solutions to support international strategic decision-making processes, most of them reveal a desire to use them because they expect it will have a positive impact on export performance and international competitiveness. The main factors for selecting a business intelligence solution are transparency of cost and benefits, excellent client service, and an attractive pricing model. The study results apply to all stakeholders who support the impact of business intelligence systems on the export performance of software firms in emerging economies. The article fulfils an identified need and call for research to study the use and impact of business intelligence on the way an emerging country’s exportation of goods actually performs, and the ability of its software firms to globalize successfully.
Keywords: artificial intelligence; business intelligence; emerging markets; global marketing; international business; international entrepreneurship; international management; machine learning; Paraguay; software industry

The Impact of Digitalization on the Speed of Internationalization of Lean Global Startups - Michael Neubert (Technology Innovation Management Review, 2018)
Lean global startups need to internationalize early and fast. The digitalization of new foreign market development helps them to more efficiently identify new market opportunities in global markets. With this approach, they are saving resources while developing the most attractive markets. This article examines how lean global startups develop new foreign markets more rapidly due to digitalization. Thus, the aim is to understand the impact of digitalization on speed of internationalization of lean global startups. The study addresses a gap in the scholarly literature and a practical need to evaluate new foreign markets and business opportunities more quickly and more regularly and to understand what helps lean global startups react more quickly to opportunities and threats with respect to changing market attractiveness. Furthermore, it outlines why and how digitalization is important throughout the internationalization process. The research followed a multiple case-study design using different sources of evidence, including 73 interviews with senior managers of lean global startups. The findings reveal that digitalization allows lean global startups to increase decision-making efficiency and to optimize strategies and processes for evaluating international markets. The findings suggest that lean global startups can benefit from the use of digital technologies by applying a more efficient foreign market development process with regular reviews and a reduced workflow, by faster mediation between local market realities and strategic goals, by analyzing all foreign markets instead of just a sample of them, and by optimizing decision-making processes including the ability to make long-term, strategic decisions due to better market information.
Keywords: artificial intelligence; big data analytics; digitalization; global marketing; international business; international business development; international entrepreneurship; international management; lean global startup; machine learning

In Competition with Oneself: A Qualitative Inquiry into Amazon’s Entrepreneurial Culture - Dev K. Dutta (Technology Innovation Management Review, 2018)
Utilizing a historiographic approach based on Amazon’s Letters to Shareholders (LTS) over a twenty-year timeframe (1997–2016), this article identifies the discerning features of the company’s entrepreneurial culture that enabled it to become one of today’s most innovative organizations. A content analysis of the LTS while coding for underlying theoretical themes reveals Amazon’s entrepreneurial culture has been increasingly celebrating a spirit of “Self-Competition”, and by embracing ideas such as “Day 1 Mentality”, “Customer Centricity”, and “Human Capital Focus”. The study findings have useful insights for entrepreneurs, founding teams, and corporate managers engaged in developing an entrepreneurial culture within their own organizations.
Keywords: corporate entrepreneurship; entrepreneurial culture; entrepreneurial orientation; innovation; qualitative methods

Inclusive Innovation in Biohacker Spaces: The Role of Systems and Networks - Jeremy de Beer; Vipal Jain (Technology Innovation Management Review, 2018)
In this article, we examine the development of biohacker spaces and their impact on innovation systems through the lens of inclusive innovation. Examining issues associated with people, activities, outcomes, and governance, we observe that biohacker spaces offer an alternative approach to biotechnological research outside the orthodox walls of academia, industry, and government. We explain that harnessing the full innovative potential of these spaces depends on flexible legal and regulatory systems, including appropriate biosafety regulations and intellectual property policies and practices, and organic, community-based social and financial networking.
Keywords: biohacker spaces; biohacking; biotechnology; crowdfunding; inclusive innovation; innovation; law; regulation; social networks

Information Security Best Practices: First Steps for Startups and SMEs - Urpo Kaila; Linus Nyman (Technology Innovation Management Review, 2018)
This article identifies important first steps toward understanding and implementing information security. From the broad selection of existing best practices, we introduce a lightweight yet comprehensive security framework with four useful first steps: identifying assets and risks; protecting accounts, systems, clouds, and data; implementing a continuity plan; and monitoring and reviewing. This article is intended primarily for startups and less mature companies, but it is likely to be of interest to any reader seeking an introduction to basic information security concepts and principles as well as their implementation.
Keywords: best practices; cybersecurity; information security; risk management; SMEs; startups

Innovation Instruments to Co-Create Needs-Based Solutions in a Living Lab - Lotta Haukipuro; Satu Väinämö; Pauliina Hyrkäs (Technology Innovation Management Review, 2018)
This multiple case study focuses on co-creation facilitated with innovation instruments in three different environments – a school, a hospital, and an airport – in which 12 SMEs and startups developed solutions based on predefined needs of customer organizations, and where stakeholders actively participated through user involvement methods facilitated by a living lab. The article provides new knowledge regarding the benefits of the co-creation, user involvement, and use of the living lab approach within different contexts. Our findings show concrete benefits of co-creation for stakeholders such as companies, customer organizations, and end users. Based on our results, we propose a new, generic model for using innovation instruments to facilitate co-creation for the development of needs-based products and services in different service domains.
Keywords: co-creation; innovation instrument; innovation process; Living lab; SME; startup; user involvement

Key Constructs and a Definition of Living Labs as Innovation Platforms - Mika Westerlund; Seppo Leminen; Christ Habib (Technology Innovation Management Review, 2018)
Despite the growing popularity of using living labs as innovation platforms and the increasing scholarly attention toward the topic, still relatively little is known about many of their central characteristics. We use a qualitative research approach to identify key constructs of living labs and to understand how these constructs show up in the operation of living labs. So doing, we used theoretical constructs from the literature on user innovation, co-creation, and living labs to analyze a sample of membership applications to the European Network of Living Labs (ENoLL). The results from the content analysis of 40 applications revealed nine key constructs that are characteristic to living labs: 1) objective, 2) governance, 3) openness, 4) stakeholders, 5) funding, 6) value, 7) communications, 8) infrastructure, and 9) methods. These key constructs provide new insight that helps us to provide a definition of living labs as innovation platforms.
Keywords: constructs; definition; ENoLL; innovation; living labs; platform

Lean Commercialization: A New Framework for Commercializing High Technologies - Saheed A. Gbadegeshin (Technology Innovation Management Review, 2018)
Commercializing high technologies is expensive, tedious, and resource intensive. Meanwhile, there is a need for quick diffusion of innovations due to economic pressures for companies and research institutes. Therefore, this article proposes a new framework: lean commercialization. The framework represents a transformation of new technology and knowledge to products and services through the application of the lean/agile methodology. This methodology focuses on how resources can be minimized during the development, manufacturing, and marketing of new products and services, while still being accepted by customers. The lean commercialization framework was developed from a case study of high-technology companies and by interviewing commercialization experts. This article contributes to the theory and practice of commercialization of high technologies and provides a procedure for the practical application of the lean commercialization framework.
Keywords: Finland; high technologies; lean commercialization; lean startup; technology-based companies

The Library Living Lab: A Collaborative Innovation Model for Public Libraries - Fernando Vilariño; Dimosthenis Karatzas; Alberto Valcarce (Technology Innovation Management Review, 2018)
New models of governance advance towards participatory schemes in which citizens not only play an active role in decision-making processes but also the processes by which new products and services are defined and introduced. In parallel, technological innovations, and the new horizons of creativity that they allow, open a huge range of options to innovation in all areas of society, particularly in the cultural field. Under these two premises – participation and innovation – the Library Living Lab initiative was born at the Public Library of Miquel Batllori Volpelleres in Sant Cugat del Vallès, Barcelona. The Library Living Lab is a space that gathers all stakeholders around the public library with the aim of exploring new methods and tools that allow us to enjoy culture both individually and collectively. This article describes how technology can be an enabling factor in a citizen-initiated grassroots project. The project implements a complete model of inter-institutional collaboration with all relevant actors around the living lab working group. The specific challenges of developing an open, flexible, and inter-connected space are identified, and the interaction dynamics based on a challenge–action–return methodology definition are described through practical examples. Our conclusions tackle the challenges of a horizon for the implementation of innovation initiatives – such as living labs – in public spaces.
Keywords: cultural spaces; innovation; library; Living lab; participatory; public spaces; technology

Living Labs versus Lean Startups: An Empirical Investigation - Dimitri Schuurman; Sonja M. Protic (Technology Innovation Management Review, 2018)
Although we seem to be living in an era where founding a startup has never been easier, studies point to the high mortality rates of these organizations. This “startup hype” has also induced many practitioner-based innovation management approaches that lack empirical studies and validation. Moreover, a lot of these approaches have rather similar angles, but use different wordings. Therefore, in this article, we look into two of these “hyped” concepts: the lean startup and living labs. We review the academic studies on these topics and explore a sample of 86 entrepreneurial projects based on project characteristics and outcomes. Our main finding is that the two approaches appear to be complementary. Living labs are powerful instruments to implement the principles of the lean startup, as the real-life testing and multi-disciplinary approach of living labs seem to generate more actionable outcomes. However, living labs also require the flexibility of a startup – ideally a lean one – to actually deliver this promise. Thus, rather than picking a winner in this comparison, we argue that combining the concepts’ different strengths can bring clear benefits.
Keywords: entrepreneurs; impact; Innovation management; lean startup; Living lab; Open innovation; testing; user innovation

Mixing Practices to Create Transdisciplinary Innovation: A Design-Based Approach - Kees Dorst (Technology Innovation Management Review, 2018)
As the problems that are our organizations are facing become more complex, dynamic, and networked, they will need to become more flexible in their ability to respond. These complex networked problem situations often cannot be tackled from a single-discipline perspective, and thus transdisciplinary innovation – that is, innovation across and between disciplinary fields – is becoming more important. But how can we achieve innovation in those in-between spaces, when all of our knowledge and established approaches are held within the disciplines? In this article, we look beyond the limiting confines of traditional disciplines by seeing them as collections of smaller units of action: practices. After a foray into the anatomy of practices, we discuss how a design-based approach to transdisciplinary thinking creates a framework for the mixing of practices, articulating new insights and creating new possibilities for action in the space between the established professions.
Keywords: disciplines; innovation; practice; transdisciplinarity; transdisciplinary education

Overcoming Barriers to Frugal Innovation: Emerging Opportunities for Finnish SMEs in Brazilian Markets - Mirva Hyypiä; Rakhshanda Khan (Technology Innovation Management Review, 2018)
Frugal innovation has become a popular concept, in academia but also in industry at large. Although there has been a great deal of discussion about the relevance of frugal innovation to the developed world, the notion’s full acceptance within small and medium-sized enterprises (SMEs) still seems far in the distance. The opportunities and barriers seen with practical implementation of frugal innovation during the development processes have received little attention. This article considers these opportunities and barriers in the context of Finnish SMEs, providing insight specifically into the approaches these companies take in Brazilian markets. Qualitative data were drawn from a case study forming part of an extensive action research-based development project called SCALA, aimed at creating suitable and scalable mobile learning services for global markets. The concepts of frugal innovation and proceeding from user needs – essential parts of the development processes – are examined by observing three Finnish SMEs and their top managers, with particular focus on their interaction with Brazilian partners. Development sessions and meetings shed light on how the companies perceived and responded to testing their products/services with six individual schools in Brazil. Although frugal innovation is seen as essential for guaranteeing long-term competitiveness of Finnish SMEs – and access to rapidly growing, unsaturated emerging markets such as Brazil can be a step in the right direction – our study highlights numerous barriers and ways to overcome them in the real-world implementation of frugality in SMEs’ development processes.
Keywords: barriers; Brazilian markets; Finnish SMEs; frugal innovation; opportunities

Patterns of Frugal Innovation in Healthcare - Hareem Arshad; Marija Radić; Dubravko Radić (Technology Innovation Management Review, 2018)
Frugal innovations have the potential to offer simple and cost-effective solutions to the healthcare challenges of the world. However, despite the potential for frugal innovations in healthcare, this context has been rarely studied. The objective of this article is to shed some light on patterns of frugal innovations in healthcare and thereby contribute to the literature. With this aim, we conducted a comprehensive literature review and searched for innovations that were labelled as frugal and were related to healthcare. This led us to a sample of 50 frugal innovations in the healthcare sector. For each of the 50 selected examples, we examined various characteristics of the innovation, such as the country of origin, first launch market, type of innovator, type of innovation, type of care, and geographic diffusion. Our findings show that most of the frugal innovations originated in the United States, followed by India. The most frequent first launch market was India. In terms of types of innovators, academia seemed to be the strongest driver. Most frugal innovations are product innovations in the fields of neonatology and general practice. In this article, we expand on these findings and examine the relationships between individual variables to reveal further insights. Finally, we offer conclusions, an outlook for frugal innovation in the healthcare sector, and future research questions.
Keywords: developing economies; emerging economies; frugal innovation; global health; healthcare

A Practice Method for Studying Creative Communities - Pekka Buttler (Technology Innovation Management Review, 2018)
Explaining innovation – even merely spotting it actually happening – is difficult. In this article, I introduce an industry-friendly approach that will enable practitioners and researchers alike to observe, interpret, and understand the different types of creativities – the raw materials necessary for innovation – that happen in creative communities. The Practice Method for Studying Creative Communities (PMSCC) is based on theories developed by Nonaka and Takeuchi. However, unlike mainstream practice-oriented methods, the PMSCC does not necessitate the use of theory-heavy conceptualizations; instead, it focuses on the everyday, creative micro-interactions in communities. As I describe in this article, the PMSCC offers practitioners and researchers an effective way to gain new insights into an otherwise relatively opaque process. Besides outlining the method, I also present results from a research project utilizing the PMSCC, showing how the method can produce worthwhile findings, foster new insights, and help practitioners hone their creative processes.
Keywords: communities; creativity; innovation; practice; research method; teamwork

The Prime Mover Matrix: A Conversation Piece for Building Strategic Innovative Capacity - Magnus Hoppe (Technology Innovation Management Review, 2018)
The article introduces the Prime Mover Matrix as a conversation piece that will help management build strategic innovation capacity and gain desired influence on industrial standards and thus power. After all, just because a company calls itself innovative and invests in R&D does not mean it is actually innovative. To be strategically innovative means that a company deliberately builds its technical innovative capacity and business innovative capacity in relation to the influence of other actors’ actions and innovations. By doing this, a company will be able to increase its influence on industrial standards and gain the necessary power to reach its objectives. It is a relative position towards a moving target, which is why companies must continuously change through learning. This means that management needs help to reflect on how their own company’s innovative capacity compares to their competitors, and they must unceasingly steer their capacity towards the desired innovation position. Today, we lack intuitive and usable tools that will facilitate strategic conversations on how to best invest for desired innovation capacity. In order to fill this void, this article proposes the Prime Mover Matrix: a model that functions as a conversation piece for triggering an assessment of an industry’s technical, business, and prime movers.
Keywords: analytical models; business innovative capacity; conversation pieces; industrial standards; innovation strategy; Prime Mover Matrix; technical innovative capacity

Q&A. Innovation and Entrepreneurial Ecosystem Research: Where Are We Now and How Do We Move Forward? - Paavo Ritala; Robin Gustafsson (Technology Innovation Management Review, 2018)
Keywords: approaches; business ecosystem; entrepreneurial ecosystem; innovation ecosystem; methods; research; theoretical foundations

Q&A. What Barriers Do Women Face in Becoming High-Tech Entrepreneurs in Rural India? - Rituparna Basu; Sarada Chatterjee (Technology Innovation Management Review, 2018)
Keywords: barriers; challenges; entrepreneurship; India; rural; technology; women

The Role of Middle Managers in the Implementation of a Corporate Incubator: A Case Study in the Automotive Sector - Rebecca Hirte (Technology Innovation Management Review, 2018)
Lately, there has been a growing tendency of corporations to establish corporate incubators as a strategic tool of transformation. However, the managers of those incubators are often lacking the appropriate knowledge and experience when it comes to setting the right framework for implementing such novel innovation units. In this context, the role of middle managers needs to be re-evaluated in order to support them with the right toolset for such an endeavour to become successful. This article analyzes the role of middle managers in the implementation of a corporate incubator by conducting an in-depth single case study within a large German automotive company. In addition to insights from a comprehensive literature review, the study’s interviews with 13 experts reveal challenges as well as key success factors from the perspective of middle managers on the stated research problem. In particular, the ability of middle managers to influence employees and top management has been considered with the aim of avoiding resistance and failure. The findings from this study contribute to the research streams of corporate incubation and middle management. In addition, the findings are particularly relevant for managers of large corporations who are facing the challenge of transforming their organization due to digitalization and unpredictable developments in the market.
Keywords: case study; corporate incubator; Innovation management; intrapreneurship; middle managers

Science Is Indispensable to Frugal Innovations - Balkrishna C. Rao (Technology Innovation Management Review, 2018)
In recent years, frugal innovations have become widely popular due to their no-frills nature that entails lower costs. However, most of the frugal innovations, at least at the grassroots level, are makeshift contraptions, made from indigenous ingenuity, that achieve their goals under constraints on various resources but may suffer from limited lifespans due to premature failure. Consequently, it is imperative that sound scientific principles not be overlooked or haphazardly applied in realizing these innovations, irrespective of their grassroots or sophisticated nature. This article therefore argues for the need to use science, sometimes at the cutting edge, to realize grassroots and advanced frugal innovations that are not prone to failure under various working conditions. In so doing, this work advocates the use of classical and new design methodologies that are rooted in science to save resources and, hence lower costs, while aiming for robust functionality of frugal products. In particular, a frugal design approach using a modern version of the safety factor called the “factor of frugality” has been propounded to effectively create any type of frugal innovation from scratch. By combining the ingenuity of the resourceful creators of frugal innovations with a scientific approach that aims to make the resulting products “fail proof”, such innovations may better contribute value to business and benefits to society.
Keywords: factor of frugality; factor of safety; frugal innovation; research; sustainable development

Smart Farming: Including Rights Holders for Responsible Agricultural Innovation - Kelly Bronson (Technology Innovation Management Review, 2018)
This article draws on the literature of responsible innovation to suggest concrete processes for including rights holders in the “smart” agricultural revolution. It first draws upon historical agricultural research in Canada to highlight how productivist values drove seed innovations with particular consequences for the distribution of power in the food system. Next, the article uses document analysis to suggest that a similar value framework is motivating public investment in smart farming innovations. The article is of interest to smart farming’s decision makers (from farmers to governance actors) and a broader audience – anyone interested in engendering equity through innovation-led societal transitions.
Keywords: agriculture; automation; big data; machine intelligence; power; responsible innovation; smart agriculture; technological values

Strategic Foresight of Future B2B Customer Opportunities through Machine Learning - Daniel Gentner; Birgit Stelzer; Bujar Ramosaj; Leo Brecht (Technology Innovation Management Review, 2018)
Within the strategic foresight literature, customer foresight still shows a low capability level. In practice, especially in business-to-business (B2B) industries, analyzing an entire customer base in terms of future customer potential is often done manually. Therefore, we present a single case study based on a quantitative customer-foresight project conducted by a manufacturing company. Along with a common data mining process, we highlight the application of machine learning algorithms on an entire customer database that consists of customer and product-related data. The overall benefit of our research is threefold. The major result is a prioritization of 2,300 worldwide customers according to their predicted technical affinity and suitability for a new machine control sensor. Thus, the company gains market knowledge, which addresses management functions such as product management. Furthermore, we describe the necessary requirements and steps for practitioners who realize a customer-foresight project. Finally, we provide a detailed catalogue of measures suitable for sales in order to approach the identified high-potential customers according to their individual needs and behaviour.
Keywords: action research; B2B industries; customer base analysis; customer foresight; customer knowledge; customer profile; data mining; machine learning; strategic foresight

A Strategic Management Maturity Model for Innovation - Ferhat Demir (Technology Innovation Management Review, 2018)
Even though strategic management is highly critical for all types of organizations, only a few maturity models have been proposed in the business literature for the area of strategic management activities. This article updates previous studies and presents a new conceptual model for assessing the maturity of strategic management in any organization. The Strategic Management Maturity Model for Innovation (S3M-i) is composed of six maturity levels with seven dimensions. The main contribution of the S3M-i is to put innovation into the agenda of strategic management. The main objective of this study is to propose a model to align innovation with business strategies. This article suggests that innovation (new breakthrough products/services and business models) is the only way of creating sustainable growth, and strategy studies cannot ignore this aspect. Maturity models should embrace innovation to respond to the dynamic business environment and rapidly changing customer behaviours.
Keywords: business model; innovation; maturity model; strategic management

Supporting Self-Determined Indigenous Innovations: Rethinking the Digital Divide in Canada - Jasmin Winter; Justine Boudreau (Technology Innovation Management Review, 2018)
This article seeks to revisit dominant narratives of digital technological development in Indigenous communities in Canada. By prioritizing Indigenous voices and drawing from concepts of self-determination and sovereignty, this analysis reorients discourse surrounding the “digital divide” towards a strength-based approach that positions Indigenous peoples as innovators and creators, not just consumers, of digital technologies. This article begins with a discussion of how dominant media has used technology and technological imagery to misrepresent Indigenous cultures and perpetuate colonial biases, and emphasizes the importance of making space for Indigenous future imagery. Following this is a discussion of digital storytelling and virtual landscapes, showcasing a small sample of Indigenous initiatives online, in video game and app development, and in augmented and virtual reality. Finally, this article considers the potential of “makerspaces” as a framework for future action to bridge theory and practice.
Keywords: digital; Indigenous; innovation; makerspaces; technology

A Taxonomy of Factors Influencing Drop-Out Behaviour in Living Lab Field Tests - Abdolrasoul Habibipour; Annabel Georges; Anna Ståhlbröst; Dimitri Schuurman; Birgitta Bergvall-Kåreborn (Technology Innovation Management Review, 2018)
The concept of a “living lab” is a relatively new research area and phenomenon that facilitates user engagement in open innovation activities. Studies on living labs show that the users’ motivation to participate in a field test is higher at the beginning of the project than during the rest of the test, and that participants have a tendency to drop out before completing the assigned tasks. However, the literature still lacks theories describing the phenomenon of drop-out within the area of field tests in general and living lab field tests in particular. As the first step in constructing a theoretical discourse, the aims of this study are to present an empirically derived taxonomy for the various factors that influence drop-out behaviour; to provide a definition of “drop-out” in living lab field tests; and to understand the extent to which each of the identified items influence participant drop-out behaviour. To achieve these aims, we first extracted factors influencing drop-out behaviour in the field test from our previous studies on the topic, and then we validated the extracted results across 14 semi-structured interviews with experts in living lab field tests. Our findings show that identified reasons for dropping out can be grouped into three themes: innovation-related, process-related, and participant-related. Each theme consists of three categories with a total of 44 items. In this study, we also propose a unified definition of “drop-out” in living lab field tests.
Keywords: drop-out; field test; Living lab; taxonomy; user engagement; user motivation

Technology Entrepreneurship in Emerging Markets: An Exploration of Entrepreneurial Models Prevalent in India - Shiv S Tripathi; Mita Brahma (Technology Innovation Management Review, 2018)
Are the features and processes of entrepreneurship – such as wealth creation, risk taking, vision, identification of a niche market, launching new products, and so on – common across the world? Many would assume they would be. However, firms that are entrepreneurial in nature and belong to emerging markets may or may not follow the established models of developed economies. In this study, we sought to explore various types of entrepreneurial models that are prevalent in an emerging market. For this purpose, we collected primary and secondary data to identify characteristics of technology-based entrepreneurial firms in India. Based on the two dimensions of degree of demand/supply and expected loss/risk, we identify four models of entrepreneurship – incremental, proactive, radical, and reactive – and illustrate each model with examples from Indian companies.
Keywords: emerging markets; entrepreneurship; India; models; technology; typology

To Internationalize or Not to Internationalize? A Descriptive Study of a Brazilian Startup - Flavia Luciane Scherer; Italo Fernando Minello; Cristiane Krüger; Andréa Bach Rizzatti (Technology Innovation Management Review, 2018)
This study examines the failed internationalization experience of a Brazilian high-tech startup. The research methodology of the study is descriptive and aims to explore whether this startup should re-internationalize, despite an unsuccessful first experience. Based on interviews with the founders, it was found that the initial internationalization took place in an incipient way, in the heat of the moment. The lack of success with the initial internationalization did not shake the directors of the startup, who aim to return to internationalization, now in a consolidated way and counting on the advice of an investor. Despite its bitter first experience, should the startup try again? Through an analysis of the lessons learned from the startup’s initial failure and insights from its consideration of a possible second attempt, this study contributes to the literature on competitiveness, internationalization, and international entrepreneurship.
Keywords: entrepreneurial; innovation; internationalization; startups; technology

A Topic Modelling Analysis of Living Labs Research - Mika Westerlund; Seppo Leminen; Mervi Rajahonka (Technology Innovation Management Review, 2018)
This study applies topic modelling analysis on a corpus of 86 publications in the Technology Innovation Management Review (TIM Review) to understand how the phenomenon of living labs has been approached in the recent innovation management literature. Although the analysis is performed on a corpus collected from only one journal, the TIM Review has published the largest number of special issues on living labs to date, thus it reflects the advancement of the area in the scholarly literature. According to the analysis, research approaches to living labs can be categorized under seven broad topics: 1) Design, 2) Ecosystem, 3) City, 4) University, 5) Innovation, 6) User, and 7) Living lab. Moreover, each topic includes a set of characteristic subtopics. A trend analysis suggests that the emphasis of research on living labs is moving away from a conceptual focus on what living labs are and who is involved in their ecosystems to practical applications of how to design and manage living labs, their processes, and participants, especially users, as key stakeholders and in novel application areas such as the urban city context.
Keywords: big data; data mining; innovation; Living lab; living laboratory; research trends; text analytics; topic modeling; topic modelling

Transdisciplinarity at the Crossroads: Nurturing Individual and Collective Learning - Chris Riedy; Dena Fam; Katie Ross; Cynthia Mitchell (Technology Innovation Management Review, 2018)
Practitioners of transdisciplinary inquiry, which we define to include research, learning, collaboration, and action, encounter innumerable tensions. Some tensions are universal, while others are unique to that particular inquiry at that point in time. Resolving these tensions requires innovative practices, which emerge through experience with transdisciplinary inquiry. In this article, we reflect on two decades of transdisciplinary inquiry at the Institute for Sustainable Futures. Drawing on that experience, we argue that one crucial innovative practice is to create space for collective, reflective learning. Such learning frequently takes place in spaces we call “crossroads”. These are formal and informal spaces where practitioners who have been on their own transdisciplinary learning journeys (experiencing diverse tensions and applying diverse approaches) come together in dialogue to share, reflect, critically and constructively question, imagine, challenge, and synthesize their experiences into collective organizational learning. Crossroads can emerge spontaneously but can also be consciously nurtured. In our experience, they help us to sustain the innovation needed for transdisciplinary inquiry and to avoid stagnation or routinization. At these reflective, and often times transformative, crossroads, we make sense of our messy, non-linear transdisciplinary journeys and develop innovations to take our transdisciplinary practices forward.
Keywords: collaborative research; collective learning; learning journeys; transdisciplinary innovation

Transdisciplinary Research in the Built Environment: A Question of Time - Paula Femenías; Liane Thuvander (Technology Innovation Management Review, 2018)
In this article, we reflect on 14 years of experience with transdisciplinary research in the built environment. We critically consider challenges and pitfalls in relation to normative definitions of transdisciplinary research derived from the literature. Our experiences from five transdisciplinary research projects are presented with a focus on each project’s aim, size, organization of work, and funding. Results show that different kinds of transdisciplinary research approaches co-exist and that these can serve different purposes and situations. In most cases, transdisciplinary projects lead to raised levels of awareness of the complexity of real-world problems among participating partners. In some cases, the outcome is a useful innovation, in order to support such innovation, a focus on real cases is encouraged. However, there might be a trade-off between the focused attention on a real case and the maintained interest among diverse participants in a larger project. An important insight is that innovation and knowledge development through transdisciplinary settings take time. It is favourable for the development of networks, common visions, trust, and innovation if consecutive transdisciplinary projects can be arranged with the same partners. We conclude the article by providing practical guidelines to support the management of transdisciplinary projects.
Keywords: built environment; consecutive projects; innovation processes; practical experiences; sustainable renovation; transdisciplinary research

Transnational Entrepreneurship: Distinctive Features and a New Definition - Eduardo Bailetti (Technology Innovation Management Review, 2018)
Definitions of transnational entrepreneurship are too general making it difficult to understand what distinguishes transnational entrepreneurship from other forms of entrepreneurship. In addition, these definitions identify the “immigrant”, “ethnic”, or “migrant” entrepreneur as the focal actor rather than the company. This makes it difficult to align transnational entrepreneurship with the theory of the firm and provide practical insights to practitioners. This article examines 11 definitions of transnational entrepreneurship, discovers the groups of words that best represent the information in a corpus comprised of 44 journal articles, identifies the key features that distinguish transnational entrepreneurship from other forms of entrepreneurship, and advances a new definition of transnational entrepreneurship. The results indicate that transnational entrepreneurship has two key distinctive features: cross-border investment logic and institutional distance – the difference in institutional context between countries. Accordingly, transnational entrepreneurship may be usefully defined as “a cross-border investment to acquire, combine, and recombine specialized individuals and heterogeneous assets to create and capture value for the company under conditions of institutional distance and uncertainty”. This proposed definition builds on the features that make transnational entrepreneurship distinctive, is consistent with the theory of the firm, and carries implications for how to grow companies at an early stage.
Keywords: cross-border; definition; entrepreneurship; features; topic modelling; transnational

Tread Carefully: Managing Identities and Expectations in High-Tech Industry–Academia Collaborations - Els De Maeijer; Tom Van Hout; Mathieu Weggeman; Ger Post (Technology Innovation Management Review, 2018)
Industry–academia collaborations are in continual flux. The changing role of academics is reflected in the interaction between industry and academia. In this article, we examine how meetings as a genre are used to establish and alter the roles and identities of participants. First, interactional analysis shows that a meeting set-up revolving around academic presentations confirms an old role division between collaborators where academic contributions are vulnerable to undervaluation. Second, we found that so called “leading individuals” show critical discourse awareness that allows partners to reposition themselves in relation to each other. They use interactional strategies to create a joint purpose, empower participants to jointly realign, and motivate them to openly share progress. This results in a power shift where academics feel free to pursue their agendas. With this article, we try to understand how the choice of linguistic features shapes social and interpersonal relations in industry–academia collaborations by focusing on open innovation as a socially contingent process.
Keywords: critical discourse awareness; industry-academia; interaction; leadership; Open innovation

Understanding the Role of Rural Entrepreneurs in Telecentre Sustainability: A Comparative Study of the Akshaya and eSeva Projects in India - Gaurav Mishra; Balakrishnan Unny R (Technology Innovation Management Review, 2018)
In rural areas of India, telecentres provide access to computers and other digital technologies and have been utilized as a delivery channel for various government services. Following a public–private partnership (PPP) model, there is a general belief among policy makers that the revenue from government-to-consumer (G2C) services would be sufficient to cover the village-level entrepreneurs’ cash flow requirements and therefore provide financial sustainability. Also, the literature suggests that telecentres have a large enough market for public-access businesses to be commercially viable. In India, around 100,000 telecentres are being set up to serve 600,000 villages – one telecentre for every six villages – to provide one-window access to government services. In the literature, a lack of government services is often quoted as a reason for telecentre failure. This study, using an exploratory approach, aims to understand the parameters that relate to the sustainability of telecentres across a number of common, government-related services. It is observed that some telecentres perform better than the others even though they have the same number of government-related services. Reasons for such differences are explored and the learnings from this research will benefit the stakeholders who are engaged in providing telecentre-based services in other developing countries. In addition, a theoretical framework is suggested to understand the dynamics between different types of sustainability parameters such as financial, social, staff, technology, and institutional. The findings of this research have policy implications in terms of the way services are designed and delivered through telecentres in developing countries such as India.
Keywords: developing countries; entrepreneurship; India; services; sustainability; telecentres

Using Constructive Research to Structure the Path to Transdisciplinary Innovation and Its Application for Precision Public Health with Big Data Analytics - Carolyn McGregor (Technology Innovation Management Review, 2018)
New approaches to complex societal challenges require a diverse mix of resources and skillsets from different disciplines to create solutions that are of a transdisciplinary innovation nature. The constructive research method enables the purposeful creation of methods, modules, tools, and techniques that have applicability well beyond the case study that motivated their creation. This research presents a bottom-up approach that follows a structured path to transdisciplinary innovation. A method is presented that demonstrates how a set of innovative research collaborations progress from disciplinary innovation to multidisciplinary innovation and ultimately onto interdisciplinary innovation. Anchored in overlapping computer science concepts, drawing on the constructive research methodology for purposeful synthesis and integration between the projects, a greater transdisciplinary goal can emerge. This method is demonstrated through a case study involving a set of big data analytics research projects involving diverse disciplines such as computer science, critical care medicine, aerospace, tactical operations, and public health. The resultant collective vision for transdisciplinary innovation that has resulted offers new approaches to maintaining individual wellness within communities across their entire lifespan on earth and in space.
Keywords: adaption; big data; critical care; precision public health; resilience; transdisciplinary innovation

Value Creation in the Internet of Things: Mapping Business Models and Ecosystem Roles - Heini Ikävalko; Petra Turkama; Anssi Smedlund (Technology Innovation Management Review, 2018)
The increasing connectivity provided by the Internet of Things (IoT) supports novel business opportunities for actors in overlapping service systems. Therefore, the co-creative nature of IoT business needs to be further studied. This article reports an empirical study on a European IoT initiative. It contributes to the understudied area of IoT ecosystem dynamics by describing different actor roles and activities in the IoT use cases, and their implications for value creation in IoT ecosystems. Our findings show how IoT ecosystem actors may take the roles of ideator, designer, or intermediary in different IoT design layers, and we recommend this perspective to better understand and describe ecosystem business models. We also discuss the theoretical and managerial implications of our findings.
Keywords: business model; ecosystem; Internet of Things; role; value co-creation

What Do Business Customers Value? An Empirical Study of Value Propositions in a Servitization Context - Kwesi Sakyi-Gyinae; Maria Holmlund (Technology Innovation Management Review, 2018)
This study was conducted in response to calls from the research community and industry for a greater empirical exploration of value propositions. It uses customer value-in-use as a starting point and employs empirical data on value propositions in a servitization context. The findings demonstrate how customers articulate the value-in-use, or benefits, of a selected offering. These results are subsequently used to develop value proposition elements that are aligned with these benefits. The implications for the value proposition literature and for companies in a servitization situation are discussed.
Keywords: customer value in use; service transition; servitization; value proposition; value-in-use dimension

When a New Platform Enters a Market, What Is the Impact on Incumbents? - Andreas J. Steur (Technology Innovation Management Review, 2018)
Digital platforms enable new forms of business models with the potential to disrupt and transform many industries. However, the impact of a platform’s market entry on incumbents has not been taken into account. In this article, our objective is to provide evidence of the impact that a platform’s market entry could have on incumbents. We proposed several hypotheses based on a literature review and then evaluated them using a large dataset from the taxi industry in New York City. Our analysis showed several changes after a platform’s market entry. In contrast to previous understanding, the results indicate that the winner-takes-it-all-effect does not generally apply to the competition between new platforms and incumbents. Regarding the date of changes following a platform’s market entry, we observed a chicken-or-egg problem in the competition between a platform and incumbents. Consequently, our results indicate that incumbents have at least one year to react to the market entry and to make adjustments.
Keywords: impact of market entry; incumbents; multi-sided market; platform competition; platforms; two-sided market

Academic Publishing, Internet Technology, and Disruptive Innovation - Haven Allahar (Technology Innovation Management Review, 2017)
After 350 years of operation, the academic journal publishing industry is imbalanced and in flux as a result of the impacts of Internet technology, which has led, over the past 20 years, to the rise of open access publishing. The introduction of open access journals, in the opinion of many researchers, is considered to be a case of disruptive innovation that is revolutionizing the industry. This article analyzes the traditional journal publishing system, the recent open access models of journal publishing as an evolving phenomenon, the nature and extent of open access as a disruptive innovation, and the implications for key stakeholders. The major finding is that open access publishing has gained traction because technology has contributed to lower publication costs, easier access to research articles, and speedier publishing processes. However, the threat posed by open access has not significantly impacted traditional publishers because of strategies employed by the major publishers and slow adoption of open access by some researchers.
Keywords: academic publishing; disruptive innovation; internet technology and publishing; journal publishing; open access publishing models

Accelerating Research Innovation by Adopting the Lean Startup Paradigm - Kaisa Still (Technology Innovation Management Review, 2017)
Converting scientific expertise into marketable products and services is playing an increasingly important role in the launching of new ventures, the growth of existing firms, and the creation of new jobs. In this article, we explore how the lean startup paradigm, which validates the market for a product with a business model that can sustain subsequent scaling, has led to a new process model to accelerate innovation. We then apply this paradigm to the context of research at universities and other research organizations. The article is based on the assumption that the organizational context matters, and it shows how a deeper understanding of the research context could enable an acceleration of the innovation process. We complement theoretical examples with a case example from VTT Technical Research Institute of Finland. Our findings show that many of the concepts from early-acceleration phases – and the lean startup paradigm – can also be relevant in innovation discussions within the research context. However, the phase of value-proposition discovery is less adequately addressed, and that of growth discovery, with its emphasis on building on a scalable, sustainable business does not seem to be addressed with the presented innovation approaches from the research context. Hence, the entrepreneurial activities at the research context differ from those in startups and internal startups in established organizations.
Keywords: commercialization; context; innovation; innovation acceleration; innovation paradox; lean startup; research; research organization; VTT

Action Research as a Framework to Evaluate the Operations of a Living Lab - Sara Logghe; Dimitri Schuurman (Technology Innovation Management Review, 2017)
In this article, we propose an action research approach to capture and act upon the delights and frustrations of panel members who participate in living lab research in order to optimize the operations of the living lab itself. We used this approach to test the effectiveness of action research in providing guidelines to practitioners to evaluate and design effective and sustainable user involvement processes in living labs. We conducted a focused literature review and an in-depth case study of both the integration of a researcher within the community and the implementation of an action research project within an existing living lab. This living lab is regarded as both a forerunner and a best-practice example in Europe. Based on our findings, we recommend co-creating the “operations” of a living lab with the users themselves following a combined action research and living lab approach.
Keywords: action research; Living lab; panel management; participatory action research; user research

Anticipating Alternative Futures for the Platform Economy - Mikko Dufva; Raija Koivisto; Leena Ilmola-Sheppard; Seija Junno (Technology Innovation Management Review, 2017)
Despite the considerable hype around platforms, our understanding of what the platform economy means and what drivers will define future development trajectories is limited. Companies and policy makers have a great need to investigate what potential opportunities will arise from the platform economy. A shared perception of uncertainties and a strong vision are prerequisites for the development of the platform economy. In this article, we describe a systematic way to develop a resilient vision for a new platform ecosystem, both from the viewpoint of national policy makers and corporate strategy makers in the heavy engineering industry. The process uses morphological analysis for scenario development and robust portfolio modelling for creating resilient strategies. The results include a list of key uncertainties, three general scenarios (sustainable development by Europe; polarization driven by China and the United States; US-driven fast, unreliable growth) as well as steel-industry specific scenarios based on these uncertainties, elements of a resilient vision, and strategies for coping with the uncertainties described by the scenarios.
Keywords: foresight; morphological analysis; platform economy; platforms; portfolio modelling; resilience; scenarios; strategy

Anticipating the Economic Benefits of Blockchain - Melanie Swan (Technology Innovation Management Review, 2017)
In this general overview article intended for non-experts, I define blockchain technology and some of the key concepts, and then I elaborate four specific applications that highlight the potential economic benefits of digital ledgers. These applications are digital asset registries, blockchains as leapfrog technology for global financial inclusion, long-tail personalized economic services, and net settlement payment channels. I also highlight key challenges that offset the potential economic benefits of blockchain distributed ledgers, while arguing that the benefits would outweigh the potential risks. The overarching theme is that an increasing amount of everyday operations involving money, assets, and documents could start to be conducted via blockchain-based distributed network ledgers with cryptographic security, and at more granular levels of detail. One economic implication of widespread blockchain adoption is that the institutional structure of society could shift to one that is computationally-based and thus has a diminished need for human-operated brick-and-mortar institutions.
Keywords: blockchain; cryptocurrencies; cryptoeconomics; cybersecurity; digital asset registries; digital goods; distributed ledgers; economics; eWallet; lightning network; long tail markets; payment channels; programmable money; smart assets; smart contracts; streaming money

Big Data and Individual Privacy in the Age of the Internet of Things - Mackenzie Adams (Technology Innovation Management Review, 2017)
The availability of “big data” and “smart” products are credited with advancing solutions to complex problems in medicine, transportation, and education, among others. However, with big data comes big responsibility. The collection, storage, sharing, and analysis of data are far outpacing individual privacy protections, whether technological or legislative. The Internet of Things (IoT), with its promise to create networks of networks, will magnify individual data privacy threats. Recent data breaches, exposing the personal information of millions of users, provide insight into the vulnerability of personal data. Although seemingly expansive, there are core individual privacy issues that are central to current big data breaches and anticipated IoT threats. This article examines both big data and the IoT using examples of data privacy breaches to illustrate the impact of individual data loss. Furthermore, the article examines the complexity of tackling technological and legislative challenges in protecting individual privacy. It concludes by summarizing these issues in terms of the future implications of the IoT and the loss of privacy.
Keywords: big data; cybersecurity; data breaches; Internet of Things; IOT; privacy; smart devices

A Blockchain Ecosystem for Digital Identity: Improving Service Delivery in Canada’s Public and Private Sectors - Greg Wolfond (Technology Innovation Management Review, 2017)
Blockchain-based solutions have the potential to make government operations more efficient and improve the delivery of services in the public and private sectors. Identity verification and authentication technologies, as one of the applications of blockchain-based solutions – and the focus of our own efforts at SecureKey Technologies – have been critical components in service delivery in both sectors due to their power to increase trust between citizens and the services they access. To convert trust into solid value added, identities must be validated through highly-reliable technologies, such as blockchain, that have the capacity to reduce cost and fraud and to simplify the experience for customers while also keeping out the bad actors. With identities migrating to digital platforms, organizations and citizens need to be able to transact with reduced friction even as more counter-bound services move to online delivery. In this article, drawing on our own experiences with an ecosystem approach to digital identity, we describe the potential value of using blockchain technology to address the present and future challenges of identity verification and authentication within a Canadian context.
Keywords: blockchain; consumer privacy; cybersecurity; digital assets; digital attributes; digital identity; identity fraud; identity verification; online privacy; online security

Categorization of Innovation Tools in Living Labs - Seppo Leminen; Mika Westerlund (Technology Innovation Management Review, 2017)
This article examines the link between innovation processes and the use of innovation tools in living labs. So doing, it develops a conceptual framework based on the literature to analyze 40 living labs in different countries. The study contributes to the discussion on living labs by introducing a new typology of living labs based on their innovation process characteristics and usage of tools: linearizer, iterator, mass customizer, and tailor. Moreover, it proposes three ways to organize innovation activities in living labs. The article concludes by providing a set of implications to theory and practice, and suggesting directions for future research on living labs.
Keywords: innovation tool; Living lab; method; Open innovation; user innovation

Collaborative Capability in Coworking Spaces: Convenience Sharing or Community Building? - Marcelo F. Castilho; Carlos O. Quandt (Technology Innovation Management Review, 2017)
This study explores the development of collaborative capability in coworking spaces. It is based on the perception of collaboration among 31 coworking founders, community managers, and coworkers of those spaces. In-depth interviews around the meaning of collaboration and its challenges were conducted in 14 coworking spaces located in six Asian countries. A set of factors was identified and a model was proposed based on a set of four dimensions: enabling knowledge sharing, enhancing a creative field, enhancing an individual action for the collective, and supporting a collective action to an effective execution. The “Convenience Sharing” and “Community Building” coworking types based on Capdevila (2014) suggest different conditions under which collaborative capability develops. Convenience Sharing coworking spaces tend to foster collaborative capability through knowledge sharing and effective execution, whereas Community Building coworking spaces tend to foster collaborative capability by enhancing a creative field and individual action for the collective. Overall, this study contributes to a theoretical model for coworking spaces to help coworking founders and community managers make strategic decisions. The findings suggest that collaborative capability in coworking spaces depends on the interlacing of a set of factors along four dimensions that relate in varying degrees of intensity to a two-fold coworking space typology.
Keywords: collaboration; collaborative knowledge work; collaborative workspaces; coworking; innovativeness

Combining Exploratory Analysis and Automated Analysis for Anomaly Detection in Real-Time Data Streams - Ahmed Shah; Ibrahim Abualhaol; Mahmoud Gad; Michael Weiss (Technology Innovation Management Review, 2017)
Security analysts can become overwhelmed with monitoring real-time security information that is important to help them defend their network. They also tend to focus on a limited portion of the alerts, and therefore risk missing important events and links between them. At the heart of the problem is the system that analysts use to detect, explore, and respond to cyber-attacks. Developers of security analysis systems face the challenge of developing a system that can present different sources of information at multiple levels of abstraction, while also creating a system that is intuitive to use. In this article, we examine the complementary nature of exploratory analysis and automated analysis by testing the development of a system that monitors real-time Border Gateway Protocol (BGP) traffic for anomalies that might indicate security threats. BGP is an essential component for supporting the infrastructure of the Internet; however, it is also highly vulnerable and can be hijacked by attackers to propagate spam or launch denial-of-service attacks. Some of the attack scenarios on the BGP infrastructure can be quite elaborate, and it is difficult, if not impossible, to fully automate the detection of such attacks. This article makes two contributions: i) it describes a prototype platform for computing indicators and threat alerts in real time and for visualizing the context of an alert, and ii) it discusses the interaction of exploratory analysis (visualization) and automated analysis. This article is relevant to students, security researchers, and developers who are interested in the development or use of real-time security monitoring systems. They will gain insights into the complementary aspects of automated analysis and exploratory analysis through the development of a real-time streaming system.
Keywords: anomaly detection; cybersecurity; exploratory analysis; real-time data streams; visualization

Comparing the Entrepreneurial Ecosystems for Technology Startups in Bangalore and Hyderabad, India - M H Bala Subrahmanya (Technology Innovation Management Review, 2017)
Technology startups are gaining increasing attention from policy makers the world over because they are seen as a means of encouraging innovations, spurring the development of new products and services, and generating employment. Technology startups tend to thrive when inserted in a conducive entrepreneurial ecosystem. Therefore, ecosystem promotion is being given increasing policy support. However, the emergence and structure of entrepreneurial ecosystems for technology startups have hardly been traced and examined in detail. In India, Bangalore occupies a unique position in the startup world, and Hyderabad is fast emerging as one of the promising startup hubs in the country. Given this background, we set out to explore and examine the structure, evolution, and growth of ecosystems for technology startups in the context of Bangalore and Hyderabad. Both the ecosystems emerged due to the initial foundation laid in the form of government–industry–academia triple helix and their interactions leading to the emergence of a modern industrial cluster followed by an information technology and biotechnology cluster, which then led to R&D cluster serving both the cities. These three clusters together, gradually and steadily, facilitated an entrepreneurial ecosystem for technology startups to emerge. The ecosystem operates within the triple helix model and has a nucleus with two outer layers: i) an inner layer of primary (indispensable) factors and ii) an outer layer of supplementary (secondary) factors. Through the analysis of the experiences of Bangalore and Hyderabad and their ecosystem evolution, its structure, and components, we derive key lessons for others within and beyond India.
Keywords: Bangalore; ecosystems; entrepreneurship; Hyderabad; India; startups; technology

Convergent Innovation in Emerging Healthcare Technology Ecosystems: Addressing Complexity and Integration - Mark A. Phillips; Tomás S. Harrington; Jagjit Singh Srai (Technology Innovation Management Review, 2017)
Precision Medicine and Digital Health are emerging areas in healthcare, and they are underpinned by convergent or cross-industry innovation. However, convergence results in greater uncertainty and complexity in terms of technologies, value networks, and organization. There has been limited empirical research on emerging and convergent ecosystems, especially in addressing the issue of integration. This research identifies how organizations innovate in emerging and convergent ecosystems, specifically, how they address the challenge of integration. We base our research on empirical analyses using a series of longitudinal case studies employing a combination of case interviews, field observations, and documents. Our findings identify a need to embrace the complexity by adopting a variety of approaches that balance “credibility-seeking” and “advantage-seeking” behaviours, to navigate, negotiate, and nurture both the innovation and ecosystem, in addition to a combination of “analysis” and “synthesis” actions to manage aspects of integration. We contribute to the convergent innovation agenda and provide practical approaches for innovators in this domain.
Keywords: complexity; convergent innovation; ecosystems; healthcare; integration

The Core Interaction of Platforms: How Startups Connect Users and Producers - Heidi M. E. Korhonen; Kaisa Still; Marko Seppänen; Miika Kumpulainen; Arho Suominen; Katri Valkokari (Technology Innovation Management Review, 2017)
The platform economy is disrupting innovation while presenting both opportunities and challenges for startups. Platforms support value creation between multiple participant groups, and this operationalization of an ecosystem’s value co-creation represents the “core interaction” of a platform. This article focuses on that core interaction and studies how startups connect producers and users in value-creating core interaction through digital platforms. The study is based on an analysis of 29 cases of platform startups interviewed at a leading European startup event. The studied startups were envisioning even millions of users and hundreds or thousands of producers co-creating value on their platforms. In such platform businesses, our results highlight the importance of attracting a large user pool, providing novel services to those users, offering a new market for producers, supporting the core interaction in various ways, and utilizing elements of the platform canvas – an adaptation of the business model canvas, which we have accommodated for platform-based business models – to accomplish these goals.
Keywords: core interaction; digital platforms; multisided markets; platform business; platform canvas; slush event; startups; value creation

A Cybersecurity Risk Assessment Framework that Integrates Value-Sensitive Design - Aida Alvarenga; George Tanev (Technology Innovation Management Review, 2017)
Medical devices today are more effective and connected than ever before, saving more patient lives and making healthcare practitioner’s jobs more efficient. But with this interconnectedness comes inherent concerns over increased cybersecurity vulnerabilities. Medical device cybersecurity has become an increasing concern for all relevant stakeholders including: patients, regulators, manufacturers, and healthcare practitioners. Although cybersecurity in medical devices has been covered in the literature, there is a gap in how to address cybersecurity concerns and assess risks in a way that brings value to all relevant stakeholders. In order to maximize the value created from cybersecurity risk mitigations, we review literature on the state of cybersecurity in the medical device industry, on cybersecurity risk management frameworks in the context of medical devices, and on how cybersecurity can be used as a value proposition. We then synthesize the key contributions of the literature into a framework that integrates cybersecurity value considerations for all relevant stakeholders into the risk mitigation process. This framework is subsequently applied to the hypothetical case of an insulin pump. Using this example case, we illustrate how medical device manufacturers can use the framework as a standardized method that can be applicable to medical devices at large. Our ultimate goal is to make cybersecurity risk mitigation an exploitable asset for manufacturers rather than a regulatory obligation.
Keywords: cybersecurity; framework; medical devices; risk assessment; value propositions; value-sensitive design

The Defining Characteristics of Urban Living Labs - Kris Steen; Ellen van Bueren (Technology Innovation Management Review, 2017)
The organization of supported and sustainable urban interventions is challenging, with multiple actors involved, fragmented decision-making powers, and multiple values at stake. Globally, urban living labs have become a fashionable phenomenon to tackle this challenge, fostering the development and implementation of innovation, experimentation, and knowledge in urban, real-life settings while emphasizing the important role of participation and co-creation. However, although urban living labs could in this way help cities to speed up the sustainable transition, urban living lab experts agree that, in order to truly succeed in these ambitious tasks, the way urban living labs are being shaped and steered needs further research. Yet, they also confirm the existing variation and opaqueness in the definition of the concept. This article contributes to conceptual clarity by developing an operationalized definition of urban living labs, which has been used to assess 90 sustainable urban innovation projects in the city of Amsterdam. The assessment shows that the majority of the projects that are labelled as living labs do not include one or more of the defining elements of a living lab. In particular, the defining co-creation and development activities were found to be absent in many of the projects. This article makes it possible to categorize alleged living lab projects and distill the “true” living labs from the many improperly labelled or unlabelled living labs, allowing more specific analyses and, ultimately, better targeted methodological recommendations for urban living labs.
Keywords: characteristics; cities; definition; living labs; TIM Review; urban living labs

The Design-Driven Living Lab: A New Approach to Exploring Solutions to Complex Societal Challenges - Rens Brankaert; Elke den Ouden (Technology Innovation Management Review, 2017)
In this study, we aimed to explore the potential of a design-driven living lab as an innovative approach to addressing societal challenges. This living lab incorporates design qualities such as exploration, open-ended results, and disruption. This approach was applied in three case studies within the context of dementia, each of which explored the impact of Qwiek.up – a media system that creates an ambient experience in a room through projection and sound. A cluster analysis of the results in the three case studies showed that the system has considerable potential for people with dementia, and possibly also for other groups. In addition, the design-driven approach led to new applications in care, improved functionality, and a broader design space. Our findings show that design-driven living labs can widen the scope of innovation and improve the value proposition of an innovative solution.
Keywords: design; Living lab; societal challenges; technology probe

Designing a Business Model for Environmental Monitoring Services Using Fast MCDS Innovation Support Tools - Tuomo Eskelinen; Teemu Räsänen; Ulla Santti; Ari Happonen; Miika Kajanus (Technology Innovation Management Review, 2017)
The free availability of open data provides opportunities to start new businesses and gain business intelligence. However, although data is often used to support decisions and actions, the possibilities offered by modern sensor technologies with connections to cloud-based data collection services are not being effectively capitalized. Data collection systems are also not generally open source solutions, even though open and flexibly adjustable systems would broaden the opportunities for solutions and larger revenue streams. In this article, we used action research methods to discover new business opportunities in a semi-open information system that utilizes environmental monitoring data. We applied a four-stage innovation process for industry, which included context definition, idea generation, and selection, and produced multi-criteria decision support (MCDS) data to help the design of business model. This was done to reveal business opportunities for an environmental monitoring service. Among these opportunities, one service-style business model canvas was identified as feasible and selected for further development. We identified items that are needed in the commercialization process of environmental monitoring services. Our process combines open environmental monitoring data, participative innovation process, and MCDS support, and it supports and accelerates a co-creative business model creation process that is cost-beneficial in terms of saving time. The results are applicable to the creation of an open data information system that supports data-driven innovation.
Keywords: business model; data collection; environmental monitoring; MCDS; open data; service innovation

Digital Technology Entrepreneurship: A Definition and Research Agenda - Ferran Giones; Alexander Brem (Technology Innovation Management Review, 2017)
Technology entrepreneurship is an established concept in academia. However, recent developments in the context of digital entrepreneurship call for revision and advancement. The multiple possible combinations of technology and entrepreneurship have resulted in a diversity of phenomena with significantly different characteristics and socio-economic impact. This article is focused on the identification and description of technology entrepreneurship in times of digitization. Based on current examples, we identify and describe characterizations of technology entrepreneurship, digital technology entrepreneurship, and digital entrepreneurship. With this new delineation of terms, we would like to foster discussion between researchers, entrepreneurs, and policy makers on the impact of digitization on entrepreneurship, and set a future research agenda.
Keywords: definitions; digital entrepreneurship; digital technology entrepreneurship; entrepreneurship; technology entrepreneurship; technology Innovation

Editorial: Blockchain (October 2017) - Chris McPhee; Anton Ljutic (Technology Innovation Management Review, 2017)
Keywords: authentication; Bitcoin; blockchain; cryptography; digital identity; economics; healthcare; internal audit; services; smart contracts; transactions; trust

Editorial: Collaboration (December 2017) - Chris McPhee (Technology Innovation Management Review, 2017)
Keywords: collaboration; collaborative capability; cooperation; coworking; education; entrepreneurial commitment; entrepreneurship; industry; interdisciplinarity; SMEs; startups; university

Editorial: Innovation in Living Labs (January 2017) - Chris McPhee; Dimitri Schuurman; Pieter Ballon; Seppo Leminen; Mika Westerlund (Technology Innovation Management Review, 2017)
Keywords: agile methods; conceptualizations; innovation labs; Innovation management; innovation tool; living labs; Open innovation; user innovation

Educational Involvement in Innovative University–Industry Collaboration - Leena Kunttu (Technology Innovation Management Review, 2017)
The positive link between university research and industrial innovation has been widely recognized among academics and industrial practitioners. A remarkable volume of previous research emphasizes the importance of the transfer of academic knowledge into the industrial domain. In this sense, it is surprising that the role of university education is an almost neglected topic in the research concerning university–industry collaboration, despite education and the creation of knowledge being a primary goal of universities and providing great potential in terms of improving competences. This study presents a case study that analyzes educational involvement in nine long-term university–industry relationships. In all the cases, the research collaboration between industrial firm and university research group is directly associated with close educational involvement. The aim of the case analysis is to understand mechanisms and practices of educational collaboration that facilitate relational learning and innovation development in university–industry relationships. The forms of educational involvement studied in this article include student projects, thesis projects, jointly organized courses, and tailored degree courses. The findings of the study reveal a number of educational collaboration practices that may facilitate relational learning, creation of new knowledge, as well as innovation development in university–industry relationships.
Keywords: academic involvement; educational involvement; innovation; knowledge transfer; university–industry collaboration

Effects of Business Model Development Projects on Organizational Culture: A Multiple Case Study of SMEs - Ulla Santti; Tuomo Eskelinen; Mervi Rajahonka; Kaija Villman; Ari Happonen (Technology Innovation Management Review, 2017)
Previous research has shown that links between organizational culture and innovativeness/performance may act as a “social glue” that helps a company develop organizational culture as a competitive advantage. In this study of three case companies, the organizational culture change due business model development projects is studied using the Competing Values Framework (CVF) tool and interviews with respondents about discovered changes. To reveal intervention and implied effects between business model development project and organizational culture changes, we used CIMO logic (context, intervention, mechanism, and outcome) to bridge practice and theory by explanatory, backward-looking research. Our case studies of companies in relatively short-duration business model development projects indicate that organizational culture may have some dynamic characteristics, for example, an increase of the adhocracy organizational type in all case companies or an increase in the hierarchical leadership type in one case company. Thus, the development of an organizational culture type can be partly controlled. Our results also indicated business model development projects do have a minor effect on organizational culture, even when development activities have not been put fully into practice. However, the more comprehensively business model development project activities have been put into practice, the larger the effect on organizational culture.
Keywords: business model; business model canvas; competing values framework; development project; organizational culture; service design; SME

The Fourth Industrial Revolution (Industry 4.0): A Social Innovation Perspective - Rabeh Morrar; Husam Arman; Saeed Mousa (Technology Innovation Management Review, 2017)
The rapid pace of technological developments played a key role in the previous industrial revolutions. However, the fourth industrial revolution (Industry 4.0) and its embedded technology diffusion progress is expected to grow exponentially in terms of technical change and socioeconomic impact. Therefore, coping with such transformation require a holistic approach that encompasses innovative and sustainable system solutions and not just technological ones. In this article, we propose a framework that can facilitate the interaction between technological and social innovation to continuously come up with proactive, and hence timely, sustainable strategies. These strategies can leverage economic rewards, enrich society at large, and protect the environment. The new forthcoming opportunities that will be generated through the next industrial wave are gigantic at all levels. However, the readiness for such revolutionary conversion require coupling the forces of technological innovation and social innovation under the sustainability umbrella.
Keywords: fourth industrial revolution; Industry 4.0; Internet of Things; social innovation

Heading for a FALL: A Framework for Agile Living Lab Projects - Tanguy Coenen; Sarie Robijt (Technology Innovation Management Review, 2017)
Living lab methodologies need to enhance reactivity to changing requirements as these appear in a project. Agile methods allow for quick reactivity, but have been critiqued for not sufficiently taking into account the end-user perspective. In this article, we describe how to blend living lab methodologies with agile methods and, to this end, we present a Framework for Agile Living Lab projects (FALL). To make the framework actionable, we propose a number of actor roles. With concrete examples from living lab practice and a discussion of the theoretical basis, this article is relevant to both academics and practitioners.
Keywords: agile; design science research; lean UX; living labs; methodology; SCRUM

Hitching Healthcare to the Chain: An Introduction to Blockchain Technology in the Healthcare Sector - Mark A. Engelhardt (Technology Innovation Management Review, 2017)
Health services must balance patient care with information privacy, access, and completeness. The massive scale of the healthcare industry also amplifies the importance of cost control. The promise of blockchain technology in health services, combined with application layers built atop it, is to be a mechanism that provides utmost privacy while ensuring that appropriate users can easily add to and access a permanent record of information. Blockchains, also called distributed ledgers, enable a combination of cost reduction and increased accessibility to information by connecting stakeholders directly without requirements for third-party brokers, potentially giving better results at lower costs. New ventures are looking to apply blockchain technology to solve real-world problems, including efforts to track public health, centralize research data, monitor and fulfill prescriptions, lower administrative overheads, and organize patient data from an increasing number of inputs. Here, concrete examples of the application of blockchain technology in the health sector are described, touching on near-term promise and challenges.
Keywords: blockchain; distributed ledger; health; patient-centred care; trust

How Researchers Use Social Media to Promote their Research and Network with Industry - Päivi Jaring; Asta Bäck (Technology Innovation Management Review, 2017)
Social media is now an essential information and interaction channel. Companies advertise and sell their products and services through social media, but this channel has not been so commonly applied to the task of selling knowledge and research work. This article studies the use of social media by researchers to promote their research and network with product developers in industry, and it presents a model of the use of social media by researchers. The data for this research was obtained by interviewing individual researchers of a research organization and surveying product developers from industry. The findings show that social media is seen as a good source of new information and contacts, and it is suitable for promoting awareness of research services and results. The results show that the speed and intensity of social media present challenges for researchers, but by being active in posting content and participating in discussions, researchers can derive benefits and enhance their personal reputations.
Keywords: brand building; industry; marketing; networking; promotion; research; researcher; social media

Hybrid Entrepreneurship: How and Why Entrepreneurs Combine Employment with Self-Employment - Marina Z. Solesvik (Technology Innovation Management Review, 2017)
Changes in the labour market and growth in the diversity of non-standard working arrangements have heightened the interest of policy makers and entrepreneurship researchers in “hybrid entrepreneurship”, which is a combination of employment and entrepreneurship. This form of entrepreneurship is particularly popular among highly educated professionals in the high-technology and R&D sectors. With the goal of improving our understanding and defining a research agenda for this phenomenon, I examined the relevant literature to clarify definitions and I undertook a research study to examine first-hand, through a longitudinal case study, the experiences of two hybrid entrepreneurs, one who intended to become a full-time entrepreneur and one who wish to be hybrid entrepreneur. The key result of the study emphasizes that hybrid entrepreneurs should not be considered as a homogeneous group: some hybrid entrepreneurs may always stay at their waged jobs and others may tend to become full-time entrepreneurs. The results have implications for policy makers wishing to encourage hybrid entrepreneurship and for researchers wishing to undertake further research into this phenomenon.
Keywords: definitions; hybrid entrepreneurs; hybrid entrepreneurship; risk taking; self-employment

Improving Internal Communication Management in SMEs: Two Case Studies in Service Design - Tuomo Eskelinen; Mervi Rajahonka; Kaija Villman; Ulla Santti (Technology Innovation Management Review, 2017)
Effective information management is a success factor for business growth, but small and medium-sized enterprises (SMEs) face challenges in transferring knowledge and information from one organizational unit to another. In this study of two case companies, participative business model development processes were designed to identify challenges and solutions in internal communication management. A service design approach based on CIMO logic (context, intervention, mechanism, and output) showed that the participative business model technique and process can identify problems and challenges in internal communication management, as well as in the prioritization of actions. The process is a creative service design process including both divergent and convergent phases. The process increased motivation among personnel to find solutions, encouraged communication, and created joint understanding on how to solve problems. The technique helped to bring tacit information into use.
Keywords: business model; internal communication management; participative process; service design; stakeholder involvement; training

Initiating a New Research Phase in the Field of International Entrepreneurship: An Interview with Professor Nicole Coviello - Nicole Coviello; Stoyan Tanev (Technology Innovation Management Review, 2017)
Keywords: born global; definitions; international business; international entrepreneurship; international new ventures; internationalization; lean and global startups

Innovation by Collaboration between Startups and SMEs in Switzerland - Fabio Mercandetti; Christine Larbig; Vincenzo Tuozzo; Thomas Steiner (Technology Innovation Management Review, 2017)
Open innovation is key to the success of many companies. It is based on the intelligent use of all possible resources, including collaborations with parties outside the firm. Although it is well known that large companies foster and use startups as experiments in their innovation process, little is known about similar activities with small and medium-sized enterprises (SMEs). The aim of this article is to report the results of research done in Switzerland on startups and SMEs. It reveals that most startups know that they must co-operate with other companies from the very beginning of their existence, and that both sides have difficulties in performing a systematic search for possible partners. Hence, to encourage the collaborative development of innovative solutions, we propose building bridges between startups and SMEs, making the identification of possible users of new technologies (SMEs) more accessible to startups, as well as making startups more identifiable by SMEs.
Keywords: collaboration co-operation; innovation; matchmaking; SMEs; startups

Lean Internationalization: How to Globalize Early and Fast in a Small Economy - Michael Neubert (Technology Innovation Management Review, 2017)
This study examines the early market internationalization of 32 high-tech startups that operate internationally from small and open economies. It uses a comparative cross-national multiple case study research design to explore how such startups may differ in their speed of internationalization. Based on interviews with the founders, the speed of early market internationalization in these startups increases significantly due to the application of lean market development processes. The findings provide a basis for developing propositions for further comparative studies focusing on the early and fast internationalization of high-tech startups based in emerging and developed markets. The study contributes to the literature on networks, internationalization, and international entrepreneurship.
Keywords: born-global firm; early and fast internationalization; global marketing; high-tech startup; international entrepreneurship; lean internationalization; small and open economy; Uppsala internationalization process

A Managerial Decision Tool for R&D Outsourcing and Partner Selection in High-Technology Industries - Iivari Kunttu (Technology Innovation Management Review, 2017)
Deciding which tasks and projects are best performed in-house and which should be outsourced to external suppliers are, alongside the supplier selection process, among the key challenges for R&D managers operating in high-technology firms. This study presents a decision tool for evaluating whether to pursue R&D tasks in-house or to outsource them. The tool also helps R&D managers to evaluate which of the supplier candidates would be best suited to undertake the task to be outsourced. The tool is based on four views of evaluation that have both managerial and theoretical roots: identity, dependence, efficiency, and competence. The tool has been developed in a qualitative multiple case study based on R&D supplier relationships and has been empirically tested in an R&D organization.
Keywords: decision tool; outsourcing; partner selection; research and development; supplier involvement

Methods for Supporting Older Users in Communicating Their Emotions at Different Phases of a Living Lab Project - Sonja Pedell; Alen Keirnan; Gareth Priday; Tim Miller; Antonette Mendoza; Antonio Lopez-Lorca; Leon Sterling (Technology Innovation Management Review, 2017)
In this article, we focus on living lab methods that support the elicitation of emotions – a key success factor in whether a design solution will be accepted and taken up over the long term. We demonstrate the use of emotional goal models to help understand what is relevant for a target user group in the early phases of design. We promote animations and storyboards to envision the context of use and to gain an understanding of how design ideas can integrate into people’s lives. For the evaluation of ideas and to further understand user needs, we show how technology probes facilitate natural interactions with a suggested solution concept. All methods have in common that they enable older adults without design or development experience to participate in the design process and work towards a meaningful solution by helping to communicate feelings and goals that are often hard to define. Lastly, we present a process model that demonstrates our emotion-led design toolkit at various phases of a living lab process.
Keywords: aging well; co-design methods; emotion-led design; expressing emotions; Living lab; personal alarm systems

Needsfinding in Living Labs: A Structured Research Approach - Louise Savelkoul; Murk Peutz (Technology Innovation Management Review, 2017)
Living labs enable innovations to be facilitated and implemented quickly and efficiently. A key element of the living lab approach is the active involvement of users. In this article, we examine a structured needsfinding phase of a living lab infrastructure project within the context of bicycle commuting. Given that effectuation costs are high, it is essential for the lab to focus on tackling the right user needs. Thus, the living lab’s needsfinding phase aims to identify user needs and wants, as measured by bicycle commuting intention. We examined intention in a structured way by following the theory of planned behaviour. The results show that bicycle commuting intention can be explained by the variables of our model (R square=0.808). The specific insights arising from the needsfinding phase are an important focus for the activities and experiments in the later phases of the living lab. The generalized insights are also relevant to innovation experts outside the area of cycling.
Keywords: commuting; cycling; intention; Living lab; needsfinding; theory of planned behaviour

Opening the Black Box of Ambidexterity: Three Product Development Stories - John Fiset; Isabelle Dostaler (Technology Innovation Management Review, 2017)
Organizational ambidexterity, which can be roughly defined as the ability for organizations to combine old and new ways of doing things to meet organizational objectives, has drawn considerable attention in the management literature in recent years. Authors distinguish clearly between structural ambidexterity, which implies that ambidextrous organizations are firms in which groups of people concentrate on traditional business or ways of doing things while others explore new avenues, and contextual ambidexterity, which characterizes companies where any individual can be ambidextrous. Our research is positioned in the contextual ambidexterity perspective. In this article, we apply the typology of four ambidextrous behaviours developed by Birkinshaw and Gibson (2004) to increase our understanding of the process whereby organizational actors are able to build on existing capabilities or business processes while developing new ones. Our results indicate that at least three of the ambidextrous behaviours proposed by Birkinshaw and Gibson (2004) (initiator, broker, and multitasker) are helpful to understand how new product development team members rely on proven approaches while simultaneously introducing new ones to successfully overcome daily challenges. Practitioners should be encouraged to become familiar with the concept of ambidexterity, to recognize when and how the successful combination of old and new ways of doing happens, and to promote these occurrences.
Keywords: adaptability; alignment; ambidextrous behaviour; contextual ambidexterity; exploitation; exploration; new product development

Orchestrating Innovation Ecosystems: A Qualitative Analysis of Ecosystem Positioning Strategies - Katri Valkokari; Marko Seppänen; Maria Mäntylä; Simo Jylhä-Ollila (Technology Innovation Management Review, 2017)
This article explores how firms can orchestrate innovation ecosystems to enhance collaboration for innovation among different actors. Most previous research on ecosystems has focused on firm-level strategies to operate in an ecosystem rather than the composition or orchestration of an ecosystem as a whole. However, finding the balance between the self-interests of involved actors is critical in order to create collaborative settings that induce different parties to jointly develop and put their best efforts into a joint endeavour. Thus, we undertook a qualitative study with 35 case companies from the metal and engineering industries, each of whom was interested in developing their position in ecosystems and improving their relational business practices. The findings suggest that there is an essential ecosystem competence that is needed by all actors in an ecosystem, regardless of their position, and that is the ability to manage dynamic strategic interactions related to innovation. This competence enables them to ensure the future vitality of the ecosystem and their own business. These results highlight the need for managers to profile their own company’s role in an ecosystem in relation to the type of ecosystems, while simultaneously evaluating the ecosystem’s ability and potential to survive.
Keywords: actors; collaboration; ecosystems; innovation; orchestration; positioning; roles; strategy

Orchestration Roles to Facilitate Networked Innovation in a Healthcare Ecosystem - Minna Pikkarainen; Mari Ervasti; Pia Hurmelinna-Laukkanen; Satu Nätti (Technology Innovation Management Review, 2017)
This study examines orchestration roles in a networked innovation context characterized by significant transformation. In particular, an exploratory case study approach is taken to study the roles of innovation network orchestrators and their actions to facilitate networked activities in different phases of the innovation process. The context of the case study, a healthcare ecosystem that aims to co-create technological innovations to support the pediatric surgery journey, provides valuable insights about orchestration and adds knowledge on specific limitations set by the orchestrator-specific and context-related issues in a professional context. The findings of this study highlight the need for careful coordination that allows shared understanding of the goals of the orchestration process and achievable innovation implementations. It is shown that parallel, evolving, and even changing orchestrator roles are needed in complex networked innovation settings.
Keywords: case study; exploratory approach; healthcare ecosystem; high-level experts; innovation orchestration; roles

Overcoming Barriers to Experimentation in Business-to-Business Living Labs - Ruben D’Hauwers; Aron-Levi Herregodts; Annabel Georges; Lynn Coorevits; Dimitri Schuurman; Olivier Rits; Pieter Ballon (Technology Innovation Management Review, 2017)
Business-to-business (B2B) living lab projects have been mentioned in different areas of academic research, but the innovation management literature requires deeper analysis of their potential opportunities and challenges. Real-life experimentation is a key requirement for living labs as it enables deeper insights in the potential success of innovations. However, the literature has not provided insights on how living lab projects can implement real-life experimentation in B2B innovation projects and does not describe appropriate conditions for experimentation in these settings. In this study, we identified three main barriers preventing real-life experimentation in B2B living lab projects: the technological complexity, the need for integration, and the difficulty in identifying testers. The barriers are discussed in detailed and potential solutions are provided to help overcome these barriers and stimulate the adoption of real-life experimentation in B2B innovation projects.
Keywords: B2B; experimentation; living labs; testing; user research

Platforms for Innovation and Internationalization - Erik Stavnsager Rasmussen; Nicolaj Hannesbo Petersen (Technology Innovation Management Review, 2017)
The high-tech global startup has many challenges related to both innovation and internationalization. From a Danish cluster of Welfare Tech firms, eight innovative and international firms were selected and interviewed. Such firms typically have to be agile and operate in virtual networks in almost all parts of their value chains. This article contributes to the understanding of how innovation and internationalization to a great extent are interlinked. The firms have developed a core product or service offering, which the firms often describe as “a platform”. Around the platform, they develop their products and services for new customers and users in new countries. The firms have to sustain a strong focus on the platform while at the same time developing their platform solution for new products, new customers, and new markets. This pivoting makes it possible to use the platform in a new context but is highly demanding for the firms. They need to be extremely agile and fast-moving but at the same time still to have a focus on the core of the firm: the platform.
Keywords: globalization; innovation; internationalization; lean and global startups; lean startup; platform

Promoting Entrepreneurial Commitment: The Benefits of Interdisciplinarity - Franziska Brodack; Anna Sinell (Technology Innovation Management Review, 2017)
This article is the first to examine the relationship between interdisciplinarity and entrepreneurial commitment in academic spin-offs. Building on literature on interdisciplinarity, academic entrepreneurship, and entrepreneurial intention, we analyzed the development of nine interdisciplinary spin-off teams comprising expertise from science, industry, and design. Our findings suggest that interdisciplinary teams engage with their ideas, maintain productive interaction, and successfully implement these ideas. Subjects in this study thoroughly developed their project proposals and implementation strategies by examining them from multiple angles. They believed not only in the value of these projects, but in their own ability to see them through. They found one another’s contributions highly inspirational and experienced a strong sense of responsibility and motivation. Communication within the teams was well managed, and tasks were clearly defined and distributed. Based on our findings, we put forward a number of propositions about the positive effects of interdisciplinarity on entrepreneurial commitment and conclude with implications for future research and practice.
Keywords: academic spin-offs; entrepreneurial commitment; interdisciplinarity; team composition; teamwork; technology transfer

Q&A. Are Universities Ready for Knowledge Commercialization? - Mohammad Saud Khan (Technology Innovation Management Review, 2017)
Keywords: commercialization; entrepreneurship; knowledge; research; technology transfer; universities

Q&A. Does Machiavelli’s The Prince Have Relevant Lessons for Modern High-Tech Managers and Leaders? - Clovia Hamilton (Technology Innovation Management Review, 2017)
Keywords: cut-throat competition; Innovation management; leadership; lean philosophy; Machiavelli; Machiavellian; management; technological innovation leadership; The Prince

Q&A. How Do Digital Platforms for Ideas, Technologies, and Knowledge Transfer Act as Enablers for Digital Transformation? - Mokter Hossain; Astrid Heidemann Lassen (Technology Innovation Management Review, 2017)
Keywords: digital platforms; digitization; enablers; knowledge management; Open innovation

Q&A. Is Internal Audit Ready for Blockchain? - Hugh Rooney; Brian Aiken; Megan Rooney (Technology Innovation Management Review, 2017)
Keywords: blockchain; controls; governance; internal audit; risk management

Realistic Creativity Training for Innovation Practitioners: The Know–Recognize–React Model - Dagny Valgeirsdottir; Balder Onarheim (Technology Innovation Management Review, 2017)
Creativity is increasingly being recognized as important raw material for innovation, which highlights the importance of identifying ways to increase the creativity of practitioners. In this article, we describe our efforts to design a creativity training program specifically for innovation practitioners. Our aim was to develop a program that would be both theoretically sound (i.e., based on a rigorous scientific foundation) and relevant for practitioners (i.e., applicable to real-world contexts). Our transdisciplinary study employed co-creation as a method to ensure that three layers of focus would be taken into consideration: metacognitive knowledge, metacognitive monitoring, and metacognitive control. The result is a program called Creative Awareness Training, which is based on the new Know–Recognize–React model.
Keywords: co-creation; cognitive creativity; creative awareness; creative process; creativity; creativity training; front-end innovation; innovation process; metacognition; transdisciplinary

Reflecting on Actions in Living Lab Research - Anna Ståhlbröst; Marita Holst (Technology Innovation Management Review, 2017)
Living labs deploy contemporary open and user-centred engagement processes in real-world contexts where all relevant stakeholders are involved and engaged with the endeavour to create and experiment with different innovations. The approach is evidently successful and builds on the perspective that people have a democratic right to have influence over changes that might affect them, such as those brought about by an innovation. In this article, we will reflect on and discuss a case in which end users took part in the development of a method that stimulates learning and adoption of digital innovations in their own homes while testing and interacting with it. The results show that, when end users were stimulated to use the implemented innovation through different explicit assignments, they both increased their understanding of the situation as well as changed their behaviour. Living lab processes are complex and dynamic, and we find that it is essential that a living lab have the capability to adjust its roles and actions. We argue that being reflective is beneficial for innovation process managers in living labs because it allows them to adjust processes in response to dynamic circumstances.
Keywords: action research; Apollon; context; digital innovations; end users; innovation process; Living lab; research process

The Sharing Economy and the Future of Personal Mobility: New Models Based on Car Sharing - Olga Novikova (Technology Innovation Management Review, 2017)
The sharing economy is an emerging phenomenon that shapes the cultural, economic, and social landscape of our modern world. With variations of the concept of the sharing economy emerging in so many fields, the area of shared mobility – the shared use of a motor vehicle, bicycle, or other mode that enables travellers to gain short-term access to transportation modes on an on-demand basis – has developed as the forerunner of the transformation to be expected in other areas. This article examines how the sphere of personal mobility has been affected by the growth of sharing economy. It contributes to the growing body of shared mobility literature by uncovering innovative mobility-based models that represent solutions on the intersection of shared mobility, physical infrastructure, and integrated-mobility schemes.
Keywords: integrated solution; mobility modes; shared mobility; sharing economy

Smart Contract Relations in e-Commerce: Legal Implications of Exchanges Conducted on the Blockchain - Philippa Ryan (Technology Innovation Management Review, 2017)
Much of the discussion around blockchain-based smart contracts has focused on whether or not they operate in the same way as legal contracts. However, it is argued that most contracts are social rather than legal in nature and are entered into because the parties trust each other to perform the agreed exchange. Little has been written to address how the blockchain’s trust protocol can enable the kind of social contracting that characterized the way exchanges were conducted before the Internet. This article aims to fill that gap by exploring blockchain-based smart contracts primarily as non-contractual social exchanges.
Keywords: blockchain; law; legal; online transactions; reputation; smart contracts; trust

Taking Real-Life Seriously: An Approach to Decomposing Context Beyond “Environment” in Living Labs - Lynn Coorevits; An Jacobs (Technology Innovation Management Review, 2017)
The maturity of living labs has grown over the years and researchers have developed a uniform definition by emphasizing the multi-method and real-life, contextual approach. The latter predominantly focuses on the in situ use of a product during field trials where users are observed in their everyday life. Researchers thus recognize the importance of context in living labs, but do not provide adequate insights into how context can be taken into consideration. Therefore, the contribution of this article is twofold. By means of a case study, we show how field trials can be evaluated in a more structural way to cover all dimensions of context and how this same framework can be used to evaluate context in the front end of design. This framework implies that living lab researchers are no longer dependent on the technological readiness level of a product to evaluate all dimensions of context. By using the proposed framework, living lab researchers can improve the overall effectiveness of methods used to gather and analyze data in a living lab project.
Keywords: context; innovation process; Living lab; real-life

Is There a Lean Future for Global Startups? - Stoyan Tanev (Technology Innovation Management Review, 2017)
This article integrates insights from the latest research on the lean startup entrepreneurial method, born-global firms, and global startups. It contributes to the clarification of terminology referring to the global aspects of startups, summarizes insights from previous literature focusing on global startups, and further substantiates the articulation of the need for considering the lean global startup as a new type of firm. The main message is that the lessons learned from the emergence of lean startup entrepreneurship offer a basis for promoting a similar lean phase in technology-based global startup research and practice. The analysis should benefit both researchers and practitioners in technology entrepreneurship, international entrepreneurship, and global innovation management.
Keywords: born global; global startup; international entrepreneurship; international new venture; lean global startup; lean startup; technology startup

TIM Lecture Series – Building Trust in an IoT-Enabled World - Jeremy Watson; John Marshall; Mike Young; Peter Smetny; David Mann (Technology Innovation Management Review, 2017)
Keywords: cybersecurity; Internet of Things; IOT; ransomware; trust; WannaCry; wireless

Towards Third-Generation Living Lab Networks in Cities - Seppo Leminen; Mervi Rajahonka; Mika Westerlund (Technology Innovation Management Review, 2017)
Many cities engage in diverse experimentation, innovation, and development activities with a broad variety of environments and stakeholders to the benefit of citizens, companies, municipalities, and other organizations. Hence, this article discusses such engagement in terms of next-generation living lab networks in the city context. In so doing, the study contributes to the discussion on living labs by introducing a framework of collaborative innovation networks in cities and suggesting a typology of third-generation living labs. Our framework is characterized by diverse platforms and participation approaches, resulting in four distinctive modes of collaborative innovation networks where the city is: i) a provider, ii) a neighbourhood participator, iii) a catalyst, or iv) a rapid experimenter. The typology is based on an analysis of 118 interviews with participants in six Finnish cities and reveals various ways to organize innovation activities in the city context. In particular, cities can benefit from innovation networks by simultaneously exploiting multiple platforms such as living labs for innovation. We conclude by discussing implications to theory and practice, and suggesting directions for future research.
Keywords: city; co-creation; collaborative innovation; innovation; Living lab; networks; Open innovation; smart city; third-generation

A University–Industry Collaborative Entrepreneurship Education Program as a Trading Zone: The Case of Osaka University - Koichi Nakagawa; Megumi Takata; Kosuke Kato; Terumasa Matsuyuki; Toshihiko Matsuhashi (Technology Innovation Management Review, 2017)
Two complementary problems are that busy practitioners find it difficult to access academic knowledge and university students lack practical experience. University–industry collaborative education is a potential solution for both of these problems by bringing together theoretical insights from universities and experiential know-how from industry. However, university–industry collaborative education has not been sufficiently studied to offer clear frameworks and mechanisms to foster effective knowledge exchanges between these two groups. In this article, we propose the metaphor of a “trading zone” as a potential analytical framework for implementing this method of education. Applying this framework to the analysis of a university–industry collaborative education program, this study proposes that the exchange of knowledge between students and practitioners is the essential learning experience and that it is made more meaningful by the heterogeneity between students and practitioners. The shared language provided by the program and those who deliver it make the exchanges efficient, and the temporary and extraordinary nature of the program accelerate those exchanges. Here, we analyze the case of Osaka University in Japan to illustrate the framework and develop associated propositions to encourage further study and validation of the framework.
Keywords: entrepreneurship education; experiential learning; technology commercialization; trading zone; university–industry collaboration

Using Artificial Intelligence and Web Media Data to Evaluate the Growth Potential of Companies in Emerging Industry Sectors - Andrew Droll; Shahzad Khan; Ehsanullah Ekhlas; Stoyan Tanev (Technology Innovation Management Review, 2017)
In this article, we describe our efforts to adapt and validate a web search and analytics tool – the Gnowit Cognitive Insight Engine – to evaluate the growth and competitive potential of new technology startups and existing firms in the newly emerging precision medicine sector. The results are based on two different search ontologies and two different samples of firms. The first sample includes established drug companies operating in the precision medicine field and was used to estimate the relationship between the firms’ innovativeness and the extent of online discussions focusing on their potential growth. The second sample includes new technology firms in the same sector. The firms in the second sample were used as test cases to determine whether their growth-related web search scores would relate to the degree of their innovativeness. The second part of the study applied the same methodology to the real-time monitoring of the firms’ competitive actions. In our findings, we see that our methodology reveals a moderate degree of correlation between the Insight Engine’s algorithmically computed relevance scores and independent measures of innovation potential. The existence of such correlations invites future work in attempting to analyze company growth potential using techniques founded in web content scraping, natural language processing, and machine learning.
Keywords: analytics; artificial intelligence; business intelligence; entrepreneurship; online textual data; precision medicine sector; startup growth potential

Value Propositions for the Internet of Things: Guidance for Entrepreneurs Selling to Enterprises - David Hudson (Technology Innovation Management Review, 2017)
This article provides entrepreneurs with guidance to help understand and express the specific and compelling value proposition for their Internet of Things (IoT) offer. IoT enables such a wide range of possible short- and long-term opportunities that IoT entrepreneurs may fall into the trap of considering IoT generally rather than positioning their offer to a buyer in a specific manner that helps win deals. The process of understanding and expressing a compelling value proposition will help the IoT entrepreneur focus their offer, understand who the real buyer is, and demonstrate tangible value to that buyer in a manner that is directed towards winning deals.
Keywords: entrepreneurship; guide; Internet of Things; offers; value propositions

All Australian Regions Are Not Born Equal: Understanding the Regional Innovation Management Sandpit - Anton Kriz; Courtney Molloy; Alexandra Kriz; Sabrina Sonntag (Technology Innovation Management Review, 2016)
In this article, we highlight and challenge an overly simplistic assessment of regions and regional innovation systems in Australia. Treating each region and place as equal and prescribing blanket policy is anathema to the reality. Having argued that places are not equivalent, we then move on to highlight that commonalities at a deeper institutional level are possible. We draw on fieldwork and ongoing action research from the Australian regions of Hunter and Central Coast (New South Wales) and Northern Tasmania. Results of the theory and case work have been instrumental in the development of 11 structural attributes of a regional innovation management (RIM) sandpit framework. The framework provides attributes but also important process insights related to regional programs, enterprise development, and project innovations. Although developing from the Australian context, we expect that the RIM Sandpit and its place-based insights can be generalized to other regions around the world.
Keywords: action research; constructed advantage; phronesis; pivot; quadruple helix; regional innovation management sandpit; RIS3; smart specialization; strategic management; triple helix

Assessing Cooperation between Industry and Research Infrastructure in Hungary - Csaba Deák; István Szabó (Technology Innovation Management Review, 2016)
In developed countries, a large share of R&D work is performed in universities, but the real significance of their contribution is larger, because they conduct most of the fundamental research. In this article, we examine one aspect of the academic sector that is visible to most outsiders, a field that requires usually the most resources as well: the research infrastructure. Hungary is currently in the process of forming its own National Infrastructure Roadmap. We present the results of a nation-wide survey carried out in 2014 by the National Innovation Office in support of the National Infrastructure Roadmap. The results represent a good starting point for developing measures and setting up goals for scientific fields. With the identification of research infrastructure usage by industry, this method might provide a best practice for other countries to undertake similar evaluations for their respective infrastructures.
Keywords: assessment; Hungary; national infrastructure; research infrastructure; survey; university

Audience Commodification: A Source of Innovation in Business Models - Datis Khajeheian (Technology Innovation Management Review, 2016)
This article reports on a research project aimed at developing a business model by changing the value-creation mechanism. The essence of this change is to persuade customers to perform actions in favour of the service provider. Such actions include responding to advertising clips to unlock value. The business model was generated from the concept of audience commodification and is based on the idea of looking at users as a source of a tradeable asset in business-to-business markets. Here, attention and actions are the assets that users pay to access the proposed value. The research includes two phases of surveys and experimentation. In the first phase, the tendency and acceptance level of users towards watching advertisements to unlock value are measured. In the next phase, a platform prototype is developed to test and understand user actions towards receiving value. The sample includes 52 users of different nationalities who were seeking relationships on an online dating platform. Results revealed that users accept advertising and will perform requested actions if they can perceive the delivered value. Practical implications of this research include insights to help move away from the current “view-based” advertising model toward new models of partnership with users in the value-creation process. This research may also stimulate further research into developing sustainable business models based on advertising revenue.
Keywords: audience commodification; business model; innovation; technology entrepreneurship; value marketing

Boundary Objects as Part of Knowledge Integration for Networked Innovation - Sari Mäenpää; Anu Helena Suominen; Rainer Breite (Technology Innovation Management Review, 2016)
Networked innovation in co-creation networks is not possible without collaborative practices. Especially in complex projects, contextual knowledge is often spread among different stakeholders. To harness this dispersed knowledge for networked innovation, working knowledge management and collaborative practices are needed. This article addresses this need for better understanding and approaches to facilitate knowledge integration for networked innovation. We consider knowledge integration as the ability to put knowledge into action, and networked innovation as the co-created goal-driven output of selected partners. Our study focuses on describing and reporting a cross-learning type of expert knowledge-integration process with boundary objects, concrete or abstract “bridges” for overcoming possible knowledge boundaries, in a co-creation network. This article adds knowledge on networked innovation through knowledge integration with boundary objects. The reported process will help managers to systematically approach problems requiring expert knowledge that does not exist within their own organization and to better integrate knowledge required for innovation within their project networks.
Keywords: boundary object; co-creation network; cross-learning; knowledge integration; networked innovation

Building Scientist Capacity in Knowledge Translation: Development of the Knowledge Translation Planning Template - Melanie Barwick (Technology Innovation Management Review, 2016)
The last fifteen years have seen a fundamental shift in the importance of knowledge translation in health research and clinical care. Health research funders have incorporated knowledge translation into their missions, strategic directions, and funding opportunities, encouraging knowledge translation and implementation science and requiring knowledge translation practice from researchers working across the health research pillars – basic, clinical, health services, and population health. Healthcare and research organizations have changed their landscape as well, hiring knowledge translation practitioners to bridge research and practice for a range of knowledge users. Universities are shifting criteria for academic promotion to incorporate knowledge translation. Growing attention to knowledge translation in research, practice, and scholarship has created a need for researchers and practitioners to develop knowledge translation skills and competencies related to their research, scholarship, and organizational activities. The Knowledge Translation Planning Template was developed to support knowledge translation planning for scientists in health and other sectors. This article provides an overview of the rationale for its development, introduces the tool components, and describes preliminary indicators of impact.
Keywords: capacity building; competencies; knowledge translation; template; tools

Co-Creating User Stories: A Tool for Making Sense of Business Opportunities - Anna-Greta Nyström; Miia Mustonen; Seppo Yrjölä (Technology Innovation Management Review, 2016)
This article discusses co-creation as a means of sensemaking among business-to-business actors, and presents a case study from the information and communications sector, in which the aim is to understand current and future media consumption and behaviour. We propose to expand the notion of co-creation in such a way that it also recognizes interaction and sensemaking between different stakeholders within an industry or sector, compared to the current view, in which the focus is on the consumers’ role in co-creation activities. Stakeholder co-creation entails jointly creating meaning of a chosen complex phenomenon by using practical tools, such as narratives in the form of user stories. Sensemaking is a narrative process and can thus be used in combination with practical facilitation tools in order to co-create user stories or other stories, and in other contexts.
Keywords: business-to-business; co-creation; sensemaking; user stories

Collaborative Innovation with External Actors: An Empirical Study on Open Innovation Platforms in Smart Cities - Jukka Ojasalo; Heini Kauppinen (Technology Innovation Management Review, 2016)
Despite the rapid increase of public–private–people partnership (PPPP) programs at the global scale, the scientific knowledge of collaborative innovation in cities is scarce. All smart city initiatives emphasize collaborative innovation for better services and products to address the needs and problems of modern cities. Indeed, there is an evident need for both scientific and practical knowledge in this area. Based on an extensive empirical study of open innovation platforms in smart cities, this article seeks to address this knowledge gap by increasing the knowledge of opportunities and challenges of collaborative innovation between a city and external actors, including companies, third sector organizations, research institutions, and citizens. The opportunities relate to novel services, products, and solutions, as well as economic gains, regional development, and systemic and process improvements. The challenges relate to city governments and external actors.
Keywords: collaboration; collaborative innovation; innovation intermediaries; innovation platform; PPPP; public innovation; public–private–people partnership; smart city; urban development

The Concept of the Entrepreneurial University Applied to Universities of Technology in Austria: Already Reality or a Vision of the Future? - Martin Sperrer; Christiana Müller; Julia Soos (Technology Innovation Management Review, 2016)
The concept of the "entrepreneurial university" is now recognized as a major driver for self-development and innovation and as an appropriate response to succeeding in highly turbulent and unpredictable markets. This article outlines and evaluates the current implementation of this concept at the universities of technology (TU) in Austria. First, to evaluate the status quo, a review of existing programs and initiatives was undertaken at the three universities comprising the "TU Austria": TU Graz, TU Wien (Vienna), and MU Leoben. Second, a questionnaire was designed on the basis of the HEInnovate framework and sent to representatives of the three universities and resulted in responses from TU Graz and TU Wien. The results underscore that the model of the entrepreneurial university represents the next step of development in higher education. Moreover, it demonstrates that there is still room for improvement at the TU Austria, especially in terms of fostering an entrepreneurial spirit among students.
Keywords: entrepreneurial spirit; entrepreneurial university; entrepreneurship; HEInnovate framework; triple helix; TU Austria; TU Graz; TU Wien

Corporate and Grassroot Frugal Innovation: A Comparison of Top-Down and Bottom-Up Strategies - Liza Wohlfart; Mark Bünger; Claus Lang-Koetz; Frank Wagner (Technology Innovation Management Review, 2016)
Frugal innovations aim at the development of basic solutions that are affordable for price-sensitive customer groups. This article looks at the similarities and differences between two major approaches, corporate and grassroot frugal innovation, and identifies initial ideas on how the two streams can learn from each other. The three pillars of sustainability (economic, environmental, and social) provide one of the guidelines for the comparison. The research is based on an analysis of case studies from various industries, six of which are presented in this article.
Keywords: case studies; corporate frugal innovation; frugal innovation; grassroots frugal innovation; startups; sustainability

Corporate Entrepreneurship: A Review and Future Research Agenda - Kamal Sakhdari (Technology Innovation Management Review, 2016)
The overarching theme of corporate entrepreneurship literature is to understand why some firms are able to generate higher levels of corporate entrepreneurship than others. While the extant literature has greatly advanced our understanding of entrepreneurial activities by established firms, less effort has been made to systematically review the literature to help us identify missing links and knowledge in prior studies. To address this gap, this article critically reviews previous important studies on corporate entrepreneurship and then develops a framework integrating previous research. Finally, the article suggests five potentially worthwhile avenues for future research.
Keywords: corporate entrepreneurship; established firms; innovation; strategic renewal; venturing

Creating Brand India: Strategies, Issues, and Challenges - Alok Chakrawal; Pratibha Goyal (Technology Innovation Management Review, 2016)
Just like a product, person, or institution, a country also has an impression in the minds of people. A brand distinguishes the product of one seller from those of the others. With the Indian Prime Minister's recent call to "Make in India", brand building is receiving more attention and momentum in the country. India is the largest democratic country with the highest GDP, and it is becoming a favourable destination for the global investment giants. But, despite various strengths and successes in image building, the country faces challenges in creating a sustainable, conducive environment for making India a production hub of the world. Bureaucracy, corruption, delay in clearance of business proposals, ethical standards and work culture, tax reforms, political interventions, socio-economic barriers, regionalism, etc. are some of the challenges that must be coped with. This article examines these various issues and challenges that must be overcome in creating Brand India.
Keywords: Brand India; challenges; economic growth; entrepreneurship; government initiatives; innovation; Make in India

Crowdfunding: Finding the Optimal Platform for Funders and Entrepreneurs - David Gedda; Billy Nilsson; Zebastian Såthén; Klaus Solberg Søilen (Technology Innovation Management Review, 2016)
As a steadily expanding source of venture capital, crowdfunding has become an alternative to traditional funding sources, such as banks and financial investors. The phenomenon of crowdfunding is represented by a growing number of Internet sites, here called crowdfunding platforms, devoted to the service. In this article, we investigate crowdfunding and their payout models, which are standard components on crowdfunding platforms. We consider the perspectives of both entrepreneurs and funders to determine the most attractive combination of models found on crowdfunding platforms. Our findings indicate that the most popular crowdfunding platforms, at the time of this study, reflect the preferences of entrepreneurs. The funders’ favoured crowdfunding model, which we call the equity model, is not currently found, in combination with the often-grouped, non-financial crowdfunding models of pre-order, sponsoring, or reward, on any of the top platforms. Thus, the research identifies a new market for crowdfunding platforms.
Keywords: crowdfunding; crowdfunding models; crowdfunding platforms; financing; payout models

The Cuckoo’s Nest Approach for Co-Creating Business Ecosystems in Smart Cities - Karlos Artto; Riikka Kyrö; Tuomas Ahola; Antti Peltokorpi; Kristiina Sandqvist (Technology Innovation Management Review, 2016)
The development of business ecosystems in smart cities is currently hampered by the absence of established approaches for facilitating long-term value and sustainability. In our view, the underlying reason is the lack of collective action involving various organizations in the design process. Collective action for the good of the whole ecosystem does not take place in existing participatory practices because of the dominating role of a single customer or designer organization (in urban development projects typically the owner-developer or lead architect), who uses their bargaining and decision-making power over others. This leads to sub-optimal behaviour where the system is optimized for the goals of one strong organization instead of collectively developed system-level goals of the business ecosystem as a whole. The Cuckoo’s Nest approach addresses this problem by inviting various expert organizations to design the system and assigning each organization design rights for the ecosystem and its system-level goal. The Cuckoo’s Nest approach enhances collective action among the organizations by making individuals from various organizations consider the interests, goals, objectives, and value-adding elements of other organizations – not just those of their own organizations. With the Cuckoo’s Nest approach, the business ecosystem comes first, and single organizations’ goals or specific design features come second. This article discusses the outcomes of two workshops where the Cuckoo’s Nest approach was used for the purpose of developing business ecosystems in connection with smart city development projects within the Helsinki Metropolitan Area. We outline the steps involved in the Cuckoo’s Nest approach and how they were applied in these two smart city projects, and we describe how it is being refined for further use in other locations and contexts.
Keywords: business ecosystem; business network; campus development; co-creation; co-design; collective action; Cuckoo’s Nest Approach; participatory planning; smart cities; sustainability

Detecting White Spots in Innovation-Driven Intellectual Property Management - Daniel Eckelt; Christian Dülme; Jürgen Gausemeier; Simon Hemel (Technology Innovation Management Review, 2016)
Technology companies scan the competitive arena for patents to discover research activities and technology trends. Patents are the outcome of innovation processes that take several month or even years, depending on the industry. The process of publishing patents usually lasts longer. A huge time gap of up to several years between early research and development activities and published patents is the consequence. Therefore, a patent is a weak indicator for the identification of early innovation activities. However, the inventor needs intellectual assets such as data, knowledge, and expertise to carry out an innovation process. It is likely that these intellectual assets can improve the competitor analysis – rendering them primary targets. In this article, we introduce a systematic approach to detect intellectual property (IP) activities of stakeholders in selected technology fields (e.g., hiring experts, taking part in research projects, gathering specific data). A technology field with a low intensity of IP activities offers great opportunities, which we call a "white spot". Our proposed approach can help identify the white spots in innovation-driven IP management and thereby help devise recommendations to improve a company’s IP portfolio.
Keywords: business model; competitive advantage; competitive arena; Innovation management; intellectual capital; intellectual property; value proposition

Developing a Startup and Innovation Ecosystem in Regional Australia - Troy Haines (Technology Innovation Management Review, 2016)
Technology is enabling change at an ever increasing pace, not only in urban contexts, but also in regional centres, where the Internet in particular is enabling entrepreneurs to compete in the global marketplace despite the size and remoteness of their home cities or towns. In regional Australia, the challenges of high unemployment, fading traditional industries, a lack of economic diversity, and a "brain drain" of talent to urban centres highlight the need for novel economic development strategies. Innovation and entrepreneurship are highlighted as potential solutions, but both require knowledge and support to be successful. In this article, the author shares lessons learned as an entrepreneur and through the ongoing development of a self-sustaining startup and innovation ecosystem in the remote region of Cairns, Australia. The model described in this article is now being applied to other regions in Australia, where trained champions are driving the development of startup and innovation ecosystems adapted to regional needs.
Keywords: Australia; Cairns; ecosystems; entrepreneurship; incubation; innovation; mentorship; regional; startups; theSPACE

Developing Tacit Knowledge of Complex Systems: The Value of Early Empirical Inquiry in Healthcare Design - Chantal Trudel; Sue Cobb; Kathryn Momtahan; Janet Brintnell; Ann Mitchell (Technology Innovation Management Review, 2016)
Infection prevention and control has been the subject of much study in medical and epidemiological research and a variety of best practice guidelines have been developed to support healthcare workers and related stakeholders. Yet, despite the availability of information, managing healthcare-associated infections remains a challenge because the relevant explicit knowledge is not being adequately developed and mobilized as tacit knowledge for use "on the front lines". Some researchers have called for a human factors perspective to help address challenges in designing for infection prevention and control, but relatively few studies have been conducted to date. Researchers also suggest that empirical inquiry is needed to better inform the design process, and particularly the design of complex systems where attention to detailed processes and interactions can support the success of an intervention. A human factors approach can help designers develop a deeper understanding of work processes, technology considerations, as well as physiological, psychological, cultural, and organizational factors. The need is particularly pressing in low-resource healthcare environments where funds, time, and human resources may be scarce and strategic design decisions based on evidence are needed to support meaningful and effective changes. With this in mind, a human factors study was conducted in an existing neonatal intensive care unit to identify the influence of product and environment design on infection prevention and control and to inform recommendations for improvement. In this case study, we illustrate how the application of an empirical, methodical approach can help design professionals and stakeholders develop tacit knowledge of complex systems – knowledge that can be used to better inform design priorities, the design process, decision making, and the allocation of resources to help maximize improvements.
Keywords: design research; ergonomics; healthcare design; human factors; infection prevention and control; knowledge mobilization; neonatal intensive care unit

A Digital Maturity Model for Telecommunications Service Providers - Omar Valdez-de-Leon (Technology Innovation Management Review, 2016)
Industries across the spectrum are being faced with a fundamental change: digital transformation. The telecommunications industry is no exception. For communications service providers, this transformation started some time ago with the emergence of so-called over-the-top (OTT) services such as WhatsApp and Skype. However, in spite of such transformation being underway, there is a lack of frameworks and tools to help communications service providers navigate such radical change. This article presents the findings of a research project to develop such a framework: the digital maturity model for telecommunications service providers. The model aims to offer a structured view of digital transformation that is specific to the context and challenges of the telecommunications industry and that can be used as a standard to help communications service providers benchmark themselves against peers or themselves as they advance their transformation. This article describes the need for the model and the methodology used to develop it, and it offers recommendations on how to use the model and further develop it as our understanding of digital transformation evolves.
Keywords: business; business transformation; digital; digital transformation; digitization; disruptive technologies; innovation; maturity model; telecommunications

Editorial: Cybersecurity (February 2016) - Chris McPhee; Dan Craigen (Technology Innovation Management Review, 2016)
Keywords: cybersecurity; intrusion; licensing; literature reviews; machine learning; malware; multisided platforms; new domains; open source

Editorial: Entrepreneurial India (May 2016) - Chris McPhee; Dharmesh Raval (Technology Innovation Management Review, 2016)
Keywords: Brand India; entrepreneurship; higher education institutions; India; intellectual property; Make in India; Open innovation; research; startups

Editorial: Insights (March 2016) - Chris McPhee (Technology Innovation Management Review, 2016)
Keywords: bootlegging; crowdfunding; emerging markets; frugal innovation; patterns; quintuple helix; underground innovation; urban living lab

Editorial: Living Labs and User Innovation (January 2016) - Chris McPhee; Seppo Leminen; Dimitri Schuurman; Mika Westerlund; Eelko Huizingh (Technology Innovation Management Review, 2016)
Keywords: closed innovation; field trials; impact assessment; living labs; Open innovation; user engagement; user innovation

Editorial: Managing Innovation (April 2016) - Chris McPhee (Technology Innovation Management Review, 2016)
Keywords: creativity; cybersecurity; entrepreneurship; frugal innovation; innovation; managing innovation; national culture; Open innovation; projects; startups

Employment Dynamics of Australian Entrepreneurship: A Management Perspective - Luke Hendrickson; Stan Bucifal; Antonio Balaguer; David Hansell (Technology Innovation Management Review, 2016)
This article attempts to draw together the literature on high-growth firms and management capability using Australian Government data from the Expanded Analytical Business Longitudinal Database. We tracked cohorts of new micro-sized firms (startups) over five years from birth. Compared with startups that had a low employment growth trajectory, medium- and high-growth micro-startups exhibited higher financial performance, higher innovation activity, and a greater propensity to seek external (debt or equity) finance. From a management perspective, medium- and high-growth startups were also significantly more likely to monitor and assess their performance across a wider range of performance indicators. High-growth micro-startups exhibited significantly higher operational process and organizational/managerial innovation, a higher likelihood of foreign ownership, and a greater demand for equity finance than medium-growth micro-startups. This data is consistent with other evidence that suggests that sustained high growth comes from superior strategic management and may suggest an ongoing role for government policy in building firm management capability in order to foster employment growth.
Keywords: Australia; creative destruction; employment; entrepreneurship; high growth; innovation; management; productivity; startup

Empowering Local Tourism Providers to Innovate through a Living Lab Process: Does Scale Matter? - David Guimont; Dominic Lapointe (Technology Innovation Management Review, 2016)
A destination management organization looking to integrate technology into its tourism offering tasked a living lab with engaging tourists and tourism providers in the process. At the end of the two-year initial funding period for an action research project, the process is a success and stakeholders are engaged in the innovation ecosystem. But what is next? By observing participants and gathering feedback from stakeholders through a Policy Delphi panel, the outcomes of the project and the intentions and actions of the tourism providers and other parties were identified. Innovation capacity has increased: spin-offs were created and stakeholders have embraced open and collaborative innovation. Now, stakeholders are determined to make the process sustainable by finding other funding sources. But what should be the level of cooperation and intervention? What level can best foster innovation and knowledge retention? A case study combining a grid of characteristics and levels of analysis for living labs was used to identify one key question: for a living lab in tourism, does scale matter? This article will explore that question and will contribute to the understanding of the living lab as a model of socio-territorial action.
Keywords: action research; destination management; innovation; level; living labs; scale; socio-territorial action; territoriality; tourism

Enhancing Early Innovation in an Urban Living Lab: Lessons from Espoo, Finland - Soile Juujärvi; Virpi Lund (Technology Innovation Management Review, 2016)
Urban areas are often characterized by complex problems, such as social and economic deprivation, segregation, or bureaucratic administration. Urban living laboratories provide a promising approach to redefining and tackling such problems in novel ways by enabling bottom-up innovation with various actors. The present study examined an urban living lab initiative in a suburban area of Espoo, Finland, where guided workshops based on the Change Laboratory method were arranged. The findings show that, before development projects are launched, it is important to dedicate sufficient time to the early innovation process, which includes building relationships, sharing knowledge, exploring ignorance, and innovating new concepts. The study emphasizes the importance of distinguishing early innovation processes from later ones, which means separating the "preject" from the "project". We conclude that successful management of an urban living lab combines bottom-up and top-down approaches.
Keywords: Change Laboratory; innovation management; innovation process; preject; urban living labs

Entrepreneurial Growth Ambitions: The Case of Finnish Technology Startups - Arto Wallin; Kaisa Still; Katja Henttonen (Technology Innovation Management Review, 2016)
Technology startups are expected to be a major driving force of economic growth in Europe. The search for new high-growth startups has been particularly topical in Finland, the country that is known for its high-tech products – and the fall of Nokia’s mobile phone business. Although a record number of startups has been established in recent years, the previously identified challenge is that only a small percentage of entrepreneurial businesses are responsible for the lion’s share of economic benefits typically associated with entrepreneurial activity. Hence, we need better understanding of what level of growth technology entrepreneurs aim to create and why there may be differences in growth ambitions among them. In this study, we undertook interpretivist case study research in pursuit of rich, empirically grounded understanding of entrepreneurial growth ambitions in the context of Finnish technology startups. We interviewed entrepreneurs at a Finnish startup event and supplemented this information with data available publicly on the Internet related to the growth ambitions of startups. Our study sought to increase understanding of the different aspects of entrepreneurial growth ambitions, and to explore the relationship between context and growth. Based on the findings, we suggest that growth ambitions should be seen as a complex, socially constructed concept. The growth ambitions of entrepreneurs in our study were influenced, at least in part, by their startups' institutional and market contexts, the scalability of their business models, their personal characteristics and experience, and their perceptions of the barriers and constraints of the field. We conclude that startups have very different growth pathways: although the growth of one startup may depend on the talent of a few software developers, the growth of another startup may be based on its success in building international sales networks. As a result, to get most out of the support provided for a startup ecosystem, support activities should be tailored to different types of high-growth startups.
Keywords: entrepreneurial innovation; growth ambitions; startups

The Evolution of Intermediary Activities: Broadening the Concept of Facilitation in Living Labs - Louna Hakkarainen; Sampsa Hyysalo (Technology Innovation Management Review, 2016)
Innovation intermediaries play an important role in open innovation endeavours. In living lab projects, where different professional identities and organizational cultures are at play, intermediary actors facilitate learning between stakeholders and manage tensions and conflicts of interest. The current living lab literature recognizes the importance and multifacetedness of these actors, but does not shed light on the work they do at a more practical level. Our study seeks to capture the variety and evolution of work tasks of user-side innovation intermediaries during and after a four-year technology project in a living lab. The study explores how these mediating actors tackle the everyday challenges of a living lab project. This article is grounded on a longitudinal qualitative case study of a innovation process for a floor monitoring system for elderly care – the "smart floor".
Keywords: co-design; elderly care; facilitation; health technology; innovation intermediaries; Living lab

Examining the Modes Malware Suppliers Use to Provide Goods and Services - Tony Bailetti; Mahmoud Gad (Technology Innovation Management Review, 2016)
Malware suppliers use various modes to provide goods and services to customers. By mode, we mean “the way” the malware supplier chooses to function. These modes increase monetization opportunities and enable many security breaches worldwide. A theoretically sound framework that can be used to examine the various modes that malware suppliers use to produce and sell malware is needed. We apply a general model specified recently by Hagiu and Wright to study five modes that malware suppliers use to deliver goods and services to their customers. The framework presented in this article can be used to predict the mode in which a malware supplier will function; to study which types of malware suppliers, agents, and customers are attracted to each mode; to discover new modes; and to better understand the threat a malware supplier presents.
Keywords: agents; customers; cybercrime; cybersecurity; malware; modes; multisided platform; suppliers

A Framework for Sustainable Circular Business Model Innovation - Maria Antikainen; Katri Valkokari (Technology Innovation Management Review, 2016)
The circular economy concept is a novel economic model aiming to foster sustainable economic growth, boost global competitiveness, and generate new jobs. In order to make the circular economy mainstream, radical and systemic innovation is needed. Currently, a majority of the business modelling tools and methods lack at least some of the identified and needed elements for innovating business models in a circular economy. In this article, we build a framework for sustainable circular business model innovation by adding important perspectives: recognizing trends and drivers at the ecosystem level; understanding value to partners and stakeholders within a business; and evaluating the impact of sustainability and circularity. We present the results of a case study with a startup company, which was designed to test the framework and provide a concrete example of its usage and future development needs.
Keywords: business canvas; business model; case study; circular economy; innovation; sustainability

Governing Quintuple Helix Innovation: Urban Living Labs and Socio-Ecological Entrepreneurship - Bastiaan Baccarne; Sara Logghe; Dimitri Schuurman; Lieven De Marez (Technology Innovation Management Review, 2016)
Growing urbanization puts pressure on both social and ecological systems. This pressure raises complex and multi-facetted challenges that can only be tackled by collaborative and distributed innovation development processes. However, theoretical frameworks that assess such collaborations are often very conceptual, with little focus on the actual governance mechanisms that facilitate them. This article studies the urban living lab concept as an inter-organizational design and multi-stakeholder innovation development process to govern the quintuple helix model for innovation by means of an action research based multidimensional case study design, which focuses on the concepts of innovation democracy, mode 3 knowledge production, the innovation ecosystem as a system of societal subsystems, and socio-ecological transition. In this way, we provide a more profound understanding of such innovation processes to tackle socio-ecological challenges by means of public–private interactions driven by eco-entrepreneurship.
Keywords: distributed innovation; quintuple helix innovation; social ecology; socio-ecological entrepreneurship; urban living labs

Implementing Knowledge Translation Strategies in Funded Research in Canada and Australia: A Case Study - Gabriel Moore; Therese Fitzpatrick; Ivy Lim-Carter; Abby Haynes; Anna Flego; Barbara Snelgrove (Technology Innovation Management Review, 2016)
There is an emerging literature describing the use of knowledge translation strategies to increase the relevance and usability of research, yet there are few real-world examples of how this works in practice. This case study reports on the steps taken to embed knowledge translation strategies in the Movember Foundation's Men’s Mental Health Grant Rounds in 2013–14, which were implemented in Australia and Canada, and on the support provided to the applicants in developing their knowledge translation plans. It identifies the challenges faced by the Men’s Mental Health Program Team and how these were resolved. The strategies explored include articulating knowledge translation requirements, ensuring a common understanding of knowledge translation, assessing knowledge translation plans, methods of engaging end users, and building capacity with applicants. An iterative approach to facilitating knowledge translation planning within project development was rolled out in Australia just prior to Canada so that lessons learned were immediately available to refine the second roll out. Implementation included the use of external knowledge translation expertise, the development of knowledge translation plans, and the need for internal infrastructure to support monitoring and reporting. Differences in the Australian and Canadian contexts may point to differential exposure to the concepts and practices of knowledge translation. This case study details an example of designing and implementing an integrated knowledge translation strategy that moves beyond traditional dissemination models. Lessons learned point to the importance of a long lead-up time, the use of knowledge translation expertise for capacity building, the need for flexible implementation, and the need for efficiencies in supporting applicants.
Keywords: funded research; implementation; knowledge mobilization; knowledge translation; organizational learning

Innovation Rhetoric and Reality: An Introduction to the TIM Review's Special Issue on Innovation and Entrepreneurship in Australia - Rowena Barrett (Technology Innovation Management Review, 2016)
In this introduction to the Technology Innovation Management Review's special issue on Innovation and Entrepreneurship in Australia, Guest Editor Rowena Barrett reflects on the perceptions of "innovation", both in terms of its evolving concepts and terminology (the rhetoric) and its frontline application (the reality). Prompted by the recent launch and ongoing implementation of Australia Government's National Innovation and Science Agenda's, this special issue focuses on insights into innovation and entrepreneurship from the Australian context.
Keywords: Australia; entrepreneurship; innovation; National Innovation and Science Agenda

Insights from Stimulating Creative Behaviours in a Project-Based Organization Team - Tracy Stanley; Judy Matthews; Paul Davidson (Technology Innovation Management Review, 2016)
Novel and useful ideas and creative behaviours originate in varied work environments, yet the characteristics of work environments that stimulate and foster such creative behaviours are not well defined. The aim of this study was to identify the influences that contribute to creative behaviours in the work environment of a global project-based professional service organization. This article is based on an investigation of the work environment of one project team undertaking interdisciplinary work in the construction of a processing plant in a remote location. This multi-disciplinary team encouraged creative behaviours through regular team meetings, ensuring the presentation of diverse views and commitments to regular interaction and collaboration in co-located environments. In addition, a technology manager dedicated to identifying potential opportunities for patenting and commercialization further extended the creative behaviours of the team by focusing on the best solution for each situation. The study contributes new knowledge to research regarding work environments that facilitate creative behaviours.
Keywords: creative behaviours; problem solving; teams; work environments

Integrating Open Innovation Platforms in Public Sector Decision Making: Empirical Results from Smart City Research - Jukka Ojasalo; Lassi Tähtinen (Technology Innovation Management Review, 2016)
The purpose of this article is to increase knowledge of integrating an open innovation platform into public sector decision-making processes. Many of the distinctive characteristics of public sector decision-making processes pose a challenge for innovation collaboration with external actors. Often, external actors are not aware of these distinctive characteristics, or they find it very difficult to adapt to them. Particularly SMEs and startups find it difficult to adjust their operation to public sector decision-making processes. The existing literature includes very little knowledge of how such an innovation platform, which is an intermediary between a city and external actors, relates to the city’s decision-making processes. Still, this is an important issue considering the prerequisites of the success of an innovation platform. This qualitative explorative study is based on data from in-depth interviews and co-creative multi-actor workshops with participants from city governments and other organizations. It proposes a model of open innovation platform for public sector decision making in a city. The article contributes to the literature dealing with innovation intermediaries as well as public sector decision making in enhancement of innovation. It identifies and introduces three different kinds of relationships that are present and partly interwoven in open innovation platforms and intermediary organizations: governing, sparring, and collaborative. The prosed model shows a practical way of organizing the three types of relationships of an innovation platform with the city’s decision making and external actors. The model also helps in combining different decision-making cultures between the public, private, and third sectors in the context of collaborative innovation.
Keywords: collaborative innovation; innovation intermediary; open innovation platform; public decision making; smart city

Intrusion Learning: An Overview of an Emergent Discipline - Tony Bailetti; Mahmoud Gad; Ahmed Shah (Technology Innovation Management Review, 2016)
The purpose of this article is to provide a definition of intrusion learning, identify its distinctive aspects, and provide recommendations for advancing intrusion learning as a practice domain. The authors define intrusion learning as the collection of online network algorithms that learn from and monitor streaming network data resulting in effective intrusion-detection methods for enabling the security and resiliency of enterprise systems. The network algorithms build on advances in cyber-defensive and cyber-offensive capabilities. Intrusion learning is an emerging domain that draws from machine learning, intrusion detection, and streaming network data. Intrusion learning offers to significantly enhance enterprise security and resiliency through augmented perimeter defense and may mitigate increasing threats facing enterprise perimeter protection. The article will be of interest to researchers, sponsors, and entrepreneurs interested in enhancing enterprise security and resiliency.
Keywords: adversarial learning; clustering; cybersecurity; enterprise; intrusion detection; intrusion learning; learning algorithms; machine learning; real-time analysis; resiliency; security; streaming network data

License Compliance in Open Source Cybersecurity Projects - Ahmed Shah; Selman Selman; Ibrahim Abualhaol (Technology Innovation Management Review, 2016)
Developers of cybersecurity software often include and rely upon open source software packages in their commercial software products. Before open source code is absorbed into a proprietary product, developers must check the package license to see if the project is permissively licensed, thereby allowing for commercial-friendly inheritance and redistribution. However, there is a risk that the open source package license could be inaccurate due to being silently contaminated with restrictively licensed open source code that may prohibit the sale or confidentiality of commercial derivative work. Contamination of commercial products could lead to expensive remediation costs, damage to the company's reputation, and costly legal fees. In this article, we report on our preliminary analysis of more than 200 open source cybersecurity projects to identify the most frequently used license types and languages and to look for evidence of permissively licensed open source projects that are likely contaminated by restrictive licensed material (i.e., containing commercial-unfriendly code). Our analysis identified restrictive license contamination cases occurring in permissively licensed open source projects. Furthermore, we found a high proportion of code that lacked copyright attribution. We expect that the results of this study will: i) provide managers and developers with an understanding of how contamination can occur, ii) provide open source communities with an understanding on how they can better protect their intellectual property by including licenses and copyright information in their code, and ii) provide entrepreneurs with an understanding of the open source cybersecurity domain in terms of licensing and contamination and how they affect decisions about cybersecurity software architectures.
Keywords: contamination; copyright; cybersecurity; GPL; license; open source; third-party code

Managing Innovation Ecosystems to Create and Capture Value in ICT Industries - Jarkko Pellikka; Timo Ali-Vehmas (Technology Innovation Management Review, 2016)
In a new knowledge-intensive economic landscape, firms need to access external knowledge sources due to their inability to generate all necessary knowledge on their own. The interaction with and learning from external knowledge sources implies that firms depend upon decisions and actions made by business partners and external support organizations. This network of linkages can be considered as an ecosystem in which commercial enterprises and non-firm organizations interact with one another and work together to create and capture value. Previous studies have shown that a firm’s ability to successfully commercialize a new product depends not only on its own technology strategy but also its capabilities to manage an innovation ecosystem strategy. Dynamic markets, intense competition, and shorter product lifecycles force companies across different industries to create and capture value more rapidly by launching new innovations. Well-defined and executed innovation ecosystem strategies can help companies to develop new markets and business opportunities for the different types of innovations and enable their businesses to grow. This study provides new insight into how an ecosystem strategy can be formed based on the traditional strategy literature and proposes a conceptual framework for senior leaders to form an ecosystem strategy.
Keywords: innovation ecosystem; management; network; strategy; value capture

Mobilizing Knowledge: The Evidence Gap for Assistive Devices - Edward D. Lemaire (Technology Innovation Management Review, 2016)
Knowledge mobilization can be hindered in healthcare technology settings where the pace of change outpaces the ability to perform high-quality research methodologies that provide timely knowledge to enable informed prescription and technology application to the end user. Although well-controlled research with appropriate sample sizes is needed, this approach must be balanced with other evidence sources to address the knowledge immediacy requirements. Using carbon-fibre ankle–foot orthoses (i.e., lower-limb braces that improve stability, alignment, and foot-to-ground placement) as a case study, various sources of assistive device evidence were explored for their contribution to the continuum of knowledge in this area. A basic level of knowledge exists, but the quality is insufficient to inform the physical rehabilitation community on selecting from the almost 70 different devices on the market and the expected clinical outcomes for a target population. A combination of enhanced single-participant reports should be considered as an important part of the knowledge continuum and essential for knowledge immediacy. This approach must also be expanded to national and multinational database initiatives that provide a better base from which to extract knowledge on assistive device performance and mobilize this knowledge to provide optimal care for people with physical disabilities.
Keywords: assistive devices; knowledge mobilization; orthosis

Open Innovation in Indian Organizations: Types of Collaboration - Shiv S. Tripathi (Technology Innovation Management Review, 2016)
In order to succeed, it is important for any organization to leverage the power of the known and unknown networks around it. The organization must collaborate with others, and to do so requires it to open up its boundaries inside-out, outside-in, or both. However, the type of collaboration required to work with other parties and the respective output is different across different organizations on account of need, R&D intensity, capability, and risk-taking ability, as well as the nature of the business and industry. The major problem that comes in the way of open innovation in Indian organizations is their risk taking ability; the more an organization collaborates, the more risk it is taking by sharing internal information with the other parties. Through a sample of 31 manufacturing-based firms in India belonging to 12 different industries, the article explores the types of collaborations that they have with various related or unrelated organizations as they engage in open innovation. The article compares the collaborations each industry has entered into to identify the industries that are more open to take risks by collaborating with other parties in multiple ways.
Keywords: collaboration; forms; India; manufacturing; Open innovation; risk; types

Outcomes from Applying Design-Led Innovation in an Australian Manufacturing Firm - Peter Townson; Judy Matthews; Cara Wrigley (Technology Innovation Management Review, 2016)
Design-led innovation has recently emerged as an approach that assists companies to develop new capabilities to respond to changing markets. Previous research has shown that the application of design-led innovation to manufacturing businesses contributed to innovation across their business model, often repositioning the business and its offerings in the market. This article presents findings from a study where the researcher was embedded in an Australian firm, working four days per week for 11 months and using action research to apply design-led innovation. Deep insights from stakeholders were translated with the company staff into new value propositions for the company. This research demonstrates the largely untapped potential of an experienced designer as an innovation catalyst to help firms develop customer-inspired innovation as they use design-led innovation to overcome barriers and recognize opportunities within a changing market context. This study contributes new knowledge regarding benefits of design-led innovation in dynamic environments.
Keywords: customer insights; design-led innovation; innovation catalyst; manufacturing

A Pattern-Based Approach to the Development of Frugal Innovations - Anne-Christin Lehner; Jürgen Gausemeier (Technology Innovation Management Review, 2016)
The economic rise of emerging markets induces a rapid growth of the global middle class. This new mass market demands products and services adapted to the needs of the local population – so called "frugal innovations". Engineers often face similar challenges while developing products and services for these markets, and therefore may develop similar solutions. By the abstraction of these solutions to transferrable solution patterns, the efficiency of the development process could be increased. In this article, we introduce a systematic approach to develop a pattern system for frugal innovations. Based on 29 selected frugal innovations, we derived the problems that led to the development of the analyzed frugal innovations. By categorizing these problems, we deduced six problem categories: education, environment, culture, infrastructure, regulation, and finance. We stripped down the solutions to these problems to their core principles, and in our subsequent analysis, we identified 56 solution patterns. Moreover, we analyzed the relationships between the abstracted solution patterns, problem areas, and frugal innovations. By using a pattern-based approach, the efficiency of the product development process could be improved significantly. As well, patterns may generate new impetus and increase creativity.
Keywords: business model; developing markets; emerging markets; frugal innovations; market service; pattern catalogue; pattern system; solution patterns

Perspectives on Knowledge Mobilization: An Introduction to the Special Issue - Kimberly Matheson; Cathy Malcolm Edwards (Technology Innovation Management Review, 2016)
In this introduction to the Technology Innovation Management Review's special issue on Knowledge Mobilization, Guest Editors Kimberly Matheson and Cathy Malcolm Edwards share their different perspectives as an academic and a knowledge broker on the process of knowledge mobilization. Despite their distinctive points of entry into the knowledge mobilization field, they share a common perspective on the value of researchers and knowledge users learning from each other, working together to co-create solutions, and the importance of contributing back into the basic research and training of the next generation. They also provide the context of the authors' contributions to this special issue, noting that the articles are rooted in the authors’ experiences in the health domain, but that they help to understand some of the challenges and rewards of integrating knowledge mobilization into research approaches more generally.
Keywords: health; interdisciplinary; knowledge mobilization; partnerships

Priority Systems at Theme Parks from the Perspective of Managers and Customers - Gilda Hernandez-Maskivker; Gerard Ryan (Technology Innovation Management Review, 2016)
Waiting times are becoming an increasingly important customer-experience challenge in theme parks. The seemingly ever-present problem of long queues for rides and attractions is being tackled by the development of priority systems. These innovations allow customers to join an alternative queue that bypasses the congestion faced by regular customers. In other words, by paying extra, customers can purchase the right to be served sooner. Such systems are becoming prevalent, but there is a lack of empirical research into priority systems at theme parks in the academic and management literature, which suggests that in-depth empirical analysis is necessary in order to understand the consumer decision-making process when making this purchase. This article examines priority systems at theme parks both from the viewpoint of park management and of customers. To address this gap, we surveyed nearly 1,000 customers at a major theme park in Spain and conducted semi-structured interviews with 10 theme park managers to assess both customer and manager attitudes towards waiting generally and priority systems specifically. Our results reveal that these priority systems facilitate market segmentation. When theme parks offer this "wait or pay" option, different groups of customers are identified based on their attitudes: those who wait in regular lines and those who are willing to pay to avoid lines. Thus, this innovative system creates an important source of new revenue while also improving the customer experience by reducing waiting times and minimizing congestion. Following a discussion of our results, we offer practical recommendations to managers who need to address the challenges of waiting times in theme parks and wish to improve both profits and customer experiences by implementing a priority system.
Keywords: innovation; managers; priority queues; theme parks; tourism; tourist behaviour; waiting time

A Process for Co-Creating Shared Value with the Crowd: Tourism Case Studies from a Regional Innovation System in Western Switzerland - Vincent Grèzes; Béatrice Girod Lehmann; Marc Schnyder; Antoine Perruchoud (Technology Innovation Management Review, 2016)
Despite the presence of a regional innovation system, the gross value added attributed to tourism in the Swiss region of Valais is declining. Innovation policies fostering private initiatives and collaboration between companies, researchers, and coaching services have been reinforced recently, and policy instruments are in place to support strategic industries. However, no incitement instrument is dedicated to supporting the co-creation and the creation of shared value through local actors. This article presents a co-creation process of shared value and the lessons learned while implementing a new mode of innovation and entrepreneurship in two case studies in the peripheral region of Valais, Switzerland. The aim of the process is the co-creation of shared value-based business models, with an emphasis on the use of crowdsourcing to find new ways to create shared value.
Keywords: business models; co-creation; crowdsourcing; innovation; regional innovation system; shared value; tourism; tourism cluster

Profiling Regional Innovation Ecosystems as Functional Collaborative Systems: The Case of Cambridge - Jukka Viitanen (Technology Innovation Management Review, 2016)
It has been widely recognized that the national and regional development of innovation ecosystems has been a relatively successful model for regional revitalization, bringing together key actors to perform the relevant technology-driven development processes. The ecosystems have been organized and combine readily public sector interests with private sector business-oriented actions. However, all regions are not uniformly successful, which leaves open the question of how to guide the sub-optimum regional systems closer to the front-runner position. Why do some score better than the others? This article presents both theoretical and practical evidence of global best practice in developing regional innovation hubs and renders a fully integrated innovation hub framework that defines a novel, holistic approach to managing these ecosystems. The framework is tested and validated through a selected case study of Cambridge, United Kingdom, identifying the key ecosystem elements that are necessary for building up a solid foundation for the innovative regions.
Keywords: Cambridge; innovation ecosystem; management; orchestration; PPP; public–private partnership; system thinking

A Proposed Approach for Idea Selection in Front End of Innovation Activities - Andrew N. Forde; Mark S. Fox (Technology Innovation Management Review, 2016)
Current research indicates that the idea evaluation processes of many firms are ad hoc or intuitive, with very few firms having defined methods. We propose a new approach to select the best ideas to pursue amidst different probable versions of the future. In support of "front end of innovation" processes, the approach emphasizes the formation of requirements for any idea that can be prioritized and measured against possible future worlds. This approach is currently conceptual; future work will develop the approach into a methodology that can be tested using real-world problems. This article will be relevant to those who are exploring novel methods and approaches to selecting the best idea within their particular domains.
Keywords: FEoI; front end of innovation; idea selection; innovation; multi-criteria decision making; possible worlds; real options; stochastic models

Q&A. How Can a University Drive an Open Innovation Ecosystem? - Gonzalo León; Roberto Martínez (Technology Innovation Management Review, 2016)
Keywords: ecosystems; Open innovation; public–private partnerships; technology transfer; university–industry cooperation

Q&A. How Can Online Platforms Contribute to Smarter and More Prosperous Regions in Europe? - Hanne Melin; Samuel Laurinkari; Taina Tukiainen (Technology Innovation Management Review, 2016)
Keywords: digital economy; e-commerce; online marketplaces; online platforms; regional integration

Q&A. How Can You Teach Innovation and Entrepreneurship? - Anna Trifilova; John Bessant; Allen Alexander (Technology Innovation Management Review, 2016)
Keywords: learning entrepreneurship; tacit knowledge; teaching innovation; university–industry cooperation

Q&A. What is the Role of Higher Education Institutions in Promoting Entrepreneurship in India? - Dharmesh Raval (Technology Innovation Management Review, 2016)
Keywords: entrepreneurship education; HEI; higher education institutions; incubation; mentoring; startups

Rejuvenating the Cider Route in Quebec: An Action Design Research Approach to Stakeholder Collaboration and Innovation - L. Martin Cloutier; Laurent Renard; Sébastien Arcand; E. Michael Laviolette (Technology Innovation Management Review, 2016)
This article examines the problem of rejuvenating collaboration for innovation among cideries (cider producers) and the regional tourism association as the historical key stakeholders of the Cider Route of the Montérégie region in Quebec, Canada. The article reports on the initial steps of an action design research approach to support the stakeholders of the Cider Route in designing an innovative solution in response to numerous challenges they face, including a lack of new initiatives and steeply declining membership among cideries. The first step of the action design research was to define the problem: to renew the collaborative process among the Cider Route stakeholders by redefining the vision, mission, and strategy leading to an artifact proposal that could take the form of a mobile application. Thus, the notion of a boundary object is employed – in relation to the process of designing an information technology artifact in the form of a mobile application for the Cider Route – as a way to understand the need to collaborate to innovate in this context. The article also reports on the ongoing second step of the action design research process, which consists of supporting the collaborative process using group concept mapping. The group concept mapping method was suggested to guide and sustain the collaborative process over time because it is a participatory, bottom-up, mixed-methods approach to evaluation and planning. The group concept mapping, applied within the action design research approach, could be helpful in two ways: first, to define the rejuvenated vision, mission, and strategy for the Cider Route; second, to define the specific functionalities of the mobile application for the Cider Route.
Keywords: action design research; agrotourism; boundary object; Cider Route; stakeholder collaboration

Research on Fire: Lessons Learned in Knowledge Mobilization - Susan Braedley (Technology Innovation Management Review, 2016)
In this article, I outline knowledge mobilization lessons learned while working on politically “hot button” issues in public policy research related to fire services. These lessons were shaped by the research funding context. Researchers are increasingly required to develop research relationships with government, industry, and community partners to ensure research is relevant to those who can best use it, to embed knowledge mobilization in research processes, to ensure that knowledge has an impact in the world beyond the academy, and to provide research funding. Perhaps not surprisingly, when my findings created challenges for research partners, controversies erupted, potentially imperiling my research program, career, and potential research impact. Drawing from my knowledge-mobilization experiences as well as those of other researchers, I offer some insights gained from mobilizing knowledge on a “hot topic” in public policy.
Keywords: catalytic validity; knowledge mobilization; public policy; public services; research values

Revealing Hidden Innovation: Patterns of External Innovation Investment in Australian Businesses - Kieran O’Brien (Technology Innovation Management Review, 2016)
Recent theory and literature suggests that many businesses now innovate based on the adoption and modification of knowledge, technology, and innovations sourced externally rather than developed in-house. Yet, little is known about the value and economic impact of expenditures on outsourced innovation activities, which are often referred to as "hidden innovation" by many scholars. The issue is due largely to a lack of consistent measurement, available data, and analyses of expenditures on hidden innovation. In contrast, there is a long history of cross-country data collection on in-house research and development (R&D) activities and costs, and much research focuses on innovations involving in-house R&D effort. This study reviews results from a survey aimed at collecting new economy-wide data on external innovation investments in Australia. The results estimate total unmeasured or "hidden" investment in external innovation activities by Australian businesses at $3.5 to $4 billion in 2014, an amount large enough to stimulate important economic activity and warrant future research. This article discusses the implications of these results for policy, business strategy, and future research on innovation.
Keywords: Australia; external investment; hidden innovation; innovation investment

The Smart City Ecosystem as an Innovation Model: Lessons from Montreal - Mohamed Reda Khomsi (Technology Innovation Management Review, 2016)
Innovations are not confined to new technologies designed to improve the manufacturing processes of a product or the provision of a service. In a context of postmodernity, the new innovation paradigm calls on organizations to choose the best innovation strategies for their broader purposes. Today, such strategies usually involve adopting organizational structures that enable better collaboration with the stakeholders of an ecosystem. This article focuses on the smart city of Montreal – selected as the 2016 Intelligent Community of the Year by the Intelligent Community Forum – as a model of innovation. The aim is to understand the distinction between "the smart city" and "the smart destination", despite the omnipresence of tourism projects in smart city development plans. Among the key lessons are the importance of engaging tourism stakeholders and the role of a dedicated organization to develop and implement the city's unique vision.
Keywords: ecosystem; innovation; Montreal; smart cities; smart destination; stakeholders

Supporting Research-Inspired Entrepreneurial Activities in India - Nikhil A. Gokhale (Technology Innovation Management Review, 2016)
Nations built on innovation, entrepreneurship, and production are able to dominate the world economy. However, risk taking has traditionally been discouraged in developing nations. The uncertainty and financial insecurity associated with entrepreneurial activities are the greatest barriers that budding entrepreneurs need to overcome in order to transition into successful entrepreneurs. This challenge needs substantial effort and steady support from society. Easy access to information, mentorship, and a network of venture capitalists and angel investors also play critical roles in promoting entrepreneurial activities. To this end, the Government of India recently launched a nationwide campaign to promote entrepreneurial activities across the country. Some of the recently emerging trends indicate that scientific and technological innovators from India are now willing to be a part of the global entrepreneurial revolution. Research-inspired entrepreneurial initiatives are expected to play a key role in facilitating India’s economic growth in the coming years. This article focuses on the initiatives undertaken by the Indian Government and by various academic institutes to facilitate entrepreneurial activities across the country.
Keywords: business; economy; entrepreneurship; financial risk; research-inspired entrepreneurship

TIM Lecture Series – An Introduction to Intellectual Property for Entrepreneurs - Elizabeth Collinson (Technology Innovation Management Review, 2016)
Keywords: Canada; CIPO; copyright; entrepreneurship; industrial design; intellectual property; patents; startups; trade secrets; trademarks

TIM Lecture Series – Huge Memory and Collection-Oriented Programming: Less Code, More Speed? - Dave Thomas (Technology Innovation Management Review, 2016)
Keywords: big data; collection-oriented programming; databases; huge persistent memory; memory; object-oriented programming; programming; queries; speed; very large databases

TIM Lecture Series – Insights from Success and Failure in Technology Businesses - Chris McPhee; Peter Carbone; Sean Silcoff (Technology Innovation Management Review, 2016)
Keywords: Blackberry; book launch; innovation; insights; lessons; management; Nortel; Research in Motion; technology; technology innovation management review; TIM Review

TIM Lecture Series – Startup Life: Lessons Learned in Entrepreneurship - Andrea Baptiste (Technology Innovation Management Review, 2016)
Keywords: entrepreneurship; lessons; startups

TIM Seminar – Transforming a Desert City into an International Cybersecurity Hub and Ecosystem - Roni Zehavi (Technology Innovation Management Review, 2016)
Keywords: Canada; collaboration; cooperation; cybersecurity; CyberSpark; Israel

Transferable Practices for Knowledge Mobilization: Lessons from a Community-Engaged Health Research Study - Renate Ysseldyk; Angela Paric; Tracy Luciani (Technology Innovation Management Review, 2016)
Community-engaged health research can have both immediate and lasting impacts, yet is often plagued with various unknowns and unanticipated delays – this can be especially true in hospital settings with older adults. In this informal case study based on the authors’ collective experiences of an unraveling of the research process, the challenges and issues faced in assessing the health benefits of the “Music & Memory” iPod program in a complex continuing care hospital wing are discussed. Specifically, the lessons learned through the processes of acquiring ethical approval to work with a particularly vulnerable population, of effectively measuring the benefits of the program, and of the day-to-day logistical issues are recounted, with suggestions for overcoming these challenges through transferable practices for working with vulnerable or older adults and mobilizing the knowledge gained.
Keywords: challenges; community engagement; complex care; health; knowledge mobilization; music; older adults

Underground Innovation: How to Encourage Bootlegging Employees to Disclose Their Good Ideas - Kamal Sakhdari; Erfan Jalali Bidakhavidi (Technology Innovation Management Review, 2016)
Employees are increasingly considered as the origin of many corporate entrepreneurial ideas. Research on “bootlegging” posits that individuals often resort to hidden activities to elaborate their initial ideas and bring them to fruition. The origins and causes of bootlegging behaviour are well argued in the literature. Yet, less is known about what drives bootleggers to uncover their hidden ideas. This research uses field data from in-depth interviews with innovators in R&D departments in different industries of Iran to identify factors stimulating bootleggers to reveal their underground ideas. We identified five groups of factors at individual, managerial, firm, industrial, and idea levels, explaining the revealing stage of bootlegging behaviour. The findings provide a better understanding of the later phases of bootlegging behaviour and the possible role of context-specific factors such as cultural and religious beliefs.
Keywords: bootlegging; corporate entrepreneurship; hidden ideas; innovation; qualitative research method; R&D departments

Urban Living Labs for Sustainability in Suburbs in Need of Modernization and Social Uplift - Katarina Buhr; Maija Federley; Anja Karlsson (Technology Innovation Management Review, 2016)
A number of urban living labs have been set up in recent years, with the aim of developing innovation processes within a multi-stakeholder partnership in an urban context. Several urban living labs focus on sustainable development, which is a visible and urgent issue in less valued suburbs in need of modernization and social uplift. We argue that, when applying the living labs approach in the context of sustainable development in suburbs, the primary focus should be society’s collective goals, as expressed through municipalities and users. The aim of this article is to show examples of how urban living labs can be applied in less valued suburbs in order to contribute to sustainability based on societal goals. We build on analyses from the research project SubUrbanLab, where urban living labs were set up in Alby and Peltosaari, two suburban areas in Sweden and Finland, respectively. We draw lessons regarding how to use urban living labs for sustainable development in order to create favourable conditions for ongoing engagement with the municipality and users towards long-term sustainability.
Keywords: city; Living lab; suburb; sustainability; urban

Value Network Design for Innovations: Developing Alternative Value Network Drafts - Martin Kage; Marvin Drewel; Jürgen Gausemeier; Marcel Schneider (Technology Innovation Management Review, 2016)
Information technology increasingly permeates established products and services, thereby making them "smart". For companies, this trend necessitates new know-how in unknown fields. Hence, traditional manufacturing companies are increasingly forced to cooperate with new players within new value networks. In contradiction to value chains, value networks oftentimes exhibit no clear hierarchies and are characterized by rather weak ties between the participating players. For a company that wants to create smart products or services, the key challenge is arranging the value network such that the customer obtains a unique value while all participants profit from their engagement. In doing so, companies have to find new partners (companies, research institutes, etc.). In this article, we present a methodology to design value networks for innovations, including approaches to identify necessary competences, find suitable partners, and bundle them to powerful alternative value networks.
Keywords: innovations; inter-company collaboration; Internet of Things; value networks

Weighing the Pros and Cons of Engaging in Open Innovation - André Ullrich; Gergana Vladova (Technology Innovation Management Review, 2016)
The positive aspects of open innovation projects are widely discussed in innovation management research and practice by means of case studies and best practices. However, enterprises, particularly small and medium-sized enterprises (SMEs) also face miscellaneous challenges in open innovation practice, leading to uncertainty and even renunciation of open innovation project participation. Thus, it is essential for SMEs to find the right balance between possible positive effects and negative consequences – the latter being the less studied “dark sides” of open innovation. However, appropriate methods of finding this balance are still lacking. In this article, we discuss the assessment of open innovation project participation by presenting a weighing and decision process framework as a conceivable solution approach. The framework includes an internal, external, and integrated analysis as well as a recommendation and decision phase. Piece by piece, we investigate the current situation and the innovation goals of the enterprise as an initial point for a decision for or against engaging in open innovation. Furthermore, we discuss the development of a software tool that automatically applies this framework and allows self-assessment by SMEs.
Keywords: benefits; entrepreneurship; Open innovation; open innovation participation; risks; self-assessment tool; SMEs

Why National Culture Should Be at the Heart of Innovation Management - Tony Smale (Technology Innovation Management Review, 2016)
Over a period of decades, a substantial body of knowledge has accumulated that correlates national culture and socially and economically important behaviour, including innovation practice. National culture is an interconnected web of mental models that is shared by national groups and transcends the individual. It is highly influential in moderating the cognition and behaviour of groups and individuals. Different resources, including cognition and behaviour, are required at the different stages of the innovation process, and the context, including national culture (within which innovation is practiced), is an important consideration in designing strategy. Because innovation is a psychological and social process, understanding how national culture moderates that cognition and behaviour within the different stages of the innovation process and how the wider innovation ecosystem impacts innovation practice is central to understanding, strategizing and managing the innovation process. However, there has been limited application of this knowledge by practitioners. Therefore, this article examines the importance of national culture from a practitioner perspective, distilling the managerial implications and providing a list of questions that serve as a checklist to enable practitioners to analyze the implications of their own national and organizational context.
Keywords: creativity; implementation; initiation; innovation; national culture

3D Printing and Its Disruptive Impacts on Supply Chains of the Future - Sebastian Mohr; Omera Khan (Technology Innovation Management Review, 2015)
3D printing technology has emerged as one of the most disruptive innovations to impact the global supply chain and logistics industry. The technology is impacting our personal and professional lives, with some claiming that the technology will revolutionize and replace existing manufacturing technologies, while others argue that the technology merely enhances some aspects of the production process. Whether evolutionary or revolutionary, 3D printing technology is recognized as a striking trend that will significantly impact supply chains. Although the expansion of 3D printing in the private consumer market is an interesting development in its own right, the biggest potential for disruption lies in industrial applications and how 3D printing will influence supply chains of the future. In this article, we examine the areas of the supply chain most likely to be disrupted by 3D printing technology and we identify the key questions that must be answered in a roadmap for future research and practice. While we seek answers to these questions, we suggest that managers should develop a flexible change management strategy to mitigate the effects of disruption to their future supply chains and take advantage of the resulting opportunities. Those that do nothing will be left wanting, because the influence of 3D printing technology on supply chains is expected to grow.
Keywords: 3D printing; additive manufacturing; disruptive innovation; logistics; supply chain

Agile New Service Development in an Interdisciplinary Context - Sabrina Cocca; Ann-Mareen Franke; Simone Schell (Technology Innovation Management Review, 2015)
This article it shows the role of services in a highly interdisciplinary context: promoting cooperation between organizations in the life sciences industry and in the engineering and automation industry. It provides insights on how required offerings of knowledge-intensive business services (KIBS) are developed systematically based on a simple service engineering process model. In addition to the content-related view of new service development, findings from a meta-view are presented. Cooperating researchers and practitioners in the new-service development process observed their own collaboration and how the applied service engineering model had to be modified dynamically to the requirements of the use case. The results show that an easy-to-use service engineering model in a highly interdisciplinary context has benefits, but success is dependent on the joint efforts of an accordingly interdisciplinary team of engineers and natural scientists; a close communication with the customers both from the life sciences industry and the engineering and automation industry; and a more agile approach.
Keywords: agile; engineering and automation; interdisciplinarity; KIBS; knowledge-intensive business services; life sciences; new service development; service engineering

Botnet Takedown Initiatives: A Taxonomy and Performance Model - Reza Shirazi (Technology Innovation Management Review, 2015)
Botnets have become one of the fastest-growing threats to the computer systems, assets, data, and capabilities relied upon by individuals and organizations worldwide. Botnet takedown initiatives are complex and as varied as the botnets themselves. However, there is no comprehensive database of botnet takedowns available to researchers and practitioners, nor is there a theoretical model to help predict the success or failure of future takedown initiatives. This article reports on the author's ongoing research that is contributing to both of these challenges and introduces a set of hypotheses relating to the performance of botnet takedown initiatives. In addition to researchers, the article will be of particular interest to personnel in technical, legal, and management functions of organizations interested in improving the quality of their communications and accelerating decision making for the purpose of launching and operating botnet takedown initiatives. It will also be of interest to entrepreneurs who wish to launch and grow cybersecurity ventures that provide solutions to botnet and malware threats.
Keywords: botnet takedowns; cyber-attacks; dismantle cybercriminal networks; disrupt online networks

Building Cyber-Resilience into Supply Chains - Adrian Davis (Technology Innovation Management Review, 2015)
The article discusses how an organization can adopt an information-centric approach to protect its information shared in one or more supply chains; clearly communicate the expectations it has for a direct (Tier 1) supplier to protect information; and use contracts and measurement to maintain the protection desired. Building on this foundation, the concept of resilience – and that of cyber-resilience – is discussed, and how an information-centric approach can assist in creating a more cyber-resilient supply chain. Finally, the article concludes with five steps an organization can take to improve the protection of its information: i) map the supply chain; ii) build capability; iii) share information and expertise; iv) state requirements across the supply chain using standards, common frameworks, and languages; and v) measure, assess, and audit.
Keywords: cyber-resilience; cybersecurity; direct suppliers; indirect suppliers; information-centric approach; procurement; requirements; resilience; supply chain; Tier 1 suppliers

Business, Innovation, and Knowledge Ecosystems: How They Differ and How to Survive and Thrive within Them - Katri Valkokari (Technology Innovation Management Review, 2015)
In management studies, the ecosystem metaphor is often utilized without clear definition and, thereby, several partially overlapping concepts such as industrial, business, service, innovation, and knowledge ecosystems have been introduced. The purpose of this conceptual article is to go beyond the confusion to define what is meant by different concepts regarding an ecosystem and especially describe the relationships between the three different ecosystem types: business, innovation, and knowledge ecosystems. The article contributes to the literature by describing how the ecosystem types differ in terms of their outcomes, interactions, logic of action, and actor roles. The results show that the three ecosystem types are interconnected from the viewpoint of the ecosystem actor. For practitioners, the article sheds more light on how the rules of the game (i.e., the logic of action) differ in the different types of ecosystems and demonstrates that different models are needed in order to operate in different ecosystems.
Keywords: business ecosystem; communities; conceptual paper; ecosystem; innovation ecosystem; knowledge ecosystem; logic of action; man-made ecosystem; platforms

Challenges in Maritime Cyber-Resilience - Lars Jensen (Technology Innovation Management Review, 2015)
The maritime industry has been shown to be under increasing levels of cyber-attack, with future attacks having the potential to severely disrupt critical infrastructure. The industry lacks a standardized approach to cybersecurity, a national approach will be counterproductive, and a global mandatory standard, while needed, will take a long time to implement. In the shorter term, this article recommends that the industry coalesce around a set of voluntary guidelines in order to reduce the risk profile and increase resilience. To provide context for these recommendations, this article examines the specific characteristics of the maritime industry in relation to cybersecurity. Examples of existing vulnerabilities and reported cyber-attacks demonstrate that the threat is current and real.
Keywords: container; cyber-resilience; cyber-risk; CyberKeel; cybersecurity; maritime; terminal; vessel

Cities as Collaborative Innovation Platforms - Taina Tukiainen; Seppo Leminen; Mika Westerlund (Technology Innovation Management Review, 2015)
In this article, we focus on the role of a city as an orchestrator for innovation. We argue that cities should establish active dialogue with their citizens, and private and public sectors actors to co-create, develop, test, and offer service innovations that utilize diverse sets of platforms such as living labs. Our research contributes to the discussions of open and user innovations from the perspective of cities as communities that involve and integrate citizens and companies to collaborative innovation activities. While acknowledging that cities are platforms for simultaneous and divergent innovation initiatives, we identify four principal types of collaborative innovation. Cities serve as platforms for: i) improving everyday life; ii) conducting consumer and citizen experiments; iii) experimenting and implementing new technologies and services; and iv) creating new innovations and economies. Finally, we offer guidelines for fostering collaborative innovation activities between the public and private sectors.
Keywords: collaborative innovation; creative citizen; industry; Living lab; Open innovation; smart city

The City as Living Laboratory: Empowering Citizens with the Citadel Toolkit - Carina Veeckman; Shenja van der Graaf (Technology Innovation Management Review, 2015)
Lately, the concept of smart cities has been changing from a top-down and mostly technological-driven approach, towards a bottom-up process that facilitates participation and collaboration among city stakeholders. In this latter respect, the city is an ecosystem in which smart applications, open government data, and new modes of participation are fostering innovation. However, detailed analyses on how to manage bottom-up smart city initiatives, as well as descriptions of underlying challenges and barriers, are still scarce. Therefore, this article investigates four collaborative smart city initiatives in Europe to learn how cities can optimize citizen involvement in the context of public sector innovation. The analytical framework focuses on the different stakeholder roles in the ecosystem and the civic capacities to participate in the innovation process. The findings illustrate how more inclusive citizen involvement can be realized by providing different tools that align with the specific capacities and skills of the citizens. Furthermore, through specified workshop formats and peer learning, citizens lacking technical skills were also enabled to participate in the evolution of their cities, and to generate solutions from which both the city and everyday urban life can possibly benefit.
Keywords: citizen involvement; Living lab; open government data; smart city; toolkit

Contextuality and Co-Creation Matter: A Qualitative Case Study Comparison of Living Lab Concepts in Urban Research - Yvonne Franz; Karin Tausz; Sarah-Kristin Thiel (Technology Innovation Management Review, 2015)
Innovation development is key to transforming a product-based economy into an innovative service economy by integrating users as co-creators in real-life environments. User co-creation and user involvement are key elements in living labs. Urban living labs add not only the urban component to the conceptual design, but also societal, political, and technological questions. Fields of analysis in urban research relate to socio-spatial environment, living together, and urban policies. The leading question of this article is: to what extent can urban living labs be used as an instrument to support these fields of investigation? Comparing three different approaches for urban living labs, ranging from socially-centred to more technology-centred, we offer a more nuanced understanding of urban living lab design in diverging research contexts. All three case studies manage to go beyond testing and improving new products, which is normally the aim of existing living labs, by embedding innovation in appropriate social, structural, and institutional frameworks, and targeting civil society involvement. The community benefits from this case study comparison because it contextualizes living labs as research methodology to be applied in future urban research projects.
Keywords: co-creation; innovation ecosystem; participation; social innovation; urban living labs

The Creativity Canvas: A Business Model for Knowledge and Idea Management - Raouf Naggar (Technology Innovation Management Review, 2015)
Innovation depends on ideas generated through creativity and the knowledge and research that make it possible to put ideas to work. However, these two activities are very dependent on the people who perform them. As demonstrated by a pilot project realized at Hydro-Québec’s research institute (IREQ), any approach that does not take this understanding into account is doomed to failure. This article proposes that what must be developed is a knowledge and idea management system designed as a coherent ecosystem that takes all controlling factors into account and is based on stakeholder interest and preferences. This ecosystem is the result of a meticulous design of each of the elements that must generally be taken into account in a business model. A business model approach includes not only developing a value proposition for knowledge and idea management that suits the target clientele but also a good understanding of the resources and activities required to deliver this value proposition and especially the ways to finance them. Key to the development of such an ecosystem is the creation of fully functional innovation communities, which are responsible for building up and nurturing their ideas and knowledge assets and getting value out of them.
Keywords: business model; business model canvas; communities; creativity; ecosystem; ideas; knowledge; R&D; research institute; technological innovation

Cyber-Resilience: A Strategic Approach for Supply Chain Management - Luca Urciuoli (Technology Innovation Management Review, 2015)
Risk management and resilience strategies in supply chains have an important role in ensuring business continuity and reliability in a cost-efficient manner. Preventing or recovering from disruptions requires access and analysis of large amounts of data. Yet, given the multiple stakeholders, operations, and environmental contexts in which a global supply chain operates, managing risks and resilience becomes a challenging task. For this reason, information and communication technologies (ICT) are being developed to support managers with tailored tools and services to monitor disruptions, enhance instantaneous communication, and facilitate the quick recovery of supply chains. Hence, the objective of this article is to shed light on managerial strategies to improve the resilience of supply chains and thereby to point out how these could be automated by means of innovative ICT systems. In particular, this article concludes by warning about existing challenges to implementing such systems. If these challenges are not correctly addressed by managers, there is a major risk of further jeopardizing supply chains.
Keywords: cross-border trade; cyber-resilience; ICT; IT; risk management; supply chain management

Cybersecurity and Cyber-Resilient Supply Chains - Hugh Boyes (Technology Innovation Management Review, 2015)
There has been a rapid growth in the use of communications and information technology, whether embedded in products, used to deliver services, or employed to enable integration and automation of increasingly global supply chains. Increased use of information technology introduces a number of cybersecurity risks affecting cyber-resilience of the supply chain, both in terms of the product or service delivered to a customer and supply chain operation. The situation is complicated by factors such as the global sourcing of technology components or software, ownership of the systems in a supply chain, different legal jurisdictions involved, and the extensive use of third parties to deliver critical functionality. This article examines the cyber-resilience issues related to the supply of products, services, and the supply chain infrastructure considering the nature of threats and vulnerabilities and the attributes of cybersecurity. In doing so, it applies a model for cybersecurity that is adapted from the Parkerian hexad to explore the security and trustworthiness facets of supply chain operations that may impact cyber-resilience.
Keywords: cyber-resilience; cybersecurity; risk management; supply chain; threat management

Cybersecurity Skills Training: An Attacker-Centric Gamified Approach - Mackenzie Adams; Maged Makramalla (Technology Innovation Management Review, 2015)
Although cybersecurity awareness training for employees is important, it does not provide the necessary skills training required to better protect businesses against cyber-attacks. Businesses need to invest in building cybersecurity skills across all levels of the workforce and leadership. This investment can reduce the financial burden on businesses from cyber-attacks and help maintain consumer confidence in their brands. In this article, we discuss the use of gamification methods that enable all employees and organizational leaders to play the roles of various types of attackers in an effort to reduce the number of successful attacks due to human vulnerability exploits. We combine two separate streams – gamification and entrepreneurial perspectives – for the purpose of building cybersecurity skills while emphasizing a third stream – attacker types (i.e., their resources, knowledge/skills, and motivation) – to create training scenarios. We also define the roles of attackers using various theoretical entrepreneurial perspectives. This article will be of interest to leaders who need to build cybersecurity skills into their workforce cost-effectively; researchers who wish to advance the principles and practices of gamification solutions; and suppliers of solutions to companies that wish to build cybersecurity skills in the workforce and leadership.
Keywords: cyber attackers; cybersecurity; entrepreneur; gamification; training

Disrupting the Disrupter: Strategic Countermeasures to Attack the Business Model of a Coercive Patent-Holding Firm - Derek Smith (Technology Innovation Management Review, 2015)
A coercive patent-holding firm operates a business model that strategically targets firms to force unforeseen patent licensing rents. Coercive patent holders use aggressive litigation tactics to instantaneously create a complicated asymmetrical expensive problem with significant business risk. The strategy creates a dominant position by leveraging legal and business pressure to force the targeted firm into an involuntarily engagement with a coercive patent-holding firm. Such engagements can be quite profitable for the patent holders – and quite devastating for targeted firms. Thus, this article attempts to synthesize a business model framework that reveals insights concerning the profit formula, key resources, and key processes that support the dominant position of coercive patent-holding firms. Based on this framework, we further synthesize countermeasures to disrupt these business model elements and diminish the dominant position. The insights and countermeasures reveal strategic options and tactics that can be leveraged against the business model of a coercive patent-holding firm to alter the dominant position and improve the business situation of the targeted firm.
Keywords: business model; business model framework; coercive patent holder; countermeasures; intellectual property; non-practicing entity; NPE; patent; patent arsenal; patent office policy; patent shark; patent troll

Editorial: Cyber-Resilience in Supply Chains (April 2015) - Chris McPhee; Omera Khan (Technology Innovation Management Review, 2015)
Keywords: cyber-attacks; cyber-resilience; cyber-risk; cybersecurity; resilience; supply chains

Editorial: Living Labs and User Innovation (December 2015) - Chris McPhee; Seppo Leminen; Dimitri Schuurman; Mika Westerlund; Eelko Huizingh (Technology Innovation Management Review, 2015)
Keywords: business models; closed innovation; context; crowdsourcing; innovation networks; living labs; Open innovation; spaces and places; urban living labs; user innovation

Establishing New Codes for Creativity through Haute Cuisine: The Case of Ferran Adrià and elBulli - Ignasi Capdevila; Patrick Cohendet; Laurent Simon (Technology Innovation Management Review, 2015)
Ferran Adrià is one of the most recognized chefs in the world. His restaurant, elBulli, was awarded five times the title of the Best Restaurant in the World. Through an analysis of the last 30 years of the creative journey of elBulli, this contribution highlights that Adrià and his team of chefs succeeded in articulating two different processes: i) a process of creativity that aimed at defining a new “school” of high cuisine and ii) a process of innovation that was expressed by the new gastronomic experiences offered to the (happy few) customers of the restaurant until its closure in 2011. A careful examination of the coupling and decoupling of these two processes shows how they fueled each other, and how the management of the organization (through a specific type of ambidexterity) was conducive to the adequate articulation of the two processes.
Keywords: ambidexterity; creative process; creativity; elBulli; exploitation; exploration; Ferran Adrià; gastronomy; haute cuisine; innovation

Governance Solutions for Wicked Problems: Metropolitan Innovation Ecosystems as Frontrunners to Sustainable Well-Being - Timo J. Hämäläinen (Technology Innovation Management Review, 2015)
The growing specialization and interdependence of societies as well as their rapid technological and economic transformation have increased the level of uncertainty and complexity in decision making and the role of wicked problems in policy making. This article analyzes the nature and evolution of wicked problems and argues that they stem from the gap between the complexity of the policy problem and the variety of the corresponding governance arrangements. This complexity gap can be closed with new governance solutions that include participation, interaction, and cooperation among stakeholders; collective learning processes; coordination by mutual adjustment and clear systemic direction, decentralization, diversity, and experimentation; and effective measures to overcome system rigidities and development bottlenecks. For several reasons, cities and metropolitan areas provide ideal ecosystems for addressing wicked problems. They have the requisite variety of resources, capabilities and services, physical proximity that facilitates rich face-to-face communication, learning and cooperation, as well as the right scope for producing and experimenting with the necessary public goods and services. The article concludes by arguing that Finland could become a global frontrunner in solving wicked problems in policy making by adopting a strategy of sustainable well-being. This strategy would build on the world-class well-being knowledge within the Finnish welfare state and the rapidly growing international research on subjective well-being and happiness.
Keywords: cities; complexity; governance; sustainability; well-being; wicked problem

The Grey Areas Between Open and Closed in Innovation Networks - Seppo Leminen; Taija Turunen; Mika Westerlund (Technology Innovation Management Review, 2015)
This study argues that there are different degrees of openness and closedness in innovation activity, and it highlights the need for more research on the "grey areas" between totally open and totally closed innovation, particularly in innovation networks where multiple stakeholders collaborate for innovation. Here, we focus on four key aspects of innovation networks, as characterized by their degrees of openness or closedness: governance, motivation, interaction, and innovation practices. The categorization is based on a review of theory and an empirical analysis of three distinct innovation networks, two of which represent the open living lab model, and one of which exemplifies the traditional closed innovation model. Our results can help managers improve efficiency in innovation networks by better understanding the grey areas between open and closed in innovation.
Keywords: closedness; innovation; innovation network; Living lab; Open innovation; openness

Identifying the Challenges in Commercializing High Technology: A Case Study of Quantum Key Distribution Technology - Anas Al Natsheh; Saheed A. Gbadegeshin; Antti Rimpiläinen; Irna Imamovic-Tokalic; Andrea Zambrano (Technology Innovation Management Review, 2015)
This article examines the challenges in commercializing high technologies successfully and sustainably using quantum key distribution (QKD) technology as a case study. Quantum communication is increasingly relevant to cybersecurity and nanotechnology, which will replace current technologies and change the way we live. To understand how such high technology could be successfully commercialized, we interviewed individuals from four metrology institutions and two international companies. The result revealed that scattered and small markets, supply chain development, technology validation/certification, a lack of available or adequate infrastructure, and after-sales services are the most serious challenges facing successful commercialization of quantum communication technology. To validate these challenges, we conducted a survey of 60 experts, 49 of whom agreed that above-mentioned factors could affect the commercialization success of QKD technology. Likewise, the survey revealed that technical development, customer orientation/awareness, and government regulations could also hinder the commercialization of QKD technology.
Keywords: after-sales services; certification; challenges; commercialization; high technology; infrastructure; market size; quantum key distribution; standards; supply chains

Implementation Prerequisites for Electronic Procurement of Services - Ute Reuter (Technology Innovation Management Review, 2015)
Service procurement is a business function of increasing importance and is highly suitable for integration of electronic support, but it suffers from severe research deficits. As yet, implementation prerequisites for electronic procurement of services are obscure and not quantifiable. In this research project, organization, formalization, and specialization of procurement and standardization and strategic importance of the procured services are identified as relevant implementation prerequisites. Measurement models for these prerequisites are established and proven through quantitative empirical research. As such, this article is a major step towards a more rigorous investigation of electronic procurement of services.
Keywords: digitalization; electronic procurement; implementation; improvement; process innovation; procurement; purchasing; service management; service procurement

Innovation on the Open Sea: Examining Competence Transfer and Open Innovation in the Design of Offshore Vessels - Odd Jarl Borch; Marina Z. Solesvik (Technology Innovation Management Review, 2015)
In this article, we discuss the role of open innovation in collaborative design processes in mature industries such as the shipping industry. We examine the design of high-tech offshore service vessels in environments characterized by high volatility and complexity. We elaborate on the role that accumulating and sharing core competences plays in speeding up the innovation process and increasing product value. We present a longitudinal case study of a shipping company implementing an open innovation approach that integrates its own core competences in offshore operations with the competences of ship designers and ship builders to develop a new design for challenging environments. In this article, we draw on an open innovation approach and a competence-based view to demonstrate how the firm can "reach out" to gain novel competences related to innovation, which may transform the competitive environment to the firm’s advantage. The article would be useful to innovation scholars and practitioners who work with innovative product development.
Keywords: Arctic; cooperative design; core competencies; offshore operations; Open innovation; shipbuilding

Introduction to the Special Issue on Creativity in Innovation - Patrick Cohendet; Laurent Simon (Technology Innovation Management Review, 2015)
Managing creativity for innovation is a key challenge in today’s economy; therefore, the management of ideas will play in increasing role in driving the growth and resilience of organizations. Rather than simple inspired insights, ideas have to be addressed as complex socio-cognitive processes, to be organized and managed. To benefit from the full value of new ideas, management must constantly balance the formal and the informal, the logic of creation and the logic of production, and must learn to couple idea-generation processes and innovation processes through renewed knowledge management practices. In this introduction to the Technology Innovation Management Review's special issue on Creativity in Innovation, the guest editors highlight the need to manage: i) ideation processes to foster creativity, ii) the tension that exists between the logic of creation and production; and iii) disruptive innovation to transform a traditional industry.
Keywords: creativity; ideas; ideation; innovation; management

Lessons in Creativity from the Innovative Design of the Swatch - Gilles Garel (Technology Innovation Management Review, 2015)
No space is off-limits to innovation, even those occupied for many years by leading players and proven solutions. The case of the innovative Swatch watch, re-examined in this article with new information and insights, demonstrates that, without knowledge, design is not possible; but, with only knowledge, all we can do is reproduce. Innovation also requires creativity, the introduction of new concepts. Knowledge needs to be associated with unbridled, surprising, and hitherto unknown creativity, as described by the concept-knowledge theory of design. In this article, a new analysis of the well-known but misunderstood case of the Swatch yield lessons about the importance of creativity and knowledge in developing innovative products.
Keywords: concept; creativity; design; engineering; innovation; knowledge; Swatch

Level Up Your Strategy: Towards a Descriptive Framework for Meaningful Enterprise Gamification - Umar Ruhi (Technology Innovation Management Review, 2015)
Gamification initiatives are currently top-of-mind for many organizations seeking to engage their employees in creative ways, improve their productivity, and drive positive behavioural outcomes in their workforce – ultimately leading to positive business outcomes on the whole. Despite its touted benefits, little empirical research has been done to date to investigate technological and individual personal factors that determine the success or failure of enterprise gamification initiatives. In this article, we provide a summary of our preliminary research findings from three case studies of gamification initiatives across different business contexts and present an empirically validated descriptive framework that details the key success factors for enterprise gamification. Our adaptation of the mechanics, dynamics, and aesthetics (MDA) framework for enterprise gamification aims to explicate the connections between end-user motivations, interactive gameplay elements, and technology features and functions that constitute effective gamification interventions in the enterprise. Following a discussion of the core elements in the framework and their interrelationships, the implications of our research are presented in the form of guidelines for the management and design of gamification initiatives and applications. The research findings presented in this article can potentially aid in the development of game mechanics that translate into positive user experiences and foster higher levels of employee engagement. Additionally, our research findings provide insights on key success factors for the effective adoption and institutionalization of enterprise gamification initiatives in organizations, and subsequently help them enhance the performance of their employees and drive positive business outcomes.
Keywords: aesthetics; behaviour change; dynamics; enterprise gamification; gameful design; gamification; human-computer interaction; mechanics; persuasive technologies; user experience

Leveraging Living Lab Innovation Processes through Crowdsourcing - Anna Ståhlbröst; Josefin Lassinantti (Technology Innovation Management Review, 2015)
Around the globe, crowdsourcing initiatives are emerging and contributing in a diversity of areas, such as in crisis management and product development and to carry out micro-tasks such as translations and transcriptions. The essence of crowdsourcing is to acknowledge that not all the talented people work for you; hence, crowdsourcing brings more perspectives, insights, and visions to, for instance, an innovation process. In this article, we analyze how crowdsourcing can contribute to the different stages of innovation processes carried out in living labs and thus contribute to living labs by strengthening their core role as innovation process facilitators. We have also identified benefits and challenges that need to be grappled with for managers of living labs to make it possible for the crowd to fully support their cause.
Keywords: citizen; crowdsourcing; ICT; innovation process; Living lab; user

Luxury and Creativity: Exploration, Exploitation, or Preservation? - Joanne Roberts; John Armitage (Technology Innovation Management Review, 2015)
This article considers the role of creativity in the production and delivery of luxury. The concept of creativity is closely aligned to the idea of luxury goods as rare and highly crafted, often unique, objects produced through artistic endeavour. Moreover, some luxuries, such as expensive cars and private jets, require leading-edge design and technologically advanced inputs. Although creativity is essential for the development of new luxury goods and services, this article highlights that some luxuries are timeless and eschew the changes associated with radical creative transformations. Following a brief discussion of the nature of luxury and creativity, a number of examples are employed to illustrate the different roles of creativity in the development and delivery of different types of luxury. The relationship between luxury and creativity is shown to be varied and complex.
Keywords: craftsmanship; creativity; innovation; knowledge; luxury

Making Smart Regions Smarter: Smart Specialization and the Role of Universities in Regional Innovation Ecosystems - Markku Markkula; Hank Kune (Technology Innovation Management Review, 2015)
What makes a "smart region" smarter? We argue that it is the active orchestration of the regional ecosystem around concepts such as knowledge co-creation and exploitation, opportunity exploration, and capacity building. Simply adding to the proliferation of software developers in the area, stimulating the activities of business clusters around information technology, and providing digitally enabled services for citizens is not enough to make a region smarter. Smartness is enhanced by a well-orchestrated regional innovation ecosystem with a strong "smart specialization strategy" that leverages the new societal roles played by universities. In this article, we describe the European Commission’s program for research and innovation strategies for smart specialization (RIS3) and show how the Helsinki Region in Finland is using smart specialization, ecosystem orchestration, and the active role of universities to enhance regional innovation and the "smartness" of the region. These activities are discussed in the context of policy documents and strategy papers from regional, national, and European authorities, which illustrates some differences between papers and practice. This is work in progress, and based on early results, we draw initial conclusions about how putting policy into practice can make smart regions smarter.
Keywords: innovation; innovation ecosystems; quadruple helix; role of universities; smart cities; smart regions; smart specialisation; smart specialization; societal innovation; triple helix

A Method and Tool to Support the Management of Systems Engineering Projects - Claude Baron; Philippe Esteban; Rui Xue; Daniel Esteve; Michel Malbert (Technology Innovation Management Review, 2015)
Too many industrial projects still fail, mainly due to the managerial techniques used. Indeed, organizational processes are more or less specifically mentioned in systems engineering standards, but in practice, project managers tend to rely more on their own standards, which sometimes set forth practices that do not align with those of the systems engineering domain, hence the reported discrepancies that very often lead to project failure. Thus, we argue that, to improve the companies’ competitiveness when developing new products, cooperation between processes related to system development and project management is key to achieving performance and success. This article presents arguments that tend to support this assertion and introduces an ongoing project to develop both a method and tool that aim to integrate both domains.
Keywords: collaborative engineering; decision support; engineering processes; project management; system design; systems engineering; systems engineering standards

Optimizing Innovation with the Lean and Digitize Innovation Process - Bernardo Nicoletti (Technology Innovation Management Review, 2015)
Actionable knowledge to improve innovation and bring value to the customers and organizations is essential in today's economy. In the past, there have attempts to apply Lean Thinking and Six Sigma to the innovation processes, with mixed results. The aim of this article is discuss how to improve innovation processes using the Lean and Digitize Innovation process, which integrates digitization into the Lean Six Sigma method. Through the redesign of innovation processes and their automation, the process aims to add value to customers, improve effectiveness, eliminate waste, minimize operating costs, and reduce time-to-market. This new method is characterized by seven stages, or "the 7 Ds" (define, discover, design, develop, digitize, deploy, and diffusion), with 29 steps. This article describes the Lean and Digitize Innovation process and presents cases where the approach has been successful in helping innovation processes from start to end: from the definition of the value for the customers up to the implementation of a prototype and engineering of the delivery processes.
Keywords: agile innovation; Innovation management; lean and digitize; lean innovation; lean six sigma; re-engineering

Orchestrators of Innovation-Driven Regional Development: Experiences from the INNOFOKUS Project and Change2020 Programme - Mervi Rajahonka; Toni Pienonen; Riikka Kuusisto; Jari Handelberg (Technology Innovation Management Review, 2015)
The article takes a practical view of regional innovation ecosystems and presents ways to advance more efficient uses of public funding instruments by regional developers. Documenting the views of Finnish regional developers into two workbooks and a toolbox, the results of the INNOFOKUS project and its Change2020 development programme identified that promoting a high-impact project culture and smart specialization in Finland requires a continuous learning and participation process. Key individuals who can make this happen are innovation orchestrators who facilitate activities and compose the big picture. This article aims to bring forth an overview of the building blocks of an enriching and energizing environment and high-impact projects, and it presents an overview of how to enable the work of innovation orchestrators, who play a critical role in facilitating innovation ecosystems.
Keywords: agile project development; experimentation-driven development; high-impact projects; orchestrator; regional development; regional innovation ecosystem; smart specialisation; smart specialization

Personal Health Systems Technologies: Critical Issues in Service Innovation and Diffusion - Doris Schartinger; Ian Miles; Ozcan Saritas; Effie Amanatidou; Susanne Giesecke; Barbara Heller-Schuh; Laura Pombo-Juarez; Günter Schreier (Technology Innovation Management Review, 2015)
Personal health system (PHS) technologies can enhance public and private health service delivery and provide new business opportunities in Europe and around the world. Although much PHS technology has already been developed and could potentially provide virtually everyone with access to personalized healthcare, research driven primarily by a technology push may fail, because it fails to situate PHS within the wider health and social care service systems. In this article, we explore the scattered PHS research and innovation landscape, as well its relevant markets, using several types of analyses: bibliometrics, patent analysis, social network analysis, stakeholder workshops, and interviews. Our analyses aim to identify critical issues in the development and implementation of service systems around PHS technologies.
Keywords: ehealth; foresight studies; health and social care; healthcare; innovation ecosystem; mhealth; personal health systems; service innovation; service systems; stakeholders; system design; technology adoption

Places and Spaces within Living Labs - Birgitta Bergvall-Kåreborn; Carina Ihlström Eriksson; Anna Ståhlbröst (Technology Innovation Management Review, 2015)
In this article, we propose the concepts of places and spaces as conceptual tools to facilitate the organization of innovation activities within living labs. We have taken a pragmatic perspective on these concepts regarding how they are integrated in design situations, and how different types of places and spaces can facilitate or hinder innovation. We have found that, by applying openness, realism, and influence in the different spaces of our living lab milieus, they have transformed into many different places depending on the stakeholders involved, the methods chosen, and the facilitation of activities. Hence, by understanding this line of reasoning, living lab managers can make more informed decisions and plans for innovation activities.
Keywords: influence; Living lab; openness; place; realism; space

Q&A. Does a Software Development Firm Need an Open Source Policy? - Hassib Khanafer (Technology Innovation Management Review, 2015)
Keywords: open source license compliance; open source management; security vulnerabilities

Q&A. How Can I Secure My Digital Supply Chain? - Richard Wilding; Malcolm Wheatley (Technology Innovation Management Review, 2015)
Keywords: cyber-crime; cybersecurity; intellectual property protection; IT security management; supply chain risk; supply chain security

Q&A. In the Innovation Game, Why Do So Many Companies Stay on the Sidelines? - Katri Valkokari (Technology Innovation Management Review, 2015)
Keywords: co-creation; co-innovation; collaboration; innovation; lead users; Open innovation; open source

Q&A. Should the Internet Be Considered Critical Infrastructure? - Walter Miron (Technology Innovation Management Review, 2015)
Keywords: communication networks; critical infrastructure; cyber-attacks; cybersecurity; information technology; Internet; vulnerabilities

Representing Botnet-Enabled Cyber-Attacks and Botnet Takedowns Using Club Theory - Olukayode Adegboyega (Technology Innovation Management Review, 2015)
A model for executing and resisting botnet-enabled cyber-attacks and botnet takedowns does not exist. The lack of this representation results in ineffective and inefficient organizational decision making and learning, hampers theory development, and obfuscates the discourse about the “best-case” scenarios for the future of the online world. In this article, a club theory model for botnet-enabled cyber-attacks and botnet takedowns is developed. Initiatives to execute and resist botnet-enabled cyber-attacks and botnet takedowns are conceptualized as collective actions carried out by individuals and groups organized into four types of Internet-linked clubs: Attacker, Defender, Botbeheader, and Botmaster. Five scenarios of botnet-enabled cyber-attacks and five scenarios of botnet takedowns are examined to identify the specific dimensions of the three constructs and provide examples of the values in each dimension. The developed theory provides insights into the clubs, thereby paving the way for more effective botnet mitigation strategies. This research will be of particular interest to executives and functional personnel of heterogeneous organizations who are interested in improving the quality of their communications and accelerating decision making when solving botnet-related problems. Researchers applying club theory to examine collective actions of organizations linked by the Internet will also be interested in this research. Although club theory has been applied to solve problems in many fields, this is the first effort to apply it to botnet-related problems.
Keywords: botmaster; botnet; botnet takedown; collective action; cyber-attack; cybersecurity

The Role of Self-Service Mobile Technologies in the Creation of Customer Travel Experiences - Chaoren Lu; Wei Geng; Iris Wang (Technology Innovation Management Review, 2015)
Through the use of self-service mobile devices, the traditional marketplace interaction is being replaced by a marketspace transaction, in which the foundation of customer-company interaction has changed. This article discusses the main actors of experiencial value creation through the physical world and virtual world in the context of transport service. The empirical data is collected from semi-structured interviews with 19 young urban transport commuters. The results show that self-service mobile devices enhance the information accessibility for passengers to create customized travel experiences through a closer interaction with other actors, including transport service providers, transport-related service providers, and other passengers. Moreover, the scope of travel experience was expanded beyond the traditional service encounter both temporally and spatially. This article is an exploration of the influence of self-service mobile devices in the changing roles of customers and companies. A key message is that executives must pay attention to how their companies create experience value in both the physical world and the virtual world, separately or in combination.
Keywords: customer experience; mobile technology; self-service device; travel experience; value co-creation

Scaling Spatial Transformation: Smart Specialization of Urban Capabilities in the Helsinki Region - Renita Niemi; Eelis Rytkönen; Robert Eriksson; Suvi Nenonen (Technology Innovation Management Review, 2015)
Societies are shifting towards more complex structures and agile networks through spatial transformation. That shift affects the ways in which citizens interact with and within their physical and virtual surroundings. The interactions define purposes for the modern hybrid spaces, depending on individual demands in relation to space and time. As facilities per se are becoming less relevant, spatial concepts and service that support, attract, and engage modern individuals must be invented. The capabilities of user-orientated processes are important in terms of connectivity, co-creation, and communication, involvement in change, and control as well as governance. This article explores the potential scaling in diverse spatial transformations and summarizes the lessons learned from managing a campus as a small city to managing a larger-scale urban area. The study uses a case study methodology: the data was collected through interviews and document analysis. The framework of five urban capabilities (5Cs), which were initially introduced by the urbanist John Worthington, guided the content analysis of data. The results indicate that the lessons learned in the diverse urban projects can be scaled from a minor urban-area campus to a large urban area. Users of spaces have a need and will to collaborate, co-create, and impact their environments. This view expands the roles of decision makers and planners to controlling the uses of spaces for supporting grassroot initiatives. Consequently, active citizens engage and contribute, which can be a driving force for co-creation, shared ownership, and attractiveness of small- and large-scale areas.
Keywords: campus management; hybrid spaces; mobile work; scaling businesses; urban development and management

Secure by Design: Cybersecurity Extensions to Project Management Maturity Models for Critical Infrastructure Projects - Jay Payette; Esther Anegbe; Erika Caceres; Steven Muegge (Technology Innovation Management Review, 2015)
Many systems that comprise our critical infrastructures – including electricity, transportation, healthcare, and financial systems – are designed and deployed as information technology (IT) projects using project management practices. IT projects provide a one-time opportunity to securely "design in" cybersecurity to the IT components of critical infrastructures. The project management maturity models used by organizations today to assess the quality and rigour of IT project management practices do not explicitly consider cybersecurity. This article makes three contributions to address this gap. First, it develops the argument that cybersecurity can and should be a concern of IT project managers and assessed in the same way as other project management capabilities. Second, it examines three widely used cybersecurity maturity models – i) the National Institute of Science and Technology (NIST) framework for improving critical infrastructure cybersecurity, ii) the United States Department of Energy’s Cybersecurity Capability Maturity Model (C2M2), and iii) the CERT Resilience Management Model (CERT RMM) from the Carnegie Mellon Software Engineering Institute – to identify six cybersecurity themes that are salient to IT project management. Third, it proposes a set of cybersecurity extensions to PjM3, a widely-deployed project management maturity model. The extensions take the form of a five-level cybersecurity capability perspective that augments the seven standard perspectives of the PjM3 by explicitly assessing project management capabilities that impact the six themes where IT project management and cybersecurity intersect. This article will be relevant to IT project managers, the top management teams of organizations that design and deploy IT systems for critical infrastructures, and managers at organizations that provide and maintain critical infrastructures.
Keywords: C2M2; capability maturity models; CERT RMM; critical infrastructures; cybersecurity; NIST; P3M3; PjM3; project management

Securing Cyberspace: Towards an Agenda for Research and Practice - Renaud Levesque; D’Arcy Walsh; David Whyte (Technology Innovation Management Review, 2015)
In this article, we seek to identify the important challenges preventing security in cyberspace and to identify the key questions that nations should set out to answer to play a leading role in securing cyberspace. An important assertion is that the challenge of securing cyberspace transcends the abilities of any single entity and requires a radical shift in our approach in how: i) research is conducted, ii) cybersecurity researchers are educated, iii) new defendable systems are developed, and iv) effective defensive countermeasures are deployed. Our response draws upon extensive source material and our personal experiences as cybersecurity professionals contributing to the establishment of the VENUS Cybersecurity Corporation, a not-for-profit corporation that aims to make Canada a global leader in cybersecurity. We view the challenge to be global and transdisciplinary in nature and this article to be of relevance world-wide to senior decision makers, policy makers, managers, educators, strategists, futurists, scientists, technologists, and others interested in shaping the online world of the future.
Keywords: Canada; challenges; countermeasures; cyber security; cybersafety; cybersecurity; cyberspace; detection; Internet of Things; leadership; mitigation; research; security

Securing the Car: How Intrusive Manufacturer-Supplier Approaches Can Reduce Cybersecurity Vulnerabilities - Mohamed Amin; Zaid Tariq (Technology Innovation Management Review, 2015)
Today's vehicles depend on numerous complex software systems, some of which have been developed by suppliers and must be integrated using "glue code" so that they may function together. However, this method of integration often introduces cybersecurity vulnerabilities at the interfaces between electronic systems. In this article we address the “glue code problem” by drawing insights from research on supplier-manufacturer outsourcing relationships in the automotive industry. The glue code problem can be framed as a knowledge coordination problem between manufactures and suppliers. Car manufacturers often employ different levels of intrusiveness in the design of car subsystems by their suppliers: the more control over the supplier the manufacturer exerts in the design of the subsystem, the more intrusive the manufacturer is. We argue that high intrusiveness by car manufacturers in defining module interfaces and subcomponents for suppliers would lead to more secure cars.
Keywords: automobile manufacturing; car design; control; cybersecurity; glue code; governance; intrusiveness; outsourcing; supplier; supplier-manufacturer relationships; vulnerabilities

Setting the Stage for Collaborative Creative Leadership at Cirque du Soleil - Laurent Simon (Technology Innovation Management Review, 2015)
Debates about the nature of leadership for creativity have been ongoing since the 1950s. But, despite the central role leadership plays in the management of creative processes, few contributions highlight the actual practice of leadership for collaborative creative ventures. This interview with the Director of Acrobatics and Coaching at Cirque du Soleil addresses the reflexive experience of a creative leader faced with the challenges of integrating multiple expertises around complex, technological, human, and poly-sensorial creative performances. In this context, leadership for collaborative creativity appears as a constant and dynamic balancing act between people, ideas, deliverables, and the position and personality of the leader.
Keywords: Cirque du Soleil; collaboration; creativity; innovation; leadership

Supply Chain Cyber-Resilience: Creating an Agenda for Future Research - Omera Khan; Daniel A. Sepúlveda Estay (Technology Innovation Management Review, 2015)
Supply chains have become more vulnerable in recent years, and high-profile cyber-attacks that have crippled the supply chains of well-known companies reveal that the point of entry for hackers is often through the weakest link in the chain. Exacerbated by growing complexity and the need to be visible, these supply chains share vital streams of information every minute of the day, thereby becoming an easy and highly lucrative target for talented criminals, causing financial losses as well as damaging brand reputation and value. Companies must therefore invest in supply chain capabilities to withstand cyber-attacks (i.e., cyber-resilience) in order to guard against potential threats. They must also embrace the reality that this often-unknown dimension of risk is the "new normal". Although interest on this topic has grown in the business world, less has been reported by the academic community. One reason for this could be due to the convergence of two different disciplines, information technology and supply chains, where supply chain cyber-risk and cyber-resilience appear to have a natural fit. The topic of cyber-resilience in supply chains is still in early stages of development, and this is one of the first journals to focus a special issue on it. Currently, the closest academic literature is within the realms of supply chain risk and resilience, where numerous models and frameworks exist. In this article, this literature is explored to identify whether these models can incorporate the dimension of cyber-risk and cyber-resilience. In doing so, we create a research agenda for supply chain cyber-resilience and provide recommendations for both academia and practice.
Keywords: cyber-risk; cybersecurity; resilience; supply chain management; theoretical foundation

Sustainable Innovation: A Competitive Advantage for Innovation Ecosystems - Kaisa Oksanen; Antti Hautamäki (Technology Innovation Management Review, 2015)
In this article, we elaborate the emerging concept of sustainable innovation and analyze the relevance of innovation as a means to solve wicked problems and enhancing sustainable well-being. We also examine the changing conditions for innovation creation: building global knowledge hubs and local innovation ecosystems. As a result, the drivers of innovation and opportunities to utilize the untapped innovation potential of people outside traditional innovation contexts are expanded and diversified. Ultimately, the success of sustainable innovation constitutes its impact on the well-being of people and vice versa: sustainable well-being is an important source of innovation and growth. The article adds to the conceptual development of sustainable innovation and its motivation, which lies in combining competitiveness, the well-being of people, and inclusive solutions.
Keywords: innovation; innovation ecosystem; sustainability; sustainable innovation; well-being

Technological Public–Private Innovation Networks: A Conceptual Framework Describing Their Structure and Mechanism of Interaction - Rabeh Morrar (Technology Innovation Management Review, 2015)
Technological public–private innovation networks, or TechPPINs, enable cooperation between public and private actors in a complex, dynamic, social, and interactive network structure. In this article, the literature on innovation networks is used to construct a conceptual framework that describes the structure and mechanism of interaction in technological public–private innovation networks. In the framework, innovation is created through a dynamic process of interaction between the public and private actors along the network lifecycle. In each stage of network lifecycle, social capital enables various interactions to occur and different modes and quantities of knowledge and technological resources to be exchanged and reinforced. Through a combination of the product lifecycle model and social network analysis, the structure of technological public-private innovation networks are examined at each stage of the lifecycle to reveal information about how the roles of public and private actors are embodied.
Keywords: conceptual framework; innovation networks; network lifecycle; networks; public–private partnership; social network analysis; technological public–private innovation networks; TechPPINs

A Technology-Assisted Design Methodology for Employee-Driven Innovation in Services - Kentaro Watanabe; Ken Fukuda; Takuichi Nishimura (Technology Innovation Management Review, 2015)
The role of employees is becoming more important in managing complex service processes and in serving the variety of customer needs in the service industry. Within efforts to promote innovation in service fields, employee-driven innovation and service design are gaining attention. Though the relationship between employee-driven innovation and service design has been discussed, the effectiveness of service-design methodologies for employee-driven innovation has not been studied sufficiently. In this article, we propose a technology-assisted design methodology to promote employee-driven innovation in services. Through our case study at an elderly-care facility, we confirmed that the proposed design methodology assisted by the communication support system could trigger employee-driven innovation and expand its influence in the service field.
Keywords: design methodology; employee-driven innovation; observation; representation; service design; service innovation

TIM Lecture Series – Communicating Strategy: How Drawing Can Create Better Engagement - Stephen Cummings (Technology Innovation Management Review, 2015)
Keywords: communicating; drawing; frameworks; illustrations; strategic management; strategy; SWOT; visual communication

TIM Lecture Series – Creating Life-Saving Media as a Social Entrepreneur - Firdaus Kharas (Technology Innovation Management Review, 2015)
Keywords: animation; culture shift; film; global health; humanitarian; media; public health; social entrepreneurship; social innovation; societal issues

TIM Lecture Series – Improving the Self-Service Customer Experience: The Case of IBM Watson and Purple Forge - Brian Hurley (Technology Innovation Management Review, 2015)
Keywords: apps; cognitive computing; IBM Watson; mobile platforms; natural language; Purple Forge; question and answer; self-service; virtual agent; voice recognition

TIM Lecture Series – The Expanding Cybersecurity Threat - Cheri F. McGuire (Technology Innovation Management Review, 2015)
Keywords: antivirus; cyber-attacks; cyber-espionage; cyber-threats; cybersecurity; data breaches; malware; private-public partnerships; ransomware; scareware; social engineering; Symantec

TIM Lecture Series – The Internet of Everything: Fridgebots, Smart Sneakers, and Connected Cars - Jeff Greene (Technology Innovation Management Review, 2015)
Keywords: Consumer Internet of Things; cyber-attacks; cybersecurity; hackers; Industrial Internet; Internet of Everything; Internet of Things; IOT

TIM Lecture Series – Three Collaborations Enabling Cybersecurity - Deborah Frincke; Dan Craigen; Ned Nadima; Arthur Low; Michael Thomas (Technology Innovation Management Review, 2015)
Keywords: book launch; collaboration; cybersecurity; entrepreneurship; NSA; research

TIM Lecture Series – When Are Software Systems Safe Enough? - Chris Hobbs (Technology Innovation Management Review, 2015)
Keywords: risk; safety; safety-critical systems; security; software systems; standards; testing

Toward a New Understanding of Creative Dynamics: From One-Size-Fits-All Models to Multiple and Dynamic Forms of Creativity - Stephen Cummings; Chris Bilton; dt ogilvie (Technology Innovation Management Review, 2015)
This article proposes an alternative to a managerial "best practice" approach to creativity based on the notion of creativity as a singular concept. Our alternative draws on three fundamental ideas that are emerging in different pockets of the creativity literature in a way that can be readily conceptualized and applied in practice. The first idea is that creativity is really about "creativities", or a cluster of different and discrete qualities that can be combined to suit the context in which they operate. The second is that creativity is not static: it is about "creativitying", or the action and the practice of combining these creativities, which evolve over time. The third is that being creative in organizations is not an individual act: rather, it is the multiple activities of groups as they go about creativitying.
Keywords: action-embedded creativity; creative dynamics; creativities; creativity; creativitying; innovation; management

A Value Blueprint Approach to Cybersecurity in Networked Medical Devices - George Tanev; Peyo Tzolov; Rollins Apiafi (Technology Innovation Management Review, 2015)
Cybersecurity for networked medical devices has been usually “bolted on” by manufacturers at the end of the design cycle, rather than integrated as a key factor of the product development and value creation process. The recently released cybersecurity guidelines by the United States Food and Drug Administration (FDA) offer an opportunity for manufacturers to find a way of positioning cybersecurity as part of front-end design, value creation, and market differentiation. However, the technological architecture and the functionality of such devices require an ecosystem approach to the value creation process. Thus, the present article adopts an ecosystem approach to including cybersecurity as part of their value proposition. It extends the value blueprint approach suggested by Ron Adner to include an additional dimension that offers the opportunity to define: the potential locations of cybersecurity issues within the ecosystem, the specific nature of these issues, the players that should be responsible for addressing them, as well as a way to articulate the added cybersecurity value as a competitive differentiator to potential customers. The value of the additional blueprint dimension is demonstrated through a case study of a representative networked medical device – a connected insulin pump and continuous glucose monitor.
Keywords: cybersecurity; ecosystem; market differentiation; networked medical devices; value proposition

Who Inhabits a Business Ecosystem? The Technospecies as a Unifying Concept - Michael L. Weber; Michael J. Hine (Technology Innovation Management Review, 2015)
Currently, many terms are used to describe business ecosystems and their inhabitants. These terms have meanings that can cause definitional confusion and an ambiguous level of analysis as to what constitutes a business ecosystem. To understand business ecosystem relationships, an unambiguous understanding of the ecosystem components is required. The importance of standardized terminology and clear definitions of these components has been recognized in the literature. From a managerial perspective, identifying the relationships a firm is situated in is valuable and useful information that can be practically applied. We propose a business ecosystem model anchored around interdependent technospecies similar to the biological model that many of the existing concepts are drawn from. Technospecies are unique entities based on their organizational routines, capabilities, and use of technology. This article will present an alternative formulation of the business ecosystem model with the aim of synthesizing the diverse terminology presently in use into a concise, common language.
Keywords: business ecosystem; business environment; complex adaptive systems; technospecies

Women Entrepreneurs in Developing Nations: Growth and Replication Strategies and Their Impact on Poverty Alleviation - Hina Shah; Punit Saurabh (Technology Innovation Management Review, 2015)
The need to improve the status of women and the promotion of women's roles in development are no longer seen merely as issues of human rights or social justice. Investments in women are now widely recognized as crucial to achieving sustainable development. Economic analyses now perceive that low levels of education and training, poor health and nutritional status, and limited access to resources not only repress women's quality of life but limit productivity and hinder economic efficiency and growth. Therefore, the development of opportunities for women is imperative, not only for reasons of equity but also because it makes economic sense and is "good development practice". The article describes the status and background of women in South Asia and highlights the need to create women entrepreneurs for poverty alleviation. Although some women do start micro-level businesses to support themselves and their families, the contribution is minor and many of these businesses are unlikely to grow or are not viable over the long term. Thus, this article focuses on women entrepreneurship development programs in light of the challenges and regional variations facing women entrepreneurs in South Asia and identifies nine areas where such programs can be strengthened. Their successful replication and implementation, in India specifically and South Asia generally, is discussed for an international audience to raise awareness of the challenges women and support institutions have faced in achieving success in fostering women entrepreneurship. It is hoped that this narration of the Indian and South Asian experience will assist in its replication in other developing nations.
Keywords: developing nations; poverty alleviation; women entrepreneurs; women entrepreneurship; women entrepreneurship development programs

3D Printing: A Revolutionary Advance for the Field of Urology? - Rebecca Neu (Technology Innovation Management Review, 2014)
Over the past decade, 3D printing has garnered considerable attention due to its broad applications, its ease of customization, and its increasing affordability. What began as the straightforward replication of simple objects has now progressed into a sophisticated industry for the fabrication of detailed products, which stands to threaten conventional forms of manufacturing and change the face of consumerism. More recently, the technology has found a footing within the medical field with the promise of applying 3D printing for the process of organ generation. With the reality of an aging population, the need for replacement organs globally will increase proportionately, while the number of donors remains static. In the field of urology specifically, the need for organ transplants is ever increasing as the number of patients in renal failure continues to rise. This article reviews the development of biological 3D printing, or biofabrication, within the field of urology and examines both the pros and the cons of this emerging technology. The cost implications of this technology for healthcare facilities are considered, as well as the entrepreneurial opportunities that arise from the emergence and evolution of 3D printing.
Keywords: 3D printing; biofabrication; biological 3D printing; bioprinting; entrepreneurship; nephrology; organ transplants; renal failure

Accessing Value-in-Use Information by Integrating Social Platforms into Service Offerings - Ville Eloranta; Juho-Ville Matveinen (Technology Innovation Management Review, 2014)
This article proposes a new approach for assessing the value derived from using a service offering (i.e., value-in-use) through the utilization of “social platforms.” We define a social platform as an adaptable digital service environment that enables the co-creation of value through social interactions with other service systems. By reviewing the relevant literature, detailed propositions are built based on the integration of theoretical concepts, thereby combining the literature on service-dominant logic, platforms, and social media. The primary argument of the article is that embedding social platforms in a company's services may result in more efficient retrieval and understanding of customer insights, better management of customer intelligence, and ultimately higher value-in-use.
Keywords: platforms; service systems; service-dominant logic; social media; value-in-use

Ambidextrous Strategies and Innovation Priorities: Adequately Priming the Pump for Continual Innovation - Nehemiah Scott (Technology Innovation Management Review, 2014)
The dynamic and unpredictable nature of the market has caused many organizations within rapidly changing industries to fail. These failures are, in part, due to a lack of continual and balanced innovation that firms should aim to achieve. That is, although firms may succeed at either refining existing competencies for incremental innovations or exploring new opportunities for radical innovations, many firms have experienced great difficulty in simultaneously pursuing and realizing success in both areas. This innovation imbalance arises when firms stick to traditional strategic notions of competition in fast-moving industries; these firms have not realized that the ability to compete in current and new markets begins with the strategies and priorities that are responsible for the very nature of innovation capabilities. The purpose of this study is to offer a reconceptualization of notions related to organizational strategy that are responsible for driving innovation capabilities. Specifically, this study develops a continual innovation framework that illustrates the impact ambidextrous strategies and priorities have on the firm’s ambidextrous innovation capability. It offers a modified concept of ambidexterity (i.e., exploration, exploitation, coordination) to reconceptualize business, marketing, and information systems strategies as ambidextrous strategy constructs. The article also discusses the relationships between constructs and the implications of this reconceptualization for researchers and managers.
Keywords: ambidexterity; exploitation; exploration; innovation; strategy

Assessing Scientific Contributions: A Proposed Framework and Its Application to Cybersecurity - Dan Craigen (Technology Innovation Management Review, 2014)
Through a synthesis of existing work on evaluating scientific theories and contributions, a framework for assessing scientific contributions is presented. By way of example, the framework is then applied to two contributions to the science of cybersecurity. The science of cybersecurity is slowly emerging. As the science and its theories emerge, it is important to extract the key contributions that characterize actual progress in our understanding of cybersecurity. Researchers and funding agencies will be interested in the assessment framework as a means of assessing scientific contributions to cybersecurity. In a nascent research area such as the science of cybersecurity, this article may contribute to a focused research program to accelerate the growth of the science.
Keywords: assessing science; cybersecurity; science of cybersecurity; scientific contributions; scientific progress; societal contributions

Assessing the Intentions and Timing of Malware - Brent Maheux (Technology Innovation Management Review, 2014)
Malware has become a significant, complex, and widespread problem within the computer industry. It represents one of the most prevalent threats to cybersecurity and is increasingly able to circumvent current detection and mitigation techniques. To help better understand when a malware attack might happen, this article proposes an intention-based classification of malware and merges it with an optimal timing model to help predict the timing of malware based on its classification. The classification model is based on an examination of eight malware samples, and it identifies four malware classifications and commonalities based on the dimensions of persistence and stealth. The goal of the article is to provide a better understanding of when cyber-conflict will happen, and to help defenders better mitigate the potential damage.
Keywords: cybersecurity; malware; optimal timing; persistence; stealth

A Citation-Based Patent Evaluation Framework to Reveal Hidden Value and Enable Strategic Business Decisions - Derek Smith (Technology Innovation Management Review, 2014)
Patent evaluation methodologies enable firms to make informed strategic business decisions by associating and revealing hidden information surrounding a patent. However, the value of a patent depends on a firm's capabilities and strategic direction; therefore, a patent evaluation requires the information to be properly related and aligned with a particular business consideration. This article reviews the literature on citation-based patent evaluation methodologies and develops a framework to help managers and entrepreneurs identify strategic groups of business considerations. The framework shows how categories of information can be interrelated to different strategic groups of business considerations, thereby providing a competitive advantage to the evaluating firm. The article includes recommendations for managers and entrepreneurs to help them make citation-based patent evaluation an ongoing business practice to enable strategic decision making.
Keywords: citation-based patent evaluation; intellectual property; literature review; patent; patent citations; patent evaluation; patent value; prior art citation

Collaborative Idea Management: A Driver of Continuous Innovation - Jesper Bank; Adnan Raza (Technology Innovation Management Review, 2014)
Despite the critical importance of innovation to most companies' ongoing success, many organizations fail to develop sustainable innovation management processes. The article explores the application of collaborative idea management to drive continuous innovation in large organizations based on our experience at Waabii, an innovation software and consulting service provider. First, we identify the key roadblocks faced by organizations in managing their innovation processes. Next, we describe the innovation model created at Waabii to help implement a sustainable innovation process, and we present a case study of an innovation management software solution, Exago Idea Market, which was implemented to create a collaborative and sustainable innovation environment in a large global telecommunications company. Finally, we offer recommendations for implementing this model of collaborative idea management. This article is particularly relevant to managers in larger organizations and practitioners of organizational change seeking to identify inhibitors of growth and business innovation and how to combat the roadblocks and create a sustainable innovation environment.
Keywords: collaboration; collaborative idea management; crowdsourcing; culture; innovation; leadership; Open innovation; strategy

Crimeware Marketplaces and Their Facilitating Technologies - Mahmoud Gad (Technology Innovation Management Review, 2014)
The cybercrime community has evolved from one in which criminals develop their own tools into one in which crimeware – tools and services to carry out or facilitate illegal online activity – can be readily bought, sold, traded, hired, or licensed in online marketplaces. Crimeware marketplaces are expected to grow significantly in the near term, and they will offer an increasing number of services and tools that target mobile computing devices. This article examines the actors, value chains, and modes of operation in underground crimeware marketplaces, and it identifies three facilitating technologies that are likely to significantly expand the reach of cybercriminals. Anonymous e-currency (e.g., Bitcoin) enables anonymous financial transactions; anonymity networks (e.g., Tor) enable anonymous Internet access; and mobile computing provides access to a very large number of potential target devices.
Keywords: anonymity; Bitcoin; crimeware marketplaces; cybercrime; dark web; underground economy

Cyber-Attack Attributes - Mehdi Kadivar (Technology Innovation Management Review, 2014)
Cyber-attacks threaten our ability to use the Internet safely, productively, and creatively worldwide and are at the core of many security concerns. The concept of cyber-attacks, however, remains underdeveloped in the academic literature. To advance theory, design and operate databases to support scholarly research, perform empirical observations, and compare different types of cyber-attacks, it is necessary to first clarify the attributes of the “concept of cyber-attack”. In this article, attributes of cyber-attacks are identified by examining definitions of cyber-attacks from the literature and information on ten high-profile attacks. Although the article will be of interest to a broad community, it will be of particular interest to senior executives, government contractors, and researchers interested in contributing to the development of an interdisciplinary and global theory of cybersecurity.
Keywords: attack characteristics; attributes; cyber-attack; cybersecurity

Cybersecurity Capability Maturity Models for Providers of Critical Infrastructure - Walter Miron; Kevin Muita (Technology Innovation Management Review, 2014)
Critical infrastructure such as power generation and distribution systems, telecommunications networks, pipelines and pipeline control networks, transportation control networks, financial networks, and government information and communications technology (ICT) have increasingly become the target of cyber-attacks. The impact and cost of these threats, as well as regulatory pressure to mitigate them, have created an impetus to secure these critical infrastructures. Managers have many controls and models at their disposal to help them secure infrastructure technology, including cybersecurity capability maturity models to enable measurement and communication of cybersecurity readiness to top management teams, regulators, and customers, thereby facilitating regulatory compliance, corporate responsibility, and improved brand quality. However, information and awareness is lacking about which models are most appropriate for a given situation and how they should be deployed. This article examines relevant cybersecurity capability maturity models to identify the standards and controls available to providers of critical infrastructure in an effort to improve their level of security preparedness. These capability models are described and categorized by their relevance to different infrastructure domains, and then recommendations are provided on employing capability maturity models to measure and communicate readiness. This article will be relevant to regulators, critical infrastructure providers, and researchers.
Keywords: adoption; bersecurity; capability maturity models; compliance; critical infrastructure; framework; municipalities; protection; regulation; standards

Cybersecurity Startups: The Importance of Early and Rapid Globalization - Tony Bailetti; Erik Zijdemans (Technology Innovation Management Review, 2014)
Corporations and government agencies worldwide seek to ensure that their networks are safe from cyber-attacks, and startups are being launched to take advantage of this expanded market for cybersecurity products, services, and solutions. The cybersecurity market is inherently global; therefore, cybersecurity startups must globalize to survive. With this article, we fill a gap in the literature by identifying the factors that make a technology startup valuable to specific stakeholders (e.g., investors, customers, employees) and by providing a tool and illustrating a process to describe, design, challenge, and invent the actions that should be performed to globalize a cybersecurity startup early and rapidly for the purpose of increasing its value. The development of the tool builds on recent advances in the resource-based literature, the review of the literature on born-global firms and business model discovery processes, and the experience gained operating the Lead to Win ecosystem. This article will be of interest to entrepreneurs and their venture teams, investors, business development agencies, advisors, and mentors of cybersecurity startups as well as researchers who develop tools and approaches that are relevant to technology entrepreneurs.
Keywords: born global; cybersecurity; globalization; startups

Defining Cybersecurity - Dan Craigen; Nadia Diakun-Thibault; Randy Purse (Technology Innovation Management Review, 2014)
Cybersecurity is a broadly used term, whose definitions are highly variable, often subjective, and at times, uninformative. The absence of a concise, broadly acceptable definition that captures the multidimensionality of cybersecurity impedes technological and scientific advances by reinforcing the predominantly technical view of cybersecurity while separating disciplines that should be acting in concert to resolve complex cybersecurity challenges. In conjunction with an in-depth literature review, we led multiple discussions on cybersecurity with a diverse group of practitioners, academics, and graduate students to examine multiple perspectives of what should be included in a definition of cybersecurity. In this article, we propose a resulting new definition: "Cybersecurity is the organization and collection of resources, processes, and structures used to protect cyberspace and cyberspace-enabled systems from occurrences that misalign de jure from de facto property rights." Articulating a concise, inclusive, meaningful, and unifying definition will enable an enhanced and enriched focus on interdisciplinary cybersecurity dialectics and thereby will influence the approaches of academia, industry, and government and non-governmental organizations to cybersecurity challenges.
Keywords: cybersecurity; cyberspace; definition; interdisciplinary; security

Designing and Managing Value Co-Creation in KIBS Engagements - Lysanne Lessard (Technology Innovation Management Review, 2014)
Knowledge-intensive business services (KIBS) such as IT development, IT outsourcing, and research and development (R&D) services have become a key component of most industrialized economies; they have been identified as an important source of employment growth in many countries and help improve the performance of firms belonging to most other sectors. KIBS have been discussed in innovation-related literature for over 15 years, with the assumption that models of innovation developed for manufacturing firms were not appropriate for them. This body of literature has also helped to identify the key characteristics and types of KIBS. However, although some empirical studies have investigated KIBS at the level of management – for example, how to manage customers’ co-production processes – there has not been much research on how to successfully establish and manage engagements among KIBS providers, clients, and other collaborators. Moreover, informal conversations with KIBS professionals show that these activities are often approached in an ad hoc manner. Yet, given the importance of KIBS, taking a more systematic approach to their design and management could improve the contribution of knowledge-intensive business service activities to our economy. This article proposes a framework for the design and management of KIBS engagements. The framework has been developed from a multiple-case study of academic R&D service engagements, as one type of KIBS engagement. It consists of a set of information to be gathered and questions to be asked by professionals responsible for establishing, monitoring, and managing KIBS engagements. The information and questions are articulated around two key processes of collaborative value creation (or value co-creation) in KIBS engagements: i) the alignment of actors’ interests, value propositions, and resources, and ii) the actors’ ability to integrate the engagement’s deliverables and outcomes as a basis for their perception of the engagement’s value. Using this framework could help to establish more successful collaborations among KIBS providers, clients, and partners; it should also help to monitor the performance of a given KIBS engagement in terms of its collaborative processes, deliverables, and outcomes from the varied perspectives of participating parties. Although the framework accounts for these different and sometimes conflicting perspectives, it is intended to be used by KIBS provider firms whose success depends at least in part from their ability to manage collaborative relationships.
Keywords: case study; KIBS; knowledge-intensive business services; service design; service management; value co-creation

Developing a Social Network as a Means of Obtaining Entrepreneurial Knowledge Needed for Internationalization - Chen Han; Adeleye Afolabi (Technology Innovation Management Review, 2014)
An internationalization process for startups is based on the exchange of knowledge and other resources required for early internationalization and fast growth, and it requires ventures to identify opportunities, conduct business, and gain a competitive advantage in a foreign market. But, how do entrepreneurs obtain the knowledge required for internationalization? Previous research suggests a role for the utilization of social networks, leading managers to ask three basic questions: i) what kinds of knowledge-based resources are urgently needed by international new ventures?, ii) how do needs for knowledge change according to different stages in the internationalization process?, and iii) how can changing needs for knowledge be met by developing and leveraging a social network? In this article, we review the related literature, discuss potential answers to these basic questions, and we suggest how a dynamic process can guide new ventures to acquire knowledge for developing resources and conducting business toward internationalization.
Keywords: business relationships; entrepreneurship; internationalization; knowledge acquisition; social networks

Disruptive Innovation vs Disruptive Technology: The Disruptive Potential of the Value Propositions of 3D Printing Technology Startups - Finn Hahn; Søren Jensen; Stoyan Tanev (Technology Innovation Management Review, 2014)
This article describes an empirical study focusing on the classification of existing business opportunities in the 3D printing technology sector. The authors address three research questions. First, how do technology startups integrate new 3D printing technologies into specific market offers? Second, which value propositions are most attractive in terms of interest from the public and investors? Third, how does the degree of disruptiveness of value propositions relate to the degree of interest from the public and investors? The most notable finding is the link between the business traction of 3D printing technology startups and the degree of disruptiveness of their value propositions. Thus, the article provides empirical support for the conceptualization of the degree of disruptiveness of the value proposition as a metric for the evaluation of the business potential of new technology startups.
Keywords: 3D printing technology; additive manufacturing; disruptive innovation; value proposition

Does Social Innovation Require Social Entrepreneurship? - Asceline Groot; Ben Dankbaar (Technology Innovation Management Review, 2014)
Social innovation is now considered an important element in the search for solutions to pressing social problems. Inspired by Schumpeter’s conceptualization of innovation, "social" entrepreneurship is thought to contribute to "social" innovation in more or less the same way that "normal" entrepreneurship consists of the introduction of "normal" innovations. In the literature as well as in practice, the definition of concepts such as social innovation and social entrepreneurship has led to considerable confusion. We aim to bring clarity to the debate, arguing that every entrepreneurial action results in some measure of intended or unintended social innovation, regardless of whether the entrepreneurs in question are considered or consider themselves "social" or not. We test our insights in an investigation of 20 social enterprises that have a commercial business model.
Keywords: entrepreneurship; institutional change; Schumpeter; social change; social entrepreneurship; social innovation; sustainability

Down the Rabbit Hole: How Structural Holes in Entrepreneurs' Social Networks Impact Early Venture Growth - Mackenzie Adams; Maged Makramalla; Walter Miron (Technology Innovation Management Review, 2014)
Social networks play a significant role in the success of new entrepreneurial ventures. They provide an accumulation of tangible and intangible resources that are linked to entrepreneurial outcomes such as growth and innovation. The structure of social networks, specifically, has been linked to these outcomes; structural holes in social networks have shown an association with entrepreneurial success. Entrepreneurs who have many structural holes in their networks are thought to benefit from a rich source of divergent information. This article examines the complex nature of the relationships among social networks, formal institutions, and the outcomes of new ventures. It also explores the effects of a social network’s structural holes on growth in the early years of a venture’s development. We propose that structural holes of a social network, through a mediating role of institutional polycentrism, play an important role in the growth and profitability of a new venture as well as potential threats of exploitation. We then provide recommendations based on the reviewed literature for entrepreneurs and managers of formal institutions.
Keywords: entrepreneurs; institutional order; social networks; structural holes; venture growth

Editorial: Cybersecurity (November 2014) - Chris McPhee; Tony Bailetti (Technology Innovation Management Review, 2014)
Keywords: crimeware; cyber-attacks; cybersecurity; globalization; malware; safety; science of cybersecurity; scientific contributions; startups

Electronic Word-of-Mouth Communication for Local Service Providers - Nora Schütze (Technology Innovation Management Review, 2014)
Word-of-mouth communication is a valuable means of marketing for small, local service providers. Face-to-face transmission is most prevalent, but electronic word-of-mouth is on the rise. Through the results of an agent-based simulation, this article shows that the penetration of word-of-mouth for a small service provider, who is locally restricted due to the inseparability of production and consumption, could benefit less from a growth in word-of-mouth connections than a larger service provider. Only if the added electronic connections are mainly local, small and larger service providers have similar effects on the penetration of word-of-mouth. The article includes a discussion of how small service providers could react to this threat.
Keywords: agent-based simulation; electronic word-of-mouth; local service provider; threshold model

Enhancing Innovation through Virtual Proximity - Tom Coughlan (Technology Innovation Management Review, 2014)
Historically, innovation strategists have focused on leveraging local resources and the development of local clusters, which have relied heavily on personal contact. It was assumed that serendipity would occur through casual contact and that this contact would result in rapid sharing of ideas. Many studies have supported this concept; however, the pace of innovation has changed and the most successful organizations promote not only physical proximity but also virtual proximity to resources. Virtual proximity refers to the level of emotional closeness between individuals, as developed through the use of information and communications technologies. This article argues that organizations can and should look to develop local virtual relationships supported by physical proximity: the mix of both virtual proximity and physical proximity can increase an organization's innovation capability.
Keywords: clusters; communication; distance; innovation; tools; virtual proximity

Entrepreneurship Education in India: A Critical Assessment and a Proposed Framework - Rituparna Basu (Technology Innovation Management Review, 2014)
Entrepreneurship education is considered as one of the most influential forces that determine the health of the economy. Hence, ignoring controversies on whether entrepreneurship can be taught, the majority of the top business schools in India offer entrepreneurship education with tailored elective courses to inculcate a wide range of skills encompassing a multi-disciplinary approach among mature management students. However, considering the basic synergies of core management subjects such as marketing and entrepreneurship, both of which provide an opportunity to develop unique solutions to satisfy customer needs, the study of entrepreneurial aspects as a prerequisite for management education and research seems indispensable when specifically catering to the growing entrepreneurial intent in developing economies. This approach necessitates a compulsory initiation of entrepreneurship courses early in the curricula of contemporary business schools. In this context, the present article aims to qualitatively review the current entrepreneurship education regime in India to propose an effective ecosystem for integrating and promoting entrepreneurship education as fundamental to mainstream business education in India.
Keywords: entrepreneurship; India; management education; marketing; qualitative research

Finding the Signal in the Noise of Patent Citations: How to Focus on Relevance for Strategic Advantage - Derek Smith (Technology Innovation Management Review, 2014)
Patent evaluations based on prior art citation data are business methodologies that can reveal hidden relationships between a patent and the associated prior art citations. These hidden relationships can further identify firms, actors and, technology and can identify strategic business relationships and opportunities. However, a fundamental problem with existing methodologies for discovering relevant relationships in citation data is noise. Citation noise obscures relevant relationships and impedes the potential value of these methodologies. This article reviews the literature on prior art citations as they relate to citation-based patent evaluation methodologies. A framework is presented to overcome citation noise and reveal relevant relationships to evaluate knowledge, technology, and invention properties, thereby opening up strategic and competitive advantages to the evaluating firm. The article provides guidance to executives and managers to help improve strategic decision making through relevant citation-based patent evaluations.
Keywords: citation noise; citation-based patent evaluation; intellectual property; literature review; patent evaluation; patent evaluation limitations; prior art citations

Finnish Knowledge-Intensive Business Services in China: Market Entry and Position in the Value Chain - Sen Bao; Marja Toivonen (Technology Innovation Management Review, 2014)
The internationalization of companies offering knowledge-intensive business services (KIBS) plays an important role in the general process of globalization. As the largest emerging market, China is attractive for Western KIBS. This article presents a case study on Finnish KIBS in China. Three companies in "clean tech" engineering, eco-cities design, and 3D media solutions describe the challenges and promoting factors in entering the Chinese markets. The study also examines the various ways of positioning the firm in the value chain through the roles of an integrator, a concept developer, and a multi-stage actor. Our findings illustrate the new business opportunities provided by China in advanced service sectors focusing on sustainability issues and creative content.
Keywords: internationalization of services; KIBS; knowledge-intensive business services; Western companies in China

Formulating an Executive Strategy for Big Data Analytics - Gopalakrishna Palem (Technology Innovation Management Review, 2014)
The recent surge in big data technologies has left many executives, both of well-established organizations and emerging startups, wondering how best to harness big data. In particular, the analytics aspect of big data is enticing for both information technology (IT) service providers and non-IT firms because of its potential for high returns on investment, which have been heavily publicized, if not clearly demonstrated, by multiple whitepapers, webinars, and research surveys. Although executives may clearly perceive the benefits of big data analytics to their organizations, the path to the goal is not as clear or easy as it looks. And, it is not just the established organizations that have this challenge; even startups trying to take advantage of this big data analytics opportunity are facing the same problem of lack of clarity on what to do or how to formulate an executive strategy. This article is primarily for executives who are looking for help in formulating a strategy for achieving success with big data analytics in their operations. It provides guidelines to them plan an organization's short-term and long-term goals, and presents a strategy tool, known as the delta model, to develop a customer-centric approach to success with big data analytics.
Keywords: big data; business vision; executive strategy; IT entrepreneurship; predictive analytics

The Government of India's Role in Promoting Innovation through Policy Initiatives for Entrepreneurship Development - Ravindra Abhyankar (Technology Innovation Management Review, 2014)
In spite of having a large publicly funded science and technology infrastructure and a sizeable education base, India has not been able to realize its innovative potential due to a fragmented innovation ecosystem. The government of India has taken many initiatives towards strengthening the innovation ecosystem, the most important of which are: i) the establishment of the National Innovation Council, whose mandate is to coordinate various innovation-related activities, and ii) the new Science, Technology and Innovation Policy 2013, which is intended to promote entrepreneurship and science-led solutions for sustainable and inclusive growth. With a focus on this new policy initiative, this article describes the current innovation ecosystem and the challenges it faces, and it discusses the efforts made by the government towards the promotion of innovation for entrepreneurship development and sustainable growth. With the implementation of this new policy the early indications are that India is poised to take a big leap towards innovation-led growth.
Keywords: economic growth; entrepreneurship; government; India; innovation; innovation ecosystem; policy

HarassMap: Using Crowdsourced Data to Map Sexual Harassment in Egypt - Chelsea Young (Technology Innovation Management Review, 2014)
Through a case study of HarassMap, an advocacy, prevention, and response tool that uses crowdsourced data to map incidents of sexual harassment in Egypt, this article examines the application of crowdsourcing technology to drive innovation in the field of social policy. This article applies a framework that explores the potential, limitations, and future applications of crowdsourcing technology in this sector to reveal how crowdsourcing technology can be applied to overcome cultural and environmental constraints that have traditionally impeded the collection of data. Many of the lessons emerging from this case study hold relevance beyond the field of social policy. Applied to specific problems, this technology can be used to improve the efficiency and effectiveness of mitigation strategies, while facilitating rapid and informed decision making based on "good enough" data. However, this case also illustrates a number of challenges arising from the integrity of crowdsourced data and the potential for ethical conflict when using this data to inform policy formulation.
Keywords: crowdsourcing; data collection; HarassMap; international development; social policy; user contribution systems

Innovation in Services: A Literature Review - Rabeh Morrar (Technology Innovation Management Review, 2014)
The article reviews the literature relevant to innovation in services, which has flourished since the 1990s. We discuss the definition of service and to what extent the characteristics of service output have influenced the conceptualization of innovation in services. Then, based on the literature review, we develop a conceptual framework for innovation in service sector, which classifies innovation in service sector into three main approaches: i) assimilation, where innovation in the service sector is assimilated from innovation in manufacturing sector; ii) demarcation, which differentiates innovation in service sector from the traditional conceptualization of innovation in manufacturing sector; and iii) synthesis, which aggregates both assimilation and demarcation approaches within a common conceptual framework. We discuss the relationship between innovation in services and economic performance using productivity and employment as two indicators of performance.
Keywords: assimilation approach; demarcation approach; economic performance; innovation; service innovation; synthesis approach

Integrating Design for All in Living Labs - Madeleine Gray; Mikaël Mangyoku; Artur Serra; Laia Sánchez; Francesc Aragall (Technology Innovation Management Review, 2014)
The European Union has identified innovation as a key driver behind business competitiveness and responsive governance. However, innovation in and of itself may not be sufficient to help businesses bring new products to market and to help governments shape public services that meet the real needs of citizens. The Integrating Design for All in Living Labs (IDeALL) project sought to identify and test methodologies for designing with users in real-life settings. The results of the experiments showed how different methodologies can be applied in different contexts, helping to provide solutions to societal issues and to create products and services that genuinely meet user requirements. In this article, we describe the methodologies used in the IDeALL project and provide examples of the project's experiments and case studies across four main areas: i) services; ii) health and social care; iii) information and communication technology; and iv) urban design.
Keywords: 3H; co-creation; design; design for all; health; HUMBLES; ICT; innovation; living labs; LUPI; methodologies; service prototyping; services; social care; urban design; user-centred approaches

IT Consumerization: A Case Study of BYOD in a Healthcare Setting - Sarah Marshall (Technology Innovation Management Review, 2014)
The ubiquity and utility of mobile devices in the consumer domain has led organizations to consider the benefits and challenges of allowing their employees to BYOD, or "bring your own device". The consumerization of information technology is a natural transition considering that devices are now commonplace in the personal lives of employees; however, despite the potential benefits to both the organization and employees, the use of employee-owned devices raises issues relating to security, governance, processes, and even organizational culture. This article focuses on the implementation of BYOD in a healthcare setting. First, the challenges of implementing BYOD in the healthcare industry are examined. Next, a case study of The Ottawa Hospital is developed to illustrate the practical benefits and hurdles that must be overcome when hospital staff begin using consumer IT devices in the workplace. Finally, recommendations are offered to help healthcare organizations develop and implement a successful BYOD strategy.
Keywords: BYOD; clinical mobile applications; electronic patient records; healthcare; iPad; IT consumerization; mobile devices

Mobile Convergence and Entrepreneurial Opportunities for Innovative Products and Services - Jeff Moretz; Chirag Surti (Technology Innovation Management Review, 2014)
Our research on 2012 and 2013 Canadian wireless service pricing indicates that data was underpriced relative to traditional voice and text messaging services. Such a situation, while potentially disadvantaging consumers of traditional mobile services, created a market that favoured competitors pursuing innovative uses of mobile data. Although more competitive pressures in the telecommunications market would provide broader benefits to Canadian consumers and facilitate greater innovation in related services, a favorable pricing differential vis-à-vis data transmission provides useful incentives. Even with recent changes to the pricing of mobile services in Canada, we should expect continued development of services that substitute data for voice and text messaging, particularly for international communications, as well as more innovative uses of mobile data.
Keywords: Canada; competition; entrepreneurship; innovation; mobile convergence; mobile services; wireless pricing

Overcoming Barriers to Collaboration in an Open Source Ecosystem - Derek Smith; Asrar Alshaikh; Rawan Bojan; Anish Kak; Mohammad Mehdi Gharaei Manesh (Technology Innovation Management Review, 2014)
Leveraging open source practices provides value to businesses when entrepreneurs and managers understand how to collaborate effectively in an open source ecosystem. However, the complex mix of different actors and varying barriers to effective collaboration in the ecosystem pose a substantial challenge. How can a business create and capture value if it depends on effective collaboration among these different groups? In this article, we review the published research on open source collaboration and reveal insights that will be beneficial to entrepreneurs and managers. We organize the published research into four streams based upon the following actor groups: i) governance actors, ii) competitors, iii) complementors, and iv) the core community. Then, through induction and synthesis, we identify barriers to collaboration, first by ecosystem and then by actor group. Finally, we offer six recommendations for identifying and overcoming barriers to collaboration in an open source ecosystem.
Keywords: business ecosystem; collaboration; collaboration barriers; communities; competitors; complementors; core community; governance; open source

Perceived Environmental Uncertainty for Startups: A Note on Entrepreneurship Research from an Indian Perspective - Susmita Ghosh; Bhaskar Bhowmick; Kalyan Kumar Guin (Technology Innovation Management Review, 2014)
In an entrepreneurship environment, understanding uncertainty is critical to startups because it is directly related to the context of decision making. In an emerging country such as India, uncertainties are more predominant due to the very nature of the emerging country, which is characterized by an underdeveloped institutional setup, a lack of protection for legal and intellectual property rights, underdeveloped factor markets, and high transaction costs. In this article, a systematic review of the existing literature on environment and uncertainty in an entrepreneurial, emerging-economy context identifies a gap of a new scale for perceived environmental uncertainty. Three primary contributions are made by this research. First, a literature review for existing uncertainty scales and their evaluation in the context of emerging countries is provided. Second, the research identifies a gap in the uncertainty measurement literature that is relevant to emerging economies. Finally, this study proposes a future research scope that can bridge the identified gap by exploring the factors of uncertainty in emerging countries.
Keywords: business environment; emerging economies; India; startups; uncertainty

Product and Service Interaction in the Chinese Online Game Industry - Patrik Ström; Mirko Ernkvist (Technology Innovation Management Review, 2014)
This article examines the rapidly-growing online game industry in China, which is a prime example of the changing regional landscape of new creative industries in East Asia. The industry’s evolution in China demonstrates the complexity of the growth of this industry through various knowledge and production networks. Despite the fact that Chinese companies were initially a second mover in this industry and had limited technological competence, they managed to move up the value chain within a few years, from operators of foreign-developed games to game developers. The catch-up process in this creative industry has differed from traditional manufacturing industries, which reflects the responsiveness and close proximity between product and service as key elements of the online game experience. This article conceptualizes this product–service offering in the industry and highlights its requirement for a widespread geographical network, as well as close proximity and responsiveness between elements of the network. In the empirical study of the growth of the Chinese online game industry described here, we argue that Chinese companies have managed to grow by utilizing the strategic control of service, player preferences, and responsiveness in this network, and translating this control into constant incremental improvement of their game development offering.
Keywords: China; Korea; MMOG; network; online gaming; product and service; service innovation

The Promoting Force of Technology for Service Innovation in High-Tech Industries - Silvia Gliem; Janny Klabuhn; Nadine Litwin (Technology Innovation Management Review, 2014)
This article focuses on the interaction between the development of technology and service innovation. It goes “back to the basics” by analyzing the first theoretical contributions to the service innovation literature from the late 1980s. These contributions were heavily technologically oriented: they aimed at bringing the results of technological innovation to the realm of services. More specifically, we focus on the model of “reverse innovation cycle” on one hand, and on the first innovation-specific categorization of services on the other. The latter introduced the division into supplier-dominated, production-intensive/scale-intensive, and science-based services. Our purpose is to examine in which ways these theoretical approaches could promote our understanding about the new phenomena of technology-service interaction in innovation. In the second part of the article, we apply these approaches in five case studies that originate from different service industries and that differ in size and technologies. The findings of the analysis demonstrate that the applicability of the approaches to the case studies depends on several factors including the kind of technology involved in the innovation activities, the stage of development of this technology, and the type of service.
Keywords: case studies; dynamic model of process and product innovation; reverse innovation cycle; service innovation; technology; technology adoption; technology development; typologies

Q&A. What is the Future of Entrepreneurship in India? - Ritu Dubey (Technology Innovation Management Review, 2014)
Keywords: ecosystem; entrepreneurship; incubators; India; social entrepreneurship; support agencies

Q&A. What Motivates Cyber-Attackers? - Chen Han; Rituja Dongre (Technology Innovation Management Review, 2014)
Keywords: cyber-attack; cybercrime; cybersecurity; hackers; motivation

Radical Versus Incremental Innovation: The Importance of Key Competences in Service Firms - Marit Engen; Inger Elisabeth Holen (Technology Innovation Management Review, 2014)
Today, innovation often takes place using open practices and relies on many sources for knowledge and information. The purpose of this article is to study how different knowledge-based antecedents influence the ability of service organizations to innovate. Using data about the Norwegian service sector from the 2010 Community Innovation Survey, we examined how three types of competence, namely R&D activities, employee-based activities, and customer-related activities, influence the propensity of firms to introduce radical or incremental innovations. The results show that R&D-based competence is important for service firms when pursuing radical innovations, whereas employee-based activities such as idea collaboration are only found to influence incremental innovations. The use of customer information was found to be an important driver for both radical and incremental innovations. The findings points to managerial challenges in creating and balancing the types of competence needed, depending on type of innovation targeted by an organization.
Keywords: community innovation survey; competences; innovation; innovation novelty; services

Resolving Legitimacy Deficits in Technology Startups through Professional Services Practices - Jay Payette (Technology Innovation Management Review, 2014)
As new ventures, technology startups face a key challenge that is specifically associated with their young age: a perceived lack of organizational legitimacy. Organizational legitimacy is an important factor in the growth and survival of new ventures and is therefore an important issue for managers and entrepreneurs to address. Although there are many different typologies for defining types of organizational legitimacy, this article argues that technology startups should focus on developing external pragmatic legitimacy as a means of acquiring the resources required to grow and thrive. However, despite the many ways by which an organization can develop external pragmatic legitimacy, few are well suited to technology startups. Based on a review of the different types of organizational legitimacy and an assessment of their applicability to the context of technology startups, this article recommends that technology entrepreneurs should consider the creation of professional services practices to help develop external pragmatic legitimacy and overcome the “liability of newness”.
Keywords: entrepreneurship; impression of viability; legitimacy; new ventures; operational verification; organizational legitimacy; pragmatic legitimacy; pragmatic validation; professional services; technology startups; viability

Reviewing the Knowledge Systems of Innovation and the Associated Roles of Major Stakeholders in the Indian Context - Punit Saurabh; Prabha Bhola; Kalyan Kumar Guin (Technology Innovation Management Review, 2014)
In this article, we review various models of knowledge systems and discusses the relationships between various component stakeholders of innovation, namely higher-education institutions, industry, and government. The article uses India as a case study to examine new challenges and opportunities facing its innovation ecosystem. Within this context, we review existing models of knowledge systems through an innovative representation exemplifying the knowledge landscape and the model positioning. We argue for a reinforcing role of major stakeholders in the proliferation of innovation and entrepreneurship, and the need to promote healthy interactions between them.
Keywords: entrepreneurship; government; higher-education institutions; industry; innovation ecosystem; innovation system; knowledge systems; models; stakeholders; university

The Role of Managers as Agents in Successful Service Innovations: Evidence from India - Shiv S. Tripathi (Technology Innovation Management Review, 2014)
The article is based on a three-year study of 70 business executives belonging to 20 large organizations operating in India to identify the kind of interventions used by agents (managers) to make service innovations successful. For the purpose of analysis, the subject organizations were classified into highly successful, successful, and unsuccessful organizations on the basis of their growth rate, and their practices were analyzed to identify the role of agents in those processes or related decisions. The article also compares the practices followed by organizations based in India with global organizations operating in India to understand the contextual issues of service innovations.
Keywords: agents; entrepreneurship; global organizations; India; intrapreneurship; managers; service innovation

Safety in the Online World of the Future - Nadeem Douba; Björn Rütten; David Scheidl; Paul Soble; D’Arcy Walsh (Technology Innovation Management Review, 2014)
In this article, we address what it means to be safe in the online world of the future by advocating the perspective whereby improving safety will improve resilience in cyberspace. We adopt a specific approach towards transdisciplinarity; present a weakly transdisciplinary model of the safety context and an initial position about what existing disciplines are most relevant; and link prospect theory to risk-based decision making as one example that could lead to a new paradigm for safety. By treating safety as a transdisciplinary challenge, there is an opportunity to enable the participants of the online world to become more productive and creative than ever before. The beneficiary of this increased productivity and creativity will ultimately be the public. The perspective of this article is of interest to senior decision makers, policy makers, managers, educators, strategists, futurists, scientists, technologists, and others interested in shaping the online world of the future.
Keywords: cybersecurity; prospect theory; risk-based decision making; safety; security; weak transdisciplinary

Strengthening Innovation Capacity through Different Types of Innovation Cultures - Jens-Uwe Meyer (Technology Innovation Management Review, 2014)
In times of increased market dynamics, companies must be capable of initiating and implementing innovation projects that vary greatly in type, speed, and degree of innovation. Many companies do not succeed. This article introduces Innolytics, an innovation management tool that allows companies to successfully face this challenge by analyzing their innovation culture and managing its development in the right direction. Analyzing empirical data from 200 staff members employed by German, Austrian, and Swiss companies using exploratory factor analysis, four types of innovation cultures were identified, each of which foster a different degree of organizational creativity. Proactive innovators (21%) promote organizational creativity at a high level and across all categories. Strategic innovators (26%) foster innovation by focusing on their strategy and their value system. Innovative optimizers (36%) promote more adaptive levels whereas operational innovators (16%) promote low levels of organizational creativity. Each type enables a company or a business unit to manage different degrees of innovation projects. The Innolytics tool introduced and described in this article will enable companies to better meet the challenges of rapidly changing markets.
Keywords: corporate creativity; innovation management; innovativeness; innovation culture; innovation capacities; organizational creativity

TIM Lecture Series – Adventures in Innovation: Inside the Rise and Fall of Nortel - John F. Tyson (Technology Innovation Management Review, 2014)
Keywords: Bell-Northern Research; BNR; company culture; industrial design; innovation; Nortel; Northern Telecom; user-centred design

TIM Lecture Series – Cybersecurity Metrics and Simulation - George Cybenko (Technology Innovation Management Review, 2014)
Keywords: cybersecurity; metrics; modelling; simulation

TIM Lecture Series – Insights on Innovation - Ibrahim Gedeon (Technology Innovation Management Review, 2014)
Keywords: customer focus; ecosystems; innovation; service provision; telecommunications

TIM Lecture Series – The Business of Cybersecurity - David Grau; Charles Kennedy (Technology Innovation Management Review, 2014)
Keywords: analytics; banking; cybersecurity; hacking; incident response; information security; intelligence; targets; threats

TIM Lecture Series – The Laboratory for Analytic Sciences: Developing the Art and Science of Analysis - J. David Harris (Technology Innovation Management Review, 2014)
Keywords: analysis; analytics; big data; collaboration; cybersecurity; framework; innovation; instrumentation; monitoring; prediction; strategy

TIM Lecture Series – Web Infections and Protections: Theory and Practice - Arnold Kwong (Technology Innovation Management Review, 2014)
Keywords: attack vectors; countermeasures; cybersecurity; infections; Internet; privacy; security; targets; threat vectors; threats

Turning Technology into Business Using University Patents - Dap Hartmann (Technology Innovation Management Review, 2014)
We present an education paradigm that stimulates innovation and entrepreneurship through a master's-level university course: "Turning Technology into Business". The course was specifically designed to connect technological research with education using patented technologies developed at the research faculties of a technical university in the Netherlands. We outline the structure and the main content of the course and explain the selection process of both the patents used in the course and the students admitted to the course. This program was initiated at Delft University of Technology in 2003 and has resulted in 10 startups that have commercialized new technologies and at least two additional dozen startups that are indirect spinoffs. To illustrate the potential of this approach, we describe the case of Holland Container Innovations, a company founded by students who developed a foldable sea container during the course.
Keywords: commercialization; entrepreneurship education; multi-disciplinary team work; patents; student entrepreneurs; technology entrepreneurship; university research

University Spinoffs: What, Why, and How? - Pinaki N. Pattnaik; Satyendra C. Pandey (Technology Innovation Management Review, 2014)
University spinoffs have remarkably strengthened the linkage between universities and industry. The number of technology patents and spinoffs coming out of university research has a significant impact on regional economic and social development. To further highlight the importance of university spinoffs, the aim of this article is to review available literature on university spinoffs and present a comprehensive overview of what university spinoffs are, why they are important, what makes them significant, and how they are or can be created. In addition to reviewing existing models of university spinoff creation, we also propose a new, multi-stage, holistic model.
Keywords: stage model; technology patents; university spinoff; university-industry linkage

Using Trademarks to Measure Innovation in Knowledge-Intensive Business Services - Matthias Gotsch; Christiane Hipp (Technology Innovation Management Review, 2014)
We present an empirical approach to measuring service innovation on the company level through the analysis of trademarks. Prior empirical investigations in several industries have shown that a trademark may be used as an innovation indicator. This article explores the use and relevance of trademarks by conducting a survey in the knowledge-intensive business services (KIBS) industries with 278 participating companies. Our survey results explain the use of trademarks as a way to protect innovation and intellectual property for KIBS. In sum, we show that trademarks can be described as adequate and useful indicators to measure new service innovations in the KIBS industries. Additionally, we show that trademarks have the potential to overcome weaknesses of traditional measurement concepts towards KIBS innovation and might make special surveys redundant in the future.
Keywords: innovation; innovation indicator; KIBS; knowledge-intensive business services; trademarks

Widening the Perspective on Industrial Innovation: A Service-Dominant-Logic Approach - Heidi M. E. Korhonen (Technology Innovation Management Review, 2014)
The servitization of industry has progressed from services as add-ons to services as solutions. Today, industrial innovation needs an even broader perspective that moves towards service-dominant logic. This logic emphasizes value co-creation in actor-to-actor networks and requires new organizational structures and practices in industry. The article presents the case of a Nordic manufacturer of arc welding equipment that has gone through an extensive development program to become more customer and service oriented. An innovative offering created during the program is analyzed as an example in order to gain deeper insight about the concrete application of service-dominant logic in business. In addition to the outcome perspective, the article discusses the implications of the service-dominant logic for innovation practices. The article illustrates the behaviour of cutting-edge servitizing manufacturers and argues that similar behaviour can be expected to become a necessity in all industrial companies with large structural changes.
Keywords: co-development; industrial service; practice; systemic innovation; value co-creation

Actor Roles in an Urban Living Lab: What Can We Learn from Suurpelto, Finland? - Soile Juujärvi; Kaija Pesso (Technology Innovation Management Review, 2013)
There is a growing trend to involve citizens in city development to make urban areas more suitable to their needs and prevent social problems. City centres and neighbourhoods have increasingly been serving as regional living labs, which are ideal platforms to explore the needs of users as residents and citizens. This article examines the characteristics and success factors of urban living labs based on a case study of Suurpelto, Finland. Urban living lab activity is characterized by a practice-based innovation process with diffuse and heterogeneous knowledge production that aims to address urban problems of varying complexity. User involvement is critical for co-creating value, but equally important is collaboration between other living lab actors: enablers, providers, and utilizers. Enabler-driven labs can be successful in creating common goals but they need providers, such as development organizations, to boost development. Proactive networking, experimentation as a bottom-up process, using student innovators as resources, as well as commitment and longevity in development work are success factors for urban living labs.
Keywords: innovation; knowledge production; networks; regional development; urban living labs

Addressing Canada's Commercialization Crisis and Shortage of Venture Capital: Will the Federal Government’s Solution Work? - Stephen A. Hurwitz (Technology Innovation Management Review, 2013)
Lack of funding is a major challenge to innovation in Canada’s emerging technology industry. This article will focus on this supply-side challenge within the complex venture capital ecosystem and discuss: i) the current shortage of venture capital available to commercialize Canada’s R&D; ii) the causes and consequences of that venture capital shortage; iii) how the federal government will address this shortage through its innovative 2013 Venture Capital Action Plan, which commits $400 million and seeks to raise at least another $800 million from outside investors; and iv) how a separate decision in the federal 2013 budget to phase out federal tax credits for labour-sponsored venture capital funds could imperil the 2013 Venture Capital Action Plan.
Keywords: 2013 Venture Capital Action Plan; Canada; commercialization; labour-sponsored venture capital corporations; VC; venture capital

Corporate Lifecycles: Modelling the Dynamics of Innovation and Its Support Infrastructure - Tamas Koplyay; Lisa Chillingworth; Brian Mitchell (Technology Innovation Management Review, 2013)
Corporate leadership and corporate culture have to be aligned to market realities to ensure the long-term success of a firm. As companies form, grow, and mature, the management of the enterprises also have to evolve through the business lifecycle. What is successful in the introduction stage may not be successful for a mature company. Firms are required to change their focus from product development, to market development, to process development, and finally to market and financial leadership. To be successful means that not only the types of employees hired have to evolve to support the culture required, but the leadership styles and management focus also have to change and adapt to the new realities that firms encounter in their market. The dynamic model presented in this article shows the broad strategic imperatives that must be met by firms, and it is presented through a graphical illustration of how successful firms manage their evolution and how firms can fail through mis-allocation of corporate efforts to non-mission critical initiatives.
Keywords: innovation; Innovation management; leadership; market lifecycle; model; organizational culture; staffing

Cybersecurity Futures: How Can We Regulate Emergent Risks? - Benoit Dupont (Technology Innovation Management Review, 2013)
This article reviews nine socio-technical trends that are likely to shape the cybersecurity environment over the next decade. These nine trends have reached various levels of maturity, and some – such as quantum computing – are still theoretically contentious. These trends are: cloud computing; big data; the Internet of Things; the mobile Internet; brain–computer interfaces; near field communication payment systems; mobile robots; quantum computing; and the militarization of the Internet. What these nine trends have in common is that they will be instrumental in generating new opportunities for offending, which will result from an exponential increase in the quantity of data, number of connection points to the Internet, and velocity of data flows that irrigate the digital ecosystem. As a result, more opportunities for malicious exploitation will be available to attackers, “security by design” will be harder to achieve in such a fluid and dynamic environment, and the performance of control mechanisms is likely to erode significantly. Technical solutions to address these challenges are already being developed by computer scientists. This article focuses on a different and complementary approach, finding inspiration in the work of regulatory scholars who have framed promising theories such as regulatory pluralism and responsive regulation to explore options for the necessary institutional adaptation to these future changes.
Keywords: cybersecurity; cybersecurity policies; digital ecosystem; emerging risks; forecasting; regulation; technological trends

A Firm-Level Innovation Management Framework and Assessment Tool for Increasing Competitiveness - Sorin Cohn (Technology Innovation Management Review, 2013)
Innovation depends on much more than just technology and R&D. It is a means to an end – competitive success and higher market value – and it needs to be managed strategically and methodically for tangible corporate performance where it matters: in the market. This article introduces a comprehensive corporate innovation management framework (v-CIM) and a targeted competitiveness assessment tool (i-TCA). Properly used by corporate leaders, this framework and its associated tool enable innovation managers to decide on priorities for competitive development, adopt appropriate innovation strategies to meet corporate goals, monitor progress, make adjustments, and help create and maintain a culture of innovation that is aligned with business goals.
Keywords: competitiveness assessment; firm-level innovation; innovation models; innovation performance; management; management effectiveness; tools

The Habitation Lab: Using a Design Approach to Foster Innovation for Sustainable Living - Paula Femenías; Pernilla Hagbert (Technology Innovation Management Review, 2013)
This article describes a first step towards a strategy for using living labs as a means to foster innovation and develop new concepts of sustainable living from an architectural point of view. The overall aim is to enable truly sustainable living through radically reduced energy and resource use thus addressing both environmental and social aspects of sustainability. Earlier research has shown that contemporary housing developments, including those with a sustainable profile, do not profoundly question modern lifestyles and consumption, which is a necessity to overcome limitations of a technological focus on environmental efficiency in construction. Thus, we see an opportunity for the discipline of architecture to engage in current investments in living lab facilities in order to push innovation in the field of sustainable housing. We introduce the concept of a "Habitation Lab", which will provide an arena for radical and high-risk design experimentation between users, building-sector actors, and academia, and we describe a case study of a planned Habitation Lab within a living lab facility where traditional solutions for daily living and habitation are questioned and new architectural innovations are explored and evaluated. The idea of using experimental activities in the field of housing is not new, and we argue that new investments should build on earlier experiences to avoid perpetuating misconceptions and repeating past failures. Furthermore, to ensure the dissemination and uptake of results, the design of the Habitation Lab should consider the innovation and learning trajectories of the building sector. We propose a transdisciplinary setting to provide a neutral arena for value creation and to increase the distribution of experiences.
Keywords: experimentation; Habitation Lab; housing development; innovation; living labs; residing; sustainable

A Heritage Economy: Business Model Innovation for Economic Wealth, Social Well-Being, and Environmental Health - Frédérick Brousseau-Gauthier; Yvon Brousseau (Technology Innovation Management Review, 2013)
Faced with the inherent unsustainability of infinite growth in a world of finite resources, the neoclassical economy is running towards a cliff. In order to avoid a hard landing, enterprises need to broaden their definitions of value and wealth to include parameters that are not currently in the economic lexicon, but are still of paramount importance in our lives. Taken from that angle, heritage can be seen as a perfect replacement for capital, because its multidimensional and complex nature opens up numerous possibilities for the creation of shared economic, social, and environmental value; the designing of value chains; and the direction of technological innovation. This article explores the various ramifications of a paradigm shift from managing capital to managing heritage, and it underlines the need to create a series of pioneering business models for enterprises to adapt and profit from a new, heritage economy.
Keywords: benefit corporation; business model innovation; heritage economy; impact investment; natural capitalism

How Can Entrepreneurs Motivate Crowdsourcing Participants? - Derek Smith; Mohammad Mehdi Gharaei Manesh; Asrar Alshaikh (Technology Innovation Management Review, 2013)
Crowdsourcing is a way to access a global crowd of talented people and to channel their talent and creative effort towards some useful endeavour. Technology entrepreneurs who may have limited resources, especially during the start-up phase of the business, will be attracted to crowdsourcing as a means to access funding, knowledge, subject matter experts, and resources on a global scale. In this article, we review the published research on crowdsourcing as it relates to motivation, and distil the insights from that research that will be useful to technology entrepreneurs. First, we organize the published research into three streams according to crowd type: i) task-based public crowd, ii) information-exchange public crowd, and iii) employee-based crowd. Next, we identify the motivational drivers common to all streams as well as the motivational drivers that are unique to each stream. Finally, we offer five recommendations for technology entrepreneurs seeking to apply crowdsourcing.
Keywords: crowdsourcing; entrepreneur; startup; technology entrepreneurship

How Do We Keep the Living Laboratory Alive? Learning and Conflicts in Living Lab Collaboration - Louna Hakkarainen; Sampsa Hyysalo (Technology Innovation Management Review, 2013)
Living lab environments are often promoted as a way to engage private companies, citizens, researchers, and public organizations in mutually beneficial learning. Based on an in-depth case study of a four-year living lab collaboration in gerontechnology, we agree that successful living lab development hinges on learning between the parties, yet its emergence cannot be presumed or taken for granted. Diverse competences and interests of participating actors often make technology development projects complicated and volatile. The study describes two specific challenges faced in a living lab project: i) power issues between the actors and ii) end-user reluctance to participate in the development of new technology. Despite the hardships, we suggest that the living lab environment worked as a catalyst for learning between users and developers. Nevertheless, realizing the benefits of this learning may be more challenging than is usually expected. Learning for interaction is needed before effective learning in interaction is possible.
Keywords: collaboration; conflicts; gerontechnology; health care; learning; living labs

How Service Innovation Boosts Bottom Lines - Claude Legrand; Rob LaJoie (Technology Innovation Management Review, 2013)
In the national quest for ground-breaking R&D discoveries and inventions, service innovation is frequently ignored at considerable cost to an organization’s bottom line and a nation’s productivity. For the fact is that innovation applied systematically to all activities outside of R&D can make the difference between uninspiring results and substantial growth in every sector. Many countries, in particular in Europe, have recognized the importance of service innovation and are devoting considerable resources to research, the capture of best practices, and the measurement of progress and success. Given the physiognomy of the modern economy, it does not make sense for leaders in the Canadian public sector to devote all available innovation investment dollars to science and technology R&D. This article explores why service innovation is not yet a priority on the innovation agenda in Canada and why we should correct the dangerous misconception that there is just one “innovation gap” that needs to be addressed. It provides practical recommendations that public and private sector leaders can use to take advantage of this under-valued, high-potential innovation opportunity and calls for the creation of a national service innovation resource to support enterprises of all sizes as a means to improve Canadian productivity.
Keywords: complex problems; innovation; innovation gap; innovative intelligence; service innovation

Introducing “Business Source”: The Future of Corporate Open Source Licensing? - Michael (Monty) Widenius; Linus Nyman (Technology Innovation Management Review, 2013)
The benefits of the open source development model have been proven by the test of time; however, making this development model economically feasible can be challenging. In this article, Monty Widenius puts forth a suggestion for a new type of license, which is the result of the lessons learned from decades of work on open source, both as programmer and entrepreneur. The result, “business source”, is a license that seeks to enable a business model that can both harness the benefits of open source while generating sufficient income for the program’s continued development. The business source license automatically changes terms after a given period: an initial non-open source license with specific usage restrictions that transforms to a fully open source license on a specific future date. In this article, we contribute a proposal for a novel license, a set of recommendations for managers, and a sample text of a business source license. This work will be of relevance to four main groups: i) those developing or managing a closed source program but who are interested in the benefits open source offers; ii) those managing open core programs; iii) projects in development; and iv) investors interested in funding open source projects.
Keywords: business source; open core; open source business models; open source software development; software licensing

Leveraging Old Intellectual Property to Accelerate Technology Entrepreneurship - Derek Smith (Technology Innovation Management Review, 2013)
Acquiring or licensing assets to older technologies, including surviving intellectual property rights, is an often-overlooked viable strategy for accelerating technology entrepreneurship. This strategy can help entrepreneurs short-cut the growth of a customer base, reduce development effort, and shorten the time to market with a minimum viable product. However, this strategy is not without risk; entrepreneurs need to be careful that the acquired intellectual property rights are not fraught with issues that could severely outweigh any perceived value. Proper investigation is required to ensure success because the current literature fails to provide tools that an entrepreneur can apply when considering the acquisition of intellectual property. This article includes a case study of a technology company – Piranha Games – that indirectly acquired sole and exclusive access to a substantial historical customer base by acquiring and licensing older technology and surviving intellectual property assets. The founders then leveraged the existing product brand and its historical customers to acquire significant funding and went global with a minimum viable product in three years. The copyright and trademark assets provided value on day one to Piranha Games by making it difficult and risky for others to exploit the technology. Based on this case study, this article offers recommendations to entrepreneurs who may benefit from acquiring old intellectual property to accelerate the growth of their startups.
Keywords: accelerated startup; business models; copyright; crowdfunding; due diligence; entrepreneurs; funding; intellectual property; old technology; product development clearance; trademark

Linking Living Lab Characteristics and Their Outcomes: Towards a Conceptual Framework - Carina Veeckman; Dimitri Schuurman; Seppo Leminen; Mika Westerlund (Technology Innovation Management Review, 2013)
Despite almost a decade of living lab activity all over Europe, there still is a lack of empirical research into the practical implementation and the related outcomes of living labs. Therefore, this article proposes a framework to create a better understanding of the characteristics and outcomes of living labs. We investigate three living labs in Belgium and one in Finland to learn how the different building blocks of living lab environments contribute to the outputs of innovation projects launched within the lab. The findings imply that managers and researchers contemplating innovation in living labs need to consider the intended inputs and outcomes, and reframe their innovation activities accordingly. We formulate practical guidelines on how living labs should be managed on the levels of community interaction, stakeholder engagement, and methodological setup to succeed in implementing living lab projects and to create user-centred innovations. That way, living lab practitioners can work towards a more sustainable way of setting up living labs that can run innovation projects over a longer period of time.
Keywords: co-creation; innovation ecosystem; Living lab; Open innovation; user involvement

A Living Lab as a Service: Creating Value for Micro-enterprises through Collaboration and Innovation - Anna Ståhlbröst (Technology Innovation Management Review, 2013)
The need to innovate is increasingly important for all types and sizes of organizations, but the opportunities for innovation differ substantially between them. For micro-, small,- and medium-sized enterprises, innovation activities are both crucial and demanding because of limited resources, competencies, or vision to innovate their offerings. To support these organizations, the concept of living labs as a service has started to emerge. This concept refers to living labs offering services such as designing the idea-generation processes, planning or carrying out real-world tests of innovations, and pre-market launch assessments. In this article, we will present the findings from a study of micro-enterprises operating in the information technology development sector, including the experienced value of services provided to the companies by a research-based living lab. We share experiences from Botnia, our own living lab in northern Sweden. In this living lab, our aim of creating value for customers is of key importance. Our study shows that using a living lab as a service can generate three different types of value: improved innovations, the role the living lab can play, and the support the living lab offers.
Keywords: experience-based values; innovation intermediary; Living lab; micro-enterprise; value

Managing Cybersecurity Research and Experimental Development: The REVO Approach - Dan Craigen; Drew Vandeth; D’Arcy Walsh (Technology Innovation Management Review, 2013)
We present a systematic approach for managing a research and experimental development cybersecurity program that must be responsive to continuously evolving cybersecurity, and other, operational concerns. The approach will be of interest to research-program managers, academe, corporate leads, government leads, chief information officers, chief technology officers, and social and technology policy analysts. The approach is compatible with international standards and procedures published by the Organisation for Economic Co-operation and Development (OECD) and the Treasury Board of Canada Secretariat (TBS). The key benefits of the approach are the following: i) the breadth of the overall (cybersecurity) space is described; ii) depth statements about specific (cybersecurity) challenges are articulated and mapped to the breadth of the problem; iii) specific (cybersecurity) initiatives that have been resourced through funding or personnel are tracked and linked to specific challenges; and iv) progress is assessed through key performance indicators. Although we present examples from cybersecurity, the method may be transferred to other domains. We have found the approach to be rigorous yet adaptive to change; it challenges an organization to be explicit about the nature of its research and experimental development in a manner that fosters alignment with evolving business priorities, knowledge transfer, and partner engagement.
Keywords: cybersecurity; experimental development; performance indicators; research; research program lifecycle; research-activity descriptions; research-requirement statements; strategic research contexts

Measuring Innovation Skills Acquired by College and Polytechnic Students through Applied Research - Robert Luke (Technology Innovation Management Review, 2013)
This article provides an overview of how colleges and polytechnic institutes are fostering innovation literacy via support for business innovation, and it outlines models for measuring innovation literacy for improved downstream innovation and productivity in industry. The article demonstrates how we can innovate innovation by taking a specific, proactive, and instrumental approach to fostering business innovation and skills acquisition gained through applied research work experience by students as part of their college education. This approach is being used by George Brown College in developing a framework for measuring this innovation potential with a long-term, outcomes-based analysis.
Keywords: applied research; business innovation; college; experiential learning; innovation literacy; logic model; polytechnic; skills; student research

Multifactor Authentication: Its Time Has Come - Jim Reno (Technology Innovation Management Review, 2013)
Transactions of any value must be authenticated to help prevent online crime. Even seemingly innocent interactions, such as social media postings, can have serious consequences if used fraudulently. A key problem in modern online interactions is establishing the identity of the user without alienating the user. Historically, almost all online authentications have been implemented using simple passwords, but increasingly these methods are under attack. Multifactor authentication requires the presentation of two or more of the three authentication factor types: “What you know”, “What you have”, and “What you are”. After presentation, each factor must be validated by the other party for authentication to occur. Multifactor authentication is a potential solution to the authentication problem, and it is beginning to be implemented at websites operated by well-known companies. This article surveys the different mechanisms used to implement multifactor authentication. How a site chooses to implement multifactor authentication affects security as well as the overall user experience.
Keywords: authentication attacks; authentication mechanisms; multifactor authentication; online security

Navigating Risk When Entering and Participating in a Business Ecosystem - Derek Smith (Technology Innovation Management Review, 2013)
Entrepreneurs typically have limited resources during the start-up phase of a business. Business ecosystems are a strategy for entrepreneurs to access and exchange many different aspects of value, resources, and benefits. However, there may be business risks for entering a particular type of ecosystem, and further risks may be encountered after entering and participating in a business ecosystem. These risks are significant and can inhibit a startup's growth. In this article, the literature on business ecosystems is reviewed as it relates to risk to discover insights of relevance to entrepreneurs, top management teams, and business-ecosystem operators. First, the published research is organized into two streams: i) risks relating to categories of business ecosystems, and ii) risks relating to participating in business ecosystems. Then, the problem is abstracted to develop a potential strategy for managing these risks, which features a pre-entry inspection followed by real-time resource management. Finally, five recommendations are offered for entrepreneurs seeking to enter and participate in business ecosystems.
Keywords: business ecosystem; due diligence; entrepreneurs; literature review; mitigation; risk; risk identification; startups; threat management

Open Innovation at the Root of Entrepreneurial Strategy: A Case from the Norwegian Oil Industry - Tatiana Iakovleva (Technology Innovation Management Review, 2013)
This article aims to extend the discussion about entrepreneurial strategies of small and medium-sized enterprises (SMEs) by including the concept of open innovation. How can SMEs overcome the challenges of resource scarcity and harsh competition? How they can gain competitive advantage in today’s ever-changing business environment? The answer to both of these questions might be through open innovation: collaborating with researchers, customers, suppliers – even competitors – as well as research institutions and universities. A common barrier to open innovation in an SME is the perception that it will be too time consuming to gain access to a knowledge base of external knowledge providers and link to “gatekeepers” of knowledge. However, an entrepreneurial mindset might help SMEs to move toward an open-innovation approach, where more codified and transferrable knowledge are important. This article discusses the implications of an entrepreneurial focus for open-innovation activities. The usefulness of the open-innovation principles are highlighted through a case study of an Norwegian SME operating in the maritime-oil industry.
Keywords: entrepreneurial orientation; entrepreneurial strategies; Open innovation; SMEs

Open Innovation Processes in Living Lab Innovation Systems: Insights from the LeYLab - Dimitri Schuurman; Lieven De Marez; Pieter Ballon (Technology Innovation Management Review, 2013)
Living labs have emerged on the crossroads of the open innovation and user innovation frameworks. As open innovation systems, living labs consist of various actors with each playing their specific role. Within this article, we will take an open innovation perspective by analyzing the knowledge spill-overs between living lab actors through three in-depth innovation case studies taking place within the LeYLab living lab in Kortrijk, Belgium. The results illustrate how living labs foster the three open innovation processes of exploration, exploitation, and retention. From our analysis, we conclude that living labs are particularly useful for exploration and, to a lesser extent, exploitation. In terms of retention, living labs seem to hold a large potential; however, the success and the nature of the innovation processes depend on the sustainability of living labs, the number of innovation cases, and the alignment of these cases with the living lab infrastructure. Based on these findings, a concrete set of guidelines is proposed for innovating in living labs and for setting up a living lab constellation.
Keywords: knowledge exchange; living labs; Open innovation; open innovation networks; user innovation

Partner Selection for Open Innovation - Marina Z. Solesvik; Magnus Gulbrandsen (Technology Innovation Management Review, 2013)
In this article, we consider open innovation from the perspectives of: i) causation and effectuation, and ii) social networking. Our empirical evidence consists of a case study of a late-stage open-innovation project aimed at creating a hybrid ship that uses liquid natural gas and hydrogen as power sources. The results show that the effectuation approach is preferable to open innovation when the initiator of open innovation aims to keep sensitive information inside the closed group, when the initiator has established an effective team of representatives from other firms from earlier innovation projects, and when the participants are geographically close.
Keywords: causation; effectuation; Norway; Open innovation; partner selection

Peer-to-Peer Enclaves for Improving Network Defence - David W. Archer; Adam Wick (Technology Innovation Management Review, 2013)
Information about cyberthreats within networks spreads slowly relative to the speed at which those threats spread. Typical "threat feeds" that are commercially available also disseminate information slowly relative to the propagation speed of attacks, and they often convey irrelevant information about imminent threats. As a result, hosts sharing a network may miss opportunities to improve their defence postures against imminent attack because needed information arrives too late or is lost in irrelevant noise. We envision timely, relevant peer-to-peer sharing of threat information – based on current technologies – as a solution to these problems and as a useful design pattern for defensive cyberwarfare. In our setting, network nodes form communities that we call enclaves, where each node defends itself while sharing information on imminent threats with peers that have similar threat exposure. In this article, we present our vision for this solution. We sketch the architecture of a typical node in such a network and how it might interact with a framework for sharing threat information; we explain why certain defensive countermeasures may work better in our setting; we discuss current tools that could be used as components in our vision; and we describe opportunities for future research and development.
Keywords: cyber countermeasures; cybersecurity; dynamic cyberdefence; enclave computing; network defence; peer-to-peer

Problemsourcing: Local Open Innovation for R&D Organizations - Sally Davenport; Stephen Cummings; Urs Daellenbach; Charles Campbell (Technology Innovation Management Review, 2013)
Open innovation and crowdsourcing are usually focused on using others external to the organization to solve your problems. How then do R&D organizations, who traditionally solve the problems of others, harness the benefits of open innovation and crowdsourcing yet maintain their mission and capabilities? "Problemsourcing" may provide the answer. In this mode of open innovation, the open call to the "crowd" of businesses is for them to suggest problems that, if solved by the R&D organization, could greatly enhance the business’ competitive advantage and therefore the nation’s economy. In this article, we describe a problemsourcing initiative developed by Industrial Research Ltd (IRL), a government-owned R&D organization in New Zealand. The "What’s Your Problem New Zealand?" competition promised NZ$1m worth of R&D services to the winning business. Using this case study, we map a range of benefits of crowdsourcing for R&D problems, including generating a potential pipeline of projects and clients as well as avoiding the challenge to the professional status of the organization’s research capability. A side-effect not initially taken account of was that, by demonstrating openness, accessibility, and helpfulness, the reputation of the research organization was greatly enhanced. The problemsourcing model provided by the "What’s Your Problem New Zealand?" competition represents a new strategic possibility for R&D organizations that complements their traditional business model by drawing on the openness that open innovation and crowdsourcing seek to leverage. As such, it can provide insights for other research organizations wishing to make use of the connectivity afforded by open innovation and crowdsourcing.
Keywords: crowdsourcing; local open innovation; Open innovation; problemsourcing; R&D

Q&A. Do Technology Startups Need Product Managers? - Alan Mcnaughtan (Technology Innovation Management Review, 2013)
Keywords: Mint; product management; product manager; startups; Wesabe

Q&A. How Do You Program Innovative Thinking into Company Culture? - Tim Ragan (Technology Innovation Management Review, 2013)
Keywords: business strategy; company culture; entrepreneurship; innovation

Q&A. Is Open Source Sustainable? - Matt Asay (Technology Innovation Management Review, 2013)
Keywords: Apache; GPL; licenses; open source; sustainability

Q&A. Should Startups Care about Application Security? - Sherif Koussa (Technology Innovation Management Review, 2013)
Keywords: application security; architecture; checklists; code reviews; cybersecurity; design; detection; prevention; software security; startups; training

Q&A. What Are the Components of Canada's Innovation Ecosystem and How Well Is it Performing? - David B. Watters (Technology Innovation Management Review, 2013)
Keywords: academia; commercialization; innovation; innovation ecosystem; performance; policy; private sector; public sector

Rapid Prototyping Using a Configurable Platform - Antonio Misaka (Technology Innovation Management Review, 2013)
This article describes an approach for speeding up the development of web applications using a configurable platform. The core idea of the approach is that developers can implement customer requirements by configuring platform components, instead of writing large amounts of “glue code” to wire the components together. This approach reduces the amount of glue code that still needs to be written and maintained, it shortens the time it takes developers to create a prototype, and it makes it easier for glue code to be reused in the future. It also allows developers to experiment with different configurations of platform components in order to find the configuration that best meets the customer's requirements. Developers are also able to manage a larger variation in customer requirements.
Keywords: configurable platform; rapid prototyping; requirements analysis; software product-line engineering; web applications

Reinventing the Wheel: Contextualizing Existing Innovations as a Path to Market Success - Jeff Moretz; Karthik Sankaranarayanan; Jennifer Percival (Technology Innovation Management Review, 2013)
In the quest to create cutting-edge products, organizations often invest substantial time, attention, and capital in primary research and development (R&D). By themselves, these R&D investments to create avant-garde products may not provide good return-on-investment. In the context of Canadian businesses, there is a significant scarcity of resources available for R&D. What can Canadian firms do to stay innovative when they face a plethora of difficulties, including insufficient funding? This article explores how organizations can leverage external innovation and existing technologies to create products or services that cater to the market needs. We present a three-pillar model along with examples of companies that attained market success in large part by contextualizing existing technologies in order to create innovative products or services. This approach provides companies with a high-level framework to facilitate resource-parsimonious creation of commercializable, innovative products that are competitive in today’s global marketplace.
Keywords: commercialization; contextualization of innovation; Innovation management; market-focused innovation; organization

Risk Management in Crowdsourcing-Based Business Ecosystems - Suchita Nirosh Kannangara; Peter Uguccioni (Technology Innovation Management Review, 2013)
The benefits of crowdsourcing are enabled by open environments where multiple external stakeholders contribute to a firm's outcomes. However, crowdsourcing typically has been examined as a general process and not from the specific perspective of a mechanism for driving value creation and capture within a business ecosystem. In this conceptual article, we highlight this research gap by examining crowdsourcing from a business ecosystem perspective and by identifying the inherent business risks in crowdsourcing-based business ecosystems. We apply the concept of ecosystem health to the crowdsourcing context, in terms of how firms create and capture value, and we examine the methods by which these firms can maximize health by mitigating risk in crowdsourcing-based business ecosystems.
Keywords: business ecosystem health; business ecosystems; crowdsourcing; risk management

Securing Canada’s Information-Technology Infrastructure: Context, Principles, and Focus Areas of Cybersecurity Research - Dan Craigen; D’Arcy Walsh; David Whyte (Technology Innovation Management Review, 2013)
This article addresses the challenges of cybersecurity and ultimately the provision of a stable and resilient information-technology infrastructure for Canada and, more broadly, the world. We describe the context of current cybersecurity challenges by synthesizing key source material whose importance was informed by our own real-world experiences. Furthermore, we present a checklist of guiding principles to a unified response, complete with a set of action-oriented research topics that are linked to known operational limitations. The focus areas are used to drive the formulation of a unified and relevant research and experimental development program, thereby moving us towards a stable and resilient cyberinfrastructure. When cybersecurity is viewed as an inherently interdisciplinary problem of societal concern, we expect that fundamentally new research perspectives will emerge in direct response to domain-specific protection requirements for information-technology infrastructure. Purely technical responses to cybersecurity challenges will be inadequate because human factors are an inherent aspect of the problem. This article will interest managers and entrepreneurs. Senior management teams can assess new technical developments and product releases to fortify their current security solutions, while entrepreneurs can harness new opportunities to commercialize novel technology to solve a high-impact cybersecurity problem..
Keywords: Canada; cyberdefence; cyberinfrastructure; cybersecurity; entrepreneurship; experimental development program; information-technology infrastructure; management; research

Security Challenges in Smart-Grid Metering and Control Systems - Xinxin Fan; Guang Gong (Technology Innovation Management Review, 2013)
The smart grid is a next-generation power system that is increasingly attracting the attention of government, industry, and academia. It is an upgraded electricity network that depends on two-way digital communications between supplier and consumer that in turn give support to intelligent metering and monitoring systems. Considering that energy utilities play an increasingly important role in our daily life, smart-grid technology introduces new security challenges that must be addressed. Deploying a smart grid without adequate security might result in serious consequences such as grid instability, utility fraud, and loss of user information and energy-consumption data. Due to the heterogeneous communication architecture of smart grids, it is quite a challenge to design sophisticated and robust security mechanisms that can be easily deployed to protect communications among different layers of the smart grid-infrastructure. In this article, we focus on the communication-security aspect of a smart-grid metering and control system from the perspective of cryptographic techniques, and we discuss different mechanisms to enhance cybersecurity of the emerging smart grid. We aim to provide a comprehensive vulnerability analysis as well as novel insights on the cybersecurity of a smart grid.
Keywords: authentication; cybersecurity; encryption; privacy; smart grid

Strategic Innovation for Business Performance: The Art and Science of Transformation - Harold Schroeder (Technology Innovation Management Review, 2013)
Despite the well-documented association between innovation and business performance, many organizations struggle in their attempts to become successful innovators. This article discusses a recommended “art and science of transformation” approach to help companies improve their innovation performance through effective organizational change. The approach is focused on four key factors: culture, collaboration, strategy, and systems. Examples are drawn from a review of previous research to demonstrate successful innovation practice using similar approaches, and examples of less successful practice are included to highlight ways in which an "art and science" approach can help overcome the difficulties often faced. The article concludes with some practical, step-by-step guidance based on the art and science of transformation framework.
Keywords: art and science of transformation; innovation; organizational change; strategy; transformation

Sustainability and Governance in Developing Open Source Projects as Processes of In-Becoming - Daniel Curto-Millet (Technology Innovation Management Review, 2013)
Sustainability is often thought of as a binary state: an open source project is either sustainable or not. In reality, sustainability is much more complex. What makes this project more sustainable than that one? Why should it be assumed in the first place that sustainability is a prolonged state of an ingraced project? The threads are pulled from their yarns in many directions. This article attempts to reconceptualize some assumed notions of the processes involved in developing open source software. It takes the stance in favour of studying the fluctuant nature of open source and the associated artefacts, not as well-defined objects, but as commons that are continually built upon, evolved, and modified; sometimes in unexpected ways. Further, the governance of these commons is an ongoing process, tightly linked with the way in which these commons are allowed to further develop. This perspective of "in-becoming" is useful in understanding the efforts and processes that need to be provided to sustainably govern the development of open source projects and the advantages for managing requirements derived therein.
Keywords: becoming; emergence; governance; open source; Ostrom; processes; requirements; sustainability

Sustainability of Open Collaborative Communities: Analyzing Recruitment Efficiency - Kevin Crowston; Nicolas Jullien; Felipe Ortega (Technology Innovation Management Review, 2013)
Extensive research has been conducted over the past years to improve our understanding of sustainability conditions for large-scale collaborative projects, especially from an economic and governance perspective. However, the influence of recruitment and retention of participants in these projects has received comparatively less attention from researchers. Nevertheless, these concerns are significant for practitioners, especially regarding the apparently decreasing ability of the main open online projects to attract and retain new contributors. A possible explanation for this decrease is that those projects have simply reached a mature state of development. Marwell and Oliver (1993) and Oliver, Marwell, and Teixeira (1985) note that, at the initial stage in collective projects, participants are few and efforts are costly; in the diffusion phase, the number of participants grows, as their efforts are rewarding; and in the mature phase, some inefficiency may appear as the number of contributors is greater than required for the work. In this article, we examine this possibility. We use original data from 36 Wikipedias in different languages to compare their efficiency in recruiting participants. We chose Wikipedia because the different language projects are at different states of development, but are quite comparable on the other aspects, providing a test of the impact of development on efficiency. Results confirm that most of the largest Wikipedias seem to be characterized by a reduced return to scale. As a result, we can draw interesting conclusions that can be useful for practitioners, facilitators, and managers of collaborative projects in order to identify key factors potentially influencing the adequate development of their communities over the medium-to-long term.
Keywords: DEA modeling; efficiency; recruitment; Wikipedia

TIM Lecture Series – Energy Efficiency and Data Security in Modern Data Centres - Jerry Glowka (Technology Innovation Management Review, 2013)
Keywords: data centre; design; energy conservation; green innovation; power saving; security; storage

TIM Lecture Series – Enhancing Competitive Position Through Innovation Beyond R&D - Sorin Cohn (Technology Innovation Management Review, 2013)
Keywords: Canada; commercialization; competition; culture; entrepreneurship; globalization; innovation; managing innovation; metrics

TIM Lecture Series – Using Risk to Drive a Security Service - Paul Card (Technology Innovation Management Review, 2013)
Keywords: cybersecurity; platforms; risk management; security; services; strategy; uncertainty

Time to Innovate: Reflections and Recommendations on Time Management for Innovation Managers - Robert J. Crawhall (Technology Innovation Management Review, 2013)
Effective time management is a critical success factor for most projects; however, it is particularly challenging for projects involving substantial innovation. For most projects, time (i.e., the schedule) becomes a management "red flag" that signals when something goes wrong or gets out of control. The challenge for projects involving significant innovation is that one or more critical activities may be of an unknown duration or involve factors outside the normal design process and require "red flagging" from the outset. Managers of innovation projects have to distinguish between those activities or work packets that are a part of “business as usual” and those that involve innovation. They must identify and quantify the schedule risks and develop strategies to mitigate them. For example, one strategy to manage time-related risk is to decouple the innovation value as perceived by the customer (innovation output) from the technology innovation that is needed to deliver the product value in a cost-effective manner (innovation input). This strategy should take into account the likely consequences of longer-than-anticipated innovation time. Two common risks associated with poor time management for innovation are running out of financial runway to reach sustainable revenue and missing a critical market window. In this article, the author reflects on almost 30 years of experience in the Canadian innovation system across several industry sectors and provides some practical recommendations on time management for innovation managers.
Keywords: commercialization; innovation; product development; technology; time management

Using Boundary Management for More Effective Product Development - John Thomson; Vince Thomson (Technology Innovation Management Review, 2013)
Twenty years ago, most companies developed their own products in a single location and brought them to market themselves. Today, original equipment manufacturers (OEMs) are enlisting partners on a global scale as subsystem designers and producers in order to create and deliver new products into the market more rapidly and more frequently. This is especially true for large, complex products from the aerospace, telecommunications, electronics, and software industries. To assure the delivery of information across organizational boundaries, new coordination mechanisms need to be adopted (boundary management). In this article, best practices are described on how OEMs and partners self-organize and use agile, cooperative techniques to maintain daily communication among numerous internal and partner engineers to better coordinate product design and system integration. This article focuses on examples from the aerospace industry; however; these tactics can be applied in any organization to innovate at faster rates, to make delivery times more predictable, and to realize shorter product development timelines.
Keywords: boundary management; collaborative product development; outsourcing; partnering; product development; review-approve process

Living Labs for Cross-Border Systemic Innovation - Hans Schaffers; Petra Turkama (Technology Innovation Management Review, 2012)
Innovation is increasingly taking place in cross-border collaborative networks, which are shaped by the characteristics of systemic innovation, the strategies and objectives of main actors, and the dynamics of the innovation process. Participation in such networks is of high importance for small firms, but requires long-term investments and a diverse range of collaboration and innovation capabilities. This article explores how living labs, understood as innovation projects based on open and user-centric innovation methodologies, can form collaboration networks to support small firms and other actors to engage in cross-border collaboration and to accelerate the development and acceptance of innovations. Based on the lessons learned from a major living lab project, APOLLON, we conclude that adopting the living labs networking approach requires thorough understanding of each party’s objectives and drivers, the alignment of operational processes, establishment of open and collaborative culture, as well as competences, methods, and tools for supporting cooperation and community building.
Keywords: collaboration; innovation; living labs; networks; systemic

Organizational Ambidexterity: How Small Technology Firms Balance Innovation and Support - John Schreuders; Alem Legesse (Technology Innovation Management Review, 2012)
Many technology entrepreneurs start their companies by focusing on an innovation that creates a market offer to attract their first customers. When the entrepreneur’s firm makes its first sale, the dynamics of the organization change and the entrepreneur faces a new challenge: how can the firm concurrently develop new products and support existing customers? This problem is of great concern to entrepreneurs who own small technology firms and is the subject of this article. In this article, we first address the innovate-versus-support dilemma that small technology firms face early in their lifecycles. Next, we describe the paradigm of the ambidextrous organization. We conclude with a discussion of five mechanisms small firms can use to achieve balance in their quest to concurrently satisfy the need to innovate while fulfilling the demands of existing clients and products.
Keywords: ambidextrous organization; entrepreneurship; innovation; support

Platformation: Cloud Computing Tools at the Service of Social Change - Anil Patel (Technology Innovation Management Review, 2012)
The following article establishes some context and definitions for what is termed the “sharing imperative” – a movement or tendency towards sharing information online and in real time that has rapidly transformed several industries. As internet-enabled devices proliferate to all corners of the globe, ways of working and accessing information have changed. Users now expect to be able to access the products, services, and information that they want from anywhere, at any time, on any device. This article addresses how the nonprofit sector might respond to those demands by embracing the sharing imperative. It suggests that how well an organization shares has become one of the most pressing governance questions a nonprofit organization must tackle. Finally, the article introduces Platformation, a project whereby tools that enable better inter and intra-organizational sharing are tested for scalability, affordability, interoperability, and security, all with a non-profit lens.
Keywords: charity; cloud computing; nonprofit; Platformation; sharing imperative; social innovation

Real-Time Mobile Communication of Power Requirements for Electric Vehicles - Derek Smith (Technology Innovation Management Review, 2012)
The periodic power requirements of an electric vehicle are difficult to predict because the vehicle's location, the amount of charge remaining in its batteries, and the timing of its next charge are not known. For clusters of electric vehicles, the problem is magnified, and there is a risk that the demand will strain and overload a power utility’s infrastructure. Operational managers are left with reactive management of the infrastructure that may defer or prevent a vehicle charge to balance power demands and safeguard the infrastructure. In this article, the following key concepts are analyzed to provide background on the problem and to outline the requirements of any solution: i) demand uncertainty and reactive management approaches, ii) electric vehicle power requirements, and iii) demand-management telecommunication capabilities. Then, by abstraction, induction, and creative synthesis, a novel solution to the problem is proposed to provide real-time mobile communication of power requirements. The proposed solution has potential to create new service and business opportunities to managers and entrepreneurs.
Keywords: disruptive innovation; electric utilities; electric vehicles; high-power devices; mobile communication; power grids; power requirements; telecommunications

TIM Lecture Series - 29 Lessons Learned in Entrepreneurship - Wes Biggs (Technology Innovation Management Review, 2012)
Keywords: entrepreneurship; lessons learned; startups; strategy; technology

TIM Lecture Series - Born Global: A Pharmaceutical Startup Perspective - Louis R. Lamontagne (Technology Innovation Management Review, 2012)
Keywords: born global; entrepreneurship; globalization; internationalization; pharmaceutical

TIM Lecture Series - Growing a Global Company Anchored on Open Source Software - Fred Dixon (Technology Innovation Management Review, 2012)
Keywords: BigBlueButton; entrepreneurship; global company; licenses; open source; startup; web conferencing

TIM Lecture Series – Intellectual Property Paradigms for Global Business - Gordon Freedman (Technology Innovation Management Review, 2012)
Keywords: global business; intellectual property; IP; patents; strategy; trademarks

TIM Lecture Series: Leadership Position in Technology Entrepreneurship and Commercialization - TIM Program (Technology Innovation Management Review, 2012)
Keywords: commercialization; global entrepreneurship; leadership; technology entrepreneurship

TIM Lecture Series: Next-Generation Technology Challenges and Business Opportunities - Dave Thomas (Technology Innovation Management Review, 2012)
Keywords: business opportunities; future of technology; next-generation technology

TIM Lecture Series - TELUS in Health: Improving Health Outcomes for All Canadians - Giovanni Pizzoferrato (Technology Innovation Management Review, 2012)
Keywords: healthcare; mobile applications; pharmacy; remote patient monitoring; TELUS

TIM Lecture Series: The Importance of Dealing with Risk for New Businesses - Tony Lackey (Technology Innovation Management Review, 2012)
Keywords: insurance; risk management; startups; technology entrepreneurship

Acquisition Integration Models: How Large Companies Successfully Integrate Startups - Peter Carbone (Technology Innovation Management Review, 2011)
Mergers and acquisitions (M&A) have been popular means for many companies to address the increasing pace and level of competition that they face. Large companies have pursued acquisitions to more quickly access technology, markets, and customers, and this approach has always been a viable exit strategy for startups. However, not all deals deliver the anticipated benefits, in large part due to poor integration of the acquired assets into the acquiring company. Integration can greatly impact the success of the acquisition and, indeed, the combined company’s overall market success. In this article, I explore the implementation of several integration models that have been put into place by a large company and extract principles that may assist negotiating parties with maximizing success. This perspective may also be of interest to smaller companies as they explore exit options while trying to ensure continued market success after acquisition. I assert that business success with acquisitions is dependent on an appropriate integration model, but that asset integration is not formulaic. Any integration effort must consider the specific market context and personnel involved.
Keywords: Acquisitions; Company Integration; Competitive M&A; Mergers

Anystone Technologies: Lessons from the First Year of a Mobile Applications Startup - Tony Wacheski (Open Source Business Resource, 2011)
The astounding growth of the mobile sector has attracted the attention of many entrepreneurs, particularly when combined with its low market-entry cost for developers and growing list of enviable success stories. For anyone with a mobile application to sell, Apple's App Store and the Android Market provide easy access to the world market. However, this market accessibility and endless opportunities increase competition and challenge the entrepreneur to stay focused. This article presents some initial observations and experiences from the first year of Anystone Technologies, a mobile applications startup, as it faced the challenges of starting a new business in this attractive but highly competitive sector.

Benefits of the Community for Partners of Open Source Vendors - Sandro Groganz (Open Source Business Resource, 2011)
Open source vendors can benefit from business ecosystems that form around their products. Partners of such vendors can utilize this ecosystem for their own business benefit by understanding the structure of the ecosystem, the key actors and their relationships, and the main levers of profitability. This article provides information on all of these aspects and identifies common business scenarios for partners of open source vendors. Armed with this information, partners can select a strategy that allows them to participate in the ecosystem while also maximizing their gains and driving adoption of their product or solution in the marketplace.

Best Practices in Multi-Vendor Open Source Communities - Ian Skerrett (Open Source Business Resource, 2011)
Multi-vendor open source communities enable companies to lower development costs and gain access to wider addressable markets. This article describes best practices for companies considering this approach. First, the different types of open source business strategies are examined along the types of participants that contribute to the communities that support them. Next, five best practices are detailed to show how companies can maximize their engagement with open source communities. Finally, the importance of foundations in implementing multi-vendor open source communities is discussed.

Beyond Technology: Enabling Communities Through Social Interoperability - Tyler Mitchell (Open Source Business Resource, 2011)
Technical interoperability between open source software projects is increasingly common. Applications that were designed to communicate effectively with other applications are more robust and give users the freedom to combine them with other applications that were built to interoperable specifications. Projects such as Apache, Linux, and other development platforms, have helped fuel this move to interoperability in unique ways, including the capability of building further applications upon their foundations. They also encouraged the development of new communities and ecosystems of users and developers. The OSGeo Foundation has taken advantage of these powerful open source platforms with several open source projects focusing on technological interoperability. However, there is also significant social interoperability taking place within the organization. What seem to start as ad hoc communities, in turn, create further opportunities for both social and technological advances. This article uses OSGeo as a case study to show that, when individuals contribute to the community and join together with other likeminded members, new technology and relationships pave the way to further innovation.

Building an Infrastructure to Support Women Founders: Lead to Win for Women - Janice Singer; Deborah Dexter (Open Source Business Resource, 2011)
This article describes a new program, Lead to Win for Women (LTW-W), created in Canada's Capital Region to dramatically increase the number of women-founded businesses and to help existing businesses grow substantially. This new program is based on the existing Lead to Win program (http://leadtowin.ca). LTW-W has four program elements. First, there is a session to help women foster ideas to launch and grow businesses. Second, there is an expert speaker series that encourages the development of practical knowledge for businesses. Third, there is a forum for owners of established firms. Fourth, there is an outreach program for college women to encourage them to start businesses. In this article, we briefly describe some existing programs to support women founders in Canada and abroad. Next, we outline the founding principles of LTW-W and describe the program in detail. Finally, we conclude with a description of the program's next steps.

Carleton Entrepreneurs: The First Keystone Off-The-Shelf Application - Tony Bailetti; Ludovico Prattico (Open Source Business Resource, 2011)
In this article, we describe the first application of the Keystone Off-The-Shelf (KOTS) platform. KOTS integrates software applications available under open source licenses with proprietary applications and services offered by small local technology companies, most of which are Carleton University spin-offs. KOTS is the engine behind the website for the Carleton Entrepreneurs program. The goals of this unique program are to: i) strengthen the entrepreneurial spirit at Carleton University; ii) help graduate and senior undergraduate students transform their ideas into compelling opportunities and successful ventures; and iii) share the best opportunities with potential investors, alumni, and friends of Carleton University. KOTS will enable the Carleton Entrepreneurs collective to achieve significant system-level outcomes that are not attainable without the platform. This collective is comprised of students, mentors, internal and external reviewers, top managers of technology university spin-off companies, academics, and friends of Carleton.

Competition in the Mashup Ecosystem - Amanda Shiga (Open Source Business Resource, 2011)
Mashups combine data from multiple sources to create innovative web applications. Data providers gain compelling advantages in offering an open application programming interface (API), but face a competitive environment where growth occurs by virtue of developers' independent choices and where competitors are also complementors. This article explores the nature of competition within the mashup ecosystem by focusing on competitive actions taken by API providers and their link to mashup network structure. The resulting insights help entrants and incumbents refine their competitive strategies within this complex and unique environment.

Control and Diversity in Company-led Open Source Projects - Michael Weiss (Open Source Business Resource, 2011)
A majority of open source development today is carried out by companies. Building on open source allows companies to focus their development effort on the points of difference over their competitors. This article discusses the recent trend towards collectives of companies that develop shared assets in the form of open source projects, and creates a model for company-led open source projects around two dimensions: the level of control over the project and the diversity of applications derived from the project. The article then explores how the model can be interpreted from a product line engineering perspective.

Control in Open Source Software Development - Robert Poole (Open Source Business Resource, 2011)
In this article, we examine typical fears associated with a perceived loss of control in an open source software development project. We describe various development models, including hybrid models that provide companies with control over key aspects of product development. Finally, a description of control within open source projects illustrates that self-regulating control mechanisms that exist in this model. A better understanding of control as a factor will help companies achieve their for-profit objectives using open source software.

Cost Optimization Through Open Source Software - Mark VonFange; Dru Lavigne (Open Source Business Resource, 2011)
The cost of information technology (IT) as a percentage of overall operating and capital expenditures is growing as companies modernize their operations and as IT becomes an increasingly indispensable part of company resources. The price tag associated with IT infrastructure is a heavy one, and, in today's economy, companies need to look for ways to reduce overhead while maintaining quality operations and staying current with technology. With its advancements in availability, usability, functionality, choice, and power, free/libre open source software (F/LOSS) provides a cost-effective means for the modern enterprise to streamline its operations. iXsystems wanted to quantify the benefits associated with the use of open source software at their company headquarters. This article is the outgrowth of our internal analysis of using open source software instead of commercial software in all aspects of company operations.

Creating an Environment That Encourages Women Entrepreneurs - Roseann O'Reilly Runte (Open Source Business Resource, 2011)
If women do not participate fully in entrepreneurial activities, we lose half the potential of our society and economic development will be limited. Women who do take on entrepreneurial roles succeed admirably. Thus, their participation is all the more important. This article cites a speech by Sheryl Sandberg, Facebook's COO, in which she offers several reasons for women's lack of participation and leadership. These factors are discussed and several solutions are proposed which could contribute to making the environment of a community more supportive and conducive to the successful participation of women in leadership roles.

Defining Good Deals in Business Collectives - Michael Ayukawa (Open Source Business Resource, 2011)
In the context of a current project at Carleton University to create creating a deal-making platform, this article presents the results of a recent review of the literature to determine: What is a good deal? This is question is asked from the perspective of the stakeholders in the development of a software-based collaboration tool that is designed to help streamline deal development between members. The stakeholders include the creators, the users, and the investors. We answer this question by examining several streams in the literature, all centered on understanding deals and deal-making processes. These streams explore the concept of a win-win deal, how value may be seen differently, and the group processes involved in deal making. A key contribution from this review suggests that deal goodness can be separated based on a Me-We construct: the impact to each and every stakeholder of the deal and the impact to the entire collective (not just the deal stakeholders). This implies one can separate the platform management problem into actor-centric (Me) and linkage-centric (We) domains. This is consistent with the notion of players balancing their self interest with the other stakeholders in the deal (Me-We). This is also consistent with the prospect of managing ecosystem health based on player and network-based metrics.

Developing Silicon IP with Open Source Tools - Arthur Low (Open Source Business Resource, 2011)
The electronic design automation (EDA) tool industry is big business, and commercial licenses are extremely expensive. Open standards have driven many proprietary EDA technologies to be publicly released as free/libre open source software (F/LOSS) and some have become IEEE standards. Competition has partly given way to collaboration and has led to these standards. The development path of important EDA tools frequently now employs F/LOSS practices, which have overcome resistance to collaborative innovation between competing businesses. F/LOSS technologies are at the vanguard of leading-edge system-on-chip (SoC) design, not just because they are free, but also because they are valuable. The first commercial integrated circuits (ICs), designed by hand, helped guide manned space flight to the moon on the Apollo missions. In the past decade, silicon IP firms have shown they are limited only by their ideas, not by limited investment opportunities, and SoC firms have shown they can greatly reduce costs while innovating on the development of the largest new IC designs. This high-end technology is made accessible to startups because of open source. It is no longer just for mega-corporations. This article reviews the history of key advances in ICs and EDA tools. The common theme presented in this article for the driver of technology innovation is the requirement to develop the most advanced microprocessor possible. Today, a low-cost, high-value-added business model can efficiently serve the market for IC subsystems licensed as intellectual property (silicon IP) in the form of compilable source code. Alternatively, for larger SoC designs, engineering budgets can be shifted from the purchase of a relatively small number of high-cost EDA tool licenses to open source EDA technologies that can be run on massive compute-server farms. The two business models are not theoretical, but realistic. The author explains how his company (Crack Semiconductor) developed commercially successful cryptographic silicon IP using entirely open source EDA technologies and how another company (SiCortex) pushed the limits of IC design and open source EDA tools by simulating and verifying a massively parallel supercomputer.

Economics of Software Product Development Collectives - Michael Weiss (Technology Innovation Management Review, 2011)
Where software product development occurs is shifting from single companies to groups or collectives of companies. In this article, we retrace the evolution of how software product development is organized and then offer insights into the economic motivation for collectives, which will be relevant to companies considering joining a software product development collective. Building on the literature on software product line economics, we identify three factors affecting the economics of collectives (level of contribution, number of members, and diversity of use), and develop a model that links those factors to three economic outcomes (time, quality, and cost). This model can be used by potential members when deciding whether or not to join a collective.
Keywords: collectives; eclipse; ecosystem; product line; software development

Editorial: Co-Creation (March 2011) - Chris McPhee; Marko Seppä; Stoyan Tanev (Open Source Business Resource, 2011)
The editorial theme for this issue of the OSBR is Co-Creation. The articles invited for publication in this special issue of the OSBR were originally presented last September at EBRF 2010, in Nokia, Finland. EBRF - the research forum to understand business in the knowledge society - is the oldest international peer-reviewed business research conference organized annually in Finland. The first EBRF conference was organized in Tampere, Finland in 2001. The grand theme of the 10th anniversary EBRF conference was "Co-Creation as a Way Forward". For this issue of the OSBR, a preliminary subset of EBRF articles were selected by a specifically designed committee of scholars that was asked to nominate EBRF articles fitting the topic of the special issue and providing valuable insights to both scholars and practitioners. We invited the authors to create specialized versions of the papers that were previously published in the EBRF 2010 Conference Proceedings by focusing on the practical relevance of their research for an audience including not only scholars but also business and technology experts. After the submission of the OSBR versions, an additional peer review process was used to select seven articles offering diverse perspectives on co-creation.

Editorial: Collectives (April 2011) - Chris McPhee; Tony Bailetti (Open Source Business Resource, 2011)
The articles in this issue of the OSBR focus on collectives that harness diversity to produce significant system-level outcomes. These collectives support members that belong to different groups and carry out activities in three different horizons: today's business (Horizon 1), the next generation of emerging businesses (Horizon 2), and the longer-term options out of which the next generation of businesses will arise (Horizon 3).

Editorial: Introducing the TIM Review (October 2011) - Chris McPhee (Technology Innovation Management Review, 2011)
Keywords: editorial; journal; TIM Review

Editorial: Miscellany (August 2011) - Chris McPhee (Open Source Business Resource, 2011)
For this issue of the OSBR, we issued a general invitation to authors to submit articles on the topics of open source business and the growth of early-stage technology companies.

Editorial: Recent Research (February 2011) - Chris McPhee (Open Source Business Resource, 2011)
The editorial theme for this issue of the OSBR is Recent Research. In this issue, the authors report on the findings and relevance of their recent research into open source and the application ecosystems.

Editorial: Technology Entrepreneurship (June 2011) - Chris McPhee (Open Source Business Resource, 2011)
The editorial theme for this issue of the OSBR is Technology Entrepreneurship. As with our May issue, which shares this theme, we have invited entrepreneurs associated with the Technology Innovation Management program at Carleton University to share their lessons and insights about growing a technology company during its early stages.

Editorial: Technology Entrepreneurship (May 2011) - Chris McPhee (Open Source Business Resource, 2011)
The editorial theme for this issue of the OSBR is Technology Entrepreneurship. We have invited entrepreneurs associated with the Technology Innovation Management (TIM) program at Carleton University to share their lessons and insights about growing a technology company during its early stages. The authors represent a range of entrepreneurial experience, from serial entrepreneurs reflecting on battles won and lost, to first-time entrepreneurs describing the early twists and turns of transforming ideas into ventures. What is common to all the articles is the approach to entrepreneurship that is nurtured in the TIM program. The TIM program is a graduate program that distinguishes itself by offering three important benefits to its students: i) a Master's degree by research; ii) opportunities for personal brand development; and iii) practical, real-world experience. In particular, personal brand development and real-world experience are gained by applying the program's lessons and the products of the student's own research to assist early-stage technology companies. If the student is an entrepreneur, they have the added benefit of applying their research and learning to further their own opportunity. In this issue, entrepreneurs from the TIM program share some of the key lessons they have learned.

Editorial: The Business of Open Source (January 2011) - Chris McPhee; Michael Weiss (Open Source Business Resource, 2011)
An open source business is a business centered around an open source offer. Companies can engage with open source projects in different ways: they can release code as open source and hope to increase the adoption of their solution; they can contribute to community-initiated open source projects and leverage the solutions the community develops; they can offer complementary services and products that add value to an open source product; and they can reduce the cost and risk of product development by pooling their non-core efforts with other companies. This issue contains six articles. The first two articles discuss cost reduction through open source, and best practices for multi-vendor open source communities. The remaining articles were contributed by graduate students in a class on Open Source Business in the Technology Innovation Management program at Carleton University in Ottawa (http://www.carleton.ca/tim). This course explored why companies participate in open source projects, how companies manage communities around their open source offers, and how companies make money from the open source projects they initiated or contribute to.

Editorial: Women Entrepreneurs (July 2011) - Chris McPhee (Open Source Business Resource, 2011)
The editorial theme for this issue of the OSBR is Women Entrepreneurs. In this issue, we examine the reasons for the relative lack of women founders and leaders in technology businesses. Our authors discuss the entrepreneurial challenges that are unique to women and what changes may be implemented to tip the balance and increase the number of women entrepreneurs.

Fostering Student Entrepreneurship and University Spinoff Companies - Tony Bailetti (Technology Innovation Management Review, 2011)
A student spinoff company strives to transform knowledge acquired by students into an income-generating business. This article outlines how a university can increase the number of spinoff companies created by its student entrepreneurs. Student spinoff companies are of interest to all forward-thinking universities, particularly those that support research and teaching programs in the field of entrepreneurship. The spinoff companies provide tangible evidence that students acquire viable entrepreneurial skills while studying at the university. In addition, student spinoff companies contribute to regional economic development, commercialize knowledge that otherwise would go undeveloped, help universities attain and expand their core missions, and increase the return on the investments in university R&D. University policies developed specifically for student spinoff companies significantly affect the growth potential of such ventures. This article provides a model and a set of principles that universities can use to support and increase the number of student entrepreneurs at their institutions. The model and principles are grounded in research findings and practical experience. In addition, the article suggests that universities adopt a results-based management approach to plan and deploy initiatives to support student entrepreneurs. The approach is widely used by government agencies interested in increasing the outcomes from their investments.
Keywords: entrepreneurship; spinoff; student entrepreneur; university

The Future of Co-Creation - Marko Seppä; Stoyan Tanev (Open Source Business Resource, 2011)
The objective of this article is to provide a brief summary of the key directions in value co-creation research that have emerged in the last 10 years. It points to several emerging streams in value co-creation research including: i) general management perspective; ii) new product development and innovation; iii) virtual customer environments; iv) service science and service-dominant logic (SDL) of marketing; and v) international markets and entrepreneurship, with a focus on the general management and innovation perspectives. In addition, the article points to another emerging new direction focusing on business co-creation. The development of business co-creation frameworks integrating the participatory role of both universities and vibrantly emerging business ecosystems represents a valuable alternative to traditional technology transfer and business administration approaches.

How Firms Relate to Open Source Communities - Michael Ayukawa; Mohammed Al-Sanabani; Adefemi Debo-Omidokun (Open Source Business Resource, 2011)
This article explores the relationship between firms and open source communities. Open source communities create, adopt, adapt, or disseminate innovation in a manner very different from a proprietary approach. To put this in context, we first define what is meant by open source community and then examine the roles members may play in these communities. Next, we illustrate that a firm can participate in an open source development community in different ways, depending on its level of sponsorship of that community. We assert that the degree of influence desired by the firm should connect to its business strategy and the firm needs to determine how its participation and support can be used to enhance its competitive position and provide new value to its customers. We next explore three main strategies to leverage and engage communities. We also examine how community interactions are affected by the degree of openness when engaging the community and how this relates to the firm's ability to protect the competitive advantage of its proprietary assets. This discussion will help firms with strategic planning when considering how to tap into this source of technical innovation that lies outside their boundaries.

Introducing the Oregon State University Open Source Lab - Anthony Casson; Leslie Hawthorn (Open Source Business Resource, 2011)
The Oregon State University Open Source Lab (OSUOSL) is the home of growing, high-impact open source communities. Its world-class hosting services enable the Linux operating system, Apache web server, the Drupal content management system, and over 50 other leading open source software projects to collaborate with contributors and distribute software to millions of users globally. Through custom software development, vendor partnerships, and industry events such as the Government Open Source Conference (GOSCON), the lab's staff and students encourage open source adoption in education, government, health care, and other sectors. In addition, the lab creates real-world educational opportunities for its students by providing high-value development and hosting services for open source communities. In this article, we describe the benefits of the OSUOSL to open source projects and to students of Oregon State University.

Key Player Identification in the Mashup Ecosystem - Monique Bardawil (Open Source Business Resource, 2011)
By combining multiples sources of data to create a new application, mashups represent a powerful source of innovation. Together, the various data providers, developers, mashup platforms, and users constitute an ecosystem that depends on innovation from these various players for its growth and success. This article summarizes recent research into the network structure of the mashup ecosystem, along with the positions and roles of entities within it. This research illustrates analytical methods for identifying key players in an ecosystem, while delivering new insights into the structure of the mashup ecosystem. Finally, the implications of these findings for entrepreneurs and incumbents are discussed.

Learning from Failure: A Case Study in Entrepreneurship - Daniel Crenna (Open Source Business Resource, 2011)
Business ventures often fail even when market demand is demonstrated and evaluated by peers, and when the project team is capable of producing the work. In this informal case study based on the author's own experiences, the topics of market size and fit, team size, human dynamics, business validation, and interaction design are explored to form a picture of how a business with seemingly promising prospects could still fail. Specifically, the challenges faced by small or single-person implementation teams are discussed, with suggestions for overcoming these challenges to produce more realistic and viable businesses.

Lessons from an Open Source Business - Fred Dixon (Open Source Business Resource, 2011)
Creating a successful company is difficult; but creating a successful company, a successful open source project, and a successful ecosystem all at the same time is much more difficult. This article takes a retrospective look at some of the lessons we have learned in building BigBlueButton, an open source web conferencing system for distance education, and in building Blindside Networks, a company following the traditional business model of providing support and services to paying customers. Our main message is that the focus must be on creating a successful open source project first, for without it, no company in the ecosystem can flourish.

Letters to the Editor - Roseann O'Reilly Runte; Rafik Goubran; Jerry Tomberlin (Technology Innovation Management Review, 2011)

Leveraging Collectives as a Technology Startup: A Case Study - Natasha D'Souza (Open Source Business Resource, 2011)
Entrepreneurs face a daunting challenge in turning a solution to a compelling problem into a viable business. Recent research into multi-sided platforms and collective action has highlighted an approach that may enable entrepreneurs to lower the risk of a new venture and increase revenue by delivering value to all stakeholders in a collective, not just to the company itself. However, the shift in thinking required to apply this new approach is a challenge of its own. In this article, we provide an overview of both the new and traditional approaches to development and commercialization. Next, we describe a problem for which we are currently developing a business opportunity to solve: helping parents provide adequate and appropriate support to children with attention deficit hyperactivity disorder (ADHD) or autism. We then use this problem as a case study to illustrate how the implementation of a facial emotion recognition software application might be substantially different depending on the development and commercialization approach used. Finally, we describe the key lessons learned and next steps in developing this business opportunity.

Managing the Challenges of Becoming an Open Innovation Company: Experiences from Living Labs - Mika Westerlund; Seppo Leminen (Technology Innovation Management Review, 2011)
High-technology firms have paved the way for user-driven innovations, but now even traditional industries are becoming increasingly open. This shift is a great challenge for companies with instituted practices, policies, and customer relationships. In this article, we identify four distinct steps in becoming an open innovation company based on our recent research into firms’ experiences with living lab experiments in the information and communication technology (ICT) sector. We describe these phases and illustrate the divergent roles that users play in each one. We conclude with a discussion on the differences between the management challenges of conventional development projects versus the open innovation model. For all firms that wish to become open innovators, we recommend that their managers promote an open organizational mindset and apply groupware that supports increased openness, because traditional project management tools are insufficient for open innovation.
Keywords: Innovation management; Living lab; Open innovation; User-driven

A Money-Making Platform for Entrepreneurs - Robert Poole (Open Source Business Resource, 2011)
New technologies such as cloud computing and platforms are beginning to emerge as simple, practical ways for entrepreneurs to start businesses in a short period of time and with little money. They allow businesses to quickly take a concept to the market to see if it will work. If the business takes off, these same technologies are ready to scale the business to reach global markets and to stay profitable the entire time. In this article, an outline is provided of key business models that have proliferated as a result of new technologies, namely multi-sided platforms, long-tail markets, and freemium business models. Next, the author describes FreebirdConnect.com, his new platform business that has emerged out of Carleton University's Technology Innovation Management program. This platform can be used by other entrepreneurs to start a new business venture that can reach new markets around the world. Finally, the article describes the steps that an entrepreneur can follow to start a low-risk, global business on the FreebirdConnect.com platform without substantial start-up capital.

A Network-Centric Snapshot of Value Co-Creation in Finnish Innovation Financing - Jukka Huhtamäki; Martha G. Russell; Kaisa Still; Neil Rubens (Open Source Business Resource, 2011)
In this article, we apply the concept of value co-creation to the analysis of linkages between organizations and their human and financial resources to observe the emergence of cooperative activities in a specific innovation system. Through visual network analysis of a federated and socially constructed dataset of organizations and their related actors, we show how co-creation occurs through financial linkages. We use the ecosystem concept as a metaphoric reference to value co-creation with a network-centric mindset. Business financing linkages reveal convergence and co-creation in the innovation ecosystem, and network analysis is used to visualize the relationships between firms. Through the lens of relationship-based synergy, we provide a snapshot of innovation funding, which highlights the collaboration of venture capital and government agencies in co-creating the emerging Finnish innovation ecosystem.

New Solutions to the Funding Dilemma of Technology Startups - Ali Kousari (Open Source Business Resource, 2011)
This article explores the current funding challenges facing technology startups and describes new models based on smaller investments and collective action. First, the advantages and disadvantages of traditional startup funding models are presented, with an emphasis on venture capital and angel investment. Next, an overview of existing seed funds, or seed accelerators, shows how entrepreneurs can leverage this approach to access subsequent rounds of funding and create successful ventures. Then, an overview of crowd funding is provided, including examples of companies that have adopted this approach to funding startups and their founders. Finally, the article presents the basis of a new approach that uses crowd funding as means of attracting investors to collectives. In these business ecosystems, startups are exposed to less risk and investors can benefit from attractive returns by investing in these promising startups.

Nokia's Hybrid Business Model for Qt - John Schreuders; Arthur Low; Kenneth Esprit; Nerva Joachim (Open Source Business Resource, 2011)
In today's challenging economy, startup companies are finding it more and more difficult to gain a foothold and traction in the market. Free/libre open source software (F/LOSS) allows a company to gain exposure to their products. However, few firms offer F/LOSS solutions alone. The vast majority combine proprietary and open source products while receiving revenues from both traditional license fees and open source offerings (Bonaccorsi and Giannangeli, 2006). This dual practice of offering F/LOSS as well as a commercial license is a hybrid business model. In this article, we focus on the hybrid business model for Nokia's Qt product: how it is implemented, why it was implemented, and the extent to which the model has been effective. The Qt story illustrates how F/LOSS business models were developed during a period when participants were just beginning to understand how to make money with open source.

Open Source License Selection in Relation to Business Models - Carlo Daffara (Open Source Business Resource, 2011)
This article provides recent research results from the European Union's FLOSSMetrics project. The results focus on the business and practical aspects of the adoption of open source within software products or as a basis of service offerings. Research into free/libre open source software (F/LOSS) is usually conducted with a software engineering focus or with an emphasis on F/LOSS as a spontaneous or directed collaboration effort. The FLOSSMetrics project expanded that research with an investigation on how licenses, business models, and project choices affect development and productization. This article provides a summary of common licensing issues and business models choices in F/LOSS, and it provides a list of recommendations for selecting a license for a software project to suit both business objectives and licensing constraints.

Private-Collective Innovation: Let There Be Knowledge - Ali Kousari; Chris Henselmans (Open Source Business Resource, 2011)
Many innovators (companies or individuals) opt for a private innovation model. This model uses resources to create a product whose intellectual property (IP) is protected by the firm. At the opposite end of the scale is the collective innovation model, in which innovators collaborate and expend resources to produce a public good. Many free/libre open source software (F/LOSS) projects rely on collective innovation. Some innovators are now combining the two models into a private-collective innovation model, in which an innovator may chose to collaborate with other innovators and spend private resources while still keeping some IP private. For example, a company may release its product's source code to the public in the hope of attracting a community of contributing developers. Such a company commits its own resources to a project, but may still hold on to the intellectual property. The success of private-collective innovation is dependent on many factors including: project interest and value, company reputation, and project status. There are benefits and risks to private-collective innovation which must be carefully weighed before making a decision to employ this model. Private-collective innovation involves the sharing of knowledge and, in some cases, the sharing of IP that may or may not be patented.

A Progress Report on the Keystone Off-The-Shelf Project - James Makienko; Antonio Misaka (Open Source Business Resource, 2011)
In this article, we provide an update on the Keystone Off-The-Shelf (KOTS) project. We begin by presenting an overview of the goals and the advantages of KOTS. Next, we describe the software components that make up KOTS. Finally, a blueprint for the first application of KOTS is described along with the plan to launch a collective of technology companies and a non-profit organization that will use, support, and evolve the software.

Proving the Expertise of Freelance Android Developers - Igor Sales; Aparna Shanker (Open Source Business Resource, 2011)
Android continues to grow in popularity as a mobile operating system. With this constant growth in popularity comes a demand for skilled, specialized platform and application developers rather than just generalists that are currently provided by outsourcing firms. This article describes a business opportunity where a collective of proven experts can be used to fulfill this need for specialized developers. A key aspect of the proposed solution is the provision of proven expertise by certifying and guaranteeing the level of specialization of developers in the collective.

Quality-Based Co-Value in SaaS Business Relationships - Xian Chen; Paul Sorenson (Open Source Business Resource, 2011)
In the past decade, the focus of information technology (IT) development has been on service-oriented architecture, especially the new service delivery model, Software-as-a-Service (SaaS). Accordingly, interest in quality management in the planning and operation of SaaS systems has increased tremendously. In practice, it is necessary to take into greater account the nature of service quality shared by both service provider and customer in the SaaS delivery. This paper introduces a study on a theory that integrates the service quality and value co-creation (co-value) in the SaaS business relationships between service provider and customer. The theory is established, in part, based on the results of a survey of Chief Information Officers (CIOs) that shows a strong correspondence between the service quality required or desired by a client and the business relationship needed between SaaS clients and providers. We have used the theory as the foundation for an approach and tool for evaluating SaaS applications.

A Rapid Prototyping Environment for Student Entrepreneurs - Frank Horsfall (Open Source Business Resource, 2011)
This article describes a project initiated in the Technology Innovation Management (TIM) program at Carleton University to develop a common development and test environment for entrepreneurs associated with the program. This environment will support a collaborative entrepreneurial community that is building complementary products around a core platform; the goal is to accelerate the quick delivery of projects to market while acknowledging that the community's resources are limited. As described in this article, the solution that was developed is called the TIM Rapid Prototyping Environment (TIMRPE). Thee TIMRPE provides a competitive advantage for entrepreneurs in the TIM program. A TIM entrepreneur can quickly jump into the development of their prototype, knowing that timely assistance and support is available. This environment now hosts several entrepreneurial projects, some of which have been described in recent issues of the OSBR, including this one. This article introduces the rapid prototyping approach, provides an overview of the TIMRPE, shares lessons learned from the early experiences with the environment, and outlines the project's next steps.

Redefining "Women's Work": Tensions Between Technology, Entrepreneurship, and Social Reproduction - Tess Jewell (Open Source Business Resource, 2011)
This article considers some of the most recent research into women's participation in technology and entrepreneurship and connects it to the literature on social reproduction in order to paint a more complex picture of the social and environmental factors that influence women's career choices. Specifically, it shows how lingering biases concerning women's reproductive functions continue to shape both men and women's expectations regarding women's aptitudes, interests, and fitness for various roles. These biases and stereotypes create barriers to women's progress at various levels, including the home, the workplace, and educational institutions. The article concludes with recommendations for how educators and entrepreneurs in science and technology can promote the inclusion of women among their ranks.

Reflecting on Fifty Issues of the OSBR - Chris McPhee (Open Source Business Resource, 2011)
This is the last article to be published in the Open Source Business Resource (OSBR). In September 2011, the OSBR will become the Technology Innovation Management Review. In this article, we look back upon the changes in the landscape of open source business and in the OSBR itself from the time it was first published in July 2007 until its last issue in August 2011. Finally, we look ahead to the upcoming changes that will be embodied by the Technology Innovation Management Review.

Renewal Through Co-Creation in Business Networks - Raimo Hyötyläinen; Katri Valkokari; Petri Kalliokoski (Open Source Business Resource, 2011)
This article presents four models of business renewal within networks based on a theoretical framework developed from earlier literature. According to the typical dimensions of business development, our framework distinguishes between the exploitation of present knowledge for efficiency and the exploration of new knowledge for new business development. Furthermore, the two network development and governance types (i.e., hub-spoke and multiplex) form the other dimension of the framework. The framework was empirically tested with five case companies and their business networks. The framework of network models may help managers to structure the business network and its renewal based on the strategic targets of a firm. Furthermore, the theoretical contribution of the paper deepens the understanding of how co-creation and interaction between the participants differ according to business focus and complexity of networks.

A Sales Execution Strategy Guide for Technology Startups - Ian Gilbert; Stephen Davies (Technology Innovation Management Review, 2011)
The majority of startups fail to consider sales execution as part of their overall strategy. This article demonstrates how a sales execution strategy can help a company take a product or service to market more efficiently and effectively by focusing on the customers that are key to generating revenue. Combined with techniques for recruiting effectively and measuring sales outcomes, a sales execution strategy helps technology startups exceed growth aspirations and potentially reduce or even eliminate the requirement for external investment. In this article, we first describe the focus of assistance currently given to startups and the reasons why sales execution strategies are often overlooked. Next, we outline recommendations for developing, implementing, and supporting a sales execution strategy. Finally, we summarize the key points presented in the article.
Keywords: entrepreneurs; sales; sales execution strategy; sales strategy; startups

Shifting an Entrepreneur's World View - Michael Ayukawa (Open Source Business Resource, 2011)
As an entrepreneur, you continually test your decisions by gaining feedback: from your customers and your investors (or lack thereof). This process of ongoing feedback is how an entrepreneur learns to shape their opportunity to accommodate their new knowledge of the environment. But this activity is very dependent on the "world view framework" of the entrepreneur. What may seem to be important turns out to be noise and important signals are dismissed. This article describes the special value for an entrepreneur of frameworks grounded in theory in general and the value of the framework of business ecosystems from two perspectives: as a member of a business ecosystem and as a creator of a business ecosystem. These two perspectives fundamentally affected the direction of adaption for our product and reshaped how we approached our (ad)venture.

The Social Management of Risk - David Péloquin; Jean Kunz; Nicola Gaye (Open Source Business Resource, 2011)
In this article, we discuss a conceptual framework on the social management of risk and highlight the role of the community sector in that process. We introduce the topic of risk, illustrate how it is distinct from the concept of uncertainty, and show how different social actors assess risk differently. Next, we introduce the "social management of risk" approach, which takes a broad view of the potential actors involved in pursuing societal objectives in relation to risk. Finally, we discuss the role of the community sector is the social management of risk. While this framework is presented in the context of social policy, it can be generalized to any situations where social actors respond to and manage risks in a multi-player environment.

Software-as-a-Service Offer Differentiation by Business Unit - Islam Balbaa (Open Source Business Resource, 2011)
This article summarizes the author's recent research into the fit between software-as-a-service (SaaS) tools and the requirements of particular business units. First, an overview of SaaS is provided, including a summary of its benefits to users and software vendors. Next, the approach used to gather and analyze data about the SaaS solutions offered on the Force.com AppExchange is outlined. Finally, the article describes the managerial implications of this research.

The Strategic Impact of Corporate Responsibility and Criminal Networks on Value Co-Creation - Frederick Ahen; Peter Zettinig (Open Source Business Resource, 2011)
This article is motivated by the increasing concern about the ever-declining security of pharmaceutical products due to the abundance of counterfeit network actors. We argue that if networks are effective mechanisms for criminal organizations to infiltrate into any value chain, then networks should also work for responsible businesses in their quests to counter this phenomenon of value destruction, which is ultimately detrimental to the value co-creation process. Thus, this article demonstrates a nuanced understanding of the strategic impact of corporate responsibility of actors in networks on value co-creation. The current discourse on value co-creation in business networks is structured in such a way that it precludes its inherent corporate responsibility component even though they are not mutually exclusive. Moreover, research on value co-creation aimed at the proactive and responsible defence of a network substance via value co-protection has been mostly scant. We propose a model of value-optimization through value co-protection and ethical responsibility. This way of theorizing has several implications for both policy making and managerial decision making in the pharmaceutical industry and beyond.

Trusted to Lead: Trustworthiness and its Impact on Leadership - Taina Savolainen; Sari Häkkinen (Open Source Business Resource, 2011)
This article discusses trust in leadership, a major issue in current business management. Paradoxically, in the environment of continuous change that characterizes many organizations today, trust is needed more but is enacted less. Trust forms a foundation for functioning relationships and co-operation. Trust is intangible - it is an intellectual asset, a skill, and an influencing power for leaders. Leadership by trust emphasizes trustful behaviour towards employees. In this article, we suggest that, in trust formation, it is trustworthiness in leader behaviour that matters. Showing trustworthiness by competence, integrity, benevolence, and credibility makes a difference in daily leadership work. The importance of trust in leadership has been widely recognized in the literature and business practice. This article focuses on how leaders enact on trust by showing trustworthiness to subordinates. The ways of building and sustaining trust and the effects of trustworthy and untrustworthy leader behaviour are examined. Two real life cases from industrial companies are presented and their implications are discussed. In conclusion, a leader's competence (ability) is one of the key dimensions in showing trustworthiness. As to untrustworthy behaviour, it is worth noting that building and sustaining trust is reciprocal in nature. A practical implication for leaders is that the development of an awareness of trustworthiness and skills for demonstrating it should be a top priority in the current business environment, which demands strong interaction, cooperation, and communication abilities.

Using Value Co-Creation to Redefine Business Models - Kati Järvi; Antti Pellinen (Open Source Business Resource, 2011)
In the information and communication technology (ICT) sector, a revolution is underway in the delivery channel of mobile service (or application) production and provision, and application stores are building up a central position as intermediaries in service delivery. The market is transforming from being one-sided to being two-sided. Thus in this article, we focus on integrating the business model concept with value co-creation with respect to the emergence of two-sided markets and intermediaries. As the transformation from a one-sided to a two-sided market and the birth of intermediaries bring forth value co-creation possibilities, this article aims to find out how value can be co-created in different mobile service production and provision models.

Which Gender Differences Matter for High-Tech Entrepreneurship? - J. McGrath Cohoon (Open Source Business Resource, 2011)
With data from successful founders of high-tech companies, we identify traits common to large majorities of them and any gender differences in those traits. There are few. Further, we identify criteria that might lead to gender imbalance among successful founders by comparing similarities and differences in the gender distribution of these traits among the general population and among successful founders. We find that signature traits of successful founders include: motivation by the desire to build wealth, and not by the inability to find traditional employment, nor because they developed a technology in a lab environment and wanted to see it make an impact; belief that startup success was due to prior industry or work experience, lessons learned from previous successes and failures, the company's management team, and good fortune, not because of state or regional assistance or alumni networks; access to mentors, and little financial pressure for a steady income. None of these dominant traits appeared to be required unequally of men and women, although some traits were unequally distributed in the general population.

Assessing Trust Between Members of a Marketplace - Eduardo Moraes (Open Source Business Resource, 2010)
Trust is very important to companies that participate in electronic markets and the keystone organizations that operate these markets. No company wishes to deal with a keystone that is not trustworthy or purchase a solution from a supplier that it does not trust. To grow a community, the keystone and the suppliers that are its marketplace members must be trusted. Providing users of a marketplace with tools to measure trust in suppliers' solutions may reduce transaction costs and increase the number of deals closed. The objective of this paper is to examine how to measure trust in suppliers' solutions offered in a marketplace. The discussion on how to measure trust in a keystone is deferred to a later paper. This paper is organized into six parts. The first part defines trust and the second examines the concept of trust transitivity, which is the use of indirect trust in a trust network. The third part describes how trust can be measured. The fourth provides an overview of the author's research, which examined how the numbers of observations about a solution-supplier's ability, integrity, and benevolence affect a customer's uncertainty and belief in the solution offered in the Eclipse Marketplace. The fifth part discusses the implications of this research for keystone operators. The last section provides conclusions and summarizes the relevance of this research.

Bloom: A Relationship Visualization Tool for Complex Networks - Frank Horsfall (Open Source Business Resource, 2010)
Faced with an ever-increasing capacity to collect and store data, organizations must find a way to make sense of it to their advantage. Methods are required to simplify the data so that it can inform strategic decisions and help solve problems. Visualization tools are becoming increasingly popular since they can display complex relationships in a simple, visual format. This article describes Bloom, a project at Carleton University to develop an open source visualization tool for complex networks and business ecosystems. It provides an overview of the visualization technology used in the project and demonstrates its potential impact through a case study using real-world data.

Blueprint and Approach to Grow Revenue in Small Technology Companies - Tony Bailetti (Open Source Business Resource, 2010)
This article examines a new approach to grow the revenue of small technology companies and technology startups. We name this new approach the business ecosystem approach. The article is organized into five sections. The first section provides a blueprint to grow revenue and an inventory of growth formulas that top management teams of small technology companies and founders of startups find useful. The second section briefly defines business ecosystems, keystones and platforms. The third section describes the business ecosystem approach to grow the revenue of small technology companies and technology startups. It compares the traditional and business ecosystem approaches to growing revenue; identifies when the business ecosystem approach works better than the traditional approach; explains what small companies and startups need to do to grow revenue using the business ecosystem approach; and describes the benefits and risks of implementing the business ecosystem approach. The fourth section compares three approaches to growing revenue and highlights the differences between i) business ecosystems and development communities and ii) the business ecosystem approach and outsourcing. The fifth section identifies the key decisions a small technology company or technology startup needs to make to become the keystone that anchors a business ecosystem.

Building a Business-to-Business Sales Process - Stephen Davies (Open Source Business Resource, 2010)
A sales strategy is not just about closing deals, it is about defining a sales process that accurately reflects an organization, its customers, and the products or solutions that it sells. By truly understanding its customers and by actually solving its customers' problems, a company can define and execute a sales process that will increase the likelihood of reaching its ultimate objective: a closed deal and money in the bank. This article describes the steps to create a business-to-business (B2B) sales process and shows how these steps are used to build a sales funnel. It also provides tips for effective and consistent execution of that process to get initial sales and improve upon them.

Building Canada's Culture of Entrepreneurship: Sure-bet to Startup Survival - Lisa Torjman; Jon Worren (Open Source Business Resource, 2010)
This article aims to debunk common perceptions around why Canada seems to be failing in its ability to create successful startups. A robust startup sector will only be made possible if Canada invests in and nurtures a culture of entrepreneurship.

The Business of Open: Common Pitfalls for Open Source Startups - Mekki MacAulay (Open Source Business Resource, 2010)
Many entrepreneurs look at open source as a panacea of sorts, a golden ticket to success. They assume that the value of the open source approach is apparent to all, undeniable, and the only way. The mistake they often make is carrying this passion into the way they form their startup. They assume that open source startups are somehow different, and that as a result they will carry themselves. I was once such an entrepreneur, with such a vision. The reality is that an open source startup isn't really that different from other startups. It still needs to have figured out all of the essential components of a successful business. An open source strategy can certainly yield a competitive advantage, bringing faster time to market, lower development cost, collaboration opportunities, ecosystem positioning, and faster adoption. But, these advantages don't come along on their own. The open source strategy is just one piece of the larger business model. The other pieces have to be strong, too, or the whole might crumble. This article reviews the essentials for all startups and highlights special considerations and pitfalls for open source startups in particular. It also discusses how startups can use an open source strategy to gain competitive advantage by focusing the passion and energy surrounding participation in open source towards value creation and acquisition.

Cloud Computing: What is it, and How Will it Affect Organizations? - Fred Waldner (Open Source Business Resource, 2010)
We believe that, in the not too distant future, most people will be making use of cloud computing. How they use the clouds will vary, but everyone will be using the cloud. It is expected that cloud computing will follow a similar path as the Internet into the corporate environment: - there will be concern about security associated with data - there will be concern about being dependent on services that are controlled by third parties - many organizations will be challenged by existing corporate processes - some organizations will be leaders in the charge while other will lag For entrepreneurial businesses, this means that cloud computing can represent business opportunities to: i) reduce costs by leveraging cloud environments to provide infrastructure and services; ii) bring an expanded portfolio of products to a global marketplace through reduced costs to access large complex infrastructure; and iii) start small and expand services quickly and economically. This article presents extracts from literature that has been published on cloud computing and provides a brief outline of a common cloud computing taxonomy used to define the cloud. After reading this article, you should have a better understanding of the basics behind cloud computing, the reasons for the large potential savings, the key challenges organizations face when implementing cloud computing, as well as the paradigm shift that cloud computing represents to organizations.

Communication Enabled Applications: What are the IP Considerations for Platform Providers? - Patrick O'Halloran (Open Source Business Resource, 2010)
A platform of CEA building blocks, such as the out-of-the-box capabilities of the Coral CEA Sandbox, provides companies with the capability to quickly build new innovative products and services. Key considerations for users of the sandbox include intellectual property, licensing, and any other dependencies inherited from use of the sandbox assets. This article presents some background on this topic and examples of how to address the associated implications.

Communication Enabled CRM - Elias Majic (Open Source Business Resource, 2010)
Customer relationship management software is used to manage and enhance a company's interactions with its customers. Typically, CRM software integrates well with other communication software, such as email, but includes little or no integration with telephone or video conferencing systems. For companies that interact frequently with their customers or internal teams by telephone or video, this greatly limits the usefulness of their CRM system. Ideally, a CRM system offers flexibility to allow communication with customers in a variety of ways and provides consistent reporting and logging of these interactions regardless of which form of communication was used. This allows for greater insight from interactions with customers and helps better understand how to meet customer needs. This article describes our recent experiences as we set out to integrate communications services provided by Coral CEA into an open-source CRM system. CoralCEA is a platform that provides developers open application programming interfaces to easily integrate powerful communication features into web applications. In our case, we were interested in enabling telephone, telephone conferencing, and video conferencing services within a CRM application. However, the article is not just relevant to CRM users, since it illustrates how powerful communication services can be easily added to almost any existing web application. After reading this article, you will have a better understanding of the basics of CRM, how better communication improves the experience for both the company and the customer, and you will hopefully be encouraged to consider integrating powerful communication services into your own web applications.

Communications Enabled Applications: Building Value, not Monetising APIs - Craik Pyke (Open Source Business Resource, 2010)
Over the past decade there have been numerous attempts at opening telecom infrastructures to developers. As each attempt evolves to the next, there is an equal desire to monetise the exposure of telecom capabilities using traditional and well understood mechanisms: charge for necessary equipment upgrades and license the application programming interfaces on a per-invocation or "block of simultaneous invocations" basis. However, the various vendors and development companies involved in creating applications with embedded communications capabilities have had to re-examine their business and technology models in an increasingly competitive applications market where the rate of applications failing to gain market traction far outweighs the rate of success. This article looks at the history of telecommunications APIs and the predominant business models that have accompanied those interfaces. By analysing the history of telecom APIs and recognising the gradual shift from a strongly vendor controlled environment to a highly accessible component of IT networks, we can recognise the shift in revenue generation from a typical monetisation model to a value based model. Additionally, we can examine how incumbents and new entrants are dealing with the more unpredictable business models and emerging methods for de-risking value based revenue opportunities.

Community 101 - Brent McConnell (Open Source Business Resource, 2010)
Recently, a quote stirred some controversy among my peers. The part about "results are not the point" was hard for some people to understand and come to grips with. Aren't results always the point? Well, as with most things, "It depends". The people and community that evolve around an open source software project will ultimately determine its success. Even if the core team launches the project with spectacular productivity and results, this phase of evolution will be fleeting if the necessary processes and community to make the project a long lasting success are not put into place. This article presents some of the actions open source community leaders can take to ensure not only results, but a system that encourages productivity and longevity.

CRC Mobile Broadcasting F/LOSS Projects - François Lefebvre (Open Source Business Resource, 2010)
The Communications Research Centre Canada, the federal government's primary laboratory for advanced telecommunications research and development, has been at the forefront of new developments in mobile digital broadcasting technologies since their inception in the late 1980s. During this time, digital replacement technologies have been standardized in an effort to rationalize spectrum use and enhance broadcasting applications with datacasting services and associated program information. Eureka DAB was the first all-digital mobile broadcasting technology to be conceived, developed and deployed. It became a widely adopted standard for digital radio in many countries around the world in the mid-1990s. DAB was officially launched in Canada in 2000. This paper presents CRC's attempt to increase collaboration and innovation in the field of mobile broadcasting by developing and offering complete end-to-end Free, Libre and Open Source Software (F/LOSS) toolsets for the transmission and reception of DAB and FM/RDS applications and services.

Deals Without Borders: A Value Proposition for the Open Global Commerce Keystone - Michael Ayukawa (Open Source Business Resource, 2010)
The Ottawa Centre for Research and Innovation (OCRI) and Carleton University have envisioned the creation of a keystone anchoring a global deal-generating business ecosystem centered in Ottawa, Canada. Through the support and common resources of the ecosystem, small and medium companies located in five international capital cities will be better able to construct and close more transnational deals through a process of collaborative and open co-creation. This is the Open Global Commerce (OGC) value proposition: "Deals Without Borders."

Developing a Replicable and Sustainable Model of Business Incubation - Ian Graham (Open Source Business Resource, 2010)
The only constant in the world these days seems to be the accelerating rate of change. This article explores, what are in the author's opinion, the driving forces of change; the decline of the TV industrial complex, business model migration, and the emergence of the knowledge economy. The changes in the way we live and work are having a very profound impact on how businesses start and grow. The paradigm and policy of the industrial era will not pave the way to success in a knowledge-based economy. The knowledge economy requires a significant paradigm shift in the way we structure incubators to successfully nurture and grow knowledge-based businesses.

Developing a Service Industry to Support the Sahana Disaster Management System - Mark Prutsalis (Open Source Business Resource, 2010)
The Sahana Software Foundation governs humanitarian free and open source software (HFOSS) projects that address the information-coordination challenges of disaster management. Sahana software has been proven effective and is recommended by numerous industry sources from both the emergency management and business sectors. It fulfills critical needs to enable organizations responding to disasters to share information across organizational lines and to track and effectively manage disaster efforts. These needs are substantial and are growing because of climate change and urban population growth, which is leaving increasing numbers of people vulnerable and susceptible to the effects of disasters. Sahana fills a unique niche in the toolkit of emergency and disaster response agencies because it facilitates critical information sharing and coordination of efforts across all types of organizations and individuals involved, and is readily flexible to the needs that arise from any particular disaster. The software has its roots in the open source business community and has always been strongly supported by that industry. In this article, we describe an industry opportunity in HFOSS and provide evidence that Sahana software can be successfully commercialized. These factors make it a ripe time for open source businesses to engage cooperatively with the Sahana Software Foundation to support the growth of a service industry around Sahana software and HFOSS.

Developing a Successful Open Source Training Model - Belinda Lopez (Open Source Business Resource, 2010)
Training programs for open source software provide a tangible, and sellable, product. A successful training program not only builds revenue, it also adds to the overall body of knowledge available for the open source project. By gathering best practices and taking advantage of the collective expertise within a community, it may be possible for a business to partner with an open source project to build a curriculum that promotes the project and supports the needs of the company's training customers. This article describes the initial approach used by Canonical, the commercial sponsor of the Ubuntu Linux operating system, to engage the community in the creation of its training offerings. We then discuss alternate curriculum creation models and some of the conditions that are necessary for successful collaboration between creators of existing documentation and commercial training providers.

Differentiating Community from Customers in an F/LOSS Business - Matthew Aslett; Stephen Walli (Open Source Business Resource, 2010)
When software companies using free/libre open source software (F/LOSS) in their product and service offerings attempt to manage the customer pipeline and develop a community, problems may arise. Project communities and customer pipelines are not the same thing, although some participants belong to both groups. This creates confusion in the business and tension with the community. F/LOSS communities have been on the rise for the past two decades. Companies began to form around F/LOSS projects in the early 1990s, with some creating their own F/LOSS projects and some wrapping themselves around existing projects. This has created tension between company managers who are trying to earn profits from software that is "available for free," and from developers in communities that do not necessarily want to create software for someone else's corporate gain. This happens regardless of whether the company created the F/LOSS-licensed project itself, or participates in external communities around other projects, or both. This article demonstrates that separating the concepts of community and customer, and of project and product, allows a business to manage clearly both challenges of developing an engaged community and maximizing profits.

Editorial: Cloud Services (April 2010) - Dru Lavigne; Mike Kavis (Open Source Business Resource, 2010)
Cloud computing may be the biggest game changer within the enterprise since the adoption of the Internet in the 1990s and the personal computer in the 1980s. The economic climate, coupled with the rate at which technology is changing, is forcing companies to reduce information technology (IT) expenditures, increase productivity, and build more collaborative solutions as opposed to building everything internally. Cloud computing allows companies to outsource functions that are not core to their business or have become a commodity. Much of the technology driving cloud computing services is open source software. The LAMP stack has become widely adopted as the standard engine running much of the cloud services. With the exception of Microsoft's Azure cloud platform, most cloud service providers have embraced open source software, allowing them to drive costs down while providing reliable services for their customers. Pay-as-you-go is the new economic model for IT as we enter a new decade. Gone will be the days of making large purchases of commercial software with huge maintenance costs. In this new world, enterprises will consume only the services they need, only when they need them, and will pay for the resources required to scale up and down as necessary. This paradigm shift should force IT executives to focus more on building business functionality and less on managing and maintaining infrastructure and commodity applications. Open source software will play a huge role in making the shift to cloud computing economically feasible. At the same time, commercial software companies are racing to the cloud and are struggling to replace their expensive software licensing models with a pay-as-you-go model in order to make them an attractive alternative to open source software in the cloud. It should be interesting to see how this plays out over the next few years. The articles that follow provide insights into what cloud computing is and how it is changing the IT landscape.

Editorial: Communications Enabled Applications (May 2010) - Dru Lavigne; Chris McPhee (Open Source Business Resource, 2010)
As anyone with a smartphone can appreciate, the power of having a mobile phone that can can access the Internet creates significant value for users and opportunities for businesses. This device-level integration of communication services and web applications is now common. However, we are only now scratching the surface of the next step in value: application-level integration. The ability to integrate communications services within web applications opens up tremendous opportunities. Examples of communications enabled applications include simple click-to-call links on a website, conference calls initiated by applications or users in response to events, interactive voice response menus, and any number of other ways that communication services, such as messaging, voice, and conference calls, can be integrated into an application to add value. I recently had the pleasure of coordinating the activities of a group of entrepreneurs, developers, and architects as they explored together how CEAs can add value to their offerings and their business ecosystem. The Elena Project was funded by IRAP to stimulate small technology companies to develop working prototypes of CEAs and expand the capabilities of the Coral CEA business ecosystem and sandbox. The project focused on using four voice services and the open source web conferencing tool BigBlueButton. Among the outcomes of this project was the realization that significant value can be leveraged when communications features become integral parts of applications. In this issue of the OSBR, a diverse group of authors share their experiences and knowledge to help others explore the value CEAs could bring to their own offerings. All of the authors in this issue participated directly in the Elena project or present analysis relating to Coral CEA.

Editorial: Economic Development (November 2010) - Chris McPhee; Saad Bashir (Open Source Business Resource, 2010)
Economic development: these two simple words are excessively used and often misused in many contexts, including municipal government. In this issue of the OSBR, we offer a mainly municipal perspective under which we discuss what economic development means and what it can deliver. Economic development acts as a headlight that can guide a city like Ottawa through a fog of national and international competition and uncertain economic realities. It is an overarching role that nudges the local government towards smart decisions around long-term investments such as infrastructure. Achieving sustainable economic development for Ottawa means investment in the creation of a toolkit that consists of tourism development, community and social economic development, transportation access, entrepreneurship support, investment attraction, workforce development and academia, export development, and performance measurement. Such a toolkit is what encourages partnerships between stakeholders and facilitates the environment for healthy economic development conditions. This last element, performance measurement, deserves honest attention but is often found missing in an economic development plan. Just like a private sector firm that must always have its eyes on its bottom line and profitability, a city must constantly measure its economic development execution and adapt to changing circumstances. This can be achieved through a comprehensive scorecard or dashboard that analyzes trends over time, as well as compares Ottawa's performance versus its competitors. Economic development is no different than the business development unit of a firm that not only has the responsibility of creating market opportunities for its company's products, but also the crucial task of conveying back-market intelligence. From the City of Ottawa's perspective, the product we should be selling to both local residents and international community is the city brand, including business, tourism, and academia, as well as gathering competitive intelligence to continuously tweak our offering. Similar to cities whose future is dependent and linked to natural resources, Ottawa's economic future is tied to a rare resource as well. However, it is not found under the earth but between the ears of the knowledge-based workers that drive innovation in Ottawa. In today's environment, where both the knowledge-based work force and investment capital are highly fluid, the economic development challenge is to relentlessly retain and grow this knowledge resource. Economic development is the type of investment that will help Ottawa earn its way to be one of the world's leading centres for business, tourism, and academia. Conversely, lack of economic development vision and investment will undoubtedly leave the city's fortunes to luck. In this issue, the authors provide diverse perspectives and insights that will help all of us address the challenges of economic development and the knowledge-based economy.

Editorial: Go To Market (July 2010) - Dru Lavigne; Corien Kershey (Open Source Business Resource, 2010)
Historically, the concept of going to market is fraught with misinterpretation, doubt, and anxiety. In Canada, the term "go to market" typically means the task of readying a product for market. In this context, it is interchangeable with "commercialization," which is another concept suffering in Canada from a definition that generally does not go beyond a software maker's front door. In other parts of the world, and specifically in the U.S., the term "go to market" is clearly interpreted as meaning all the activities required to successfully launch a product into the marketplace and realize both market share and profit. Going to market is about bringing the right benefit to the right market at the right price through the right channels. Ideally, the entire go-to-market process begins with the identification of a problem or sought-after benefit that a market segment has deemed a priority. More realistically, though, it begins with identifying the segment that best suits the software offering and then determines the business model, positioning and message, pricing, channels, and engagement techniques that will work best in building share in that segment. This issue attempts to take some of the doubt and anxiety from what seems to be the daunting task of pushing a product out of the door and into the harsh realities of a demanding market. It provides clear-eyed discussions of some of the main components, tips and advice from the "battle-scarred," and useful tools that can be readily used.

Editorial: Growing Business (June 2010) - Dru Lavigne; Mekki MacAulay (Open Source Business Resource, 2010)
Growth is important for any business, especially technology companies that operate in an environment of constant innovation, advancement, and evolving consumer needs. It is essential to maintain long term profitability, develop a brand, and attract new investment. But the path to successful growth is not obvious, and is filled with hurdles. Growth requires capital, making consistent revenue a necessity. But figuring out the smartest way to invest capital to promote growth can be a daunting task. Growth can also require some experimentation with different stategies, weathering the occasional failure along the way, in order to find one that is the right fit for the company. But where do you start? Book stores have hundreds of books on business growth, with many promising a surefire strategy for success. But the reality is that there is no single growth formula that works for all businesses. Entrepreneurs must understand what drives their business--something that might be very different from other, similar businesses--and leverage this knowledge in order to grow. Growth requires focus, and energy must be directed on one particular aspect at a time, such as revenue growth, market growth, product line growth, or even shareholder growth. Trying to extend in all directions at once is a sure path to failure. Disciplined, incremental, consistent growth is the formula for success, no matter how that success is defined by the business.

Editorial: Humanitarian Open Source (December 2010) - Chris McPhee; Leslie Hawthorn (Open Source Business Resource, 2010)
In recent years, our increasingly connected world has provided us with a greater understanding of the needs of our fellow global citizens. The devastating worldwide impact of natural disasters, disease, and poverty has been raised in our collective awareness and our ability to collectively alleviate this suffering has been brought to the fore. While many of us are familiar with donating our funds to better the lives of those less fortunate than ourselves, it is often easy to overlook a core component of facing these global challenges: information technology. The humanitarian open source movement seeks to ameliorate these sufferings through the creation of IT infrastructure to support a wide array of goals for the public good, such as providing effective healthcare or microloans to the poorest of the poor. Achieving these goals requires a sophisticated set of software and hardware tools, all of which work to save and improve lives in some of the most difficult of situations where the availability of electricity, data, IT knowledge, etc. may be low or lacking altogether. It should come as no surprise that the humanitarian open source domain attracts a great deal of attention from software developers, engineers, and others who find that they are able to both solve intense technical challenges while helping to improve the lives of others. However, to support ongoing humanitarian needs, the communities who produce humanitarian free and open source software (HFOSS) and hardware have increasingly identified the need for business models to support their efforts. While the lower cost of using open source software and hardware solutions means that more funds can be directed to aid and comfort those in need, the goodwill of developer communities and the funds of grantees alone cannot grow the ecosystem sufficiently to meet ever-growing global needs. To face these challenges - poverty, global health crises, disaster relief, etc. - humanitarian open source projects must fully engage the market and provide cost-effective, efficient solutions to the technical aspects of these challenges. In this issue of the OSBR, our authors from several open source software and hardware projects explore not only the global need for humanitarian open source projects, but also the business cases for humanitarian-focused ICT.

Editorial: Interdisciplinary Lessons (August 2010) - Chris McPhee; Mekki MacAulay (Open Source Business Resource, 2010)
Some believe that great advances, discoveries, and innovation result from concentrated efforts within distinct fields. However, progress using this traditional practice has been slowing for some time. The next great discoveries are unlikely to come from further refinements in highly-specialized fields working in isolation. Rather, they will come from creative collaboration between practitioners and researchers from two or more distinct fields, combining their knowledge, theoretical principles, and methodologies in ways never before considered. This issue analyzes lessons from other disciplines to provide a new perspective on the challenges faced by open source communities, practitioners, entrepreneurs, and other participants. The goal is to extract and apply the collective wisdom of a diverse group of authors to help solve relevant problems. The first two articles in this issue provide specific interdisciplinary lessons from diverse fields that are relevant to open source communities. The remaining articles describe projects in which platforms are being developed to promote, encourage, and analyze interdisciplinary work.

Editorial: Keystone Companies (September 2010) - Chris McPhee (Open Source Business Resource, 2010)
The editorial theme for this issue of the OSBR is Keystone Companies. A keystone company is the member of a business ecosystem that owns, operates, and evolves the platform. The origin of the keystone concept is a good example of the importance of interdisciplinary lessons, which was the theme of last month's issue. In an architectural arch, the wedge-shaped piece of stone in the centre is called the keystone. It is regarded as holding all the other stones in place and the arch would collapse if it were removed. Although most arches would collapse upon the removal of any of the other stones, the keystone is usually the final stone put in place during construction and is required to realize the structural integrity of the arch. Accordingly, in addition to its central physical position in the arch, it has been given a symbolic position of disproportionate importance in relation to the other stones. The strong symbolism of the keystone has lead to the term being applied to other situations and systems where one element exerts disproportionate influence over the other elements and therefore plays a role in maintaining the integrity of the system. In particular, the term has been adopted in the biology literature using the concept of a keystone species in an ecosystem or community. In turn, the concept and its related research have been applied to the management literature where, instead of a keystone species, a particular organization or company plays the role of a keystone in a business ecosystem. In biology, the defining characteristic of a keystone species is that its influence is disproportionate to what might be expected based simply on its total biomass in the community. A classic example is the North American beaver (Castor canadensis), which exerts a disproportionate effect on its habitat through its dam-building activities. Although the "keystone" label is applied to the species, it actually reflects the role the species currently plays within a specific ecosystem. Thus, the keystone concept is context dependent; the importance of a species in one community may be different from its importance in another. The keystone species concept has been the subject of intense debate and research activity over the past 40 years. Biologists wish to identify and study the effects of keystone species primarily to guide conservation management. The keystone species concept suggests that management efforts can be focused on protecting an individual keystone species, and these focused efforts also theoretically provide protection for the other species that depend directly on the keystone or indirectly on the community it maintains. In business management, the keystone species concept proved to be a useful interdisciplinary lesson, but not before another concept was borrowed from biology. The framework of the biological ecosystem concept was first applied to the business management field by James Moore in 1993 when he introduced the term "business ecosystem" in his article "Predators and Prey: A New Ecology of Competition." Moore used this new term to describe an economic community of organizations that co-evolved their capabilities around a particular innovation and work cooperatively to meet the needs of customers. Building on Moore's work, others have extended the business ecosystem concept and suggested that the keystone species concept in biological ecosystems can be usefully applied to business ecosystems. In particular, through their book The Keystone Advantage, Marco Iansiti and Roy Levien popularized the concept of strategically minded keystone companies that, "shape and coordinate the ecosystem, largely by the dissemination of platforms that form a foundation for ecosystem innovation and operations." In this issue of the OSBR, the authors offer different perspectives on a new approach for small technology companies, industry associations and business development organizations to generate revenue. The new approach builds on the keystone company concept.

Editorial: Mobile (March 2010) - Dru Lavigne; Thomas Kunz; François Lefebvre (Open Source Business Resource, 2010)
Open source software and hardware has become an accepted way of developing new and interesting applications in many information and communication technology domains: operating systems, databases, Web infrastructure, and applications. It's not surprising that with the increasing popularity of mobile handheld devices, users and researchers have explored the power of open approaches to providing innovative new applications and services in this domain. However, unlike personal computers and the Internet, mobile handsets were tightly controlled by mobile network operators (MNOs) who developed a vertical ecosystem by integrating the communication infrastructure, the handheld device hardware, and often the applications installed on those devices. The software and protocols running the mobile communications infrastructure and devices are often standardized by membership-only bodies, where large MNOs and manufacturers have a predominant influence. These players invest significant financial resources into shaping the industry along their vision to gain a competitive advantage. A current example is the ongoing battle about the dominant radio access technology for 4G cellular systems: LTE vs. Wimax. These trends have changed recently. Companies such as Google, Nokia, or Openmoko and Industry Alliances such as the Open Handset Alliance are providing the core building blocks, both in hardware as well as software, of increasingly open mobile devices. This issue of the OSBR reviews the relevant trends in the open mobile platform space from a number of perspectives. As the articles in these issue show, there is a lot of exciting ongoing work that brings the power of open source development to the mobile space. This trend is not just confined to the mobile devices as there are also efforts in the development of open mobile infrastructure elements and whole systems.

Editorial: Sales Strategy (2010) - Chris McPhee (Open Source Business Resource, 2010)
The editorial theme for this issue of the OSBR is Sales Strategy. While "marketing" is everything a company does to build interest in its offers, "sales" consists of converting these offers into cash. By "sales strategy," we refer to all sales planning and process development activities leading up to the actual selling of a product or service. In his recent blog post at MaRS Discovery District, Mark Zimmerman answered a question he is frequently asked by the founders of startups: "How do we find a good sales person?" In short, his answer is "Don't." This is not meant as a slight to sales professionals, but rather, Zimmerman is advocating that companies should not equate having sales professionals to having a sales strategy. Sales professionals have a critical role to play in a company's success, but they are being given an impossible task if asked to sell something that has not been validated with customers. Zimmerman explains that sales professionals should be hired only once a company has validated that the value proposition resonates with customers and that the sales model will be effective. This lesson also applies to established companies, where existing sales staff require this same foundation to be effective. So how does a company determine whether its value proposition resonates with customers? The answer, of course, is to talk to customers. In the OSBR and elsewhere, the need for early customer input is a dominant theme in recent discussions of product development, marketing, and now sales strategy. By talking to customers, listening to how they describe their needs, and interpreting how their needs could be met, a value proposition can tested and refined. It is far more efficient and effective to iteratively refine a value proposition before attempting to sell than to attempt a salvage operation in response to slumping sales. Customer input is also a critical ingredient in developing an effective sales strategy. In this issue of the OSBR, our authors provide a diversity of perspectives on sales strategy development and implementation, including the role of customer input.

Editorial: Startups (February 2010) - Dru Lavigne (Open Source Business Resource, 2010)
Bob Sutor, Vice President of the Open Source and Linux division at IBM, recently stated that "there doesn't seem to be very many good guides about the nuts and bolts of starting an open source business". He speculates that one reason is that "there is no one way to start and run a business that involves open source". The authors in this issue of the OSBR are serial entrepreneurs, startup founders, and professionals who provide services to and interact daily with startups.

Editorial: Success Factors (January 2010) - Dru Lavigne (Open Source Business Resource, 2010)
The editorial theme for the January issue of the OSBR is "success factors". Which factors separate the open source projects that provide quality software and receive wide-spread adoption from other projects which are not well maintained? What traits should a business look for when considering which open source software to use? How does a company decide which open source project to contribute to, partner with, or use as a base to build its products or services? The authors in this issue explore: the importance of well defined processes, the value of documentation to end users, the diverse tasks of a community manager, the value provided by participants who don't contribute code, and how a community can assist in creating training materials. Each concentrates on a particular success factor, and as a whole, provide a fuller picture of what to look for in a successful open source project or company.

Emerging Open Source Health Information Business Ecosystems in Resource-Poor Environments: the OpenMRS Experience - Dawn Smith (Open Source Business Resource, 2010)
OpenMRS is a rapidly growing open source community that supports emerging healthcare environments around the world through the collaborative development of an open source medical record system platform. This article provides a brief history of the project, including how the humble beginnings of the collaborative have grown to unlock business opportunities for indigenous populations and also provide sustainable, scalable, locally supported health information infrastructures.

Enterprise Mashups: Cloud-Based, Cloud-Driven and Cloud-Derived Applications - John Crupi; Chris Warner (Open Source Business Resource, 2010)
After Google Maps Mashups launched the mashup craze in 2005, this consumer-based idea quickly evolved, matured and migrated into the enterprise. Structured tools and platforms emerged that codified more formal, repeatable approaches to mashups emerged, including products like IBM Mashup Center, JackBe Presto, and WSO2 Mashup Server. Finally, the emergence of cloud-based hosting platforms and cloud-based data services have given many enterprises access to a richer set of options for mashup creation and deployment. So where are mashups in the enterprise today? The goal of this article is to document and share mashups use-cases. It is also an effort to expand upon the previous OSBR articles Open APIs, Mashups and User Innovation and Mapping Mashup Ecosystems. We hope you find it provides practical mashup implementation examples and patterns collected through empirical and anecdotal research conducted with commercial and government mashup practioners. In the last three years we have performed many formal interviews and surveys with commercial and government mashup practioners in all 50 United States and over 50 countries around the world. The examples in this article are based on the practical implementation examples and patterns collected through this empirical research as well as anecdotal information from our own implementation experiences of 'inside the firewall' and cloud-based mashups. Much of the research cited is based upon data collected from the 3,890 members of JackBe's Mashup Developer Community and that community's Presto Cloud mashup platform running on Amazon EC2. From our research we've learned many things about the ways in which mashups are (or are expected to be) applied. One macro-trend appears to unite all other enterprise mashup trends and patterns: enterprise mashups are most applicable in data-intensive areas of an organization where i) information needs are dynamic; and ii) data must reach the user. Given the explosive rate of data growth in enterprise data in recent years, enterprise mashups can have meaning to just about every organization. The cloud plays a critical role in the relevance and value of enterprise mashups. The value of a mashup increases exponentially as more data sources are incorporated into them. It is easy to assume that the onus is upon data sources inside the enterprise firewall and in the past this was generally true. The recent rapid growth of enterprise-quality cloud-based data sources makes it much easier to establish genuinely meaningful mashups from third-party data services.

Entrepreneurial Growth: An Entrepreneur's Choice - Tomas Marko (Open Source Business Resource, 2010)
Growth is a risky but necessary procedure for startups to survive. Growth may be assessed in the context of employees, customers, revenue, liquidity, profit, geographic locations and a variety of other dimensions. Regardless of the growth type, hurdles always exist. An entrepreneur who understands the risks, and knowingly takes them, will have a chance to grow; whereas one who is not willing to take risks will not. This article describes both the risks and benefits associated with growth. It then examines six hurdles entrepreneurs face when attempting to grow a company: company culture, networks, strategic planning, money, company structure, and skill development.

Establishing and Engaging an Active Open Source Ecosystem with the BeagleBoard - Jason Kridner (Open Source Business Resource, 2010)
There should be little doubt that any given area of technology will eventually be occupied by open solutions. Rather, it is a question of "who" and "when." In mobile and embedded platforms, there is not a single dominant proprietary solution to displace, unlike desktop software. Instead, open software produces interface and compatibility experiences on par with proprietary software. At points where no proprietary solution is clearly differentiated from open solutions and the barriers to participation are kept low, open innovation thrives at the forefront of the technology. This article introduces BeagleBoard, a project that creates powerful, open, and embedded devices based on the BeagleBoard hardware, a low-cost, fan-less single-board computer. By lowering the barriers to participation and making commitments to support and sustain the architecture to preserve the innovation from that participation, BeagleBoard.org has built an active and growing community of hobbyists and professionals advancing the state of the art in low-power embedded computing, here and now.

Experiences From the OSSIE Open Source Software Defined Radio Project - Carl B. Dietrich; Jeffrey H. Reed; Stephen H. Edwards; Frank E. Kragh (Open Source Business Resource, 2010)
This article briefly describes OSSIE, a university-based open source Software Defined Radio project based on the U.S. Department of Defense's Software Communications Architecture. The OSSIE software has proven useful for rapid prototyping by industry as well as for published research and education of hundreds of graduate and undergraduate students and short course participants. In addition to examples of OSSIE's successes, the project's challenges and approaches to mitigating and overcoming them are described.

Fundamentals of a Volume Market Engine - Fred Holahan (Open Source Business Resource, 2010)
This article discusses the unique challenges commercial open source companies face in bringing their products and services to market. It recommends an overhaul of traditional software vendor market approaches in favour of a volume market strategy and identifies the core technology, content, and best practice methodologies of that strategy. The article is organized into five sections. The first section discusses the nature of open source customer relationships. It explains why the traditional sales funnel metrics do not apply in a commercial open source context. The second section introduces the concept of "progressive engagement" and discusses the lifecycle of open source relationships. The third section, multi-channel demand generation, identifies techniques for improving lead flow and quality by incorporating traditional lead sourcing techniques into the volume market model. The fourth section makes the case for marketing automation software and discusses some of the critical elements of an automated marketing infrastructure. The fifth section covers high-value content - the raw fuel of a volume market engine. It offers helpful insights for marketers to build and manage their content portfolios.

Go-to-Market Targeting: Know the Market and Whether It Cares - Corien Kershey (Open Source Business Resource, 2010)
This article explores the importance of good segmenting and targeting to early-stage companies. Most software companies fail within the first three years, and one of the prime reasons is a lack of a focused approach to a single, carefully-chosen target market. Most software companies take the approach of attacking multiple segments simultaneously to see which will work out best, but run out of time and money before they reach an answer. A concentrated strategy that focuses resources on a single segment that the company can win and dominate quickly significantly reduces go-to-market risk. Choosing a segment in the right direction is more important than choosing the right segment. This article provides a series of six steps to help companies work through a segmenting and targeting exercise that will give them the best chance of success. The article provides real-world tools to help deal with an essential issue.

Growing Revenue with Open Source - Mekki MacAulay (Open Source Business Resource, 2010)
To survive, a company must grow revenue from the core of their business. This article describes how open source can be used to help support revenue growth. We suggest seven strategies and provide examples of successful implementations for each.

How the FreeBSD Project's Processes Help Companies Build Products - George Neville-Neil (Open Source Business Resource, 2010)
The processes that open source projects use to produce new work and maintain the quality of their code base is a subject that comes up infrequently in discussions of open source. One reason for this is that engineers and programmers are usually loathe to deal with issues that are not directly related to the piece of code or technology that they are working on. Successful businesses know that good processes lead to continued success. The attributes that attract a business to an open source project are stability, reliability, and longevity. Stability gives a business the confidence to invest time into developing products on the project's platform, safe in the knowledge that the next incremental step in development won't be torpedoed by some unforeseen change. Reliability is often not associated with open source and many projects are perceived as being too cutting edge for a business to build upon. Longevity is of value as many businesses are inherently conservative in their approaches, attempting to reduce the risks of adopting any technique or technology. One way to reduce risk is to work with an open source project that has a proven track record of delivering quality products, on schedule. This article attempts to dispel the myth of the perceived tension between a formally run business and the apparently less formally run open source projects with which a business interacts. We describe how one particular open source project has developed processes which provide its users, customers, and partners with a product that is stable, reliable, and long lived.

How to Add Value to your Business with CEA: A Practical Approach - Daniel Cardenas (Open Source Business Resource, 2010)
Companies are always trying to differentiate themselves from the rest of the pack by applying different strategies such as improving customer service, increasing the efficiency of their operations, or reducing their costs. Most of the time, however, these goals are competing against each other for scarce resources, and managers often need to decide to concentrate on one. A small company can effectively and simultaneously accomplish these goals for a fraction of the cost by implementing communications-enabled business processes or solutions, which are a set of technology components that add real-time networking functionality to applications. One particular implementation of this framework is the one provided by Coral CEA. Coral CEA is a business ecosystem anchored around CEA functionalities that are offered as building blocks, out-of-the-box components that link the capabilities and intelligence of networks platforms with the power of current applications to provide a new set of features and functionalities. In this article, we show how a small company called Rezact, located in the ski resort town of Mont-Tremblant, Quebec, successfully implemented CEA capabilities within its own operations using Coral CEA services.

The Humanitarian FOSS Project - Ralph Morelli; Allen Tucker; Trishan R. de Lanerolle (Open Source Business Resource, 2010)
The Humanitarian Free and Open Source Software (Humanitarian FOSS) Project is primarily an educational project whose goal is to engage more undergraduates in building free and open source software (FOSS) that benefits their community. Over the past four years, increasing numbers of undergraduates and computer science programs have been inspired by the Humanitarian FOSS project to make significant contributions to several active open source software development projects that have benefited organizations such as the Portland, Maine Ronald McDonald House, and the New York City Salvation Army. This article provides examples of several Humanitarian FOSS projects and describes other initiatives aimed at promoting undergraduate education about FOSS and its application within the community.

Humanitarian Free and Open Source Software - Chamindra de Silva (Open Source Business Resource, 2010)
Humanitarian free and open source software (HFOSS) represents the application of free and open source software (FOSS) to the coordination problems faced in the humanitarian and disaster-response domains. FOSS has found a natural home serving the humanitarian domain because of certain problem patterns that promote the use of an open source approach. HFOSS also integrates two volunteer-rich communities that have much in common: the humanitarian community and the open source community. HFOSS is not distinct from the free and open source approach, but is rather a specialization of its principles. This article explores and elaborates on that natural alignment by presenting the concepts of HFOSS and the ecosystem that sustains it.

IEEE Humanitarian Projects: Open Hardware for the Benefit of the Poorest Nations - Glenn McKnight; Alfredo Herrera (Open Source Business Resource, 2010)
An opportunity to solve some of the pressing needs of impoverished nations may be effectively addressed by the active sharing of open hardware solutions. As other articles in this issue of the OSBR demonstrate, open source software is already being used as an effective technology to address humanitarian needs in developing countries. The adoption of open hardware, as an alternative to commercial off-the-shelf products, may be another effective solution to global development challenges. In this article, we will not discuss the socio-economic aspects inherent with global initiatives; but there is a need for meaningful dialogue to come up with appropriate and long-lasting solutions. The focus of this article is on one of the recent activities of the Institute of Electrical and Electronic engineers (IEEE): the Humanitarian Technology Challenge. The Challenge identified three humanitarian problems that could be solved through technology and challenged participants to find an open-source approach to tackle them. The challenges were Reliable Electricity, Data Connectivity, and Personal Identification Records. This article describes the work part of the Reliable Electricity challenge from three perspectives: i) that of the initial HTC Reliable Electricity team; ii) its offspring, called Community Solutions Initiatives (CSI); and iii) an IEEE Canada group called the Humanitarian Initiatives Committee. All of these groups are part of the IEEE.

Implementing a Deal Development Platform for Business Ecosystems - James Makienko; Leonard De Baets (Open Source Business Resource, 2010)
This article describes a project to develop a platform that promotes transactions between customers and suppliers within a business ecosystem. A web-based platform is being developed to track customer interactions and manage the flow of deals through development stages. The solution will be implemented using an open source customer relationship management tool that will be customized to suit the particular needs of a business ecosystem.

Improving Product-Market Fit by Engaging an Open Source Community - Craig Fitzpatrick (Open Source Business Resource, 2010)
While many commercial software vendors still balk at the idea of open source, producing and participating in open source software (OSS) projects can provide significant benefits to a company. One benefit is improving product-market fit. This article introduces the concept of product-market fit. It then provides an example of one startup's experience with opening a portion of their code. Finally, it discusses the importance of building community and some of the motivators of community participation.

Inspired by Open Source and CEAs: The Future of Collaborative Healthcare Delivery in Canada - Andrew Ceponkus (Open Source Business Resource, 2010)
Open source and communications enabled applications are emerging as a vital part of e-Health strategies across Canada. This article provides an overview of lessons learned from our investigation of collaborative telehealth systems delivery in Canadian healthcare. Specifically, the role of open source software and CEAs with respect to pan-Canadian patient record management and telehealth service prototyping are discussed.

Integrating Lessons from Other Disciplines into Open Source Practice - Mekki MacAulay (Open Source Business Resource, 2010)
Open source theory and practice is inherently interdisciplinary. Viewing the challenges faced by open source communities, businesses, and contributors through the lenses of different disciplines can yield novel solutions. This article reviews select lessons from the diverse fields of fashion, gaming, and scientometrics. It examines the way these other industries have addressed issues that are of relevance to the open source community and suggests ways to put these lessons to good use.

Integrating the Power of Open Source Telephony with Web 2.0 Technology - Jean-Pierre Poulin (Open Source Business Resource, 2010)
For technology companies seeking to harness powerful open source technologies, few can argue against the usefulness of modern Web 2.0 platforms. Considering how ubiquitous the Internet has become, an entrepreneur would certainly be ill-advised to not use some Web 2.0 platform to facilitate access to Communication Enabled Applications. This article enumerates the lessons learned by one startup in order to demonstrate the need for a balanced approach to CEA to facilitate access to untapped markets.

Keystone: Adjective or Noun? - Michael Weiss (Open Source Business Resource, 2010)
The gopher tortoise is an unassuming land animal that inhabits sandy regions of the southeastern United States. Like many other desert inhabitants it needs to seek shelter from the heat of the sun. Gopher tortoises are very adept at digging burrows in which they can hide during the peak hours of the day. These burrows offer shelter to many other species that are not able to dig underground. Without the burrows dug by tortoises many types of rodents and snakes would not be able to survive. The existence of the gopher tortoise in its ecosystem affects the health of many other species. The gopher tortoise is an example of a keystone species or keystone. As in biological ecosystems, some companies or institutions in business ecosystems are instrumental for the better well-being of others. They play the role of a keystone. In this article, we examine the question of what makes a keystone a keystone. We introduce two perspectives on that question: one provided by ecology, the other by network analysis. We then review how the term keystone is used by the literature on business ecosystems. Two lessons that readers should take from this article are that the keystone concept, as used by the majority of the business ecosystem literature, is not clearly articulated, and that there are many unresolved issues in applying the concept to business ecosystems.

Keystone Off-The-Shelf - Tony Bailetti (Open Source Business Resource, 2010)
In this article, we describe the Keystone Off-The-Shelf (KOTS), a project to create a toolkit for platform owners. The toolkit will include everything that is required to operate a platform that supports a new approach to grow the revenue of small technology companies. The purpose of this article is to provide an overview of the KOTS project and the new approach to development and commercialization that it supports. We first describe the project's goal, objective, deliverables, and leadership. Next, we compare the new approach to development and commercialization that KOTS supports with two traditional approaches. We then identify the culture that best supports the new approach and provide an overview of the three key conceptual building blocks of this approach: integration of stakeholders' interests into development and commercialization decisions, value co-creation, and trust building. Finally, we provide the conclusions.

Low Cost Cellular Networks with OpenBTS - David Burgess (Open Source Business Resource, 2010)
In mid-2007, Kestrel Signal Processing, Inc., a small software radio consulting shop in northern California, started writing an implementation of a GSM basestation. The initial developers were myself and Kestrel co-founder Harvind Samra. Our goal was to create a new kind of light-weight cellular network that could be built out inexpensively in remote and sparsely populated areas. Our software-radio GSM system, now called OpenBTS, was released publicly under the GPLv3 license in September 2008 and will be used in pilot deployments with small operators by the time this article goes to publication. This will probably be the first use of a free software basestation in a public cellular network, where both network operators and subscribers can download and read the full source code of the GSM protocol stack that connects their handsets to the rest of the world and where the operators will be free to modify the system to meet their specific needs. This article introduces the goals and evolution of the OpenBTS project.

Major Events: Good Economics and Exposure to the World - Bob Yates (Open Source Business Resource, 2010)
Major events of all kinds, especially sport events, are becoming a major element in the competitive arsenal of cities and and their economic development and tourism offices. Major events bring people to the city, provide attractions for residents, and ensure that the city's name is profiled in the national and international media. But they also can involve major infrastructure investment in facilities and amenities, some of which might have limited post-event utility. This article discusses some of the pros and cons of event hosting as an economic strategy and suggests some useful decision-making guidelines.

Mifos: Ending Poverty with Software - Adam Feuer (Open Source Business Resource, 2010)
Free and open source software (FOSS) and business are key elements for solving the largest problems facing humanity. In this article, we focus on the challenge of eradicating poverty, a significant economic condition that affects billions of people worldwide. We outline the role of microfinance - the use of small loans to help poor people establish businesses - in eliminating poverty. We then describe the Mifos Initiative, a FOSS project to provide banking software to support microfinance institutions. Although we focus on the specific case where software is being used to address the problem of poverty, the approach and lessons learned can be applied to other great problems facing humanity.

Migrating an Existing Business to a New Approach to Revenue Generation - Howard Rosenblum (Open Source Business Resource, 2010)
Traditional development and commercialization models take too long, cost too much, and expose founders to excessive risk. A new approach for small technology companies to generate revenue has been proposed by Bailetti. In the new approach, the top management team of a small technology company uses a a platform to co-create value by collaborating with all the stakeholders of its development and commercialization decisions and builds trust on its work practices and market offers. The purpose of this article is to provide the lessons learned from working with a top management team of a profitable business that uses a traditional approach to development and commercialization and wishes to migrate to the new approach. The article will be useful to managers and owners of existing small companies and vendor-neutral, non-profit organizations that wish to grow their businesses. The article is organized as follows. First, a hypothetical situation of a musical band illustrates the options available to a company that wishes to increase its revenue. This example is based on our work with a local technology. Next, we describe the lessons we learned while preparing the plan to migrate the existing company to the new approach to generate revenue. The hypothetical situation is used to illustrate the lessons learned. Finally, conclusions are provided.

A New Engine of Economic Development - Robert Poole (Open Source Business Resource, 2010)
As our global economy shifts from one dominated by production to one based on knowledge, governments are looking for new ways to add value to the people they serve. Open Government initiatives have emerged as one response to these new economic realities. In this article, we discuss how the theory of a multi-sided stakeholder platform can be applied to create an innovative engine of regional economic development. We describe that engine, its parts, and the value that the participants realize from it.

Open is the New Closed: How the Mobile Industry uses Open Source to Further Commercial Agendas - Andreas Constantinou (Open Source Business Resource, 2010)
Openness is a much-misunderstood word. It represents a kind of good-will moniker to which people attach an impressive variety of definitions: open source code, open standards, open handsets, openness as in transparency, shared roadmaps, open application programming interfaces (APIs), open route to market, and so on. It is a very forgiving term as far as definitions go. One of the mobile industry's favourite facets of openness is open source code. Since 2007, tens of mobile industry giants and consortia have embraced open source in some form or other: the Symbian Foundation, LiMo Foundation, Google's Android, Nokia's Qt, Apple's WebKit and Nokia+Intel's Meego are the initiatives that have hit the industry front pages. On the surface, these initiatives use open source licenses, but that only tells half the story. Behind the scenes, Google, Apple, Nokia and others use restrictive governance models and control points that effectively detract the very freedoms that open source licensing is meant to bestow. This discusses the many forms that governance models can take, and how they are used in the mobile industry to tightly control the roadmap and application of open source projects.

Open Source Contributions as a Complement to Your Sales Strategy - Jason Côté; Julian Egelstaff (Open Source Business Resource, 2010)
Freeform Solutions, a not-for-profit IT consultancy, discovered a large portion of its work was being carried out without being paid for directly from consulting fees. This led to an investigation of the nature of such pro bono work, and what value it could provide to Freeform and its clients. Supporting open source communities was determined to be the most significant use of the time possible. Accordingly, Freeform has taken steps to focus a significant portion of its work on that task, and to integrate this work with its overall orientation to clients. This commitment to open source provides a strong differentiator in the marketplace. It also enables one kind of prioritization of sales leads. Ultimately, the commitment to the work is considered the most important aspect of the work, rather than the specific kind of activities that are undertaken, or how they are paid for.

The Open Source Mobile Cloud: Delivering Next-Gen Mobile Apps and Systems - Hal Steger (Open Source Business Resource, 2010)
Cloud computing is gaining acceptance as an efficient and cost-effective architecture to deploy many types of systems. More recently, mobile cloud computing has entered the scene, as an important means to deliver mobile apps and data. This article discusses trends that are driving the adoption of the mobile cloud, important components of mobile cloud infrastructure, and the role of open source.

Open Source Partner Strategy: Are Your Core Businesses Aligned? - Susan Riekki-Odle (Open Source Business Resource, 2010)
Technology companies have historically viewed partnerships through myopic, one-way lenses, asking only: "What can this partner do for me?" This type of thinking is even more pervasive with channel sales partnerships, where technology vendors limit the exploration of value to short term revenue contribution. Vendors must broaden their scope and range of site when embarking on a path of partnership strategy. Ecosystem analysis, economic modeling, and creative go-to-market development are critical components of successful partnership strategies. This article discusses this critical business strategy through a real world example and an overview of best practice.

An Open Source Solution for Startups - William Stewart (Open Source Business Resource, 2010)
Can open source help startup companies reduce cost, save time, and improve their productivity? This article describes the experience of the startup Eseri which spent three years integrating the world's best open source software into a complete turn-key small to medium enterprise information technology solution. Eseri uses their own system to run the company. Having recently launched, they have targeted startups as their most important market segment.

Open Source User Assistance: Ensuring That Everybody Wins - Janet Swisher (Open Source Business Resource, 2010)
This article describes the importance of user assistance to the success of open source projects and offers some suggestions on fostering community contributions to open source user assistance. The term "user assistance" encompasses all the ways that users get help in figuring out how to use a product, spanning the traditional categories of both documentation and support. User assistance provides opportunities for participation by community members who are not software developers. This in turn relieves the burden on developers for filling these roles while broadening the community. Projects should support the differing motivations of members in these roles while providing leadership and direction, removing barriers to contribution, and engaging in concerted efforts. Licensing for open source documentation should likewise be open, to support user freedom and foster community collaboration. Leaders in open source user assistance need to share ideas across projects in order to improve their offerings.

Open to Everyone: How Open Source Communities Can Benefit from Diversity Without Disunity - Teresa Jewell (Open Source Business Resource, 2010)
Open source is at once a type of software licensing, a community model, an ideology, and a social movement. As a movement aiming not only to promote open source software within the software development community, but also to change the attitudes of commercial users, it can benefit from lessons learned by earlier social movements. This article is intended for entrepreneurs, developers, and open source proponents who wish to maximize the market for their products. It will begin with a discussion of the successful strategies and common pitfalls of the feminist movement. It will then apply these lessons to the open source community. Overall, it will discuss the importance of united ideologies, inclusive communities, and the pursuit of legislative changes in promoting open source software as a viable alternative to traditional proprietary software.

OpenOttawaLibre: An Interdisciplinary Approach to Building Creative Cities - Michael Ayukawa; Julie Dupont (Open Source Business Resource, 2010)
OpenOttawaLibre (OOL) is a multidisciplinary approach that is being developed to strengthen Ottawa's position as a creative city. Faced with stiff competition from globally dominant mega-centres, smaller cities like Ottawa can compensate for their size by actively bringing together people to exchange ideas, share perspectives, and form new partnerships to solve existing and emerging problems. OOL will make it easy to organize these events and lower the risk by developing an ecosystem with experienced facilitators, physical resources, and proven processes. OOL is anchored by Ottawa's cultural planning group and aims to make Ottawa a global magnet for creative industries and talent.

Ottercall: A Language Learning Company - Elias Majic (Open Source Business Resource, 2010)
Using computer-assisted speech recognition to evaluate the pronunciation of a speaker, Ottercall provides its customers with feedback on how to improve their language skills. In this article, Ottercall's plan to enter a crowded competitive environment will be described. The article first describes the language-learning market and the points of difference between existing solutions. Next, it will outline the various strategies and decisions considered by Ottercall in developing its market entry strategy. Finally, the lessons learned through this process will be shared.

Performance Testing From the Cloud - Tom Lounibos (Open Source Business Resource, 2010)
This article discusses the opportunities and challenges when leveraging the cloud to performance test large-scale websites and applications. Getting performance right, particularly at web-scale, requires a level of passion that results in both a view of the big picture and an attention to detail. We'll describe how to use the scale of the cloud to gain confidence when deploying sites servicing potentially massive amounts of web traffic. We'll start by describing what we mean by the cloud in order to set context. We'll then describe the components that comprise SOASTA's CloudTest and focus on how we deliver the offering to the market, including a look at the key tenets of the cloud testing methodology based on SOASTA's experiences.

Plumbing the Internet with PostgreSQL: An Open Source Case Study - Ram Mohan (Open Source Business Resource, 2010)
It's no secret that open source software can offer substantial cost savings to startup companies. Anybody with an idea and a limited amount of capital can launch a web-based business and scale it relatively quickly using a simple and robust LAMP infrastructure. But what about startup companies contracted to provide crucial parts of the Internet's plumbing, such as a domain name registry? This article describes how registry manager Afilias deployed open source, particularly the PostgreSQL database management software, at the core of its business from the very outset, allowing it to scale as business grew. It also underlines the importance of actively engaging with the open source community in order to get the most out of your investment.

Private Clouds: Reality or Fog? - Ronald Schmelzer (Open Source Business Resource, 2010)
Product marketers love a bandwagon, and no bandwagons have been more appealing in the past ten years of information technology as the Service Oriented Architecture and Cloud Computing ones. Much of the challenge of marketing products is getting the attention of the target customer in order to create an opportunity to pitch products or services to them. Of course, if it doesn't work with one bandwagon, as the old adage goes, try, try again. This is why we often see the same products marketed with different labels and categories applied to them. Product vendors will insist that they have developed some new add-on or tweaked a user interface to include the new concept, but at the very core, the products remain fundamentally unchanged. It is particularly frustrating when product marketing gets in the way of implementing what otherwise would be a valuable concept. Competing vendor, consultant, and individual implementer messages on what a specific term means interferes with realizing real value. This is especially the case with the emerging concept of private clouds. While the term could potentially have real meaning and lasting value, the product and consulting marketers have turned any potential meaning into mush that hides that value. Cloud computing is primarily loosely-coupled, location-independent virtualized services run on abstracted infrastructure with the primary intent of reducing IT expenditures, increasing flexibility, or improving overall system robustness. Given that this is the general cloud concept, is there any value in a new concept called "private clouds?" How does the addition of the word private add value to the service-oriented cloud computing that has been discussed for a handful of years? Is it a valuable term, or mere marketing spin? This article first examines the range of definitions being applied to the private cloud concept, then offers a summary on the value provided by private clouds.

Q&A. How can a community be considered "open source" if its primary objective is to promote commercialization? - Mike Milinkovich (Open Source Business Resource, 2010)
How can a community be considered "open source" if its primary objective is to promote commercialization?

Q&A. How do you make money with open source? - Tarus Balog (Open Source Business Resource, 2010)
How do you make money with open source?

Q&A. How do you motivate potential participants to pay to join a platform? - James Makienko (Open Source Business Resource, 2010)
A company that operates a multi-sided platform must convince participants to pay an affiliation fee to access the platform. The challenge is to determine what it will take to motivate the participants to pay to collaborate with each other. To motivate participants to pay an affiliation fee, a multi-sided platform must deliver unique value to the various stakeholder groups its sides represent. For example, if a platform is designed to generate revenue from three stakeholder groups: developers, users and researchers, it must deliver unique value to each of these three groups. Developers must receive more value from participating in the platform than the value received from not participating in the platform. The same holds true for users and researchers. To generate revenue, a platform must be designed to deliver compelling value propositions for each stakeholder group. To illustrate how this can be achieved, we will describe five lessons learned while defining value propositions for a technology company.

Q&A. How is social network analysis used in studies of open source? - Chulaka Ailapperuma; Senthilkumar Mukunda; Shruti Satsangi (Open Source Business Resource, 2010)
Social network analysis (SNA) can be used to study online communities, including free/libre open source software (F/LOSS) developer teams. SNA techniques provide insight into these communities and enable researchers to make predictions based on these insights. They can be used to model the nature and patterns of interactions that can be used as a predictor of group behaviour, trust, knowledge generation, and information diffusion (Crowston et al., 2010). SNA can also be used make predictions about other kinds of networks other than pure social networks, such as networks based on relationships between code artifacts. In this article, we answer the question of how SNA has been used to study open source. We begin by describing social networks and how they can be deconstructed to examine the relationships between entities within them. Next, we discuss social networks within F/LOSS communities and describe how SNA gives insights into the various actors and groups acting within networks. Finally, we provide an overview of common SNA measures used to study open source, including examples of how they have been used to provide insights about F/LOSS communities.

Q&A. Should All Women Aspire to Be Entrepreneurs? - Cate Huston (Open Source Business Resource, 2010)
Many authors, in this issue of the OSBR and elsewhere, highlight the relative lack of women entrepreneurs and suggest ways that we can overcome the challenges women face so that we can increase the numbers. However, I wish to offer another perspective. I do not want to be an entrepreneur and I am not the only woman who feels this way. Here, I wish to highlight the importance filling gaps as a form of leadership. This alternative to entrepreneurship is valuable and is also in need of encouragement.

Q&A. What business models are currently used with open source software? - Thomas Prowse (Open Source Business Resource, 2010)
Over the past 15 years, I have seen OSS move from a technological novelty or curiosity to a key foundational element of our information economy. As a technology lawyer, I have found it fascinating to witness the parallel evolution of business models in this space. To answer this question, I will give a broad overview of some of the established and emerging OSS business models that companies, organizations, and individuals are currently using.

Q&A. Which is the better path to take, as a push or a pull startup? - Harley Finkelstein (Open Source Business Resource, 2010)
Which is the better path to take, as a push or a pull startup?

Q&A. Why Is There a Dearth of Women on High-Growth Technology Startup Teams? - Ruth Bastedo (Open Source Business Resource, 2010)
Through my work with women-led startups, I have come to the following conclusion: as an industry, we should be focusing on increasing the number of women on startup teams. We should be ensuring that women team members have an equity stake in the business and have meaningful leadership roles on the management teams. If a woman is President and CEO, that is wonderful, but I feel that it is even more important just to have women present and engaged. I believe that the diversity in viewpoint and life experience that women leaders bring to the table impact the performance of companies in a complex, global, and increasingly interconnected world. This is the world in which Canadian startups have to compete and thrive in order to boost our country's productivity levels. Women have to have a seat at the table, and by being there, have the potential to impact the success of Canadian startups.

Re-evaluating Open Source for Sustaining Competitive Advantage for Hosted Applications - Daniel Crenna (Open Source Business Resource, 2010)
The use of open source in hosted solutions is undoubtedly widespread. However, it is seldom considered important in its own right, nor do the majority of hosted solutions providers contribute to or create open source as natural artifacts of doing good business. In this exploration of the nature of hosted solutions and their developers, it is suggested that not only consuming open source, but creating and disseminating it to collaborators and competitors alike, is essential to success. By establishing an open source ecosystem where hosted solutions compete on differentiation rather than lose time and money to concerns that are expected by users, do not add value, and benefit from public scrutiny, hosted solution providers can reduce the cost of their solution, the time it takes to deliver new ones, and improve their quality without additional resources.

The State of Free Software in Mobile Devices - Bradley M. Kuhn (Open Source Business Resource, 2010)
I started using GNU/Linux and Free Software in 1992. In those days, while everything I needed for a working computer was generally available in software freedom, there were many components and applications that simply did not exist. For highly technical users who did not need many peripherals, the Free Software community had reached a state of complete software freedom. Yet, in 1992, everyone agreed there was still so much work to be done. Even today, we still strive for a desktop and server operating system, with all relevant applications, that grants complete software freedom. Looked at broadly, mobile telephone systems are not all that different from those 1992-era GNU/Linux systems. The basics are currently available as Free, Libre, and Open Source Software (F/LOSS). If you need only the bare minimum of functionality, you can, by picking the right phone hardware, run an almost completely F/LOSS operating system and application set. Yet, we have so far to go. This article discusses the current penetration of F/LOSS in mobile devices and offers a path forward for free software advocates.

Strategies for Selling Services - Patrick O'Halloran (Open Source Business Resource, 2010)
With the service economy on the ascension, companies are yearning for mechanisms to connect their service solutions to their customer's problems, and have the customer acknowledge that their solution is the best. In order to meet these requirements, the foundations of the model used to deploy such solutions need to be concrete. The solution must capture the fundamental nature of the target markets and embody all of the customers' expectations. This article reviews literature that will inform the development of these models and identifies relevant strategies to enable growth options around service-based solutions.

Technical Entrepreneurs Benefit From Business Ecosystems - Tony Bailetti (Open Source Business Resource, 2010)
The objective of this article is to highlight nine creative companies that are part of Lead to Win and describe how they benefit from this vendor-neutral business ecosystem. This paper is organized into three sections. The first section provides an overview on technical entrepreneurship, creative companies and business ecosystems. The second section describes nine startups located in Canada's National Region and identifies how their founders benefit from Lead to Win. The third section provides key takeaway messages about technical entrepreneurship and business ecosystems.

TriSano: Collaborating for the Good of Global Public Health - Mike Herrick (Open Source Business Resource, 2010)
Healthcare and public health continue to experience significant changes, driven primarily due to new legislation and economic challenges. These changes mean that those in healthcare and public health are under pressure to respond differently in order to meet the health needs of the population. Additionally, public health is collaborative, by nature. Epidemiologists, informaticians, public health officials, nurses, and doctors fluidly come together to prevent disease and protect the health of the global citizens. This article explores how collaboration and open source software helps healthcare and public health address their challenges across the globe. It is based on the experiences of the TriSano project from the past three years. It traces the history of the project and the refinement of its business model and product offerings to illustrate how collaboration based on a shared business vision with industry thought leaders leads to sustainable software and communities. Finally, insights are shared from working at the intersection of a humanitarian open source project and the business world.

The Value of Cloud Computing - David Linthicum (Open Source Business Resource, 2010)
The movement to cloud computing is the disruptive change that information technology (IT) departments will soon face as cloud computing begins to have an effect on the modern enterprise. IT managers must learn how to give as well as take information in this new, shareable environment, while still protecting their company's interests. Innovative companies will take advantage of these new resources, such as cloud computing, and reinvent themselves as unstoppable forces in their markets. Those who don't take advantage of this revolution will become quickly outdated, perhaps out of business. This article will discuss what cloud is, and how it can potentially have value within your enterprise. Rather than a hype-driven view of cloud computing, this article will provide you with the guidance you need to get started defining the value of cloud computing.

What's the Value of an Eyeball? Passive Participation in Open Source Ecosystems - Mekki MacAulay (Open Source Business Resource, 2010)
Passive participants in open source ecosystems should not be viewed as leeches as they contribute value to the ecosystem. Every eyeball has value. By better understanding the roles of passive participants in the ecosystem, keystone companies can assign resources, such as community managers, more effectively and better leverage the value these participants create. The next challenge is to better quantify the value of passive contribution. This article discusses how passive participants in open source ecosystems play an important role in value creation in the ecosystem. It examines why the value they add is not well captured by current measures and suggests areas of future research, the outcomes of which would enable keystone companies to better position themselves.

When Small is Big: Microcredit and Economic Development - George Brown (Open Source Business Resource, 2010)
Microcredit - the extension of small loans - gives people who would otherwise not have access to credit the opportunity to begin or expand businesses or to pursue job-specific training. These borrowers lack the income, credit history, assets, or security to borrow from other sources. Although the popularity and success of microcredit in developing countries has been trumpeted in the media, microcredit is established and growing in the United States and Canada as well. Its appeal comes from its capacity to provide the means for those who have the ability, drive, and commitment to overcome the hurdles to self-sufficiency. In this article, the role of microcredit as a stimulant for economic development is examined. First, its importance for the establishment of small businesss is described. Second, the article provides an overview of the general microcredit climate in the United states and the local situation in the Ottawa area. Third, brief stories about individuals who have received this type of loan reveal the human impact behind the economic benefits. Finally, the role of microcredit in funding startups is analyzed in comparison to other sources of available funding. The article concludes with a summary of the benefits of microcredit as a win-win proposition for economic development.

Why Intellectual Property Will Not Save the Canadian Economy - David J. French (Open Source Business Resource, 2010)
Notwithstanding public statements by many individuals, obtaining intellectual property (IP) rights is not the objective that will allow Canadian industry to thrive in the future. The objective for each company should be identifying and delivering relevant innovations that will appeal to consumers and which will also survive in the high-pressure environment of world competition. Surviving in business in the future will increasingly become more of a challenge due to the increasing competence of foreign competitors. Establishing IP rights is a bonus that can make a few companies richer than they would otherwise have been. But most winners will succeed because of their focus on a consumer-based target objective - delivering customer-satisfying products at prices that will displace competitive alternatives - and not because of IP. Obtaining IP rights should not displace the focus from providing value to customers. To survive, that value should be sufficiently innovative so as to place companies ahead of competitors. Businesses will have to continue to innovate in order to stay ahead of competitors. If some businesses can acquire the comfort of meaningful IP protection, that will be a plus. However, a business has to have good fundamentals to survive and to thrive.

Youth Entrepreneurship: Ottawa's Portfolio in Talent Development - Sonia Riahi (Open Source Business Resource, 2010)
Youth's natural disposition for innovation and change make young people well suited for entrepreneurship, provided the community can give youth the right support to overcome their challenges and improve their odds of success. A city's economic development benefits from youth entrepreneurship in terms of employment creation, product and service innovation, market competition, community revitalization, and income generation. Youth entrepreneurs face greater challenges then adult entrepreneurs, and therefore would benefit from talent development programs to support them with skills, mentoring, networking, and access to resources in order to increase their rate of success. This article looks at the youth entrepreneurship programs available in Ottawa, examines how they rate, and identifies some opportunities for improvement in the delivery of programs.

The 100-Mile Client Roster - Emma Jane Hogbin (Open Source Business Resource, 2009)
In 2005, two Canadians began a one-year experiment in eating only locally grown foods and started what is now known as The 100-Mile Diet. In the open source world, we know about giving back to our software community, but this is sometimes to the detriment of our physical community. It is hard to see the businesses around us when so many interactions take place online and in the digital neighbourhood. The world has gotten smaller in the last hundred years and products made on the other side of the world are common in businesses and households. As we muddle through our current economic crisis, we are encouraged to support our neighbours, their jobs, and to "buy local." Many household repair services must be locally obtained, but this is not necessarily true for software-related services. Many businesses are choosing to outsource the production of software and related support services to a cheaper labour force in other countries. As consumers, we know that buying locally often costs a premium; we also know it supports our neighbours and recycles our money back into our own physical community. This article examines the importance of giving back to the local community. It uncovers ways for businesses to expand and gain new revenue streams when they focus on open source software and use open business models.

Accelerating Successful Technical Entrepreneurship - Peter Carbone (Open Source Business Resource, 2009)
Technical entrepreneurship is often associated with innovation, research and invention. However, the motivation for entrepreneurship is the creation of wealth and commercialization of an idea. Wide scale disruptions in the economy, consolidations in industry, and the shift in value towards applications and applied technology create new challenges for the entrepreneur and the need for new business approaches to commercialization. Business ecosystems can effectively address these challenges. This article describes Coral CEA, the keystone of a worldwide ecosystem anchored around the commercialization of communication enabled applications. The vision of Coral CEA is to create new companies and knowledge jobs by implementing new commercialization models and driving massive innovation that is linked to commercialization.

Applied Collaboration Studios: Transforming Complex Problems into Systems of Continuous Social Innovation - Stephen Huddart; Anil Patel (Open Source Business Resource, 2009)
This paper asserts that the voluntary or social sector plays a pivotal role in generating and disseminating social innovations through collaboration with diverse partners. The authors explore the potential to engender a quantum shift in the sector's efficiency, reach, and impact through the combined use of open source technologies, social process tools and collaboration platforms. The objective is to contribute to a new generation of intelligent social systems, enabling an evolutionary recalibration of relationships among ourselves, our social and economic institutions, and the planet. As a means of integrating and disseminating the most promising approaches, the concept of Applied Collaboration Studios is proposed. Its primary activities would be: i) dissemination of open source technologies; ii) ongoing instruction and coaching in the use of social process tools; iii) the assembly and launch of multiple collaboration platforms; and iv) collaboration with other like initiatives to create ecologies of scale that inform and precipitate systems change toward greater resilience. The paper concludes with a reflection on the conditions necessary for such a project to come into being as an open source initiative, and an invitation to contribute to an ongoing discussion.

The Arrival of the Mobile Internet Thanks to the Economics of Open Source Software - Stephen R. Walli (Open Source Business Resource, 2009)
The promise of the mobile Internet has been long in coming. In 1992, then Apple CEO John Sculley was promising this "pocket-sized digital communicating devices" market would be "the mother of all markets", while Intel CEO Andrew Grove called it "a pipe dream driven by greed." Since then the mobile phone business has exploded, and personal digital assistants like the Palm Pilot have burst onto the scene. The launch of the RIM Blackberry brought a real email interface to the PDA world. The World Wide Web itself continues to grow enormously, with Netcraft's December 2008 survey receiving responses from 186,727,854 websites. We are just now arriving at a convergence in the market that is 16 years in the making. Handset and PDA manufacturers, mobile network operators, chip manufacturers, and computer platform hardware and software vendors all collide with the economics of the Web, collaborative development, and open source software. Indeed, we are seeing a point in history in which the mobile handset manufacturers and their partners are using open source software and collaborative development to ensure they do not get trapped in the narrow margin price war that caught the personal computer original equipment manufacturers in the previous technology wave.

The Benefits to ISVs of Working with Large Enterprise Consumers on Open-Source Projects - Kingston Duffie (Open Source Business Resource, 2009)
Selling software to consumers is tough as they want perfection and expect to pay nothing. Consumers are fickle and the competition can be fierce. By comparison, large enterprises have big problems and buckets of money to spend on solutions, allowing you to focus your marketing on a small target. While large enterprises sound like ideal customers, the small independent software vendor selling to a large enterprise faces long sales cycles, extreme quality expectations, challenges integrating into a complex jungle of pre-existing systems, and the need to partner with others to create a complete solution. At Fanfare, we believe that there are a variety of successful software business models that employ open source strategies. One such strategy is to sell closed source solutions constructed on top of an open source platform. In fact, the Eclipse Foundation considers enabling this kind of business model as one of its mandates. We sell a complete system test automation solution that is built on top of Eclipse and sold to customers as a "turnkey" solution using Eclipse's Rich Client Platform technology. In this article, we examine six benefits of this approach. Some of these benefits apply to any ISV, but many are specific advantages for ISVs selling into large enterprises.

BIRT: Building Next Generation BI Using Open Source - Tom Bondur; Jason Weathersby (Open Source Business Resource, 2009)
The Business Intelligence and Reporting Tools Project is a highly successful open source business intelligence (BI) project developed and released as part of the Eclipse ecosystem. In this article, we look at the genesis of the BIRT project, why Actuate chose the open source development model, and the benefits that this project brings to the BI user community.

BSD Advocacy and Breaking Through Market Barriers - Melanie Groves VonFange (Open Source Business Resource, 2009)
Currently, proprietary businesses dominate the operating systems market. In 2008, Microsoft Windows controlled 87.9% of the market with Mac OS X following up with 9.73%, leaving only 2.37% of the market to open source alternatives. However, in the past year alone, Linux market share has grown from .80% to 1.02% (a 27.5% increase) and other open source operating systems have grown from .22% to .58% (a 163% increase). These figures translate into millions of open source operating system users. The question is how to continue these upward trends and break the stranglehold that proprietary operating systems have on the markets. This article discusses the role that open source advocacy plays in increasing open source usage.

Business Intelligence: A Primer - John Kemp; Benjamin Dietz (Open Source Business Resource, 2009)
This article provides a primer on business intelligence (BI) and serves as an introduction to the concepts used throughout the rest of the articles in this issue of the OSBR. We define BI, discuss the components of a BI solution, explain the types of BI tools and provide a brief overview of the evolution of BI.

Co-creation: a New Way of Doing Business in an Age of Uncertainty - Anna Kirah (Open Source Business Resource, 2009)
Co-creation can be defined as the continual feedback loop and collaboration with all stakeholders in a value chain throughout any given process of designing, developing and implementing meaningful products, services, organizational and strategic changes. It replaces the hierarchical approach to management and the linear approach to innovation, affording all stakeholders the possibility to influence and bring forth meaningful and relevant solutions in a collaborative environment. Co-creation results in the development of goods, services and experiences that are uniquely designed to meet people's particular needs, values, meaning and context. It leads to a profitable advantage for both companies and the people who will be using these goods and services as well as for the people working within the organizations. The purpose of this article is to share some experience -driven insights on how co-creation could help businesses to live in an age of uncertainty.

Collaborating Across Disciplines - Joseph Wilson (Open Source Business Resource, 2009)
Anecdotal evidence suggests that truly innovative ideas and successful adaptation to market conditions comes from collaboration with people across traditionally demarcated fields of study. In science, economics, and business, it is new ideas that are imported from other realms that are most successful in affecting change. The Treehouse Group is a Toronto-based collective of thinkers from a wide variety of backgrounds that seek to subvert the traditional notion of what constitutes a conference or a networking opportunity by using a wide variety of brainstorming techniques and cross-disciplinary activities to engage participants.

Collaborative Software Development in the Enterprise - Ian Skerrett (Open Source Business Resource, 2009)
Open source has been many things to many people. In most cases, open source software has focused on the tools and the infrastructure software used to build and deploy applications. Relative to infrastructure, little use or investment has occurred in the development of industry specific or vertical oriented open source solutions. This is not only a missed opportunity for organizations, but it is also possibly the next wave of open source collaborations. An important lesson of OSS is a development process that requires collaboration between individuals and organizations that isn't necessarily driven by a traditional hierarchy of command and control. Information technology departments are driven to be more efficient while simultaneously creating innovative new solutions to meet their business needs. More and more, companies are turning to external sources for ideas that drive innovation. A series of books by Henry Chesbrough has coined the term "innovation networks" to discuss research and development departments that treat their research and development systems as an open system. They describe how to include partners, customers and even competitors as part of an extended research and development team. However, that series does not answer the question "can OSS can be used to establish innovation networks for IT departments?". Further, what steps are required to establish a successful software innovation network and what are the resulting benefits for organizations? For the most part, this article will draw upon the experiences of Eclipse open source projects. These projects often include competing independent software vendors that collaborate on building a common platform for developer tools integration.

Community-Built Software: What I Learned from Calagator - Audrey Eschright (Open Source Business Resource, 2009)
Many open source projects start with a single developer trying to scratch an itch by making a new tool for their own use. But what if the need to be addressed is bigger, and affects more people? How can the creation of open source software involve a whole community? At the start of 2008 I decided to build a solution to an ongoing problem in my hometown of Portland, Oregon. Portland's growing technology scene was having trouble tracking all of the user groups, meetups, and events that people were planning. I started a central calendar using Google Calendar, but found it hard to maintain. People planning the events needed the ability to make their own updates without me having to add them individually as users. A single, central information source that would be completely open to the community at large was needed. The solution became an open-source calendar aggregator called Calagator. The process of creating that solution became a very rewarding community-building effort. By trying different things along the way, we learned how to organize an open source project to encourage community development, and code sprint practices for group work sessions, and worked with a number of tools that make collaboration easier.

Components of Co-creation - Stephen Allen; Tony Bailetti; Stoyan Tanev (Open Source Business Resource, 2009)
Value co-creation is an emerging innovation, marketing and business paradigm describing how customers and users are seen as active participants in the design of personalized products, services and experiences. Often this participation is organised via the Internet to enable the opportunity for customers to integrate their knowledge, experience and skills into existing, modified or entirely new market offerings reflecting their personal preferences, needs and contexts. There is a growing body of literature dedicated to the discussion of value co-creation frameworks, mechanisms and processes. However, these typically focus on the study, discussion and analysis of a small number of cases using deep, ethnographic description of their practices aiming at conceptualization and categorization of the different types of interactions between end users, the firm and the value network. Although useful, such an approach misses the advantages of an empirically driven quantitative approach that benefits from larger size samples and is more appropriate for theory building through the development and testing of hypotheses. It is important, therefore, to seek the development of a research methodology that combines the benefits of both qualitative and quantitative research approaches for studying the nature of value co-creation. The article provides a first attempt to identify the main research steps of such a methodology. It provides some preliminary results on the key components of value co-creation between firms and end customers based on the application of web search and Principal Component Analysis (PCA) techniques. The analysis of these preliminary results is then used as an opportunity to identify a number of research questions to be addressed in future research. The emerging research questions follow the inner logic of the value co-creation phenomenon as well as the nature of the results reported in this article. The specific nature of the results was found to be suitable for the application of small-N techniques such as the Qualitative Comparative Analysis (QCA) technique which combines the advantages of both qualitative and quantitative techniques. One of the main contributions of this article is to suggest and explore the possibility for using the QCA technique in future research on value co-creation.

Developing a Portal for Open Source Creation: A Brief Study - Karen Opas-Lanouette (Open Source Business Resource, 2009)
This article discusses the historic genesis of one company's development of a portal and platform system that enables creators and their fans to work collaboratively between different mediums such as sequential art, graphica, concept, gaming, film/TV, and music. We examine challenges that arose and which are common to many startups. These include the protection of the intellectual property rights (IPR) of all parties, using open source software development to develop the portal, and the financial and personal toll that arises over the course of a startup?s journey.

Economic Free Software Perspectives - Carlo Daffara (Open Source Business Resource, 2009)
"How do you make money with free software?" was a very common question just a few years ago. Today, that question has evolved into "What are successful business strategies that can be implemented on top of free software?" To properly answer this question, it is important to distinguish between the legal, procedural and business model aspects of free/libre and open source software, and how those aspects interact. For example, the licensing aspect influences the development strategy, the kind of development community that can be created around a project, and the potential business models that can provide a monetization strategy for a company that is interested in adopting an open source project as part of the internal company strategy. This article provides the most recent results from the FLOSSMETRICS project and its recent survey of the business model of more than 200 open source companies.

Editorial: Arts & Media (October 2009) - Dru Lavigne; Anthony Whitehead (Open Source Business Resource, 2009)
The editorial theme for the October issue of the OSBR is arts and media. While code development is often described as an art form, it is less common to see a connection between traditional arts and open source. The articles in this issue explore that connection and the nascent possibilities for content creators, user communities, and entrepreneurs.

Editorial: Business Intelligence (September 2009) - Dru Lavigne; Sam Selim (Open Source Business Resource, 2009)
For the past decade, traditional proprietary tools from Cognos, Business Objects, Microstrategy, Hyperion, Oracle and Informatica have dominated BI environments throughout North America and Europe. The larger the customer it seemed, the bigger their appetite for spending money on proprietary BI tools. BI vendors have made billions selling software to larger clients throughout North America, much of it in the form of multi-million dollar site licenses. Large customers continue to pay huge perpetual annual maintenance fees, usually 20+ % of the initial license cost. Costs for additional users and new features requiring additional license fees can quickly add up to 40% - 50% of the annual BI budget. This has caused many organizations to scrutinize and question the value of their ongoing BI software expenditures. In these challenging financial times, cost conscience CIOs and Directors around the world are looking for ways to reduce the ongoing costs of administering their BI program, and a large number of them are turning to open source BI tools.

Editorial: Collaboration (July 2009) - Dru Lavigne; Stephen Huddart (Open Source Business Resource, 2009)
The editorial theme for the July issue of the OSBR is "collaboration". While online collaboration has been a hallmark of open source software (OSS) communities, the articles in this issue demonstrate that open collaboration extends far beyond the creation of software. The authors discuss diverse collaboration opportunities including: brainstorming across disciplines, social innovation, aggregating non-profit donations, the green environment movement, open educational resources, introducing students to communities, and managing single-user software applications.

Editorial: Commercialization (February 2009) - Dru Lavigne (Open Source Business Resource, 2009)
The number of market offers that rely on open source to generate companies' revenues is increasing. Open source has transformed how we develop software, hardware, content, and scientific knowledge. It is now transforming how we commercialize the market offers that generate revenue for companies that rely on open source projects. Commercialization is the theme of the February issue of the OSBR. The focus is on how new market offers that use open source to make money.

Editorial: Enterprise Participation (January 2009) - Dru Lavigne; Donald Smith (Open Source Business Resource, 2009)
In The Role of Participation Architecture in Growing Sponsored Open Source Communities, Joel West and Siobhan O'Mahony argue that "to some extent, firms and technical communities have always collaborated to create standards, shared infrastructure, and innovation outcomes that are bigger than any one firm can achieve." and that "there is increasing evidence that path breaking innovations cannot occur without a community to interpret, support, extend and diffuse them". When considered in this light, it should not be surprising that more enterprises, both large and small, are increasing their participation in open source communities to drive innovation. The theme for this month's issue of the OSBR is enterprise participation and the authors provide practical advice for effective enterprise/community collaboration. Their experiences provide perspectives on: i) the Eclipse Foundation, which maintains an ecosystem of over 150 enterprises that participate in Eclipse open source projects; ii) an independent software vendor that sells closed source solutions constructed on top of an open source platform to large enterprise customers; iii) the impact of major players collaborating on a common open source platform for the mobile industry; iv) the role users can play in the very large (over 14 million) GNOME community; and v) the lessons a scientist from the National Research Council of Canada learned when he released software and started a small open source community.

Editorial: Geospatial (March 2009) - Dru Lavigne; Dave McIlhagga (Open Source Business Resource, 2009)
The recent emergence of MapQuest, Google Earth, Garmin GPS, and many other modern geospatial products make it seem that mapping technologies are a relatively new component of today's information technologies. In fact, the mapping industry was one of the original adopters of technology when geographic information systems were first developed over 40 years ago. The fruits of this backroom technology, once the domain of highly trained specialists, is now being leveraged by hundreds of millions, if not billions, of consumers around the world. Open source geospatial technologies have followed this same path from niche technology to mainstream component and are now critical to many of the applications that business and consumers use on a daily basis. Google Earth, for instance, incorporates a critical component of the open source geospatial stack to deliver satellite imagery to several hundred million installations around the planet. In the following articles, you will learn more about how these critical niche technologies have evolved from small grassroots activities to thriving technology projects under the umbrella of the Open Source Geospatial Foundation, and ultimately into key commercial components of industry.

Editorial: Open APIs (April 2009) - Dru Lavigne; Michael Weiss (Open Source Business Resource, 2009)
A few short years ago, the term "Internet" reflected the technical savvy sitting at a workstation reading email or using a search engine to find data. Today, people of all ages are using all manner of devices to: obtain public transit directions with Google Maps, share photos using Flickr and videos using YouTube, Tweet their whereabouts, meet new friends through Facebook, and perform countless other activities which have quickly become ubiquitous to every day life. This new generation of online activities is the result of open APIs, mashups, and rich Internet applications. These concepts are the focus of the April issue of the OSBR. The authors have done an excellent job of taking the editorial theme of "Open APIs" from the mysterious realm of programming into their applicability to daily life and business.

Editorial: Open Source in Government (May 2009) - Dru Lavigne; James Bowen (Open Source Business Resource, 2009)
Last summer, the Center for Strategic and International Studies published the sixth update to their Open Source Policy survey. The survey "tracks governmental policies on the use of open source software as reported in the press or other media." The report lists 275 open source policy initiatives. It also breaks down by country and by government level whether the policy on the use of open source is considered to be advisory, preferential, or mandatory. The editorial theme for the May issue of the OSBR is "open source in government" and we are pleased that the authors have drawn upon their experiences to provide insight into public policy regarding open source for many parts of the world.

Editorial: Tech Entrepreneurship (August 2009) - Dru Lavigne; David Hudson (Open Source Business Resource, 2009)
Entrepreneurship is the lifeblood of any technology business and really describes the character of those who would see their new ideas achieve commercial success. That character includes: risk taking and the ability to deal with uncertainty from many quarters, creativity and the ability to connect ideas in surprising ways, orchestration and the ability to marshal resources, and the ability to deliver a message with impact whether in the proverbial elevator or when the customer is listening to best and final offers. There is so much required of an entrepreneur, in some ways it is surprising that we have any at all. I've recently had the opportunity to witness a wide variety of entrepreneurs in action through the Lead to Win program. Lead to Win was started to assist innovation and entrepreneurship in the Canadian National Capital region. The program is certainly a response to the economic times and recognizes that when the tech sector is depressed, people who might otherwise find employment in established companies are more likely to start a business of their own. Lead to Win is designed to help entrepreneurs who have a deep technology background but need help building out some of the other dimensions of that entrepreneurial character. It has been a great pleasure to discover that the demand for Lead to Win has exceeded our expectations easily by a factor of two or three. The diversity of people, technologies and market opportunities that have come forward in what is often described as a government and telecom town is extremely encouraging. The patterns and themes in this diversity have the prospect of tapping into existing ecosystems and creating entirely new ones. This notion of entrepreneurship and how it unfolds in established and new fabrics of companies and customers is the centerpiece of this month's issue of the OSBR. Successful entrepreneurs do not exist in isolation and are able to see massive opportunity by leveraging those around them.

Editorial: Value Co-Creation (December 2009) - Dru Lavigne; Stoyan Tanev (Open Source Business Resource, 2009)
The December issue of the OSBR continues our discussion on the topic of value co-creation. According to Prahalad and Krishnan, most of the succesful companies in 2015 will be using value co-creation practices and companies that do not make the efforts to adopt such practices will soon lack a serious competitive advantage. Business models based on value co-creation are not simply adopting a new possible way of doing business. Value co-creation business models follow the way society goes and missing this tendency might be critical for businesses. The key danger is to try seeing value co-creation within the context of our old thinking. This is an easy human mistake that could lead to the wrong questions to answer. In exploring value co-creation, we have not discussed all the possible answers, but have set a stage for finding the right questions.

Editorial: Value Co-Creation (November 2009) - Dru Lavigne; Stoyan Tanev (Open Source Business Resource, 2009)
The relationship between companies that produce and distribute goods and the consumers who purchase and use those goods is often portrayed as "us vs. them". While technology provides the tools needed for communication and collaboration, company-consumer collaboration is often met with skepticism. Is it possible for companies and the users of their products to form mutually beneficial relationships that create value? The concept of value co-creation attempts to answer that question and it is the editorial theme of the November and December issues of the OSBR. Co-creation: New pathways to value reminds us that "It is...the quality of the relationship that companies form with and facilitate among their customers, which will determine how knowledge is created, shared and transferred". The authors in this issue introduce us to who is involved in these relationships, their motivations, and techniques.

Editorial: Women in Open Source (June 2009) - Dru Lavigne; Rikki Kite (Open Source Business Resource, 2009)
Whether you look at industry studies, online articles, or perhaps even around your own company, you'll see that women make up a small percent of the people working in free/libre and open source software (F/LOSS). Over the years there's been a growing interest in why so few women participate in this rapidly growing community and, more importantly, what can be done to help encourage more participation. Fortunately, members of the community - both male and female - are actively ramping up their efforts to attract more women to the F/LOSS community. Resources such as LinuxChix.org, the Geek Feminism Wiki, as well as publications, blogs, and articles written by and about women, draw attention to this growing, influential group of F/LOSS participants. Events, such as the Women in Open Source track at the Southern California Linux Expo, help women network and connect with other members of the F/LOSS community, while also increasing their visibility. In this issue of the Open Source Business Resource, innovative, energetic women discuss their specific projects, what other women in the field are doing, and their efforts to promote F/LOSS to people within their communities and internationally.

The Emerging Promise of Business EcoSystems - Peter Carbone (Open Source Business Resource, 2009)
This article highlights the relevance of new business models and ecosystems in the knowledge-era economy. We begin with an introduction then argue that the shift in what is valued drives the need for new business models. The third section provides examples of innovative business models. The fourth section describes two key roles in an ecosystem: keystone and niche player. Finally, the last section provides the conclusions of this article.

Enabling Geospatial Business Intelligence - Thierry Badard; Etienne Dubé (Open Source Business Resource, 2009)
Recently, interest in the huge potential of Geospatial BI has increased. It aims at combining geographic information system (GIS) and business intelligence (BI) technologies. Geospatial BI combines spatial analysis and map visualization with proven BI tools in order to better support the corporate data analysis process and to help companies make more informed decisions. BI is a business management term which refers to applications and technologies that are used to gather, provide access to, and analyze data and information about company operations. BI applications are usually used to better understand historical, current and future aspects of business operations. BI applications typically offer ways to mine database- and spreadsheet-centric data to produce graphical, table-based and other types of analytics regarding business operations. BI systems give companies a more comprehensive knowledge of the factors affecting their business, such as metrics on sales, production, and internal operations, in order to to make better business decisions. Be aware that BI is a different from classical databases and much more complex. This article provides a rapid introduction to some important BI concepts. It then highlights the need for geospatial BI software and deals with the integration of the spatial component in a BI software stack in order to consistently enable geo-analytical tools. We then present different works performed and tools designed by the GeoSOA research group.

Enabling the Creative Entrepreneur: Business Ecosystems - Brian Hurley (Open Source Business Resource, 2009)
To paraphrase John Donne, "no business is an island". Any business is part of a complex ecosystem that includes suppliers, customers, partners, and competitors. A successful business is able to leverage its connections within the ecosystem to its advantage. This article provides an overview of business ecosystems and how they provide opportunities for creative entrepreneurs to foster economic development and wealth creation.

Entrepreneurship in an Established Company - John Boden (Open Source Business Resource, 2009)
There are some fundamental differences between how you go about being innovative in a startup and how you go about it when you have more than 350 customers in 75 countries already running their business on your product. Put another way, you have to approach entrepreneurship differently when you have over 2,000 active deployments serving 40 million people every day. We faced that challenge at Movius Interactive Corporation. This article provides a description of how we took on the challenge of revitalizing innovation and entrepreneurship and how open source plays a part.

The Expanding Role of Entrepreneurs in the Creation and Development of Internet Ecosystems - Gordon Quinn (Open Source Business Resource, 2009)
Technology-based ecosystems are everywhere. Consumer Internet-based ecosystems are almost always very large scale entities because the Internet has few real boundaries. The center of these ecosystems is often a large company that is a household name and has played a significant role in creating, or at least shaping, the market segment its ecosystem serves. Because of this, Internet ecosystems are often thought of as the exclusive domains of large established companies. In the past that was typically the case, but tech entrepreneurs are now increasingly able to act as the driving force behind the creation of Internet-based ecosystems. Entrepreneurs are moving into the role of ecosystem creation and development, and the established big companies are evolving to a supporting role of ecosystem enabler, investor, and operator. This article will review and contrast the roles of tech entrepreneurs with the roles of large established Internet companies in the creation and development of consumer Internet ecosystems.

The Feds are Ready for a Change - Mike Gifford (Open Source Business Resource, 2009)
Canada is at the tipping point for acceptance of open source. Open source software and culture has reached a critical mass in the business world and it is also being actively deployed within the Canadian government. While open source has contributed outstanding code, its impacts are even more profound, raising core values of participation, co-operation and standardization. However, like many large institutions, there has been reluctance to modernize its official position regarding this approach to software development. There is still considerable investment in existing procurement practice and thousands of jobs and billions of dollars are being invested in old information technology (IT) solutions. This article discusses the global momentum in federal government departments to support open source as well as some of the problems with the federal government's procurement process. However, despite the problems and relatively slow adoption of open source technology, there is movement for adoption. Federal government policies may be lagging behind other G7 governments, but it is being implemented across the civil service. There are also many people within government, at all levels, who understand the advantages of using open source.

First Steps towards Mapping the Economy's Genome - Evan Andrews (Open Source Business Resource, 2009)
Companies are increasingly being pressured to be green, although it is not always clear what this means. Upon closer examination, the concept of green can be seen as an emergent quality of the interactions between many companies, many chemicals, and our environment - all driven by our collective purchases. This tangled web can be better understood with the right analysis methods, software, and data, but these resources are currently scarce and expensive. The intellectual capital companies need to navigate this landscape can be quickly dispersed if they encourage the construction of an open environmental infrastructure of tools and data. This article discusses the analysis methods, software, and data that can be used to help companies, the economy, and society become greener, faster.

F/LOSS is Commercial Software - David A. Wheeler (Open Source Business Resource, 2009)
Many people mistakenly use the term "commercial software" as if it was the opposite of Free/Libre Open Source Software (F/LOSS). This is in spite of: i) the rise in commercial development and support for F/LOSS; ii) the goal of most F/LOSS projects to incorporate improvements, which is actually a form of financial gain; iii) official definitions of "commercial item" that include F/LOSS; and iv) F/LOSS licenses and projects that clearly approve of commercial support. In reality, there are two types of commercial software: proprietary software and F/LOSS. This paper provides examples for each of the four points mentioned above, briefly notes some alternative terms, and ends with some conclusions, and explains why it is important to understand that F/LOSS software is almost always commercial.

Freely Licensed and Open Source Pipelines for Art Based Film and Media Production - Anthony Whitehead (Open Source Business Resource, 2009)
Given the number of free/libre and open source licensed tools, and the number of "no cost" applications at the fingertips of the artist/animator/film developer today, the ability to "create what you will" is now an option for everyone. The advent of affordable media development tools has opened up the world of media production to those who were previously locked out of the Hollywood studio system. Proprietary software including Adobe Creative Suite, Autodesk?s Maya, Nuke, After Effects, Final Draft, and a litany of other necessary tools creates a financial wall so high that ?will? cannot overcome it alone. In this article, we examine a standard pipeline from a birds-eye-view for anyone with a will to create an Indie film. Without breaking the bank, the entire pipeline is achievable using F/LOSS tools and content that is available under a creative commons license. This allows high quality media development for all. In many cases, these same tools are being used by the Hollywood elite.

Geospatial: An Open Source Microcosm - Paul Ramsey (Open Source Business Resource, 2009)
Open source has seen great success in general information processing, but does it have a future in vertical markets? In this article, we examine how geospatial open source provides an example of the market challenges of a mid-sized vertical market.

Geospatial Primer: in Search of the Next "Killer App" - Andrew Ross (Open Source Business Resource, 2009)
Soon after Codd wrote his paper on relational algebra in 1970, relational databases significantly changed the way people manage data. Today, relational databases are the workhorses of enterprise data storage. Similarly, imagine a world without email or the Internet. What will the next "killer app" or "killer service" look like? What kinds of attributes and features will it provide? In this article, we provide a primer on geospatial technology. We then explain possible reasons for growth in the geospatial industry, examine Ingres' geospatial project, and relate the material to learnings about open source as a protocol for business.

The GNOME Foundation Is All About People - Stormy Peters (Open Source Business Resource, 2009)
As open source projects mature, they tend to join or create foundations which manage the project's financial and software assets, provide a marketing and legal entity, and sometimes help to set the direction of the project. As non-profit organizations, foundations have a specific structure defined by the jurisdiction in which they were formed. This structure typically includes a volunteer board of directors and sometimes paid staff such as a secretary or executive director. As Executive Director of the GNOME Foundation, I am often asked "what do you do?". This article will introduce the structure of the GNOME project and its Foundation, describe how the Foundation works to support the GNOME project, and discuss the roles of the people within the GNOME Foundation.

Government Transparency via Open Data and Open Source - Jennifer Bell (Open Source Business Resource, 2009)
Industry analyst Gartner describes web services based on open government data as having a "greater potential effect on the ability to transform government than anything else in the Web 2.0 world". In his technology platform, Barack Obama has made groundbreaking promises related to increasing government accountability by: i) publishing data in open formats; and ii) using online tools to involve citizens in government decision making. These transformative ideas have not yet spread to politics in Canada. As citizens, we trust that money is being wisely spent on the systems that run our country. We trust that the people governing us have the skills, time, and information they need to make the best decisions. We trust that bureaucracies are well-designed and that the people in them are motivated to make those bureaucracies better. Unfortunately, it's hard to trust what you can't see. By publishing information in open, machine-readable formats, governments can take a powerful step towards building public trust. By sharing information, governments can start to channel the expertise of the citizenry outside of the civil service to build more effective and inclusive ways of running the country. The non-profit VisibleGovernment.ca is working to make online tools for civic participation based on open government data a reality in Canada. This article describes why open government data is not only a requirement for greater government transparency, but also a valuable investment in our country's infrastructure.

How Companies Make Money Through Involvement in Open Source Hardware Projects - Edy Ferreira; Stoyan Tanev (Open Source Business Resource, 2009)
The study of open source software (OSS) development and business strategies has become the subject of significant research interest. However, there is little research on business models associated with the development of open source assets other than software such as hardware or content. This article provides an overview of current business models for creating revenue for both open source software and hardware. It then summarizes our research of market offers to identify the ways companies use open source hardware (OSH) projects to make money. The research results provide insights about the dimensions of open source business models in an area other than typical software development.

How Open Source Strengthens Business Models - Tony Bailetti (Open Source Business Resource, 2009)
For a company's commercialization efforts to succeed, it needs to come up with great market offers which have great business models. Open source (OS) is neither a business model nor a market offer. A market offer with a weak business model will derive little benefit from OS regardless of how good the OS may be. Little is known about how OS strengthens the business model of a company's market offer. This article provide a conceptual tool that can be used to capture, share and communicate the strength of a company's business model and help articulate tacit knowledge into explicit knowledge. The second half of the article provides many examples that show how OS strengthens a company's business model. This paper is relevant to: i) top management teams who must formulate their companies' business models clearly and communicate what is expected from OS; ii) top management teams who are considering investing in OS projects, participating in OS development, or influencing schedules and priorities of OS projects; iii) staff of OS foundations who must attract company investment and participation in their OS projects; and iv) academics who undertake research in the alignment of product development and OS evolution for the purpose of improving business performance

The Human Factor in Open Source - Cat Allman (Open Source Business Resource, 2009)
It is easy to focus on the purely technical side of engineering: design, coding, documentation, licensing issues, and the release process. The interpersonal aspects of engineering also have a vital part to play. An important and frequently overlooked part of the successful free/libre and open source enterprise are the soft skills of communication, administration, and relationship building. Google uses, creates and supports open source software both as the raw material of code, and as a development model. My work in the Open Source Programs Office at Google as one member of a three person Outreach team is almost entirely about the mechanics of building good relations between the F/LOSS community at large and Google. This article describes our day-to-day tasks which are variously focused on student programs, external communications, event management, and financial administration.

An International Look at Women in Open Source - Cathy Malmrose (Open Source Business Resource, 2009)
When attending conferences, working with various open source teams, and generally interacting with people in the open source world, we see women as a small representative minority. The disparity leaves us wondering: "How to activate the other 50% of the population?". The question, "How do we include more women?" has been asked many times and answered in many ways. Cathy Malmrose, CEO of ZaReason, a Linux hardware company, stated, "possibly the most immediately effective solution is to showcase women internationally and their contributions. By simply talking about what women are doing all over the world, it creates an atmosphere of acceptance, encouraging more women to try contributing, no matter where they are located or what their situation is. Our goal is to normalize the experience of having women on open source projects". This issue of OSBR is a powerful effort to do just that. This article provides a glance at women in open source internationally. It is by no means comprehensive and is based solely on a random sampling of women who are currently contributing. The goal of this article is to give you a sense of the breadth and depth of women contributing to open source.

An Introduction to Open APIs - TIM Program (Open Source Business Resource, 2009)
This article provides a glossary of terms associated with open APIs which can serve as an introduction to the other articles in this issue of the OSBR. We conclude with some additional resources, video and text, which present further thoughts on the business value inherent in open APIs.

Lessons on Community Management from the Open Source World - Angela Byron (Open Source Business Resource, 2009)
From the outside (and often times from within, too), the success of healthy open source projects defies all logic. Scores of individuals from all over the world, all of whom have different skill levels, use cases, and experience, not to mention native languages and time zones, collaborate together in order to help make a project succeed. How is it that all of this chaos comes together and creates something wonderful and useful? And moreover, what lessons can be taken from how open source projects work "on the ground" and applied to our practical, daily lives and organizations? This article will attempt to extrapolate some of the experience gleaned from being immersed for over four years in the Drupal project. Drupal is an open source website building tool which has transformed from a small hobby project in 1999 to a robust framework powering hundreds of thousands of websites today. But behind buzzwords like "social publishing" and "content management framework" there lies a diverse, passionate, and vibrant global community. We present some of the key ingredients to the community's success, many of which can be applied to any organization.

Licensing of Open APIs - G.R. Gangadharan (Open Source Business Resource, 2009)
Two major trends in software development today are the open source paradigm and the notion of software as a service. The combination of these has lead to the concept of open APIs and mashups. Since late 2005, there has been a rapid proliferation of applications, referred to as mashups, that combine data and services provided by third parties through open APIs with data sources owned by users. Open APIs give users access to the data or services of an information technology platform. A well-known example is the Google Maps API, which generates maps for a given location, whose output can be combined with other data and services into mashups. Combining services and data from multiple sources raises several issues related to intellectual rights in mashups. However, the concept of mashups is currently in a nascent stage, and service and data providers often underestimate the relevance of these issues. In this paper we give an overview of open API licensing and provide examples from current open APIs. We then briefly discuss licensing of open APIs.

Mapping Mashup Ecosystems - Michael Weiss (Open Source Business Resource, 2009)
Mashups enable, users to "mix and match" data and user interface elements from different online information sources to create new applications. The creation of mashups is supported by a complex ecosystem of interconnected data providers, mashup platforms, and users. In our recent research, we examined the structure of the mashup ecosystem and its growth over time. The main contribution of our research is a method for the analysis of mashup ecosystems. Its novelty lies in the development of techniques for mapping the mashup ecosystem, and the use of network analysis to obtain key characteristics of the ecosystem and identify significant ecosystem members and their relationships. In this paper, we summarize the key steps of our analysis method, describe the members of the mashup ecosystem, and discuss the managerial implications of our analysis.

Measuring Modularity in Open Source Code Bases - Steven Muegge; Roberto Milev (Open Source Business Resource, 2009)
Modularity of an open source software code base has been associated with growth of the software development community, the incentives for voluntary code contribution, and a reduction in the number of users who take code without contributing back to the community. As a theoretical construct, modularity links OSS to other domains of research, including organization theory, the economics of industry structure, and new product development. However, measuring the modularity of an OSS design has proven difficult, especially for large and complex systems. In this article, we describe some preliminary results of recent research at Carleton University that examines the evolving modularity of large-scale software systems. We describe a measurement method and a new modularity metric for comparing code bases of different size, introduce an open source toolkit that implements this method and metric, and provide an analysis of the evolution of the Apache Tomcat application server as an illustrative example of the insights gained from this approach. Although these results are preliminary, they open the door to further cross-discipline research that quantitatively links the concerns of business managers, entrepreneurs, policy-makers, and open source software developers.

The Micro- and Macro-levels of Co-creation: How Transformations Change People's Preferences - Tore Kristensen (Open Source Business Resource, 2009)
Radical technologies can lead to extreme transformations of their users and even societies. Innovation researchers, archeologists, economic- and technological historians, and other scholars have studied past radical innovations to rationalize how these innovations emerged. This knowledge is indispensible for business and governmental decision makers. However, most research studies lack the human dimensions, such as "what did these innovative people think?" and "what were their personal motivations?". In many instances, we don't even know who the inventors were. In this article, we argue that a better understanding of personal transformations may lead to an increase of co-creation effectiveness and efficiency. First, this article will explore the nature of the personal transformations taking place among ordinary people as consumers and users of cultural institutions. Such institutions have been created to enable people to learn and grow individually and to create a sense of community and cohesion. Second, we discuss the co-creation aspects of personal transformation processes. This will be seen in two contexts: that of the individual who is transformed, and in terms of the different value contributions to a community of users.

A Model for Sustainable Student Involvement in Community Open Source - Chris Tyler (Open Source Business Resource, 2009)
A healthy community is the lifeblood of any open source project. Many open source contributors first get involved while they are students, but this is almost always on their own time. At Seneca College we have developed an approach to sustainably involving students in open source communities that has proven successful in a course setting. This paper outlines Seneca's approach and discusses the results that have been obtained with it. We will examine the key factors for successful student integration into open source communities and steps that educational institutions and open source projects can each take to improve student involvement.

Motivating Stakeholders for Co-created Innovation - Alex Pedrosa (Open Source Business Resource, 2009)
Today's profit orientation forces companies to focus on their core competencies and, at the same time, provide customers with multiple new offerings. To meet these two requirements, companies need to develop innovations in collaboration with different stakeholders including suppliers, customers, and users. While Managers and researchers discuss the benefits coming from the process of co-creating innovations with the various stakeholders, little is known about what motivates different stakeholders to engage in the co-creation of innovations. The purpose of this article is to highlight the first results of a qualitative study that focuses on the different types of value stakeholders can expect from co-creating innovations.

Offline: Where Tech Communities Succeed With Women - Selena Deckelmann (Open Source Business Resource, 2009)
Conferences are one way that women can be drawn into the free/libre and open source software ecosystem. Many different approaches are needed to increase women's participation in F/LOSS, but face-to-face interaction has proven to be a critical part of the way the technology community in Portland, Oregon has thrived. This article describes through anecdotes the successes of this community, and suggests how other communities could benefit from Portland's experience.

Open Source BI: A Market Overview - Steve Holub (Open Source Business Resource, 2009)
The following survey provides a list of open source software tools used in business intelligence (BI) and data warehousing systems. The tool selection criteria was based on the frequency and currency of the releases and on whether the product has released a stable build which could be used in a production environment. We only present those solutions which have had updates within the past two years. Our study looked at BI tools in the following categories: i) databases; ii) extract, transform, and load; iii) master data management; iv) BI reporting tools; and v) data mining. In the case of an open source software bundle that overlaps categories, we divide the software bundle into its separate parts for ease of categorization.

Open Source BI Reporting Tool Review - Benjamin Dietz; Lily Singh (Open Source Business Resource, 2009)
The main purpose of a business intelligence (BI) system is to provide access to information for decision makers. Reporting tools help to create, administer and distribute reports. Reports can be classified into three categories: i) standard reports containing information in table form; ii) cubes which are online analytical processing reports designed to analyze multidimensional data; and iii) dashboards which provide an overview of selected reports and key performance indicators. Each of these report types are often supplemented by graphical representations of the data. There are many different reporting solutions available in the open source market. In this article, we compare four open source reporting solutions. They give a good insight of the current state of the market and are among the the most popular solutions in use today.

Open Source Resources in Education: Opportunities and Challenges - Norm Friesen (Open Source Business Resource, 2009)
The education community has been at the forefront in envisioning and conceptualizing infrastructures intended for utilizing and sharing digital content or resources. However, this community has faced challenges in making these visions a reality. We begin by describing a relatively early attempt at creating an economy for sharing educational resources, referred to as learning objects. We then discuss two approaches to opening up educational contents to the world under the auspices of the more recent Open Educational Resources movement. One of these approaches has focused on creating open resources from scratch, utilizing Wiki content development and management technologies in the wake of the phenomenal success of Wikipedia. A second approach is represented by developments in Open Courseware. Following the example of MIT's Open Courseware, this approach has more recently been adopted by many other educational institutions under the OCW Consortium. We conclude by making the case that this second approach may represent the most promising of recent developments in the adaptation of open source and open content to educational practices and technologies.

Open Source: Shifting Buying and Evaluation Patterns of BI Users - John Kemp (Open Source Business Resource, 2009)
The emergence of open source software (OSS) has changed the buying patterns and approaches for the evaluation and selection of business intelligence (BI) tools. This article discusses how the buying patterns have changed and what it means for businesses looking at open source BI software.

Open Source Web Based Geospatial Processing with OMAR - Mark Lucas; Scott Bortman (Open Source Business Resource, 2009)
The availability of geospatial data sets is exploding. New satellites, aerial platforms, video feeds, global positioning system tagged digital photos, and traditional GIS information are dramatically increasing across the globe. These raw materials need to be dynamically processed, combined and correlated to generate value added information products to answer a wide range of questions. This article provides an overview of OMAR web based geospatial processing. OMAR is part of the Open Source Software Image Map project under the Open Source Geospatial Foundation. The primary contributors of OSSIM make their livings by providing professional services to US Government agencies and programs. OMAR provides one example that open source software solutions are increasingly being deployed in US government agencies. We will also summarize the capabilities of OMAR and its plans for near term development.

Opening the Source of Art - John Bell (Open Source Business Resource, 2009)
The open source community has developed a number of tools and philosophies to assist in distributed software development. The Still Water Lab at the University of Maine believes that these tools and philosophies can be adapted to facilitate other forms of distributed creative endeavours. It has developed two tools that reinterpret the ideas used in open source software through the lenses of artistic creation and preservation: The Pool and the Variable Media Questionnaire. This article discusses how several of the ideas used in software development have influenced Still Water's approach to making tools that support artistic production.

Q&A. How can an individual or small business give back to an open source community? - Mike Kavis (Open Source Business Resource, 2009)
How can individual or small business give back to an open source community?

Q&A. What do investors look for in a business venture? - James Bowen (Open Source Business Resource, 2009)

Q&A. What lessons can "green" computing learn from open source? - Venkat Mangudi (Open Source Business Resource, 2009)
What lessons can "green" computing learn from open source?

Q&A. What will Oracle do with Sun’s open source offerings? - Sam Selim (Open Source Business Resource, 2009)
Sam Selim answers the question "What will Oracle do with Sun?s open source offerings?"

Reassuring End Users Of Open Source: The OSGeo Example - Tyler Mitchell (Open Source Business Resource, 2009)
Furthering the adoption of open source software (OSS) is often seen as a natural, contagious progression as more developers and users share with others about the success of their projects. But how can an open source project even hope to compete with proprietary commercial products with massive marketing budgets and staff? Aside from not typically having large financial resources for marketing, other factors can lead enterprise users to look elsewhere for guarantees of product longevity and a robust support ecosystem around the product. Without these features, many users and businesses alike would not consider the software as an option or have a desire to become involved. This is equally true with open source geospatial software projects which are focused on presenting freely available mapping and geographic analysis tools to the world. The Open Source Geospatial Foundation seeks to address the needs mentioned above, to promote the excellent software that is available, and to provide a model where businesses can join in promotion and development. OSGeo undertook some novel approaches to encouraging new and existing support options which boosted confidence within the business sector by helping to ensure that project code will be publicly accessible for years to come. In this article, we discuss the factors needed to get open source geospatial products into the hands of those users willing to test, use and eventually admire them as their favourites, or to go one step further and recommend them as a corporate solution. We examine the advantages provided by using marketing to help promote open source projects and then consider how this can boost business confidence in the use of the software. The article closes with a look at how a natural ecosystem of open source users is able to create something bigger and more consequential than each project could attain on its own.

A RESTful Implementation of Geospatial Web Services - Haris Kurtagic; Geoff Zeiss (Open Source Business Resource, 2009)
In "What is Web 2.0?" Tim O'Reilly identifies the characteristics that distinguish Web 2.0 from the first generation of Web applications. One key aspect is participation. Instead of users simply consuming information, Web 2.0 technology enables all of us to participate in building content. The power of Web 2.0, in Tim O?Reilly?s words, is that it provides a platform for "harnessing collective intelligence". Perhaps the best known example of this is Wikipedia, which is distinguished from other online encyclopedias by the fact that its content is provided by users rather than a small group of experts. This model has been so successful, even the Encyclopedia Britannica has adopted a Web 2.0 approach. A critical challenge to participation is interoperability--integrating the islands of technology that characterize most information technology organizations. There have been earlier attempts to create a standard framework for distributed computing such as CORBA and DCOM, but the complexity of these environments has limited their adoption. A more recent and simpler approach is Representational State Transfer (REST). In this article we begin with an examination of the critical challenges facing organizations responsible for maintaining our utility, telecommunications and transportation infrastructure, outline how open standards are helping to address these challenges, and then discuss how geospatial data and services can be exposed over the web. We introduce REST, outline a RESTful implementation of geospatial web services that provides simple and open access to geospatial data over the web using standard web protocols, and describe a prototype web site developed using RESTful web services by the City of Nanaimo.

The Role of Consumers Within an Open Source Community - Stormy Peters (Open Source Business Resource, 2009)
The software provided by the GNOME Project is produced by a large community comprised of several thousand developers, translators, quality assurance testers, and documentation writers. Consumers are represented in the community by technical users and organizations that distribute GNOME technologies. And while the community reaches out regularly to non-technical end users and welcomes any that approach the community, these two worlds rarely interact. This article draws upon our experience within the GNOME Project to examine the question "Why do consumers and the community rarely interact?". Our insights may prove useful for other projects and consumers wishing more interaction.

So Are You A Contributor?: Women's Contributions to Linux and Open Source Span Technology and Business - Amanda McPherson (Open Source Business Resource, 2009)
While there are over 60 names on the list of women in open source on the Geek Feminism wiki, there are far more than 60 women making their mark in open source. I work with talented people every day in my role as Vice President of Marketing and Developer Programs at the Linux Foundation, and see first-hand the contributions women make at the technology and business levels. This article presents some of the techniques used by the Linux Foundation to encourage a culture of inclusion and to foster a wide variety of open source contributions.

So You Wanna be a Linus Torvalds? The Do's and Don'ts of Running a Small Open Source Project - Alain Désilets (Open Source Business Resource, 2009)
In this paper, we present a series of lessons learned on how to effectively run a small open source community. These lessons are based on my own experience as the leader of VoiceCode, a project that aims at developing an integrated programming-by-voice toolbox. It provides tools that allow programmers with Repetitive Strain Injury (RSI) to write computer code by talking to their machine instead of typing. The VoiceCode project started in 1999 by the National Research Council of Canada, and was first officially released in 2003. The system is now at a point where it can be used by programmers to do real work, and there have been over 9,100 downloads so far. The project has also attracted the attention of the media. In the process of leading this project, we have learned many important lessons; too many to discuss exhaustively here. We will however share three that seem particularly important.

Social Actions: Making the Web More Philanthropic - Peter Deitz; Christine Egger (Open Source Business Resource, 2009)
Social Actions makes it easier for people to turn their good intentions into meaningful action. The organization has created an open source database of actions people can take on any issue. The actions in the database come from across the social web and include everything from volunteer opportunities to micro credit loans. It currently aggregates opportunities to make a difference from 50+ action sources, including: CanadaHelps, Kiva, Idealist, GlobalGiving, GiveIndia, and Greater Good South Africa. Using the Social Actions application programming interface, we encourage third party developers to build web and mobile applications that intelligently distribute actions from our database on the websites, social networks, and mobile phones that millions of people use every day. This article describes how Social Actions applies open source principles to the organization's products and processes. In its entirety, Social Actions is intentionally designed to contribute to the ongoing and vibrant conversations about open source practices and principles.

Social Media and Open Source: Worlds Apart? - Aaran Duncan; Glenn McKnight (Open Source Business Resource, 2009)
Social Media, also known as Web 3.0, is not your granddaddy's Internet. How it is used is in a constant state of change. The rising tide of expectations, together with innovation, are pushing various platforms, especially in mobile technology. Mobile has become a compelling format to interface with the Internet, bringing a new spin to the phrase "One Laptop Left Behind". We believe that the degree to which open source communities embrace mobile and Social Media technologies dictates their relevance to the general public. We also believe that open source and Social Media communities can learn and benefit from each other. This article explores the increasingly intersecting worlds of Social Media, mobile, and open source. We describe how Social Media has the potential to change the way communities use and create open source tools to better align with end-user expectations.

A Social Vision for Value Co-creation in Design - Liz Sanders; George Simons (Open Source Business Resource, 2009)
The Cluetrain Manifesto was introduced in 1999, calling for a powerful global conversation between companies and the people they serve. Since then, the conversation has started and is finally gaining momentum. Co-creation is the buzzword of the day to describe the various types of conversations that are taking place. But the conversation has multiple perspectives. It can be applied to multiple domains ranging from sales tactics and branding contests to strategic, human-centered means of affecting social transformation. In this article we try to articulate a vision for value co-creation by focusing on its social aspects. It is our hope that such social vision will contribute to existing perspectives so that future conversations can take place in a more productive way. The suggested framework organizes the seemingly disparate applications, comparing the mindset, goals and results of three types of value co-creation: monetary, use/experience and social. Although these three types of value co-creation are all relevant, we believe that the social type of value provides a real opportunity for significant social change. However, the rules of engagement for this type of co-creation are particularly challenging. Participation must be face-to-face to allow for real-time interaction to take place. Empathy for the people who will be affected by change is key. Visualization of the collective assets is essential. And having the appropriate mindset about co-creation is the single most important component for success.

Special Considerations for Business Intelligence Projects - David Currie (Open Source Business Resource, 2009)
A business intelligence (BI) project has to be managed with as much discipline as any other information technology (IT) project in order to be successful. There are a few items that need special consideration given the nature of BI solutions, regardless of the specific methodology or technology involved. This article will discuss how to extract maximum value from an investment in BI software.

The Steady March of the European Penguins - Gijs Hillenius (Open Source Business Resource, 2009)
Open source licenses allow public administrations to change, share and re-use their applications freely. Open standards allow for connectivity and interoperability between the applications. For a wider use of open source software by public administrations, it is equally important to require the use of open standards in the public sector. Open source projects can face difficulties when using proprietary standards, especially if these latter require usage royalties. The member states of the European Union made steady progress in 2008 in developing information technology policies on open source and open standards. Spain and France have taken the lead, yet in all EU member states examples of administrations using open source software can be found. Europe's competition commissioner Neelie Kroes warned the EU's institutions to follow suit and use open standards: "I know a smart business decision when I see one". This article provides an overview of the advancements and some of the setbacks of the implementation of open source and open standards by public administrations in the 27 member states of the European Union in 2008. It is mostly based on the news items the author wrote for the European Union's Open Source Observatory and Repository.

TellTable: Collaborative Work Using Single User Applications - Andy Adler; John C. Nash; Sylvie Noël (Open Source Business Resource, 2009)
Many work environments require collaborative writing and editing of documents in diverse formats. In simple cases, there is essentially one author who receives approvals and comments from others. In other cases, the document is genuinely collaboratively authored using asynchronous or synchronous methods. A common way to collaboratively edit a document is to exchange draft versions between authors via email. This method introduces the possibility of conflicting changes and missed contributions as well as a significant burden as all members of the team are responsible for version control. The principle difficulty is that independent changes can be made to different versions, which must later be reconciled manually. It is also difficult to determine when and why a change was made. This article introduces TellTable, an open source system designed to allow single-user software applications to be managed in a collaborative manner. We will discuss current collaboration models, the technical aspects of the TellTable software framework, security issues in its implementation, and tests of performance.

Torys Technology Law Speaker Series: Open Source Licenses and the Boundaries of Knowledge Production - Byron Thom (Open Source Business Resource, 2009)
The University of Ottawa, Faculty of Law is Canada's premiere legal program in law and technology. The Torys Technology Law Speaker Series brings prominent speakers from around the world to discuss current topics in law and technology. A new approach to open source software was presented to students and faculty at the University of Ottawa on March 11, 2009. Michael Madison, Associate Dean for Research and Professor of Law at the University of Pittsburgh School of Law, presented "Open Source Licenses and the Boundaries of Knowledge Production". Prof. Madison spent time outlining and answering questions on a novel interpretation of copyright in the age of OSS. Using historical examples, he called for the courts to incorporate a spatial framework to deal with open source licenses. His approach was particularly relevant and timely in light of a recent opinion from the US Court of Appeals for the Federal Circuit, Jacobsen v. Katzer.

Transparency in Government - Darlene Meskell (Open Source Business Resource, 2009)
The focus of the Spring 2009 Intergovernmental Solutions Newsletter was Transparency and Open Government. The introductory article, republished here with permission, introduced the topic and the rest of the Newsletter. It provides an overview of current initiatives in both the United States and other parts of the world. Other articles from the Newsletter are referenced by page number.

Use of Moodle for Single Entry Portal at Riga Technical University - Tom Schmit; Zigmunds Zitmanis (Open Source Business Resource, 2009)
This article discusses the reasons for the decision of Riga Technical University (RTU) in Latvia to choose an open source product as the application to create ORTUS. ORTUS is an acronym for Open Riga Technical University Services and provides the single point of entry into electronic services for the University.

Use of Open Source Software by the Brazilian Government - Edgy Paiva (Open Source Business Resource, 2009)
In most countries, government initiatives that encourage the use of open source software are primarily motivated by the goal of reducing costs. In Brazil, the goal is different. According to Rog?rio Santanna, Secretary of Logistics and IT at the Brazilian Ministry of Planning, Budget and Management, "open source is a strategic choice of the Brazilian Federal Government since 2003 because it reduces costs, increases the competition, creates jobs and develops the knowledge and intelligence of our country. Our preference for open source is not motivated only by economic aspects. But there is also the possibility to develop new products, distribute the knowledge, access to new technologies and to stimulate the development of software in collaborative environments". This article shows how the Brazilian Government is using OSS, gives some examples of successful Brazilian projects that use OSS, explains some difficulties for implementing OSS, and makes a comparison of the advantages and disadvantages of using OSS.

Using JavaScript Toolkits to Create Rich Internet Applications - Owen Byrne (Open Source Business Resource, 2009)
Since 2004, the number of Rich Internet Applications has increased, making them a key component of the Web 2.0 phenomenon. Many RIAs have been developed using JavaScript and AJAX. AJAX is used to access remote data sources, that reside on the server or are available through an open API, directly from within the application. The rich variety of applications would not be available today without the concurrent appearance of many, powerful JavaScript toolkits that have taken the development of these applications from labour-intensive to nearly painless. These toolkits provide an open source alternative to the proprietary products developed by Adobe (Flash/Flex/Air) and Microsoft (Silverlight). This article provides two examples that demonstrate the evolution of RIAs, then compares the features of the most commonly used JavaScript Toolkits used to create RIAs. We then discuss how freely available toolkits are able to compete against proprietary alternatives. Finally, we provide some concluding remarks based on our experience with creating enterprise RIAs.

Value Co-Creation and New Marketing - Aron Darmody (Open Source Business Resource, 2009)
Co-creation grants consumers free rein to work with company-provided resources in the production of their own value offerings. The ongoing participation of active consumers in the production of their own use and exchange value inverts the long-standing marketing orthodoxy of the company as the arbiter of value. Rather than resist this fundamental shift in the locus of value creation, savvy firms positively embrace the change and seek to manage consumer freedoms in order to harness the consumers' productive capabilities. Using the example of the Apple iPhone and App Store, and drawing on labour theories of value and Foucault's notion of government, we show how granting consumers freedom through co-creation has become the most effective mode of production for contemporary marketers.

Value Co-creation as Part of an Integrative Vision of Innovation Management - Stoyan Tanev; Mette Knudsen; Wolfgang Gerstlberger (Open Source Business Resource, 2009)
Value co-creation is an emerging concept in business, marketing and innovation management. Its growing interest points to the emergence of a new semantic wave in innovation research that requires the adoption of new terminology, frameworks and fields of research exploration. There is a number of existing research streams that provide a solid starting point in the discussion of different perspectives on co-creation. One key research aspect that needs to be further addressed is the potential benefits from the adoption of value co-creation practices and strategies. This article shares insights from an attempt to position the value co-creation paradigm within an integrative vision for innovation management research and practices. This positioning is a challenging task as the meaning of the terms "value co-creation" and "integrative" innovation management need to be more fully clarified. We attempt to identify an appropriate plane of conceptual integrity that could be used to describe the innovation management field within the context of its relation to value co-creation.

Value Co-creation: Lessons from Lead to Win Ecosystem - Tony Bailetti; David Hudson (Open Source Business Resource, 2009)
While the concepts of value co-creation and business ecosystems have become dominant, there is lack of conceptual clarity as to the role of co-creation in a business ecosystem. The objective of this article is to provide concrete examples of co-creation in vendor neutral ecosystems using lessons learned from operating the Lead to Win ecosystem. In a vendor neutral ecosystem, no vendor dominates and membership is open to all individuals and organizations that meet specific criteria. The article is organized into three sections. The first section provides a short description of the Lead to Win ecosystem. The second section uses concrete examples to illustrate the lessons learned about co-creation in vendor neutral ecosystems. The third section describes key takeaways based on our five months experience operating the keystone of the Lead to Win ecosystem.

Viable Business Models for Corporate Co-creation Communities - Kim op den Kamp (Open Source Business Resource, 2009)
The participation of people in online communities is rapidly increasing and the shared data, information and knowledge in these communities is becoming greater and more diverse. The social community Facebook.com has over 300 million active members and over 40 billion photos uploaded to the site each month. Wikipedia.org has more than 75,000 active contributors, who are working on 10 million articles in more than 260 languages. The opportunities of these large sources of information gathered in communities are being discovered by companies. Harley Davidson has established a large community where motorbikes and accessories are presented and discussed by members. Moreover, members interact about user- and maintenance tips. Participation in this community has been found to increase the commitment and affection for the Harley Davidson brand. The toy manufacturer LEGO has over 2.5 million participants in their community, 40% are adults, and 3,000 new designs are uploaded to this community weekly. The best designs are produced and sold in stores. The use of co-creation communities seems promising. However, the main business model elements that strengthen successful co-creation communities have not been defined yet. The elements of these communities that create value, that require resources, and that incur costs have not been explored in detail. The objective of this article is to provide insights into three main business model elements of co-creation communities: the value proposition, the value network, and the revenue model. These elements will be specified for distinctive new product development phases. The insights are obtained from our in-depth study of seven co-creation communities. We will conclude with some recommendations for creating successful co-creation communities.

Ways of Engaging Consumers in Co-production - Michael Etgar (Open Source Business Resource, 2009)
As co-production becomes an important engagement for many consumers-suppliers situations, the issue of how to encourage consumers to engage in co-production becomes an important question. Marketers need to recognize that co-production is not an automatic consumer situation but a conscious decision by consumers to engage in such activities. This article presents several factors which may enhance the ability of consumers to engage in co-production. To engage consumers, marketers have to ensure that they offer those products and services that can be individually adjusted and modified, and to present them to consumers who have a higher propensity to engage in co-production activities. In order for consumers to agree to such endeavours, marketers must find what kind of benefits targeted consumers seek in such activities. Those usually encompass economic, psychological and social needs. Then, they have to offer them packages which can fulfill such needs.

Adaptive Co-management and the Learning that Leads to Social Innovation - Nancy Doubleday (Open Source Business Resource, 2008)
Learning and social innovation are linked. Adaptive co-management offers strategies that empower learners to take responsibility, collaborate and create. To improve our understanding of how social innovation is nurtured, we examine three projects that used the adaptive co-management approach to support learners working in autonomous groups to create social goods and fill perceived gaps. The student projects led to the following social innovations: i) an organic food market serving students; ii) an open source approach to design in a field where proprietary approaches are more common; and iii) a model that extends the impact of what first year university students learn well beyond the classroom.

Blood on the Tracks: 6 Years of Technical Entrepreneurship in Ottawa - John Callahan; Tony Bailetti (Open Source Business Resource, 2008)
In 2002, twenty nine engineers and computer scientists completed a Lead-to-Win (LTW) program in Technical Entrepreneurship. The LTW program was a pilot program designed for former Nortel employees to gain the skills needed to become entrepreneurs. Of the participants, fifteen started technology businesses, ten tried to attract venture capital funding, eleven tried to grow their companies with no venture capital funding, and seven established five technology businesses headquartered in Ottawa. These businesses attracted over $91 million from venture capital firms during one of the worst economic times to hit this region and created over 280 jobs globally. On May 15th at the Partnership Conference Series, John Callahan and Tony Bailetti, directors of the LTW program, and three of the LTW graduates spoke about the lessons learned during and since the program.

The Canadian DMCA: A Betrayal - Michael Geist (Open Source Business Resource, 2008)
Having had a few more hours to think about Industry Minister Jim Prentice's Canadian DMCA, I am left with one dominant feeling--betrayal. I have already highlighted the key provisions and coverage (and note that it will take some time to fully assess the implications of this bill) but it is immediately apparent that the concerns of thousands of Canadians--now over 45,000 on the Fair Copyright for Canada Facebook group alone--have been realized. If enacted, the Canadian DMCA would strongly encourage the use of technological locks and lawsuits. While Prentice has given a handful of new rights to Canadian consumers, each is subject to many limitations and undermined by the digital locks provisions that may effectively render the new rights meaningless.

Child-Centric Laptop to Help Address Social Needs - John Roese (Open Source Business Resource, 2008)
The One Laptop Per Child Foundation, founded by MIT professor Nicholas Negroponte and a team of educators, developers and technologists, was launched in 2005 to design, manufacture and distribute laptop computers that are affordable enough to provide every child in the world with access to new channels of learning. Known as the XO, the little green-and-white US$188 laptop has since gone on to introduce computer literacy and self-empowered learning to children in countries and environments previously considered inaccessible. It's also an example of social innovation, where companies like Nortel are leveraging novel approaches-including open source software development-to drive change that will benefit society.

Community Building: NetBSD in Hindsight - David Maxwell; Lubomir Sedlacik (Open Source Business Resource, 2008)
The NetBSD Project is one of the oldest modern open source software projects. It provides an operating system that runs on over 50 hardware architectures (also called ports), including the IBM PC, Motorola PowerPC, and Sun UltraSPARC machines. Founded in May of 1993, the project has supported the operating system's active development and managed contributions from thousands of individuals. Prior to the New York City BSD Users Group Conference held in October, 2008, NetBSD developers from across the globe held a face to face meeting for planning and problem solving. Four developers from Sweden, Canada, the US, and Slovakia took a few minutes to think about how the NetBSD community has evolved over the past fifteen years. This article summarizes those perspectives and provides insight into how an open source community maintains development momentum while managing contributions from a large number of volunteers with varying skill levels from across the globe.

Contrasting Proprietary and Free/Open Source Game Development - Alessandro Rossi; Marco Zamarian (Open Source Business Resource, 2008)
Free/Libre Open Source Software (F/LOSS) development practices are gaining momentum in the computer game industry. This traditionally proprietary industry is becoming more interested in the F/LOSS paradigm for developing complex software projects. Software practitioners, both managers and developers, need to understand the potential in order to benefit properly from incorporating F/LOSS practices into their proprietary production cycle. Comparisons between proprietary and F/LOSS software development processes are usually characterized in terms of the relationship between property rights, revenue distribution and power within a network of actors. By contrast, coordination and control practices, mediating artifacts and development tools, and the interactions between the different actors involved in the development are often neglected. Proprietary and F/LOSS development differ in terms of the knowledge exchanges between the relevant actors and the different strategies employed to overcome information asymmetries. Recognizing this difference is an essential step for evaluating how proprietary, closed-source software houses can benefit by integrating various F/LOSS practices into their development agenda.

Coverity Report - David Maxwell (Open Source Business Resource, 2008)
On May 20, 2008, static analysis tool vendor Coverity released a report entitled "Open Source Report 2008". The report includes information gathered over the first two years of the Coverity Scan project which was developed as part of a contract from the US Department of Homeland Security. Coverity provides its analysis tools to open source projects in order to identify quality and security flaws in the codebases. Once identified, the developers of the open source projects are given the information in order to facilitate hardening of the software. The report includes information about the progress made by various projects using the Scan service. Additionally, the Scan databases constitute one of the largest and most diverse collections of source code to be built and analyzed while tracking changes to those code bases over a two-year period. This data provides a substantial set of samples for considering some questions about the nature of software. The report investigates relationships between codebase size, defect counts, defect density, function lengths, and code complexity metrics. This article highlights some of the results from the report.

Creating Disruptive Value For Not-For-Profit Organizations Using Open Source - Fred Dixon; Jill Woodley (Open Source Business Resource, 2008)
Much of the currently available off-the-shelf software offers too many features and does not meet the unique usability needs of non-technical or disabled users using old hardware. When leveraging open source components to rapidly build products for not-for-profit organizations, the speed of development doesn't reduce the need to make the product accessible by the users. This article shares the experiences of a unique community/university partnership to bring accessible technology to the non-profit community in the National Capital Region.

The CUE Factor: Community-University Engagement for Social Innovation - Edward Jackson (Open Source Business Resource, 2008)
The Association of Universities and Colleges of Canada informs us that our universities produce one-third of the roughly $10 billion in research and development generated in Canada. Our post-secondary institutions house some of Canada's most talented inventors and analysts as well as some of the best laboratories and think-tanks. The full value of this innovation is achieved when a university is able to successfully engage with the local geographic community in which it is based, including specific communities of interest that reside in the locality. Such meaningful and continuous community-university engagement (CUE) at the local level is a crucial pre-condition before a university can successfully execute partnerships with open source communities, which by their nature are dispersed across the globe, to create social value. By effectively engaging both the local and open source communities, Canadian universities can play a pivotal role in social innovation that addresses challenges in our own country as well as overseas. Accordingly, universities across Canada should increase their CUE factors by deepening and broadening their teaching, research and volunteering activities with the external constituencies that have the greatest need for sustainable solutions to the challenges they face every day. If social innovations are to make a real difference, Canadian universities must step forward in a major way. This article sets out a dynamic model for CUE and provides examples of creative local initiatives.

Data Access in Canada: CivicAccess.ca - Tracey P. Lauriault; Hugh McGuire (Open Source Business Resource, 2008)
There is a global movement to liberate government-"owned" data sets, such as census data, environmental data, and data generated by government-funded research projects. This open data movement aims to make these datasets available, at no cost, to citizens, citizen groups, non-governmental-organizations (NGOs) and businesses. The arguments are many: such data spurs economic activity, helps citizens make better decisions, and helps us understand better who we are and where we are going as a country. Further, these data were collected using tax dollars, yet the government holds a monopoly which makes data available only to those able to pay the high access fees, while some data is not made available at all. The open data movement is lagging in Canada as demonstrated by exorbitant fees for such basics as the data set of postal codes correlated to electoral districts. This data could be used for any number of civic engagement projects, but it costs thousands of dollars due to Statistics Canada's policies of cost recovery. This article aims to bring these issues to a wider public. The long-term vision is a country in which citizens, specialists, professionals, academics, community groups and even businesses can work together, developing innovative information access and visualization tools, better decision-making models, and more tools responsive to the needs of the citizens. Liberating data will spur grassroots research on important social, economic, political and technical areas, currently hampered by lack of access to and high cost of civic data. Further, we want to link the debate about data to questions of government transparency and accountability, which pivot on access to accurate, reliable, and timely data.

Developing an Open Source Reference Implementation of the Canadian Electronic Health Records Solution - Mark Yendt; Duane Bender; Brian Minaji (Open Source Business Resource, 2008)
Developing a reference implementation of the Canada Health Infoway pan-Canadian Electronic Health Record Solution standard can be a useful step in ensuring the successful and cost-effective development of full scale electronic health systems in the Provincial Ministries of Health across Canada. These jurisdictions could benefit from the knowledge gained and the artifacts created in this prototype environment. The reference implementation utilizes an Enterprise Service Bus architecture and a Service Oriented Architecture design approach to build a Health Information Access Layer, as recommended by Canada Health Infoway. The system components and supporting technology developed will be released as open source. This set of technology could represent a starting point for prototyping an implementation in a production environment, for creating a standards development platform, for standards conformance testing, and/or as a test bed for evaluating alternative software components in a HIAL environment. Mohawk Applied Research Centre for Health Informatics at Mohawk College in Hamilton, Ontario, along with public and private sector partners, is continuing to build a reference implementation of the pan-Canadian Infoway standard that demonstrates the ESB/SOA approach. This article summarizes the project to date and suggested future research areas that will reduce the cost, risk and time barriers to widespread adoption of eHealth systems in Canada.

Driving Innovation Through Interoperability - John Weigelt (Open Source Business Resource, 2008)
Today's difficult economic environment provides a time of change where information technology matters more than ever. As business and service delivery leaders look to become even more effective and efficient in meeting their client's expectations, they are increasingly looking to electronic channels as an integral element of their business strategies. Regrettably, the ever increasing pace of technological change often disconnects the technology from the business requirements. This disconnection hides technology innovations from the business and has a broader impact of preventing business innovation. This article discusses the role service oriented architecture and interoperability can play in keeping an organization innovative and competitive. We also discuss Microsoft's interoperability principles, its commitment to its open source community, and the benefits of embracing openness as part of an organization's business strategy.

Editorial: Accessibility (July 2008) - Dru Lavigne (Open Source Business Resource, 2008)
Much has changed since the term "open source" was coined ten years ago. The idea of sharing code, once relegated to research institutions and hobbyists, is starting to reach ubiquity in the consciousness of both government and business. More recently, this concept has extended beyond software. Everything from hardware to data to knowledge is becoming "open". Despite this trend towards openness--or perhaps due to the stark contrast openness provides--accessibility remains a difficult obstacle to overcome. The issues surrounding accessibility take many forms. In the first article, Pierre-Paul Lemyre from the University of Montreal reminds us that everything old is new again. While the difficulties surrounding the open source licensing of software are still being resolved, those same difficulties are now being experienced when providing open access to data and knowledge. He proposes a global licensing repository as a solution towards providing access while complying with licensing terms. Marco Zehe from the Gnome Accessibility Project concentrates on ensuring that the features found in software applications are accessible to all, including those with disabilities.

Editorial: Building Community (October 2008) - Dru Lavigne; Michael Weiss (Open Source Business Resource, 2008)

Editorial: Communications (April 2008) - Dru Lavigne (Open Source Business Resource, 2008)
Two reports issued this week provide very different numbers regarding the adoption of open source. IDC proclaims that "the economic slowdown in the United States may actually boost demand for open source services. If organizations adopt more open source software as part of a strategy to reduce software costs, the demand for related services should increase". The US-based survey reports that "almost 60% of the survey respondents said their company's spending on open source increased in 2007". This is in stark contrast to Statistics Canada's findings that "17% of private sector firms reported using open source software" and "3% of private firms and 13% of public organizations reported customizing open source software".

Editorial: Education (August 2008) - Kevin Goheen; Dru Lavigne (Open Source Business Resource, 2008)
The August issue of the OSBR is focused on "education". The relationship between open source software (OSS) and education is extremely broad and also very important. One could argue that OSS creation and adoption has been driven by faculty and research leaders, with eventual buy-in from the commercial sphere. This should not be a surprise; university research labs are populated with individuals possessing an abundance of creativity, a need to work with platforms for innovation, and a shortage of funding. My own lab's experience with clever graduate students and finite funding sources forced us to collaborate with the National Research Council of Canada on open source helicopters.

Editorial: Enabling Innovation (December 2008) - Dru Lavigne; Steven Muegge (Open Source Business Resource, 2008)
This issue of the OSBR provides many examples of using open source principles to enable innovation. These innovations go beyond code creation and address the diverse issues of: declining computer science enrollment, a lack of affordable publishing tools for online exhibitions, the rising costs of text books, the need for process automation in developing countries, easy-to-use and accessible solutions for the not-for-profit sector, adding open source to a proprietary Fortune 500 company's business strategy, and reducing duplicated costs.

Editorial: Enterprise Readiness (May 2008) - Dru Lavigne (Open Source Business Resource, 2008)
In January 2008, Gartner released their "Top Predictions for IT Organizations and Users, 2008 and Beyond". Their analysis around open source included the key finding that it "has become impractical for mainstream IT organizations to avoid or ignore the influence of open source across a wide variety of industry market segments. Doing so will put organizations at a serious disadvantage against competitors that are leveraging mature, stable and well-supported open-source technologies for significant return-oninvestment and total-cost-of-ownership opportunities." Does this mean that the enterprise is finally ready for open source? As Bernard Golden points out in the first article, it is impossible to answer that question when it is framed that way--there are just too many open source projects, each possessing varying degrees of maturity and usability. Bernard further posits a key point that enterprises themselves vary from early adopters to pragmatists. Fortunately, resources are available for gauging the applicability of a specific open source product to meet the needs of a particular organization.

Editorial: Health and Life Sciences (November 2008) - Dru Lavigne; Brian Barry; Peter Tanner (Open Source Business Resource, 2008)
The length of Wikipedia's list of open source healthcare software may come as a surprise to many readers. This issue of the OSBR provides an excellent introduction to the complexities and interoperability issues associated with healthcare software and the role open source can play in helping to resolve these issues. This month's authors also provide insight into an open source projects that follows open standards, lessons learned from providing a reference implementation, the benefits of a healthcare ecosystem, and the value of open source projects working closely with standards organizations.

Editorial: Interoperability (January 2008) - Dru Lavigne (Open Source Business Resource, 2008)
In December, the Open Solutions Alliance published CEO Predictions 2008 which contains the responses received from their 2007 Customer Forum Series. A key finding was that the interoperability of open source with other open source and proprietary solutions was a primary concern. Several of the CEOs polled included interoperability in their answer to the question "what is the biggest challenge for the open source software industry in 2008?".

Editorial: Open Data (February 2008) - Dru Lavigne (Open Source Business Resource, 2008)
On February 8, as the Open Source Definition and the Open Source Initiative entered their second decade, Bruce Perens published his reflections in State of Open Source Message: A New Decade for Open Source. He states his intent was to provide "another way of talking about Free Software, tailored to the ears of business people". Seeing that Gartner is predicting that "by 2011 at least 80% of commercial software will contain significant amounts of open source code", it would appear that the open source message has succeeded in reaching the ears of business people. While awareness of open source code has reached a certain level of maturity, the innovation possibilities extend beyond the code itself. As you'll see in this issue of the OSBR, awareness of open "data" is still in its infancy, resulting in many untapped opportunities.

Editorial: Procurement (March 2008) - Dru Lavigne (Open Source Business Resource, 2008)
Earlier this month, the European Commission issued a press release stating that it "will take a more pro-active approach to its own use of open source" and that "for all new development, where deployment and usage is foreseen by parties outside of the Commission Infrastructure, open source software will be the preferred development and deployment platform." While this is a strong stance regarding the use of open source, the European Commission still considers itself to be "an early adopter of open source". Canada has yet to issue such a clear cut procurement policy towards open source. It has been five years since e-cology corporation made its recommendations in its fact finding study funded by the Canadian Federal Government. The current official position is that "departments and agencies base their decisions to acquire, develop and use software (including open source software) on their business needs and the principles set out in the government's Federated Architecture Program." The Canadian Federal Government's position is wide open to interpretration and often leaves open source contractors to struggle against departments who are ignorant of and perhaps hostile to open source, and a bidding process that uses terminology which assumes a proprietary business model. Citizens are also affected, as can be seen in the example of Statistics Canada requiring the use of a particular proprietary operating system and software application in order to complete a mandatory Canadian Automated Export Declaration form.

Editorial: Security (June 2008) - Dru Lavigne (Open Source Business Resource, 2008)
If you google the phrase "open source security", you'll find plenty of articles which debunk the "myth" of open source security, fuel the debate of Linus' law vs. security through obscurity, or argue which type of software, proprietary or open source, is more secure. Yet, the question "which type of software is more secure?" is impossible to answer. Software security is highly dependent upon many variables: the programming language used, the practices implemented by the individual programmers, the processes imposed by the specific organization overseeing the programmers, and the configuration of the software by a particular end-user. This issue of the OSBR examines several facets of open source security. Jake Kouns from the Open Security Foundation introduces an open source project which manages a global collection of vulnerabilities, available for free use by the information security community. David Maxwell from the Coverity Scan project discusses their report on code defect trends from an analysis of several hundred open source projects, representing 55 million lines of code, through 14,000 build sessions over a two year period.

Editorial: Social Innovation (September 2008) - Dru Lavigne; Tony Bailetti (Open Source Business Resource, 2008)
If the overwhelming response we received to this month's call for submissions is any indication, those engaged in open source are also passionate about social innovation. We could have easily published a 100 page issue, but opted instead to save some submissions for upcoming issues as they are also suited to the themes of Building Community and Enabling Innovation. Tony Bailetti of the Talent First Network is one of the driving forces behind the OSBR. He is guest editor this month and I think you'll agree that he has done an excellent job of finding authors from industry, academia, and non-profits who are on the frontlines of social innovation in Canada. This issue is jam-packed with resources and examples of initiatives--enough to leave you thinking "I had no idea so much was happening in Canada". They aren't meant to be exhaustive, but the insights and lessons learned can be applied to similar initiatives across the globe.

The Emerging Role of Open Source in Healthcare - Brian Barry (Open Source Business Resource, 2008)
Healthcare has been characterized as a multi-trillion dollar cottage industry. It is highly fragmented, labour intensive, barely connected, extremely competitive, and has many different vendors and proprietary solutions. The rising cost of healthcare is straining budgets at all levels of government and imposing financial burdens on corporations and individuals alike. Against this backdrop, legitimate concerns about privacy have led to a plethora of regulations requiring complex administrative, physical and technical infrastructure to safeguard sensitive health information. Governments are attempting to impose standards and specifications from the top down to improve efficiency in healthcare delivery. These standards are broad, complex and, for the most part, lack implementations. In short, things are in a bit of a mess. A consensus is emerging around two initiatives that promise to improve the current situation. The first is to foster widespread adoption of Electronic Health Records. The second is to improve accessibility and interoperability between EHR systems. In this article, we present Open Health Tools, an open source ecosystem where members of the health and information technology professions can collaborate to build interoperable EHR systems.

Experiments, Expertise and Google Summer of Code (TM) - Leslie Hawthorn (Open Source Business Resource, 2008)
Computer Science seems to no longer hold sway as the career of choice among North American undergraduates. A variety of reasons for the steady decline of enrollment - down 60% in the United States since 1999 - have been explored. These include economic factors such as concerns about job security and the accompanying increase in off-shoring of information technology roles. Further, studies have noted that Computer Science as a whole simply doesn't look like much fun to today's incoming student populations. There's a general perception that Computer Science means spending one's day chained to a keyboard and monitor, scraping by as a "code monkey". In particular, students cite a lack of a social element as a major deterrent to pursuing a career in Computer Science. In this article, we examine the Google Summer of Code program, the world's first global initiative to introduce College and University students to free/libre open source software development. Over the past four years, the program has provided a model that allows College and University students to more deeply engage with the joys of computing. The experience of our participants stands in sharp contrast to the generalizations mentioned in the previous paragraph. We will discuss the origins and evolutions of the program, as well as its structure. We will also discuss how students benefit by participating in GSoC, focusing on some select success stories. Finally, we discuss how Google views this investment in the F/LOSS community and its potential to improve the overall progression of Computer Science as a discipline.

A Flat Network for the Unflat World: Open Educational Resources in Developing Countries - Steven Muegge; Monica Mora; Kamal Hassin; Andrew Pullin (Open Source Business Resource, 2008)
Open educational resources (OER) apply the principles of openness - particularly the freedoms of use, modification and redistribution - to digital materials for teaching, learning, and research. OER can potentially touch all areas of education, from elementary schools to higher education to professional development all over the world, but we are particularly excited about the potential to expand access to education in developing countries. That is the focus of our research and the topic of this article.

Free and Open Source Licenses in Community Life - Stefano De Paoli; Maurizio Teli; Vincenzo D'Andrea (Open Source Business Resource, 2008)
The objective of this article is to examine how software licenses in build and shape political and technological boundaries. We examine the cases of the Geographic Resources Analysis Support System( GRASS) geographical information system and the OpenSolaris operating system. The first project is GPL licensed software developed by a worldwide community of voluntary programmers; the second project is sponsored by a company and released under the Common Development and Distribution License (CDDL) license.

Free and Open Source Software: Overview and Preliminary Guidelines for the Government of Canada - Robert Charpentier (Open Source Business Resource, 2008)
After a slow beginning in the late 1990s, Free/Libre and Open Source Software (F/LOSS) has been constantly growing in importance and expanding in many software architectures all over the world. This impressive growth has been supported by the numerous successes, the high-quality reputation of F/LOSS-based systems and, of course, by the expectation of cost savings. In 2003, Defence Research and Development Canada (DRDC) initiated a special study to determine the role of F/LOSS in our information system architectures. This study was later expanded to the whole Government of Canada (GoC). This article summarizes some key findings based on the original DRDC report published in 2004. It includes a general introduction to F/LOSS followed by some guidelines in assessing the usefulness of F/LOSS in GoC project contexts.

How is Copyright Relevant to Source Data and Source Code? - Joseph Potvin (Open Source Business Resource, 2008)
One of the essentials of a healthy and democratic economy is that the rules of engagement should be understandable to people whose interests are affected by them. There are two aspects of copyright law to which all software and database professionals ought to be familiar, but usually are not. First, they should know that factual data listed in an obvious structure is not covered by copyright law, no matter how much work went into collecting it. Second, they should know that under the Canadian Copyright Act, programming code is considered to be a "literary work". This article outlines how copyright is related to source data and source code, and why this is important to both technical and business professionals in the field.

How Universities Can Enable Social Innovation - Kim Matheson (Open Source Business Resource, 2008)
This article describes key conditions that enable a successful university agenda for social innovation. Integral to this success is an overarching institutional commitment to the value of social innovation so that it pervades the university's activities, ranging from the active encouragement of collaboration across the disciplines to policies regarding intellectual property. It is suggested that it is important that social innovation activities transcend disciplinary boundaries and social sectors. Finally, facilitating open access to information and resources may be foundational to achieving relevant and sustainable solutions.

Hybrid Software Boosts High Performance Computing Productivity - David Rich (Open Source Business Resource, 2008)
Users of high performance computing have long enjoyed the availability of both commercial and open source software (OSS). But they typically resided in separate worlds. Open source was favored by the academic and government research communities while commercial independent software vendors served the HPC needs of specific industries, such as aerospace or energy. This article examines how the wall between these two software worlds is crumbling as industry increasingly adopts more open source tools.

Implementing Open Data: The Open Data Commons Project - Jordan Hatcher (Open Source Business Resource, 2008)
Free and libre/open source software (F/LOSS) movements have spawned similar solutions in many other contexts, each at differing stages of development. As F/LOSS enters the routine and familiarity of middle age, the open content movement--open source for non-software copyright and best embodied by the work of Creative Commons--has just graduated university and is getting a feel for the world. Even younger is the open data movement, whose legal tools have just started to come online.

Key Elements of Social Innovation - Allyson Hewitt (Open Source Business Resource, 2008)
This article describes four key elements of social innovation: i) social technology; ii) innovation intermediaries; iii) people who drive innovation; and iv) openness. By taking experiences from social technology and examining the impact of "open everything", this article posits the value of innovation intermediaries as critical enablers of success in the emergent field of social innovation.

Ladder of Participation: Business Models for Peer Production - Michel Bauwens (Open Source Business Resource, 2008)
Open source software is just one part of a much wider social and economic ecosystem that is evolving around increased participation of what-used-to-be consumers. New roles are emerging, including "produsers", with an intentional 's', to refer to the amalgamation of being both a user and a producer, and "end-makers", another intentional concept to be contrasted with end-users. In this new ecosystem, produsers and end-makers either partially, but sometimes fully, produce value, aided or unaided by institutions and companies. This creates new dynamics that need to be understood. One way of increasing our understanding is to look at the inter-locking dynamics of both businesses and the participant-communities, for which the following article constructs a model of Interaction. Each distinct type of relationship generates different dynamics and associated business models.

Language Insecurity - Frederic Michaud; Frederic Painchaud (Open Source Business Resource, 2008)
Developing reliable and secure software has become a challenging task, mainly because of the unmanageable complexity of the software systems we build today. Software flaws have many causes, but our observations show that they mostly come from two broad sources: i) design, such as a malicious or unintentional backdoor; and ii) implementation, such as a buffer overflow. To address these problems, our research group at Defence Research and Development Canada (DRDC) Valcartier first worked on design issues. A prototype of a UML design verifier was built. Our approach was successful, but we faced two difficulties: i) specifying interesting security properties at the design level; and ii) scalability of the verification process. Building on this experience, we studied design patterns for the implementation of security mechanisms. The output was a security design pattern catalog, available from the authors, that can help software architects choose mature and proven designs instead of constantly trying to reinvent the wheel. This paper addresses the implementation issues from our evaluation of currently available automatic source code verifiers that search for program sanity and security bugs. From this evaluation, it becomes clear that the choice of programming language to use when starting an open source project can have many important consequences on security, maintainability, reliability, speed of development, and collaboration. As a corollary, software quality is largely dependent on the adequacy of the programming language with respect to the desired properties of the system developed. Therefore, the adoption of open source software (OSS) should consider the programming language that was used.

Making Open Source Ready for the Enterprise: The Open Source Maturity Model - Bernard Golden (Open Source Business Resource, 2008)
One of the questions always asked about open source is whether it's ready for the enterprise. But framing the question in that fashion blurs the issue. With over 100,000 open source products available for download at the click of a mouse, there is no blanket answer comprehensive enough to describe the entire universe of open source products. The real question facing an enterprise is whether, based upon its unique requirements, a specific open source product will satisfy its needs. Far from being a vaguely existential question, this question is extremely pragmatic, completely localized, and, as we shall see, wholly capable of being answered. This article, extracted from chapter four of "Succeeding with Open Source" presents the Open Source Maturity Model (OSMM). The OSMM is designed to enable organizations to evaluate open source products and understand whether a product can fulfill the organization's requirements.

Method for Qualification and Selection of Open Source Software - Raphaël Semeteys (Open Source Business Resource, 2008)
For a company, the choice to opt for software as a component of its information system, whether this software is open source or commercial, rests on the analysis of needs and constraints and on the adequacy of the software to address these needs and constraints. However, when one plans to study the adequacy of open source software (OSS), it is necessary to have a method of qualification and selection adapted to the characteristics of this type of software and to precisely examine the constraints and risks specific to OSS. Since the open source field has a very broad scope, it is also necessary to use a qualification method that differentiates between numerous candidates to meet technical, functional and strategic requirements. This document describes the QSOS (Qualification and Selection of software Open Source) method, conceived by the technology services company Atos Origin SA to qualify, select and compare OSS in an objective, traceable and argued way. The method can be integrated within a more general process of technological watch which is not presented here. It describes a process to set up identity cards and evaluation sheets for OSS.

Mirth: Standards-Based Open Source Healthcare Interface Engine - Jacob Brauer (Open Source Business Resource, 2008)
The Mirth Project is an open source healthcare interface engine and interface repository created and professionally supported by WebReach. Mirth provides standards-based tools to develop, test, and deploy interoperability solutions for healthcare information systems and information exchanges. This article provides an overview of healthcare interface engines. It discusses Mirth and the healthcare and connectivity standards it supports. Lastly, the article compares Mirth to other interface engines.

The Need for F/LOSS (Governance) Operations - Andrew Back (Open Source Business Resource, 2008)
The case for the effective operation of Free/Libre and Open Source Software (F/LOSS) in the enterprise has never been stronger. Yet in some quarters, the chasm between senior management's perception of the penetration of F/LOSS within their organization, and the reality, has never been wider. And when you consider that Gartner predicts that "by 2012 more than 90% of enterprises will use open source in direct or embedded form", this suggests that the development of an effective F/LOSS policy will become increasingly necessary for business operations. Many enterprises, for now, are sourcing the majority of their F/LOSS solutions via a vendor. This does not remove the need for governance. Even with commercial arrangements in place, it is crucial that business have an understanding of F/LOSS communities: what drives them, how to interact with them, and what obligations they may have to them. The game has changed and innovation is no longer the reserve of software vendors with large development budgets. Software development is now enabled by open licenses that afford great freedoms and, in doing so, facilitate widespread collaboration. With this unprecedented pace of innovation, comes new obligations. We argue that the need for education around F/LOSS communities and licensing is clear.

Omeka: Open Source Web Publishing for Research, Collections and Exhibitions - Tom Scheinfeldt (Open Source Business Resource, 2008)
Well into the second decade of the web, many collecting institutions and aspiring digital humanists still find it difficult to mount online exhibitions and publish collections-based research because they lack either technical skills or sufficient funding to pay high priced web design vendors. The digital libraries and archives fields have produced high quality repository and collections management software, but these packages carry too much technical overhead and pay too little attention to web presentation and end user interface for most digital humanities projects. Commercial blog packages have made it easy for digital humanists to publish materials to the web, but the blog's structure of serial text posts does not allow them to present deep collections or complex narratives. That is why the Center for History and New Media at George Mason University, in partnership with the Minnesota Historical Society, has created Omeka. From the Swahili word meaning "to display" or "to lay out for discussion," Omeka is a next generation web publishing platform for academic work of all kinds, one that bridges the university, library, and museum worlds through--and by helping to advance--a set of commonly recognized web and metadata standards. Omeka is free and open source. It offers low installation and maintenance costs--appealing to individual scholars and smaller cultural heritage projects and institutions that lack technical staffs and large budgets. It is standards based, extensible, and interoperable--insuring compliance with accessibility guidelines and integration with existing digital collections systems to help digital humanists of all stripes design online exhibitions more efficiently. Omeka brings Web 2.0 technologies and approaches to digital humanities websites, fostering the kind of user interaction and participation that are central to the mission of digital humanities, and providing the contribution mechanisms, tagging facilities, and social networking tools that audiences are coming to expect.

Open Carrier Grade Base Platform - Vijay Mahendran (Open Source Business Resource, 2008)
This article introduces the SCOPE Alliance, a vertical alliance focused on accelerating the development of open standards for carrier grade base platforms, the base platforms satisfying the carrier grade requirements of the telecommunication industry. The focus of these network equipment providers is to build base platforms comprised of hardware, middleware, and an operating system using open modular building blocks to provide service solutions. Secondly, the article presents an adoption model along with the benefits, risks and factors affecting the adoption of open CGBPs by telecommunication companies. This adoption model is beneficial to top management teams and project managers who wish to improve the product development process. It also provides startups and independent software vendors a reference model to cost effectively deliver products and obtain maximum return.

Open Hardware Business Models - Edy Ferreira (Open Source Business Resource, 2008)
In the September issue of the Open Source Business Resource, Patrick McNamara, president of the Open Hardware Foundation, gave a comprehensive introduction to the concept of open hardware, including some insights about the potential benefits for both companies and users. In this article, we present the topic from a different perspective, providing a classification of market offers from companies that are making money with open hardware.

Open Health Tools: Tooling for Interoperable Healthcare - Skip McGaughey; Ken Rubin (Open Source Business Resource, 2008)
The Open Health Tools initiative is creating an ecosystem focused on the production of software tooling that promotes the exchange of medical information across political, geographic, cultural, product, and technology lines. At its core, OHT believes that the availability of high-quality tooling that interoperates will propel the industry forward, enabling organizations and vendors to build products and systems that effectively work together. This will ?raise the interoperability bar? as a result of having tools that just work. To achieve these lofty goals, careful consideration must be made to the constituencies that will be most affected by an OHT-influenced world. This document outlines a vision of OHT?s impact to these stakeholders. It does not explain the OHT process itself or how the OHT community operates. Instead, we place emphasis on the impact of that process within the health industry. The catchphrase ?code is king? underpins this document, meaning that the manifestation of any open source community lies in the products and technology it produces.

Open Innovation 2.0 - Michael Grove (Open Source Business Resource, 2008)
The objective of this article is to argue for a new model that guides the efforts of multiple stakeholders to solve a problem. The new model is referred to as Open Innovation 2.0 Its main benefit is to gain competitive advantage through effective spending combined with enterprise to enterprise collaboration instead of traditional cost reduction.

Open Source and Open Standards: Working Together for Effective Software Development and Distribution - Jon Siegel; Richard Mark Soley (Open Source Business Resource, 2008)
Many open source projects implement open standards. We interviewed five developers who implemented different open standards in open source projects to find out how much interplay there was between implementors and standards developers and how important this communication was as they programmed the details of the specifications. Our somewhat unexpected finding was that developers preferred to work from the printed specification, separate from the standards source. When asked for a reason, most reported that resource constraints prevented them from writing code and specifications at the same time; another factor was the satisfaction that comes from working independently. Most of the developers we spoke to were more than halfway through their development before they even considered reporting specification problems to the source organization. Although this speaks well for the overall quality of computer industry specifications, it also means that feedback from open source developers is not getting back to the specification's authors.

Open Source e-Procurement Software - Dave Stephens (Open Source Business Resource, 2008)
While every business needs to track the purchase of goods and services, many small and midsize businesses have been discouraged from using centralized software solutions due to high up-front licensing fees, expensive implementations, and the level of organizational training necessary to get the full value out of an enterprise-class procurement solution. This article provides an overview of the benefits provided by e-procurement solutions, then introduces the first open source e-procurement software and the business model for the company behind the open source project.

Open Source in Canada's Public Sector - Glenn McKnight; Evan Leibovitch (Open Source Business Resource, 2008)
The story of the growth of open source use in Canada has been far more a matter of evolution than revolution, so quiet in its pace that its progress has been difficult to measure. This has posed many challenges to Canadian open source advocates in their efforts to ensure that their country does not lag behind the rest of the world in understanding the social and business benefits open source provides. Perhaps some of the leading soldiers in the trenches might be our civil servants who protect the public purse. In addition to managing and minimizing the costs of delivering necessary services, public sector projects should also advance the social good through the delicate balance of transparency and efficiency.

Open Source Interoperability: It's More than Technology - Dominic Sartorio (Open Source Business Resource, 2008)
The Open Solutions Alliance is a consortium of leading commercial open source vendors, integrators and end users dedicated to the growth of open source based solutions in the enterprise. We believe Linux and other infrastructure software, such as Apache, has become mainstream, and packaged solutions represent the next great growth opportunity. However some unique challenges can temper that opportunity. These challenges include getting the word out about the maturity and enterprise-readiness of those solutions, ensuring interoperability both with each other and with other proprietary and legacy solutions, and ensuring healthy collaboration between vendors and their respective customer and developer communities.

Is Open Source Right for your Library? - Carl Grant (Open Source Business Resource, 2008)
We all know that feeling in our gut, that moment when it?s time to sign the order for a new software program for your library. It's accompanied by a host of nagging questions: "Is it the right decision?" "Have we overlooked anything?" "Will this work?" "Have we considered all our options?" The decision to acquire or upgrade a library automation package is never an easy one and every director, when faced with this decision, wants to choose the best package at the best value that most fully meets the needs of users. Today, that decision is complicated by a new option, that of open source. This article will examine when and why open source software (OSS) might be appropriate for your library. It also discusses why so many libraries are moving towards OSS and some of the disadvantages that you should be aware of should you decide to move in that direction.

Open Source, Social Innovation and a New Economy of Engagement - Stephen Huddart (Open Source Business Resource, 2008)
Open source technologies and social innovation have emerged at a time when it is critical to adopt inclusive, creative, multi-disciplinary approaches to solving complex social and environmental problems. This article examines the relationship between open source, social innovation and engagement. It reviews four areas where their interplay has afforded organizations working in the (mainly Canadian) social sector with new tools and approaches to managing change. These tools include: i) collaboration and learning platforms; ii) social networking programs; iii) resource allocation websites; and iv) advocacy tools. An examination of two organizations leading social change in Canada suggests that to address society's larger problems, social innovators must also make use of economic incentives, facilitated or hosted conversations, and partnerships. Finally, two areas where innovation is urgently needed are identified as sustainability education and the means by which we participate in democratic processes and government decision-making.

Open Source Software for Corporate IT - Bruno von Rotz (Open Source Business Resource, 2008)
Of all the choices available when selecting open source software (OSS), which ones are likely to meet business and technology requirements? What tools, if any, exist to help companies assess the enterprise readiness of a proposed open source solution? This article introduces the Enterprise Open Source (EOS) Directory, a resource which was designed to help corporations accustomed to evaluating commercial closed source software find enterprise-ready open source solutions.

Open Source Software Foundations - Zhensheng Xie (Open Source Business Resource, 2008)
Communities that develop open source software (OSS) are virtual entities on the Internet, not legal entities. Some open source communities establish open source software foundations (OSSF) in order to protect their intellectual property and carry out contractual arrangements. As legal entities, OSSF help communities attain their long-term goals, hold community assets, provide resources to communities, and balance interests amongst different stakeholders. When OSS started to draw more business interests, commercial companies became involved with open source communities. The emergence of OSSF provides a good platform and opportunities for companies to exert their influence in a more official way. This article summarizes our recent research regarding the relationships between company involvement, governance, revenue, and OSSF.

Open Source Telecom - Jim Van Meggelen (Open Source Business Resource, 2008)
Open source telecom platforms have matured to the point where they are often functionally superior to more traditional products. A case in point is asterisk, an open source PBX (private branch exchange) and telephony engine, which was recently named "best IP PBX" in InfoWorld's 2008 Technology of the Year Awards. While industry recognition can be a compelling argument for adoption, it is still difficult to stake one's reputation on the implementation of any software in a mission-critical solution without having first built a solid foundation on which to do so. With the right approach, you can deliver a superior open source solution to your telecom problems, at far less cost than using proprietary offerings. Implementing an open source telecom system is similar to any development project: there are steps you can take to lower risk and ensure a successful result. This article provides a practical approach for technical implementors to build a track-record of success that will help win approval for more challenging business initiatives.

Open Source Vulnerability Database Project - Jake Kouns (Open Source Business Resource, 2008)
This article introduces the Open Source Vulnerability Database (OSVDB) project which manages a global collection of computer security vulnerabilities, available for free use by the information security community. This collection contains information on known security weaknesses in operating systems, software products, protocols, hardware devices, and other infrastructure elements of information technology. The OSVDB project is intended to be the centralized global open source vulnerability collection on the Internet.

Open Sourcing Social Change: Inside the Constellation Model - Tonya Surman; Mark Surman (Open Source Business Resource, 2008)
The constellation model was developed by and for the Canadian Partnership for Children's Health and the Environment. The model offers an innovative approach to organizing collaborative efforts in the social mission sector and shares various elements of the open source model. It emphasizes self-organizing and concrete action within a network of partner organizations working on a common issue. Constellations are self-organizing action teams that operate within the broader strategic vision of a partnership. These constellations are outwardly focused, placing their attention on creating value for those in the external environment rather than on the partnership itself. While serious effort is invested into core partnership governance and management, most of the energy is devoted to the decision making, resources and collaborative effort required to create social value. The constellations drive and define the partnership. The constellation model emerged from a deep understanding of the power of networks and peer production. Leadership rotates fluidly amongst partners, with each partner having the freedom to head up a constellation and to participate in constellations that carry out activities that are of more peripheral interest. The Internet provided the platform, the partner network enabled the expertise to align itself, and the goal of reducing chemical exposure in children kept the energy flowing. Building on seven years of experience, this article provides an overview of the constellation model, discusses the results from the CPCHE, and identifies similarities and differences between the constellation and open source models.

Open Standards vs. Open Source: a Case of the OpenAccess Standard - Stoyan Tanev; Amy Xu; Jim Wilmore (Open Source Business Resource, 2008)
In this article we provide some insights into the relationship between non-code based open assets, open development processes, and open standards. The insights are based on a case study of the OpenAccess Project of the Silicon Integration Initiative. The unique relationship between the OA standard's openness, evolution and adoption is an example of how open processes could be used to enable design tool interoperability, innovation, and cooperation.

The OpenTTT Approach - Carlo Daffara (Open Source Business Resource, 2008)
There is no shortage of data and results that demonstrate that open source software, when adopted with appropriate best practices, can significantly lower costs and provide quality IT (information technology) solutions, especially for small and medium enterprises. For example, the Consortium for Open Source Software in Public Administration project demonstrated that by using best practices for OSS procurement, not only was software acquisition cheaper, but the evaluation of tangible and intangible costs over 5 years demonstrated a cost reduction ranging from 20% to 60%. The EU study on the impact of OSS indicates that OSS can reduce software research and development costs by 36%, while the INES project found that companies adopting OSS increased profits and reduced time to market and development costs in 80% of the trials. If OSS is so advantageous, why is so little use of it perceived in the marketplace, especially among SMEs? We present the preliminary results of an European project called OpenTTT to improve the adoption rate and study the effectiveness of best practices in OSS adoption within small and medium enterprises.

OSS Spending Trends in Education - Justin Davidson (Open Source Business Resource, 2008)
Open source software (OSS) is becoming more prominent within the education market as more educational institutions turn towards open source as a solution that meets their needs. However, open source is not appropriate for all, and institutions should be cautious about implementing OSS. When adopting open source, institutions should ensure it is a strategic decision and not just a philosophical one. At Datamonitor, a provider of online data, analytic and forecasting platforms for key vertical sectors, we believe that the role of OSS will become increasingly important in education. The solutions available are becoming more sophisticated and stable. Currently, 56% of education institutions are using OSS and open source is clearly making headway into the education market. Furthermore, there are a number of varying factors driving institutions towards OSS and not all institutions are implementing OSS for the same reason. OSS offers an alternative method through which an institution can implement a technological solution, along with it's own variety of benefits and pitfalls. However, the increased popularity of OSS will not prevent proprietary software solutions from having an important role to play in education. Instead, OSS and proprietary solutions are going to become even more entwined together and the line between open source and proprietary solutions will blur.

A Panamanian Initiative to Embrace the Future - Monica Mora (Open Source Business Resource, 2008)
The International Center for Technological Development and Open Source Software (CIDETYS) in Panama is a non-profit organization, promoted by the Panamanian government to harness the potential of Information and Communication Technologies (ICT) and open source software (OSS) to create social benefits for its population. An important goal of the center is to collaborate with international organizations and become a leader in Central America in the development, use and implementation of ICT and OSS. This article describes the main activities that CIDETYS will be focusing on during the first years of operations, how this initiative was born, and a story of the implementation of OSS in the region of Extremadura, Spain that inspired the creation of CIDETYS.

The Personal Research Portal - Ismael Peña-López (Open Source Business Resource, 2008)
Digital technologies have forever changed the way that knowledge is disseminated and accessed. Yet, the main problem knowledge workers face is invisibility: if people don't know that you know, and people are not aware of what you know, you do not exist. Governments and institutions are being pushed to foster Open Access (OA) literature as a way to achieve universal reach of research diffusion at inexpensive and immediate levels. Most efforts have been made at the institutional level, dedicating little energy to what the individual can do to contribute. The philosophy and tools around web 2.0 bring clear opportunities for individuals to contribute and to build a broader personal presence on the Internet and a better diffusion for their work, interests or publications. We propose the concept of the personal research portal (PRP) as a means to create a digital identity for knowledge workers--tied to one's digital public notebook and personal repository--and a virtual network of colleagues working in the same field. Complementary to formal publishing or taking part in offline meetings, the PRP would be a knowledge management system that would enhance reading, storing, and creation at both the private and public levels, and contribute to create an online identity that, in turn, will help to create a network whose currency is knowledge.

Power of Openness to Solve Textbook Access Problems - David Wiley (Open Source Business Resource, 2008)
Article 26 of The Universal Declaration of Human Rights attests that access to educational opportunity is a basic human right. Yet while a myriad of publishing technologies flourish around us, the staple of classroom teaching, the textbook, is becoming so expensive as to be increasingly inaccessible. In this article we describe how Flat World Knowledge is leveraging principles of openness to bring textbooks back into reach of all students, creating significant social value in a manner that will sustain itself over the long-term.

Project Conifer - Art Rhyno (Open Source Business Resource, 2008)
Sharing resources lies at the heart of librarianship, and libraries have a long history of collaborative projects and initiatives. It comes as no surprise then to find that libraries have a natural synergy with open source software and there have been some recent activities where open source solutions have been applied to large scale services. This article describes a project between several Ontario university libraries to work together on a mission critical OSS application for their campuses.

Q&A. Besides compliance, are there any business reasons for maintaining an accessible website? - Glenn McKnight (Open Source Business Resource, 2008)
Your questions answered and reader feedback.

Q&A. Does lack of product management impact the users of open source? - Paul Young (Open Source Business Resource, 2008)
Most commercial software companies employ product managers to handle the planning and marketing of software products, whereas few open source projects have a product manager. Does lack of product management impact the users of open source?

Q&A. Does the Google Summer of Code project provide any value to open source projects and the students who participate? - Murray Stokely (Open Source Business Resource, 2008)
Google recently announced their fourth Summer of Code. Does the Summer of Code project provide any value to open source projects and the students who participate?

Q&A. Why use OSS, other than the licensing cost of the software? - Alan Morewood (Open Source Business Resource, 2008)
Your questions answered and reader feedback.

Reducing Global Poverty and Disease with Community and Technology: An Open Source Perspective - Cliff Schmidt (Open Source Business Resource, 2008)
Literacy Bridge, a non-profit technology startup, is using open source software (OSS), open hardware, and open content to solve some of the world's most challenging problems: global poverty and disease. Through the development and application of a digital audio device, Literacy Bridge's Talking Book Project is designed to make access to information available and affordable to those who have the fewest resources but the greatest need. This article summarizes the Talking Book Project and describes how six aspects of successful open source projects are being applied to improve global literacy and access to information. Most importantly, this project demonstrates the power of combining community and appropriate technology to change the world.

Security Hardening of Open Source Software - Robert Charpentier; Mourad Debbabi (Open Source Business Resource, 2008)
In today's computing world, security takes an increasingly predominant role. The industry is facing challenges in public confidence at the discovery of vulnerabilities and customers are expecting security to be delivered out of the box, even on programs that were not designed with security in mind. Software maintainers must face the challenge to improve the security of their programs and are often under-equipped to do so. Some are taking advantage of open source software (OSS) for their production systems as the availability of the source code facilitates their validation and answers their need for trustworthy programs. OSS are often implemented using the C programming language (26% according to SourceForge.net), making it is necessary to investigate the security issues related to C. This paper summarizes key concepts related to security hardening, and demonstrates its applicability on the C language. We also propose a progressive approach to integrate security services and protection measures into existing software to ultimately make it more resistant against cyber-attacks. Given our ever increasing dependability on information technologies, it becomes critically important to provide tools to maintainers that will facilitate and accelerate the security hardening process, increasing the effectiveness of the effort and lowering the resources required to do so.

Sharing Information on the Semantic Web: The Reminiscence of an Old Legal Issue - Pierre-Paul Lemyre (Open Source Business Resource, 2008)
The success story of open source software (OSS) makes us see very clearly that in a networked world, centralized production of information is not the only viable model. It is now largely understood that distributed production can often equal and surpass it, both in quality and quantity. This has led people in all disciplines to rethink their relationship with information, giving birth to a plethora of initiatives generating value by promoting the mass collaboration of individuals over shared sets of information. Based on rich Internet applications, wikis, social tagging or social networking technologies, these initiatives gave birth to a revolution that has been dubbed Web 2.0. Whether they originate in non-profit or business ventures, they all add up to the ever increasing mass of accessible and reusable information. For current information hubs that have been developed through independent channels, it is anticipated that the next step in the evolution of the web will make seamless integration possible. This development should create tremendous opportunities for those capable of building innovative services and knowledge products on top of this shared knowledge base. In fact, along with the technological foundations of this web of ideas, practical commercial implementations are already starting to appear. However, these early experiments highlight the fact that the most important challenge to overcome might not reside in the technology itself. Instead, the management of rights may, more than anything else, hinder the efficient aggregation of distributed information.

Social Innovation: Access and Leadership - Roseann O'Reilly Runte (Open Source Business Resource, 2008)
We live in an age where the rapid pace of technological innovation and the ability to disseminate knowledge far exceed our capacity to ensure that all members of society receive their benefits. The challenges in providing access to technology have been largely solved in this globally connected world. How to best use that technology to increase social value and alleviate lack of education, poverty, and other societal problems is an ongoing question with no easy answers. This article explores the challenges for social innovation and the use of information technology. These challenges are: i) access to technology; ii) access to learning; iii) the use of technology in teaching and research; and iv) the establishment of a framework of knowledge.

Social Innovation in Sub-Saharan Africa - Steven Muegge; Chukwuemeka Afigbo (Open Source Business Resource, 2008)
SW Global is an African-based application service provider of information technology infrastructure and software. This article describes how SW Global, a for-profit private sector company, creates high-impact value at universities and governments in developing countries through an innovative business model anchored around service subscriptions, open source software, and open content.

Software Accessibility: Where Are We Today? - Marco Zehe (Open Source Business Resource, 2008)
While it seems intuitive that applications, especially open source ones, should allow all to use and enjoy them, many developers are unaware of the need for accessible applications. Providing accessibility in information technology is not difficult, but it does require a basic understanding of different types of disabilities, commonly used assistive technologies, and the special accessibility features built into languages and standards. Most of all, accessibility requires a conscious effort and a desire to include everyone. The accessibility of computer software has seen drastic improvements over the past two decades. This article reviews this progress, examining the technologies developed and offering guidelines for developers to create accessible applications.

TIM Lecture Series: A Practitioners Guide to Ecosystem Development - Mike Milinkovich (Open Source Business Resource, 2008)
On September 3, 2008, Mike Milinkovich, Executive Director of the Eclipse Foundation, delivered a presentation entitled "A Practitioners Guide to Ecosystem Development". This lecture introduced the fundamental concepts of ecosystems and how the Eclipse Foundation matches the theory. This report provides the key messages from the lecture.

TIM Lecture Series: Building Technical Communities - Ian Skerrett (Open Source Business Resource, 2008)
On June 4, 2008, Ian Skerrett from the Eclipse Foundation delivered a presentation entitled " Building Technical Communities". This section provides the key messages from Ian's lecture. Ian used his observations of working in the Eclipse community to explain why community building is important, its critical elements, and how the traditional roles within an organization relate.

TIM Lecture Series: Ecosystem Approach to the Commercialization of Technology Products and Services - Tony Bailetti (Open Source Business Resource, 2008)
On March 28, 2008, Tony Bailetti, Director of Ontario's Talent First Network, launched Carleton University's TIM Lecture Series with a presentation entitled Ecosystem Approach to the Commercialization of Technology Products and Services. The TIM Lecture Series provides a forum to promote the transfer of knowledge from university research to technology company executives and entrepreneurs as well as research and development (R&D) personnel. This conference report presents the key messages and insights from the three sections discussed during the inaugural presentation.

TIM Lecture Series: OSGi and Server-Side Eclipse - Dwight Deugo (Open Source Business Resource, 2008)
On August 27, 2008, Dwight Deugo from Carleton University delivered a presentation entitled "OSGi and Server-Side Eclipse". This lecture introduced the fundamental concepts of OSGi, a component integration platform to provide interoperability of applications and services. It also discussed how the Equinox project has incorporated OSGi into the Eclipse platform and gave an overview of the impact it has had on Server-Side Eclipse. This report provides the key messages from the lecture.

TIM Lecture Series: Privacy and Security in a Connected World - Douglas King (Open Source Business Resource, 2008)
On May 7, 2008, Douglas G. King, Assistant Professor of Systems and Computer Engineering at Carleton University, delivered a presentation entitled "Privacy and Security in a Connected World". The TIM Lecture Series provides a forum to promote the transfer of knowledge from university research to technology company executives and entrepreneurs as well as research and development personnel. This conference report presents the key messages and insights from the three sections discussed during Professor Kunz's presentation.

TIM Lecture Series: The State of Open Source Software and Corporate Software - Doug Levin (Open Source Business Resource, 2008)
On April 16, Doug Levin, CEO of Black Duck Software, gave a presentation entitled The State of Open Source Software and Corporate Software Development. This conference report presents the key messages and insights from the three sections discussed during the presentation.

TIM Lecture Series: Trends in Technology Marketing - Stoyan Tanev (Open Source Business Resource, 2008)
On May 23, 2008, Stoyan Tanev from Carleton University delivered a presentation entitled "Trends in Technology Marketing". This section provides the key messages from Dr. Tanev's lecture. Tanev's lecture discussed current trends in technology innovation and marketing by focusing on the evolution of traditional marketing concepts.

TIM Lecture Series: Wireless Sensor Networks: What and Why? - Thomas Kunz (Open Source Business Resource, 2008)
On April 30, 2008, Thomas Kunz, Director of the Talent Innovation Management (TIM) program at Carleton University delivered a presentation entitled "Wireless Sensor Networks: What and Why?". The TIM Lecture Series provides a forum to promote the transfer of knowledge from university research to technology company executives and entrepreneurs as well as research and development personnel. This conference report presents the key messages and insights from the three sections discussed during Professor Kunz's presentation.

TIM Series: Open APIs, Mashups and User Innovation - Michael Weiss (Open Source Business Resource, 2008)
On June 11, 2008, Michael Weiss from Carleton University delivered a presentation entitled "Open APIs, Mashups and User Innovation". This section provides the key messages from the lecture. Michael's lecture examined the structure of the mashup ecosystem as well as implementation issues, including licensing.

TIM Series: Practicing Safe Software: Good Software Record - Mahshad Koohgoli (Open Source Business Resource, 2008)
On June 18, 2008, Mahshad Koohgoli, CEO of Protecode, delivered a presentation entitled "Practicing Safe Software: Good Software Record". This section provides the key messages from the lecture. Mashad's lecture discussed the drivers behind establishing software IP (intellectual property) pedigree as well as the preventive and corrective methods of detecting and managing external IP in a project.

TIM Series: Theory, Evidence and the Pragmatic Manager - Steven Muegge (Open Source Business Resource, 2008)
On July 2, 2008, Steven Muegge from Carleton University delivered a presentation entitled "Theory, Evidence and the Pragmatic Manager". This section provides the key messages from the lecture. The scope of this lecture spanned several topics, including management decision making, forecasting and its limitations, the psychology of expertise, and the management of innovation.

Treasury of the iCommons: Reflections of a Commons Sourcing Lawyer - Thomas Prowse (Open Source Business Resource, 2008)
This article advances the thesis that commons sourcing is the emerging third wave of commercial transformation. It begins with the iCommons concept and its origin in open source software (OSS) methodologies and emergence in other business models. It then defines commons sourcing and situates it with respect to the two earlier waves of commercial transformation. It concludes with some reflections by a commons sourcing lawyer.

Uses of Creative Commons Licenses - Minjeong Kim (Open Source Business Resource, 2008)
A recent study examined the uses of Creative Commons (CC) licenses and their potential to resolve the conflict surrounding copyright law in the digital communications era. This article summarizes the major findings of that study, originally published in the Journal of Computer-Mediated Communication.

Why Give Knowledge Away for Free? The Case for Open Educational Resources - Jan Hylén (Open Source Business Resource, 2008)
An apparently extraordinary trend is emerging. Although learning resources are often considered as key intellectual property in a competitive higher education world, more institutions and individuals are sharing digital learning resources openly and without cost, as open educational resources (OER). The issues of why this is happening, who is involved, and the important implications were addressed in a 2006 study carried out by the OECD Centre for Educational Research and Innovation with the support of the Hewlett Foundation. The main conclusions are summarised here, together with some insights from a follow-up, and not yet published, study from spring 2008. Higher education is facing a number of challenges: globalisation, an aging society, growing competition between higher educational institutions both nationally and internationally, and rapid technological development. OER is itself one of these challenges, but may also be a sound strategy for individual institutions to meet them. The trend towards sharing software programmes through open source software and research outcomes through open access publishing is already so strong that it is generally thought of as a movement. It is now complemented by the trend towards sharing learning resources: the OER movement. OER are a fascinating technological development and, potentially, a major educational tool. They accelerate the blurring of formal and informal learning, and of educational and broader cultural activities. They raise basic philosophical issues dealing with the nature of ownership, the validation of knowledge, and concepts such as altruism and collective goods. They reach into issues of property and its distribution across the globe. They offer the prospect of a radically new approach to the sharing of knowledge, at a time when effective use of knowledge is seen as the key to economic success, for both individuals and nations. OER projects can expand access to learning for everyone, but most of all, for non-traditional groups of students. They thus widen participation in higher education. They can be an efficient way of promoting lifelong learning, both for individuals and for government, and can bridge the gap between non-formal, informal, and formal learning.

Adding Value to Information Systems Using Free Data - Ervin Ruci (Open Source Business Resource, 2007)
This article provides an example of how a graduate student in Ontario used open source software and freely available data to solve a technical dilemma, start and grow a business, and provide services which benefit many. It also illustrates how easily new features and customizations can be developed when an API is made available to its users.

Building an Open Source Company One Penguin at a Time - Bill White (Open Source Business Resource, 2007)
Roaring Penguin Software Inc. started as a one-person consulting company in 1999. A year later, David F. Skoll, the company's President and CTO, was asked to develop an e-mail filtering tool. David developed MIMEDefang, an e-mail filter that used Sendmail's Milter facilities. David donated the code to the open source community, and kept developing MIMEDefang as a free tool for system administrators. Today, the MIMEDefang code is available at at the website. By 2002, it was obvious that there was a need for a packaged mail-filtering solution suitable for end-users. David decided to go ahead and write what became CanIt-PRO. Whereas MIMEDefang is suited to system administrators who are familiar with Perl and comfortable with writing their filtering policies in Perl, the CanIt product line allows end-users to control their filtering through a simple web-based interface. The company transformed itself from a consulting company to a product development company. This transformation required significant changes.

Company Interactions with Open Platforms - Tammy Yuan (Open Source Business Resource, 2007)
The telecommunications industry is moving away from building communications and data service networks using proprietary platforms of specialized hardware, closed interfaces, and proprietary technologies. Increasingly, the industry is assembling new networks on open platforms comprised of both commercial-off-the-shelf (COTS) software and open source components. Carrier Grade Linux (CGL) stands at the center of the move to open architectures. This article addresses three questions. 1) What motivates companies to incorporate CGL specifications into their products? 2) How do companies adopting CGL create and appropriate value? 3) What roles do these companies play in the ecosystem anchored around the CGL Working Group initiative? These questions are of interest to top management teams facing pivotal decisions of whether or not to incorporate open platforms into their products, and how to compete in a world where those same platforms are available to competitors.

Comparing the BSD and GPL Licenses - Bruce Montague (Open Source Business Resource, 2007)
There are many reasons, not all necessarily altruistic, for the popularity of Open Source Software (OSS). This article provides an overview of software and licensing, and suggests usage examples for two well-known open source licenses: the GPL and BSD license. This article does not discuss recent GPLv3 developments and reflects my own experiences, not necessarily those of my employer.

Competitive Actions of Open Source Firms - Glen McInnis (Open Source Business Resource, 2007)
Early in 2006, Microsoft CEO Steve Balmer made a public statement that Microsoft had no trouble competing with open source rivals on features. Balmer was downplaying the fact that Open Source Software (OSS) has changed the nature of competition in the software industry from one of feature-based competition to a much more complex model for competition. Traditional firms like Microsoft are not simply competing against a loose group of programmers who produce OSS; they are competing against other firms who have chosen to use OSS as part of their product or service offering. This article is an examination of competition in this new environment where firm-to-firm competition includes those firms making use of OSS. The evolution of the marketplace becomes evident when competition is viewed as a series of small, but discrete actions that are carried out by a firm. Each of these actions is intended to improve the firm's standing in the marketplace. Such actions can be classified as one of six different types of competitive action: (i) pricing, (ii) marketing, (iii) new products, (iv) capacity, (v) service, and (vi) signaling.

Competitive Open Source - Peter Carbone (Open Source Business Resource, 2007)
Peter Carbone describes insights gained from a joint industry-university research project.

Conference Report: Open Education 2007 - Andrew Pullin; Kamal Hassin; Monica Mora (Open Source Business Resource, 2007)
Open Education Resources (OER) are educational material and resources that the general public can freely use for teaching, learning, and research. Like Open Source Software (OSS), OER contain content that is freely reused and redistributed without the traditional restrictions imposed by copyright. OER also includes the tools used to develop, improve, and distribute this content to communities. The Open Education 2007: Localizing and Learning conference was held at Utah State University in September. The conference focused on the ability of people to learn as simply publishing OER content online does not guarantee that it can be effectively used for learning. This theme was investigated from two perspectives. The first was from the developer perspective with the sharing of efforts to localize the educational content and make it more relevant to the people using it. The second was from the user perspective where organizations utilizing or deploying OER spoke of their experiences, challenges, and successes. This report provides an overview of the sustainability, localization, technological, legal and interoperability issues raised at the conference. It concludes with the authors' views regarding the future direction of OERs, based on their research being conducted at Carleton University's Technology Innovation Management program.

Defining Open Source - Russ Nelson (Open Source Business Resource, 2007)
The Open Source Initiative and the Free Software Foundation share a common goal: that everyone should be free to modify and redistribute the software they commonly use. 'Should' is of course a normative word. For the FSF, 'should' is a moral imperative. Anything else is an immoral restriction on people's activities, just as are restrictions on speech, press, movement, and religion. For the OSI, freedom is a necessary precondition for a world where "software doesn't suck", in the words of a founder of the OSI. The FSF started from its founder's GNU Manifesto widely published in 1985. Given the manifesto's hostility to copyright, and given the failure of the Free Software Foundation to gain any traction amongst commercial users of software even with a 13-year head start, a group of people gathered together in 1998 to talk about a new strategy to get the corporate world to listen to hackers. They were impressed by Eric Raymond's Cathedral and the Bazaar's take-up among business leaders.

Eclipse: A Premier Open Source Community - Donald Smith; Mike Milinkovich (Open Source Business Resource, 2007)
Donald Smith and Mike Milinkovich examine the factors that grew the Eclipse community into a thriving ecosystem.

Editorial: Business Models (August 2007) - Dru Lavigne (Open Source Business Resource, 2007)
At the close of the 20th century, Tim O'Reilly wrote The Ten Myths About Open Source Software: Do any of these still sound familiar? 1. It's all about Linux versus Windows 2. Open source software isn't reliable or supported 3. Big companies don't use open source software 4. Open source is hostile to intellectual property 5. Open source is all about licenses 6. If I give away my software to the open source community, thousands of developers will suddenly start working for me for nothing 7. Open source only matters to programmers; most users never look under the hood anyway 8. There's no money to be made on free software 9. The open source movement isn't sustainable; people will stop developing free software once they see others making lots of money from their efforts 10. Open source is playing catch up to Microsoft and the commercial world

Editorial: Clean Intellectual Property (December 2007) - Dru Lavigne (Open Source Business Resource, 2007)
As 2007 draws to a close, three emerging trends are gaining momentum. The first is that companies are releasing formerly proprietary code under an open source license. The second is that open source companies are being acquired or are issuing public offerings. The third trend is that very large number of citizens increasingly uses the Internet to oppose politicians and law makers who threaten, sometimes unwittingly, the fundamental principles of open source development. These three trends tie into this month's editorial theme: Clean intellectual property or clean IP. In a nutshell, clean IP is about reducing license incompatibilities and non-compliance with licensing terms. Clean IP significantly affects the value of the code released as open source and the value of a company that develops and markets software.

Editorial: Defining Open Source (September 2007) - Dru Lavigne (Open Source Business Resource, 2007)
In his book Foresight and Understanding: An Inquiry into the Aims of Science, Stephen Toulmin wrote "Definitions are like belts. The shorter they are, the more elastic they need to be. A short belt reveals nothing about its wearer: by stretching, it can be made to fit almost anybody." Keep in mind the nature of elasticity while reading through this issue of the OSBR. The theme this month is "Defining Open Source"; however, you'll find that the articles build upon and extend both the Open Source Definition and the Free Software Definition. This stretching in order to fit almost anybody is bound to make the open source purist uncomfortable; it is our intent to provoke thought and we look forward to receiving and publishing reader feedback.

Editorial: Introducing the OSBR (July 2007) - Dru Lavigne (Open Source Business Resource, 2007)
Welcome from the Editor.

Editorial: Licensing (October 2007) - Dru Lavigne (Open Source Business Resource, 2007)
In his book Open Source Licensing: Software Freedom and Intellectual Property Law, Lawrence Rosen defines licensing as "the legal way a copyright and patent owner grants permission to others to use his intellectual property". When you consider that the bread and butter of a company usually revolves around its intellectual property, it's not suprising that open source licenses are often regarded with suspicion. How is it possible for a company's interests to be protected by a license written by another party? And how can a company provide "open" access to its intellectual property without "giving away the store"? Simon Phipps, Chief Open Source Officer for Sun Microsystems, once stated in an interview: "While open source licensing lets people have access...this doesn't have to mean that chaos ensues." This issue of the OSBR provides insights to help navigate the chaos that is often associated with open source licenses.

Editorial: Support (November 2007) - Dru Lavigne (Open Source Business Resource, 2007)
What is your first thought when you encounter the term "open source support"? A programmer typing the answer to a question using a chat utility? Hours spent scouring the Internet for a working configuration sample? Contacting a support engineer at a commercial call centre? If you find it difficult to think about a support engineer, you're not alone. Actuate's recently published 2007 Open Source Survey of senior personnel from financial services, Telco, and public sector organizations across North America and Europe indicates that 46.3% of respondents cite the lack of availability of long term support as a major barrier to their company's adoption of open source technologies.

Ensuring Software IP Cleanliness - Richard Mayer; Mahshad Koohgoli (Open Source Business Resource, 2007)
At many points in the life of a software enterprise, determination of intellectual property (IP) cleanliness becomes critical. The value of an enterprise that develops and sells software may depend on how clean the software is from the IP perspective. This article examines various methods of ensuring software IP cleanliness and discusses some of the benefits and shortcomings of current solutions.

Ensuring the Quality of Open Source Software - David Maxwell (Open Source Business Resource, 2007)
Open Source Software (OSS) has been embraced by individuals for decades, but only recently have organizations around the globe looked upon open source as an attractive and practical alternative to proprietary software. In addition to its appealing price tag, usually free, OSS can be inspected, modified, and freely redistributed according to the terms of its license. In spite of this, open source developers still find their code quality and security challenged by a question that has followed them from the beginning: "If it's free, how good can it be?"

Enterprise Open Source Support - Stormy Peters (Open Source Business Resource, 2007)
Open Source Software (OSS) has permeated the enterprise. Some organizations still prohibit the use of OSS altogether, but they are unquestionably in the minority. For most companies, it's not a question of "should we use OSS"? but rather, "how and where can we best take advantage of open source solutions"? As companies have shifted from prohibiting OSS use to embracing it, they must now deal with technical support issues. This article examines the various option available to support companies that use OSS.

Evolution of an Open Source Strategy - Kelly Rankin; Ronald Baecker (Open Source Business Resource, 2007)
On June 8th, 2005, we officially launched the ePresence (http://epresence.tv/) Interactive Media Open Source Consortium, at the Knowledge Media Design Institute (KMDI), University of Toronto (UofT). We had been researching and developing ePresence, our webcasting, webconferencing, and archiving software project for about five years. Throughout the early phase of the project we used the system to produce live webcasts of KMDI's annual lecture series. Eventually word spread about our webcasting system and other universities, such as Memorial University in Newfoundland, became interested. It was obvious that the time to share our project with the world had come, but what wasn't obvious to us at the time was how we were going to do that.

Five Stage Approach to Licensing - Thomas Prowse (Open Source Business Resource, 2007)
This article will set out a practical five stage approach to Open Source Software (OSS) legal issues for organizations that are working, or thinking of working, in this area. While OSS affords a plethora of legal challenges and ongoing developments that merit treatment, I will focus on a general framework for managing OSS legal issues. Since I will provide general legal information and not legal advice, I strongly encourage your organization to work with legal counsel with competency in the OSS area to address its specific circumstances.

Free as in Adjective, Not as in Verb - Amos Hayes (Open Source Business Resource, 2007)
Open source provides an avenue for distributing academic research well beyond the covers of journals or the lunchtime chatter of sharp-minded thinkers to a much broader audience. Interestingly, the choice of open source license is often a choice of community. By understanding the goals and underlying philosophy of a research project, one is better equipped to find a suitable license and attract a community with similar interests. This article provides an examination of a particular academic research project's licensing goals and presents some of the lessons learned during the license selection process.

Improving Application Development by Managing Licensing Issues - Doug Levin (Open Source Business Resource, 2007)
Over the past ten years, the Internet and open source software (OSS) have enabled developers to fundamentally change the way they produce software. Increasingly, distributed teams are collaborating to assemble software from reusable components and their own proprietary code rather than building applications entirely from scratch. The component-based development model is fundamentally changing the software industry. It enables organizations that develop software, either for commercial sale or for in-house use, to accelerate project timelines, improve software quality, and reduce development costs. If not managed properly, the complexity inherent in this new world of mixed-IP (Intellectual Property) can pose business and technical risks to an organization. This paper draws on the experiences of the Black Duck Software team, our customers, and other industry experts to propose new approaches to managing IP in this new world. It describes a set of best practices that companies can use to avoid the risks and gain the benefits of the component-based approach to software development.

An Introduction to Rights Expression Languages - G.R. Gangadharan; Michael Weiss (Open Source Business Resource, 2007)
The objective of this article is to: i) extend the discussion of licensing to non-software assets and ii) provide an introduction to rights expression languages (RELs). Licensing is not limited to software. We can associate a license with any kind of asset that holds intellectual value, and can thus be turned into a source of revenue. Here, our interest is on information assets, which include software and software components, but also services, processes, and content. For instance, a song that a user downloads from iTunes is an information asset. So is a web service such as the Google Maps API (application programming interface).

Key Changes to the GNU General Public License - Eric Smith (Open Source Business Resource, 2007)
On June 29, 2007, the Free Software Foundation (FSF) issued the GNU General Public License Version 3. The issuance of GPLv3 marked the end of a remarkable public consultation process aimed at revamping the license to address issues that the FSF considers to be a threat to the Free Software movement, and to clarify issues that have been misunderstood or debated since the publications of GPL Version 2 (GPLv2). This article introduces the rationale for changing the GPL and introduces the changes that affect patents, Digital Rights Management (DRM), license compatibility, and the linking issue.

Keystone Organization for Ontario's Open Source Ecosystem - Rowland Few (Open Source Business Resource, 2007)
Many companies, individuals and organizations in Ontario produce and use open source assets and processes to provide unique value to their customers, clients, and themselves. To better enable these companies, individuals and organizations to (i) co-evolve capabilities and roles, (ii) align themselves with companies holding leadership roles, and (iii) invest in shared visions, the Talent First Network (TFN) has become the keystone organization of Ontario's open source ecosystem. This article introduces the TFN and identifies the steps it is taking to better support the Ontario Open Source Ecosystem.

Lead Projects - Peter Hoddinott; Richard Alam (Open Source Business Resource, 2007)
Corporate Directory Platform and the Ottawa Tech Community described.

Ontario Research Commercialization Program - Brad DeFoe; Dmitri Prokopiev (Open Source Business Resource, 2007)
Brad DeFoe and Dmitri Prokopiev describe the Ontario Research Commercialization Program.

Open Educational Resources - Monica Mora (Open Source Business Resource, 2007)
This article first introduces open content and open educational resources (OER), then compares OER and open source software (OSS), and finally discusses issues of OER project sustainability.

Open Hardware - Patrick McNamara (Open Source Business Resource, 2007)
I have been involved in a number of debates on what exactly constitutes open hardware. While the definition is a bit harder to pin down than that of open source software, I believe hardware can be loosely placed into four categories of openness. They are, in order of least to most open: Closed, Open Interface, Open Design, and Open Implementation.

Open Source as Community - Nelson Ko (Open Source Business Resource, 2007)
What does it really mean to participate in an open source software community? If a company's open source strategy is limited to acting as end user of open source software, is there a business need to understand the nature of open source communities? Should it be the goal of all businesses to become an active participant in open source communities, or become recognized as a significant contributor? Business users of open source software can broadly be divided into those who use open source software as end-users, and those who incorporate underlying open source technology into their products and services. This article will first address both these groups with the important facets of understanding and evaluating community in the selection of open source software, and then elaborate on the role of active participation in open source communities to enhance the value that can be obtained from the use of open source. It is based upon lessons I've learned from becoming progressively involved in a particular open source software community, Tikiwiki, and comparisons with other open source communities which I've made to identify commonalities and differences.

Open Source Assets - Tony Bailetti; Peter Hoddinott (Open Source Business Resource, 2007)
The Open Source Definition or OSD defines the criteria to which the distribution terms of software must comply for it to be deemed to be open source software. The term open source, however, is used to label a broad assortment of phenomena that fall well outside the established OSD. In addition, there is ambiguity in what is meant to be covered by the terms source and open. We envisage a definition of open source that equally applies to software, hardware schematics, content, and processes, not just software.

Open Source Licensing in the Enterprise - Stormy Peters (Open Source Business Resource, 2007)
Studies show that most open source projects are licensed under the General Public License (GPL) and it is estimated that over 75% of open source projects are licensed under either the GPL or the LGPL (Lesser GPL). Yet, it has been my company's experience that the open source software used by our enterprise customers is primarily Apache licensed software. This article examines several factors which may shed some light on this disparity, including the issues raised by enterprise customers and the software product selection process used by OpenLogic (http://www.openlogic.com).

Open Source on Trial - Kamal Hassin (Open Source Business Resource, 2007)
The way we develop software is continuously evolving: the everyday processes and practices used to produce software are becoming more efficient, and it is common for a team of developers to change several times over the life of a software project and for the components used to come from a variety of sources. However, the benefits of these changes cannot be fully appreciated unless correct policies and strategies are used to capture value from innovation. This is where the worlds of technology and Intellectual Property (IP) law collide and where license compliance is fundamental in protecting a company's IP and avoiding legal conflicts.

Open Source Telecommunication Companies - Peter Liu (Open Source Business Resource, 2007)
Little is known about companies whose core business is selling telecommunications products that lever open source projects. Open source telecommunications (OST) companies operate in markets that are very different from typical software product markets. The telecommunications market is regulated, vertically integrated, and proprietary designs and special chips are widely used. For a telecommunications product to be useful, it must interact with both access network products and core network products. Due to specifications in Service Agreements Levels, penalties for failures of telecommunications products are very high. This article shares information that is not widely known, including a list of OST companies and the open source projects on which they depend, the size and diversity of venture capital investment in OST companies, the nature of the commercial product-open source software and company-project relationships, ways in which OST companies make money, benefits and risks of OST companies, and competition between OST companies. Analysis of this information provides insights into the ways in which companies can build business models around open source software. These findings will be of interest to entrepreneurs, top management teams of incumbent companies that sell telecommunications products, and those who care about Ontario's ability to compete globally.

Protecting Information Technology Property Rights - Russell McOrmond (Open Source Business Resource, 2007)
New copyright legislation is on its way from the Canadian government, and may have been tabled by the time you are reading this. While we won't know exactly what is in the bill until it is tabled in the House of Commons for first reading, the Government has made many statements indicating that it intends to ratify the highly controversial 1996 WIPO treaties. I believe it is important for open source developers and users to be aware of how some of the proposed changes may affect open source in Canada.

Putting Maps on the Web with Open Source Technologies - Dave McIlhagga (Open Source Business Resource, 2007)
In this time of excitement over the emergence of mapping technologies like Google Earth, Personal Navigation Devices, GPS technologies for tracking vehicles, and so much more, a little known phenomenon has also been taking place: the explosive growth of open source mapping technologies. Leading the way in this area is DM Solutions Group (DMSG) - a small company based in Ottawa, Canada who is working closely with customers and partners from around the world to incorporate mapping into their web environments. Web Mapping is a highly specialized niche market that can be applied to almost every conceivable industry. It is this peculiar combination that is at the heart of why the open source software development approach has been so successful in this area.

Q&A. How one can develop a business model around open source? - Peter Hoddinott (Open Source Business Resource, 2007)
How can one develop a business model around open source if the resource is freely available?

Q&A. What effect do supply and a demand have on open source commercialization? - Ian Graham (Open Source Business Resource, 2007)
I've read that commercialization has both a supply and a demand side. What effect do these two sides have on open source commercialization, specifically in Canada?

Q&A. What is the state of open source in public administration? - Christian Meloche; Luc Lalande (Open Source Business Resource, 2007)
What is the state of open source in public administration?

QNX Hybrid Software Model - Lawrence Rosen (Open Source Business Resource, 2007)
QNX Software Systems' new software model integrates open source and proprietary software products in new ways. It is a step forward in the embedded systems market toward openness and freedom of software development, and it gives QNX customers significantly greater flexibility to extend and adapt QNX technology for their own purposes. The new QNX model is an effort to address fundamental problems in the way proprietary embedded software is traditionally developed and distributed. Today, the rate of change to software and hardware is so rapid, and software so complex, that vendors and customers alike struggle to keep up. Often, software vendors are their own worst bottleneck, as they work to fix or extend their existing products while also attempting to satisfy new, and often divergent, customer needs. Meanwhile, the sophisticated users and customers in the embedded market often know exactly what features and functions they want; many would make the modifications themselves if allowed to do so. And many of them would welcome opportunities to cooperate and share the results of their collective development efforts, just as they would in an open source project. A pure open source approach doesn't work in all cases, and it doesn't work for QNX which does not believe that relinquishing all control over their intellectual property and giving it away for free would best serve the interests of their customers.

A Rallying Moment for Canadian Open Source Software - Andy Kaplan-Myrth (Open Source Business Resource, 2007)
In the Canadian copyright reform arena, the events of early December, 2007 changed everything. In late November, it was widely anticipated that new copyright legislation would be introduced in the model of the controversial American Digital Millennium Copyright Act (DMCA). The bill was rumored to include harsh anti-circumvention laws, which grant software distributors the right to seek legal remedies for circumvention of technological locks on content. In response, veteran Canadian copyright advocates issued an appeal to Canadians to take an interest in the bill and to call for fair and balanced copyright. Canadian citizens answered that call in unexpected numbers, both online and offline. A Facebook group, called Fair Copyright for Canadians, grew to over 25,000 members within two weeks, and provided grassroots advocacy tools to citizens. A new website, called CopyrightforCanadians.ca, established itself as a centre for news on the bill and consumer advocacy. Using these tools, Canadians wrote letters, met with politicians, and demanded balance. With their words and their actions, not only did Canadians delay the introduction of the bill until next year, but they put copyright in the spotlight and showed legislators that fair and balanced copyright can capture the public imagination.

Software Licensing - G.R. Gangadharan (Open Source Business Resource, 2007)
G.R. Gangadharan discusses the many dimensions of software.

Special Considerations for Financial Services Firms - Sourcelabs (Open Source Business Resource, 2007)
Infrastructure Open Source Software (OSS), including middleware, database packages, and the Linux operating system, is increasingly being deployed by financial institutions. Many OSS packages are selected and incorporated directly into custom applications by developers, thus bypassing traditional purchasing channels and their attendant legal, standards, and technical review processes. Because of this, Information Technology (IT) management is often unaware of the OSS running in their data centers, and sometimes support and maintenance measures are not in place for OSS running in production applications. With the advent of regulatory structures such as the Basel II accords, the reliability of computing systems is increasingly subject to regulatory scrutiny. Not having adequate support and maintenance measures in place creates a significant compliance risk for financial institutions. This article describes these risks and outlines best practices for an anti-failure program that brings systems depending on OSS packages into compliance while reducing overall operational risk.

Supporting Not-for-Profits: an Opportunity for the Commons - Jason Côté; Julian Egelstaff (Open Source Business Resource, 2007)
In 2004, the Nonprofit Open Source Initiative (NOSI) released "Choosing and Using Free and Open Source Software: A Primer for Nonprofits". The primer describes the potential impact that Free/Libre and Open Source Software (F/LOSS) might have on the not-for-profit (NFP) sector. In a recently released update, the primer concludes that, despite many advances in the use of F/LOSS in the sector over the past several years, a real and perceived lack of support remains a significant barrier to the increased adoption of F/LOSS by NFPs. Support is often the last thing people think of when they think of F/LOSS and NFPs. Instead, people tend to focus on the price, which is of particular importance to cash-strapped NFPs. There is a widely held belief that free software represents a cost savings to NFPs.

TFN: Open Source and Innovation - Tony Bailetti (Open Source Business Resource, 2007)
Tonay Bailetti explains the goals and progress of the Talent First Network Program.